The OCEAN ICE mooring compilation: a standardised, pan-Antarctic database of ocean hydrography and current time series - Zhou, S.; Dutrieux, P.; Giulivi, C. F.; Jenkins, A.; Silvano, A.; Auckland, C.; Abrahamsen, E. P.; Meredith, M.; Vaňková, I.; Nicholls, K.; Davis, P. E. D.; Østerhus, S.; et al. (Earth Syst. Sci. Data, 2025)
Continuous moored time series of temperature, salinity, pressure and current speed and direction are of great importance for understanding the continental shelf and under-ice-shelf dynamics and thermodynamics that govern water mass transformations and ice melting in and around Antarctic marginal seas. In these regions, icebergs and sea ice make ship-based mooring deployment and recovery challenging. Nevertheless, over decades, expeditions around the fringe of Antarctica sporadically deployed and recovered hundreds of moored instruments, including those facilitated through ice shelves boreholes. These datasets tend to be archived in a wide range of data centres, with, to our knowledge, no clear format standardisation. As a result, systematic analysis of historical mooring time series in the marginal seas is often challenging. Here we present the first version of a standardised pan-Antarctic moored hydrography and current time series compilation, with broad international contributions from data centres, research institutes and individual data owners. The mooring records in this compilation span over five decades, from the 1970s to the 2020s, providing an opportunity for a systematic study of the pan-Antarctic water mass transport and shelf connectivity. As a demonstration of the utility of this compilation, we present spectral analysis of the compiled current velocity time series, which unsurprisingly shows the dominating presence of tidal variability within most records. This component of the variability is fitted using multi-linear regression to tidal frequencies, and the tidal fit is removed from the original time series to leave de-tided variability. Given the limited record durations to months to years, de-tided variability is dominated by synoptic (3–10 d period), intraseasonal (10–80 d) and seasonal (∼6 months–1 year) signals. The spatial distribution of the kinetic energy integrated within frequency bands is presented and discussed within respective regional contexts, and future avenues of research are proposed. This data compilation is assembled under the endorsement of Ocean-Cryosphere Exchanges in ANtarctica: Impacts on Climate and the Earth System (OCEAN ICE) project (https://ocean-ice.eu/, last access: 23 October 2025) funded by the European Commission and UK Research and Innovation. It is available and regularly updated in NetCDF format with the SEANOE database at https://doi.org/10.17882/99922 (Zhou et al., 2024a).
Publisher: Copernicus Publications
Keywords: Sørishavet; database; geofysikk; hydrografi; oseanografi

A potential new sea surface temperature proxy based on isomeric highly branched isoprenoid lipid biomarkers: EZ25 - Belt, Simon T.; Smik, Lukas; Husum, Katrine; Knies, Jochen (Organic Geochemistry, 2025)
Two tri-unsaturated and isomeric (E/Z) highly branched isoprenoid (HBI) diatom lipid biomarkers were quantified in 228 water column samples collected from the English Channel, West Svalbard (Arctic), the Scotia Sea (Southern Ocean) and East Antarctica. We found that the relative amounts of the two HBIs correlate well with water temperatures taken at the time of sampling. Based on these findings and some other HBI data reported previously, we suggest that the proportion of the HBI E-isomer (termed EZ25) may serve as a new proxy for palaeo sea surface temperatures, including in the polar regions. Next steps will involve determination of EZ25 in surface and downcore sediments to ascertain whether the temperature response described herein translates well to the geological record.
Article number: 105056
Keywords: Scotiahavet; Sørishavet; biogeokjemi; biomarkører; geologi; paleontologi; polarområdene

Dynamical reconstruction of Southern Ocean and Antarctic climate variability since 1700 - Dalaiden, Quentin; Goosse, Hugues; Holland, Paul R.; Barthelemy, Antoine (Scientific Data, 2025)
Understanding long-term climate variability in the high latitudes of the Southern Hemisphere is critical due to the key role of the Southern Ocean in the global climate system. However, sparse observations (in space and time) coupled with strong internal variability limit our ability to interpret the origin of recent changes, and their longer-term context. Here we present a dynamically consistent reconstruction of the Antarctic atmosphere and Southern Ocean from 1700 to 2023. We first use data assimilation (DA)-based Antarctic atmospheric reanalyses that combine instrumental observations (1958–2023) and paleoclimate proxies (1700–2000) with Earth System Models to reconstruct key surface climate fields. We then drive a global ocean–sea-ice model with this atmospheric reanalysis to simulate historical ocean conditions, including temperature, salinity, currents, and sea-ice-related variables at 1° resolution. This reconstruction provides the first long-term physically consistent dataset of Antarctic atmosphere–ocean variability, suitable for studying low-frequency climate variability, evaluating climate models, and potentially driving regional atmospheric and ocean models as well as ice sheet models.
Keywords: Sørishavet; global klimamodell; klimamodeller; paleoklimatologi

Dive wiggles as a proxy of prey consumption in krill-feeding penguins - Oosthuizen, W. Chris; Schoombie, Stefan; Chimienti, Marianna; Pistorius, Pierre A.; Lowther, Andrew D. (Journal of Experimental Marine Biology and Ecology, 2025)
The dive profiles of pursuit-diving marine predators are often used to infer foraging behaviour, including potential indicators of prey consumption. ‘Wiggles’ are undulations in dive profiles that relate to foraging activity in a variety of marine predators. In penguins, wiggles are sometimes used as a proxy for prey consumption (e.g., catch per unit effort, CPUE), but this relationship remains poorly validated and likely varies with diet. We deployed animal-borne video cameras and depth recorders on chinstrap penguins (Pygoscelis antarcticus; n = 37) and identified over 17,000 euphausiid prey captures - mainly Antarctic krill (Euphausia superba) - during dives deeper than 3 m (n = 2458 dives). Using the video-observed prey captures as a reference, we tested how well various wiggle metrics derived from 1 Hz depth data predicted krill consumption by the penguins. Wiggle metrics generally showed a positive but noisy and highly variable relationship with the number of krill captured per dive, with association strength varying among metrics. While it is tempting to infer detailed foraging behaviours from dive wiggles (including ‘bottom distance’ generated by the R package diveMove), our results show: (1) notable rates of foraging – non-foraging dive misclassification; (2) only moderate agreement between CPUE estimated from wiggle counts and video observations; and (3) imprecise predictive models of actual prey consumption. While wiggle analyses offer some insight into prey consumption of krill-feeding penguins, our results suggest that alternative methods (e.g., acceleration-based indices) are needed to obtain more robust quantitative estimates of prey consumption.
Keywords: Sør-Orknøyene; Sørishavet; biologging; marin biologi; marin økologi; pingviner; sjøfugler

Refining Zooplankton Diet Composition Studies Over Short and Long Time Scales by Combining 18S Metabarcoding With Fatty Acid Analyses - Pauli, Nora-Charlotte; Metfies, Katja; Neuhaus, Stefan; Graeve, Martin; Cleary, Alison C.; Iversen, Morten H.; Meyer, Bettina (Molecular Ecology Resources, 2025)
ABSTRACT Understanding diet composition is essential for unravelling trophic interactions in aquatic ecosystems. DNA metabarcoding, utilising various variable regions of the 18S rRNA gene, is increasingly employed to investigate zooplankton diet composition. However, accurate results depend on rapid inactivation of digestive enzymes and DNA nucleases through proper sample processing and preservation. In this study, we compare the prey communities of Antarctic krill retrieved from the 18S variable regions V4 and V7 and assess how different processing treatments affect the detected prey composition of both krill and salps. Our findings highlight the critical importance of prompt sample processing for species with highly efficient digestive enzymes, such as krill, to preserve rapidly digested prey, including gelatinous plankton. Comparative analyses of the V4 and V7 regions revealed significantly different prey communities within the same krill samples, indicating that these regions may not be suitable for direct comparisons within or across studies. To complement molecular approaches, we also analyse fatty acids (FA) as trophic markers which provide insights into dietary habits over both short and long time scales. By comparing FA signals from stomach and tissue samples of the same krill and salp individuals, we identified significant differences in trophic markers representing different plankton groups. These findings emphasise the necessity of separating digestive tract from tissue to distinguish between short- and long-term diet signals. Furthermore, integrating FA analysis with metabarcoding offers valuable insights into zooplankton digestion efficiency across taxonomic levels. This combined approach enhances our understanding of zooplankton feeding ecology and trophic interactions in marine ecosystems.
Publisher: John Wiley & Sons, Ltd Article Number: e70030
Keywords: Sørishavet; Weddellhavet; genetikk; krill; marin biologi; marine økosystemer; zooplankton

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Article number: 304
Keywords: Sørishavet; geologi; klimaendringer; klimamodeller; oseanografi; paleogeografi; paleoklimatologi; paleoseanografi

Basal Melt Rate Variability and Tidal Current Vertical Structure From Observations Beneath Ronne Ice Shelf, Antarctica - Anselin, J.; Nicholls, K. W.; Holland, P. R.; Taylor, J. R.; Østerhus, S.; Makinson, K. (Journal of Geophysical Research: Oceans, 2025)
This study examines the interplay between water column structure, tidal currents, and basal melting at a site beneath Ronne Ice Shelf, using a 3-year data set of oceanographic measurements, and a collocated year-long time series of radar-derived melt rate estimates. Currents at the site are characterized by mixed semidiurnal tides with strong spring-neap variability, superimposed on a nontidal flow. The product of current speed and thermal driving, both measured approximately 19 m from the ice base, explains 88% of the melt rate variability. Although current speed is the dominant driver of this variability, thermal driving also contributes non-negligibly on spring-neap and longer timescales. The semidiurnal tidal ellipses feature marked vertical variations, transitioning from nearly rectilinear in the mid-water column to more circular and clockwise (CW)-rotating near the ice. This depth-dependence of the semidiurnal tide is attributed to the differential influence of boundary friction on the CW and anticlockwise (ACW) rotary components near the critical latitude (where the tidal frequency equals the Coriolis frequency). A theoretical model, which assumes depth-independent eddy viscosity, successfully reproduces the observed 3-year mean vertical structure of the tidal ellipses. Considering the total tidal current rather than individual constituents, ice base friction damps both the time-mean flow speed and the tidal fluctuations, with attenuation varying over the spring-neap cycle, peaking during spring tides. The observed latitude- and time-dependent effects of ice base friction on the barotropic tide are not captured in parameterizations that estimate tide-induced friction velocity by scaling the time-averaged barotropic tidal speed with a constant drag coefficient.
Publisher: John Wiley & Sons, Ltd Article number: e2025JC022524
Keywords: Antarktis; Sørishavet; Weddellhavet; glasiologi; hydrografi; isshelf; oseanografi

Bout time for krill: contrasting Adélie penguin foraging behaviour during years of high and low krill availability - Riaz, Javed; Machado-Gaye, Ana Laura; Chimienti, Marianna; Kato, Akiko; Ropert-Coudert, Yan; Alegría, Nicolás; Barbosa, Andrés; Soutullo, Alvaro (Animal Behaviour, 2025)
Understanding how marine predators structure and adjust their foraging in response to prey field characteristics is a longstanding objective in marine ecology. This is particularly challenging in Southern Ocean ecosystems, where logistical and financial constraints hinder assessment of predator foraging and prey field information at relevant spatial and temporal scales. Here, we examine how Adélie penguins, Pygoscelis adeliae, a key Southern Ocean indicator species, perform and organize their foraging behaviour during two contrasting years of krill (Euphausia superba) abundance. Using multiyear krill acoustic data from King George Island in the West Antarctic Peninsula (WAP), we assess broad seasonal conditions in krill availability. We also analyse a suite of penguin biologging data (spatial location, dive and accelerometry-derived activities) during the same period to identify broad behavioural differences in their bout-diving activity, a classical measure of the temporal organization of foraging in diving predators. During years of high krill abundance and availability, penguins performed shorter dive bouts (consisting of shallower and shorter-duration dives), which were more concentrated in time and space. Despite these differences in bout structure, prey capture attempts occurred at the same rate within bouts. These findings challenge traditional interpretations assuming that increased bout durations (and related proxies of prey capture effort) signal increased krill patch abundance and profitability. Although additional data are required to understand the full scope of penguin bout diving and krill prey field associations, our work improves understanding of penguin behavioural variation and provides insights into how foraging behaviours could potentially be used to interpret krill availability at predator- and management-relevant scales.
Article number: 123260
Keywords: Sørishavet; ekkolodd; krill; marin biologi; marin økologi; marine økosystemer; matauk; pingviner; plankton

Robustness and Mechanisms of the Atmospheric Response Over the Southern Ocean to Idealized Freshwater Input Around Antarctica - Xu, Xiaoqi; Martin, Torge; Beadling, Rebecca L.; Liu, Jiping; Bischof, Sabine; Hattermann, Tore; Huo, Wenjuan; Li, Qian; Marshall, John C.; Muilwijk, Morven; Pauling, Andrew G.; Purich, Ariaan; et al. (Geophysical Research Letters, 2025)
Enhanced Antarctic ice sheet mass loss yields ocean surface freshening, cooling and sea ice expansion, which result in changes in the atmospheric conditions. Using the Southern Ocean Freshwater Input from Antarctica (SOFIA) multi-model ensemble, we study the atmospheric response to a 100-year idealized freshwater release of 0.1 Sv. All models simulate a surface-intensified tropospheric cooling and lower-stratospheric warming south of 35°S. Tropospheric cooling is attributed to sea ice expansion and the associated albedo enhancement in winter and a colder sea surface in summer. This cooling yields a downward displacement of the tropopause, reduced stratospheric water vapor content and ultimately warming around 200 hPa. An enhanced southward eddy heat flux explains warming at 10?100 hPa during austral winter. Despite a temporally (and spatially) uniform prescribed freshwater flux, a prominent sea ice seasonal cycle and atmosphere dynamics result in a distinct seasonal pattern in the occurrence and magnitude of the temperature responses.
Publisher: John Wiley & Sons, Ltd Article number: e2024GL113734
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi

Impacts of the CICE sea ice model and ERA atmosphere on an Antarctic MetROMS ocean model, MetROMS-UHel-v1.0 - Äijälä, C.; Nie, Y.; Gutiérrez-Loza, L.; De Falco, C.; Lauvset, S. K.; Cheng, B.; Bailey, D. A.; Uotila, P. (Geoscientific Model Development, 2025)
In recent years, the Antarctic sea ice has experienced major changes, which are neither well understood nor adequately reproduced by Earth system models. To support model development with an aim to improve Antarctic sea ice and upper-ocean predictions, the impacts of updating the sea ice model and the atmospheric forcing are investigated. In the new MetROMS-UHel-v1.0 (henceforth MetROMS-UHel) ocean–sea ice model, the sea ice component has been updated from CICE5 to CICE6, and the forcing has been updated from ERA-Interim (ERAI) to ERA5 reanalyses. The two versions of MetROMS evaluated in this study use a version of the regional ROMS ocean model including ice shelf cavities. We find that the update of CICE (Community Ice CodE) and ERA reduced the negative bias of the sea ice area in summer. However, the sea ice volume decreases after the CICE update but increases when the atmospheric forcing is updated. As a net result after both updates, the modelled sea ice becomes thinner and more deformed, particularly near the coast. The ROMS ocean model usually yielded a deeper ocean mixed layer compared to observations. Using ERA5, the situation was slightly improved. The update from CICE5 to CICE6 resulted in a fresher coastal ocean due to a smaller salt flux from sea ice to the ocean. In the ice shelf cavities, the modelled melt rates are generally underestimated compared with observations, with the largest underestimation coming from the ice shelves in the too cold Amundsen and Bellingshausen seas as well as from the Australian sector in East Antarctica. These identified sea ice and oceanic changes vary seasonally and regionally. By determining sea ice and oceanic changes after the model and forcing updates and evaluating them against observations, this study informs modellers on improvements and aspects requiring attention with potential model adjustments.
Keywords: Amundsenhavet; Bellingshausenhavet; Sørishavet; havis; klimaendringer; klimamodeller; klimatologi; meteorologi; sjøis

Can we really use design-free hydroacoustic data from fishing vessels for assessing abundance and distribution of marine species? A proof of concept analysis on Antarctic krill - Canseco, J.A.; Niklitschek, E.J.; Skaret, G. (Ecological Indicators, 2025)
Euphausia superba is a well-known Antarctic crustacean of great economic and ecological importance, whose management requires accurate and precise abundance and distribution estimates. Such estimates are difficult to achieve given the remoteness, extension, and large spatio-temporal variability of its geographic distribution. Acoustic data collected on board krill fishing vessels during normal fishing operation has a great potential to enhance such abundance and distribution estimates. In the present work we test the hypothesis that design-free hydroacoustic data collected during regular fishing operations can be used to produce abundance and distribution estimates with similar accuracy and precision than design-based scientific surveys. Thus, we produced and compared distribution and abundance estimates produced using either design-free hydroacoustic data collected during regular fishing operations or design-based data from scientific surveys conducted off the South Orkney Islands during summer 2017 and 2019. Following a Bayesian geostatistical approach that considered and fitted simultaneously the spatial and temporal correlation of the data, we tested different auto-correlation structures and selected the most informative models. The comparison included the means and coefficients of variation (CV) of the probability of presence (p), conditional density (d) and relative abundance index (RAI) estimates. In addition, we also simulated scenarios of parallel and orthogonal transects and obtained RAI estimates from each scenario to compare with design-based and design-free estimates for each year. In 2017, the mean RAI estimated using design-free data (94 421 m2; CV: 14 %) was ∼ 50 % higher than the one estimated with design-based data (60 232 m2; CV: 42 %), both within the fishing area. In 2019, the mean RAI estimated using design-free data (509 413 m2 CV: 6 %) was ∼ 5-fold higher than the one obtained using design-based data (113 654 m2; CV: 33 %) in the same area. Design-free RAI estimates were highly sensitive to extrapolating the inference area from fishing to the high-density sub-area. On the other hand, changing from an hourly-resolved spatio-temporal model to a purely spatial model resulted in neglectable changes. Despite observed differences in mean estimates, both methods identified similar areas of high presence and density of Antarctic krill north and north-west of the South Orkney Islands. The 2017 estimate from design-free data was probably affected by a larger dispersion of krill, and a less observed effective area during regular fishing operations. Our results show that despite using state-of-the-art methods for processing and analyzing design-free, acoustic data collected by the fishing fleet, it still yielded unreliable RAI estimates. The bias and uncertainty related to design-free data were reduced when parallel or orthogonal transects were applied although orthogonal transects yielded results with increased accuracy as they were only 21 % lower and 0.02 % higher than the true value in 2017 and 2019, respectively. Other possible approach to minimize bias would be integrating hydroacoustic information from multiple vessels.
Article number: 113284
Keywords: Sørishavet; geostatistikk; hydroakustikk; krill; marin biologi; oseanografi

Ephemerality and Performance: Sastrugi: Sounds of Antarctic Sea Ice - Chua, Sean Minhui Tashi; Chester, Diana (Leonardo, 2025)
This paper explores the research, making, and performance of Sastrugi: Sounds of Antarctic Sea Ice. Combining the techniques of sonification, field recording, and musique concrète, Sastrugi orchestrates multisensory world building where immersive soundscapes, data-driven violin composition, and expansive visuals narrate the poignant tale of vanishing sea ice in the Antarctic and Southern Ocean. In the face of a record-breaking year for Antarctic sea ice in 2023, this project emerged as a vital testament to the Earth’s changing climate and highlights the power of creative approaches for engaging audiences with science and vast amounts of data.
Keywords: Sørishavet; fotografi; havis; klimaendringer; kunst; musikk; sjøis

Observation-Based Estimate of Net Community Production in Antarctic Sea Ice - Dalman, Laura A.; Meiners, Klaus M.; Thomas, David N.; Deman, Florian; Bestley, Sophie; Moreau, Sébastien; Arrigo, Kevin R.; Campbell, Karley; Corkill, Matthew; Cozzi, Stefano; Delille, Bruno; Fransson, Agneta; et al. (Geophysical Research Letters, 2025)
Abstract Antarctic sea ice is one of the largest biomes on Earth providing a critical habitat for ice algae. Measurements of primary production in Antarctic sea ice remain scarce and an observation-based estimate of primary production has not been revisited in over 30 years. We fill this knowledge gap by presenting a newly compiled circumpolar data set of particulate and dissolved organic carbon from 362 ice cores, sampled between 1989 and 2019, to estimate sea-ice net community production using a carbon biomass accumulation approach. Our estimate of 26.8?32.9 Tg C yr?1 accounts for at least 15%?18% of the total primary production in the Antarctic sea-ice zone, less than a previous observation-based estimate (63?70 Tg C yr?1) and consistent with recent modeled estimates. The results underpin the ecological significance of sea-ice algae as an early season resource for pelagic food webs.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; fotosyntese; havis alger; karbondioksid; karbonsyklus; oseanografi; primærproduksjon; sjøis

A chlorophyll halo over maud rise in the southern ocean - Ducrocq, Bertrand; Steiger, Nadine; du Plessis, Marcel; Sallée, Jean-Baptiste; Moreau, Sébastien; Swart, Sebastiaan (Nature communications, 2025)
Phytoplankton blooms above the seamount Maud Rise in the Antarctic Ocean have been reported but their emerging mechanisms and their importance for the wider Southern Ocean are not well known. We use satellite data spanning over the last two decades and in-situ data collected from a ship, an underwater glider and Biogeochemical-Argo profiling floats to understand the processes involved in the formation of Maud Rise phytoplankton blooms. We find that the seamount generates upwelling of warm deep water that transports heat, and likely dissolved iron, to the surface via diapycnal mixing. This creates a recurring annular structure of chlorophyll concentration (or chlorophyll halo) in correspondence with the previously observed warm water and sea ice halo over Maud Rise. The in-situ observations reveal integrated chlorophyll-a concentrations of up to 100 mg·m(-2), which suggests exceptionally high phytoplankton biomass within the Southern Ocean, thus making the seamount a regional phytoplankton hotspot.
Place: England
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; oseanografi

A new dynamic distribution model for Antarctic krill reveals interactions with their environment, predators, and the commercial fishery in the south Scotia Sea region - Freer, Jennifer J.; Warwick-Evans, Victoria; Skaret, Georg; Krafft, Bjørn A.; Fielding, Sophie; Trathan, Philip N. (Limnology and Oceanography, 2025)
The management strategy for the Antarctic krill (Euphausia superba) fishery is being revised. A key aim is to spatially and temporally allocate catches in a manner that minimizes impacts to both the krill stock and dependent predators. This process requires spatial information on the distribution and abundance of krill, yet gaps exist for an important fishing area surrounding the South Orkney Islands in the south Scotia Sea. To fill this need, we create a dynamic distribution model for krill in this region. We used data from a spatially and temporally consistent acoustic survey (2011-2020) and year-specific environmental covariates within a two-part hurdle model. The model successfully captured observed spatial and temporal patterns in krill density. The covariates found to be most important included distance from shelf break, distance from summer sea ice extent, and salinity. The northern and eastern shelf edges of the South Orkney Islands were areas of consistently high krill density and displayed strong spatial overlap between intense fishing activity and foraging chinstrap penguins. High mean krill density was also linked to oceanographic features located within the Weddell Sea. Our data suggest that years in which these features were closer to the South Orkney shelf were also years of positive Southern Annular Mode and higher observed krill densities. Our findings highlight existing fishery?predator?prey overlap in the region and support the hypothesis that Weddell Sea oceanography may play a role in transporting krill into this region. These results will feed into the next phase of krill fisheries management assessment.
Publisher: John Wiley & Sons, Ltd
Keywords: Scotiahavet; Sør-Orknøyene; Sørishavet; Weddellhavet; ekkolodd; fiskerier; krill; oseanografi; plankton

Inferring the seasonality of sea ice floes in the Weddell Sea using ICESat-2 - Gupta, M.; Regan, H.; Koo, Y.; Chua, S. M. T.; Li, X.; Heil, P. (The Cryosphere, 2025)
Over the last decade, the Southern Ocean has experienced episodes of severe sea ice area decline. Abrupt events of sea ice loss are challenging to predict, in part due to incomplete understanding of processes occurring at the scale of individual ice floes. Here, we use high-resolution altimetry (ICESat-2) to quantify the seasonal life cycle of floes in the perennial sea ice pack of the Weddell Sea. The evolution of the floe chord distribution (FCD) shows an increase in the proportion of smaller floes between November and February, which coincides with the asymmetric melt–freeze cycle of the pack. The freeboard ice thickness distribution (fITD) suggests mirrored seasonality between the western and southern sections of the Weddell Sea ice cover, with an increasing proportion of thicker floes between October and March in the south and the opposite in the west. Throughout the seasonal cycle, there is a positive correlation between the mean chord length of floes and their average freeboard thickness. Composited floe profiles reveal that smaller floes are more vertically round than larger floes and that the mean roundness of floes increases during the melt season. These results show that regional differences in ice concentration and type at larger scales occur in conjunction with different behaviors at the small scale. We therefore suggest that floe-derived metrics obtained from altimetry could provide useful diagnostics for floe-aware models and improve our understanding of sea ice processes across scales.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; fjernmåling; havis; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis

Local Drivers of Antarctic Spring Sea Ice Retreat - Himmich, Kenza; Vancoppenolle, Martin; Stammerjohn, Sharon; Bocquet, Marion; Madec, Gurvan; Fleury, Sara (Geophysical Research Letters, 2025)
Antarctic sea ice has changed significantly over the past four decades; yet limited understanding of fundamental processes, including its seasonal cycle, hinders our ability to interpret these changes. Here, we examine the processes determining the moment when sea ice locally disappears each spring, defined as the retreat date, using satellite observations over 1994?2020. We find that climatological retreat date is driven by sea ice melt in most of the seasonal ice zone and strongly constrained by the seasonal maximum ice thickness. Ice removal due to drifting ice export predominantly drives retreat only in coastal polynyas. At interannual timescales, retreat date anomalies are also preconditioned by prior maximum ice thickness, which affects melt-driven spring ice loss through the ice-albedo feedback, though this effect appears limited to specific regions. Winds emerge as a primary driver of interannual variability in the retreat date, influencing both drift- and melt-related spring ice removal processes.
Publisher: John Wiley & Sons, Ltd Article number: e2025GL114764
Keywords: Sørishavet; havis; klimamodeller; klimatologi; oseanografi; sjøis

Synoptic Drivers and Moisture Sources of Snowfall in Coastal Victoria Land, Antarctica - Hofsteenge, M. G.; Cullen, N. J.; Sodemann, H.; Katurji, M. (Journal of Geophysical Research: Atmospheres, 2025)
Snowfall is an important component of the mass balance of ice sheets and glaciers in Antarctica. In coastal Victoria Land (VL), changes to snowfall can impact ice masses, landscapes, and coastal ecosystems. Coastal VL is characterized by strong gradients in snowfall rates between the polar desert of the McMurdo Dry Valleys and the high accumulation in northern VL. Extreme precipitation events significantly contribute to total precipitation, with the largest contribution in the Terra Nova Bay area. We present a comprehensive analysis of snowfall dynamics in this region, using a Lagrangian moisture source diagnostic to study moisture sources and Self-Organizing Maps (SOM) to link these to different synoptic weather types. The moisture for snowfall in VL originates from the Southern Ocean, with more local sources in the Ross Sea embayment in summer when sea ice is reduced. We show a strong division in moisture sources between northern and southern VL, with the north receiving precipitation from moisture sources to the west and southern VL from the east. Precipitation in northern VL results from meridional transport of marine air from lower latitudes, while precipitation in southern VL is related to cyclonic disturbances in the Ross Sea that bring moisture from the east. Extreme precipitation in northern VL occurs during blocking highs that intensify meridional transport. Such intrusions of marine air, sometimes in the form of atmospheric rivers, do not impact the more isolated western Ross Ice Shelf and southern VL further in the Ross Sea embayment.
Publisher: John Wiley & Sons, Ltd Article number: e2024JD042021
Keywords: Rosshavet; Sørishavet; havis; klimatologi; meteorologi; nedbør; sjøis

Assessing trawls size selectivity in Antarctic krill: The role of sex and maturity stages - Krag, Ludvig Ahm; Brčić, Jure; Herrmann, Bent; Nalon, Marco; Krafft, Bjørn Arne (Regional Studies in Marine Science, 2025)
Understanding the connection between maturity stages and morphology in relation to size selectivity in trawls is essential for assessing the impact of various fishing gear on the population structures of harvested species, their fishing mortality rates, and the efficiency of the gear used. The Antarctic krill (Euphausia superba) fishery is the largest in the Southern Ocean by volume, and there is increasing interest in expanding the industry. The krill fishery employs different trawl designs and is not currently subject to technical regulations specifying the types of fishing gear and mesh sizes that can legally be used. There is a need to establish a robust model predicting size selectivity that includes the morphological variation in the population of krill. Male and female Antarctic krill are described with 12 maturity stages, from juveniles to sexually mature adults, each with distinct morphological features. The current study established a morphological description of each individual krill maturity stage to identify and parameterize what determines size selectivity using the FISHSELECT framework. This framework is used to predict size selectivity for each of the different stages in various mesh sizes and openings relevant to the krill fishery, in both actual and virtual populations. The results can be used to assess size selectivity for specific fishing gears and population structures, facilitating more accurate understanding and modeling of the fishery’s impact on the demographic composition of the krill stock.
Article number: 104223
Keywords: Sørishavet; fiskerier; fiskeriforvaltning; krill; marine økosystemer; plankton; populasjonsbiologi

Southern Ocean Carbon Export Revealed by Backscatter and Oxygen Measurements From BGC-Argo Floats - Liniger, Guillaume; Moreau, Sébastien; Lannuzel, Delphine; Carranza, Magdalena M.; Strutton, Peter G. (Global Biogeochemical Cycles, 2025)
The Southern Ocean (south of 30°S) contributes significantly to global ocean carbon uptake through the solubility, physical and biological pumps. Many studies have estimated carbon export to the deep ocean, but very few have attempted a basin-scale perspective, or accounted for the sea-ice zone (SIZ). In this study, we use an extensive array of BGC-Argo floats to improve previous estimates of carbon export across basins and frontal zones, specifically including the SIZ. Using a new method involving changes in particulate organic carbon and dissolved oxygen along the mesopelagic layer, we find that the total Southern Ocean carbon export from 2014 to 2022 is 2.69 ± 1.23 PgC y?1. The polar Antarctic zone contributes the most (41%) with 1.09 ± 0.46 PgC y?1. Conversely, the SIZ contributes the least (8%) with 0.21 ± 0.09 PgC y?1 and displays a strong shallow respiration in the upper 200 m. However, the SIZ contribution can increase up to 14% depending on the depth range investigated. We also consider vertical turbulent fluxes, which can be neglected at depth but are important near the surface. Our work provides a complementary approach to previous studies and is relevant for work that focuses on evaluating the biogeochemical impacts of changes in Antarctic sea-ice extent. Refining estimates of carbon export and understanding its drivers ultimately impacts our comprehension of climate variability at the global ocean scale.
Publisher: John Wiley & Sons, Ltd Article number: e2024GB008193
Keywords: Sørishavet; biogeokjemi; fotosyntese; fytoplankton; havis; karbon syklus; sjøis

Giant iceberg meltwater increases upper-ocean stratification and vertical mixing - Lucas, Natasha S.; Brearley, J. Alexander; Hendry, Katharine R.; Spira, Theo; Braakmann-Folgmann, Anne; Abrahamsen, E. Povl; Meredith, Michael P.; Tarling, Geraint A. (Nature Geoscience, 2025)
Ice-sheet mass loss is one of the clearest manifestations of climate change, with Antarctica discharging mass into the ocean via melting or through calving. The latter produces icebergs that can modify ocean water properties, often at great distances from source. This affects upper-ocean physics and primary productivity, with implications for atmospheric carbon drawdown. A detailed understanding of iceberg modification of ocean waters has hitherto been hindered by a lack of proximal measurements. Here unique measurements of a giant iceberg from an underwater glider enable quantification of meltwater effects on the physical and biological processes in the upper layers of the Southern Ocean, a region disproportionately important for global heat and carbon sequestration. Iceberg basal melting erodes seasonally produced winter water layer stratification, normally forming a strong potential energy barrier to vertical exchange of surface and deep waters, while freshwater run-off increases and shoals near-surface stratification. Nutrient-rich deeper waters, incorporating meltwater loaded with terrigenous material, are ventilated to below this stratification maxima, providing a potential mechanism for alleviating critical phytoplankton-limiting components. Regional historical hydrographic data demonstrate similar stratification changes during the passage of another large iceberg, suggesting that they may be an important pathway of aseasonal winter water modification.
Keywords: Sørishavet; Weddellhavet; biogeokjemi; glasiologi; global oppvarming; hydrografi; klimaendringer; klimatologi; oseanografi

Global Marine Flyways Identified for Long-Distance Migrating Seabirds From Tracking Data - Morten, Joanne M.; Carneiro, Ana P. B.; Beal, Martin; Bonnet-Lebrun, Anne-Sophie; Dias, Maria P.; Rouyer, Marie-Morgane; Harrison, Autumn-Lynn; González-Solís, Jacob; Jones, Victoria R.; Garcia Alonso, Virginia A.; Antolos, Michelle; Arata, Javier A.; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad-scale oceanic migration routes (?marine flyways?) used by multiple pelagic, long-distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989?2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long-distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad-scale flyways followed by most pelagic migratory seabirds tracked to-date at an ocean-basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure-of-eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind-driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean-basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.
Publisher: John Wiley & Sons, Ltd Article number: e70004
Keywords: Sørishavet; biogeografi; biologging; sjøfugler; økologi

Multi-model assessment of the deglacial climatic evolution at high southern latitudes - Obase, T.; Menviel, L.; Abe-Ouchi, A.; Vadsaria, T.; Ivanovic, R.; Snoll, B.; Sherriff-Tadano, S.; Valdes, P. J.; Gregoire, L.; Kapsch, M.-L.; Mikolajewicz, U.; Bouttes, N.; et al. (Climate of the Past, 2025)
The Quaternary climate is characterized by glacial–interglacial cycles, with the most recent transition from the last glacial maximum to the present interglacial (the last deglaciation) occurring between ∼ 21 and 9 ka. While the deglacial warming at high southern latitudes is mostly in phase with atmospheric CO2 concentrations, some proxy records indicate that the onset of the warming occurred before the CO2 increase. In addition, high southern latitudes exhibit a cooling event in the middle of the deglaciation (15–13 ka) known as the “Antarctic Cold Reversal”. In this study, we analyse transient simulations of the last deglaciation performed with six different climate models as part of the 4th phase of the Paleoclimate Modelling Intercomparison Project (PMIP4) to understand the processes driving high-southern-latitude surface temperature changes. As the protocol of the last deglaciation sets the choice of freshwater forcing as flexible, the freshwater forcing is different in each model, thus complicating the multi-model comparison. While proxy records from West Antarctica and the Pacific sector of the Southern Ocean suggest the presence of an early warming before 18 ka, only half the models show a significant warming at this time (∼ 1 °C or ∼ 10 % of the total deglacial warming). All models simulate a major warming during Heinrich Stadial 1 (18–15 ka), concurrent with the CO2 increase and with a weakening of the Atlantic Meridional Overturning Circulation (AMOC) in some models. However, the simulated Heinrich Stadial 1 warming over Antarctica is smaller than the one suggested from ice core data. During the Antarctic Cold Reversal, simulations with an abrupt AMOC strengthening exhibit a high-southern-latitude cooling of 1 to 2 °C, in relative agreement with proxy records, while simulations with rapid North Atlantic meltwater input exhibit a warming. Using simple models to extract the relative AMOC contribution, we find that all climate models simulate a high-southern-latitude cooling in response to an AMOC increase with a response timescale of several hundred years, suggesting the choice of the North Atlantic meltwater forcing substantially affects high-southern-latitude temperature changes. Thus, further work needs to be carried out to reconcile the deglacial AMOC evolution with the Northern Hemisphere ice sheet disintegration and associated meltwater input. Finally, all simulations exhibit only minimal changes in Southern Hemisphere westerlies and Southern Ocean meridional circulation during the last deglaciation. Improved understanding of the processes impacting Southern Hemisphere atmospheric and oceanic circulation changes accounting for deglacial atmospheric CO2 increase is needed.
Keywords: Antarktis; Sørishavet; deglasiasjon; klimamodeller; paleoklimatologi

Dive wiggles as a proxy of prey consumption in krill-feeding penguins - Oosthuizen, W. Chris; Schoombie, Stefan; Chimienti, Marianna; Pistorius, Pierre A.; Lowther, Andrew D. (Journal of Experimental Marine Biology and Ecology, 2025)
The dive profiles of pursuit-diving marine predators are often used to infer foraging behaviour, including potential indicators of prey consumption. ‘Wiggles’ are undulations in dive profiles that relate to foraging activity in a variety of marine predators. In penguins, wiggles are sometimes used as a proxy for prey consumption (e.g., catch per unit effort, CPUE), but this relationship remains poorly validated and likely varies with diet. We deployed animal-borne video cameras and depth recorders on chinstrap penguins (Pygoscelis antarcticus; n = 37) and identified over 17,000 euphausiid prey captures - mainly Antarctic krill (Euphausia superba) - during dives deeper than 3 m (n = 2458 dives). Using the video-observed prey captures as a reference, we tested how well various wiggle metrics derived from 1 Hz depth data predicted krill consumption by the penguins. Wiggle metrics generally showed a positive but noisy and highly variable relationship with the number of krill captured per dive, with association strength varying among metrics. While it is tempting to infer detailed foraging behaviours from dive wiggles (including ‘bottom distance’ generated by the R package diveMove), our results show: (1) notable rates of foraging – non-foraging dive misclassification; (2) only moderate agreement between CPUE estimated from wiggle counts and video observations; and (3) imprecise predictive models of actual prey consumption. While wiggle analyses offer some insight into prey consumption of krill-feeding penguins, our results suggest that alternative methods (e.g., acceleration-based indices) are needed to obtain more robust quantitative estimates of prey consumption.
Article Number: 152115
Keywords: Sørishavet; biologging; marin biologi; pingviner; sjøfugler; økologi

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Article Number: 304
Keywords: Sørishavet; global klimamodell; klimamodeller; klimatologi; meteorologi; oseanografi; paleoseanografi

Modeling Antarctic Sea Ice Variability Using a Brittle Rheology - Santana, Rafael; Boutin, Guillaume; Horvat, Christopher; Ólason, Einar; Williams, Timothy; Rampal, Pierre (Journal of Advances in Modeling Earth Systems, 2025)
Sea ice is a composite solid material that sustains large fracture features at scales from meters to kilometres. These fractures can play an important role in coupled atmosphere-ocean processes. To model these features, brittle sea ice physics, via the Brittle-Bingham-Maxwell (BBM) rheology, has been implemented in the Lagrangian neXt generation Sea Ice Model (neXtSIM). In Arctic-only simulations, the BBM rheology has shown a capacity to represent observationally consistent sea ice fracture patterns and breakup across a wide range of time and length scales. Still, it has not been tested whether this approach is suitable for the modeling of Antarctic sea ice, which is thinner and more seasonal compared to Arctic sea ice, and whether the ability to reproduce sea ice fractures has an impact on simulating Antarctic sea ice properties. Here, we introduce a new 50-km grid-spacing Antarctic configuration of neXtSIM, neXtSIM-Ant, using the BBM rheology. We evaluate this simulation against observations of sea ice extent, drift, and thickness and compare it with identically-forced neXtSIM simulations that use the standard modified Elastic-Visco-Plastic (mEVP) rheology. In general, using BBM results in thicker sea ice and an improved correlation of sea ice drift with observations than mEVP. We suggest that this is related to short-duration breakup events caused by Antarctic storms that are not well-simulated in the viscous-plastic model.
Publisher: John Wiley & Sons, Ltd Article number: e2024MS004584
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Publisher: John Wiley & Sons, Ltd Article Number: e71847
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; klimaendringer; marin biologi; marin økologi

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Publisher: John Wiley & Sons, Ltd Article number: e71847
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; marin biologi; marin økologi

Decline of Antarctic Circumpolar Current due to polar ocean freshening - Sohail, Taimoor; Gayen, Bishakhdatta; Klocker, Andreas (Environmental Research Letters, 2025)
The Antarctic Circumpolar Current (ACC) is the world’s strongest ocean current and plays a disproportionate role in the climate system due to its role as a conduit for major ocean basins. This current system is linked to the ocean’s vertical overturning circulation, and is thus pivotal to the uptake of heat and CO2 in the ocean. The strength of the ACC has varied substantially across warm and cold climates in Earth’s past, but the exact dynamical drivers of this change remain elusive. This is in part because ocean models have historically been unable to adequately resolve the small-scale processes that control current strength. Here, we assess a global ocean model simulation which resolves such processes to diagnose the impact of changing thermal, haline and wind conditions on the strength of the ACC. Our results show that, by 2050, the strength of the ACC declines by ∼20% for a high-emissions scenario. This decline is driven by meltwater from ice shelves around Antarctica, which is exported to lower latitudes via the Antarctic Intermediate Water. This process weakens the zonal density stratification historically supported by surface temperature gradients, resulting in a slowdown of sub-surface zonal currents. Such a decline in transport, if realised, would have major implications on the global ocean circulation.
Publisher: IOP Publishing Article number: 034046
Keywords: Sørishavet; Sørishavsstrømmen; klimaendringer; klimamodeller; oseanografi

Giant pit craters on the modern seafloor above magma-induced hydrothermal vent complexes of Scotia Sea, offshore Antarctica - Somoza, L.; Andreassen, K. M.; Plaza-Faverola, A.; Medialdea, T.; Gafeira, J.; González, F. J.; Dickens, G. R. (Scientific Reports, 2025)
Massive injection of 13C depleted carbon to the ocean and atmosphere coincided with major environmental upheaval multiple times in the geological record. For several events, the source of carbon has been attributed to explosive venting of gas produced when magmatic sills intruded organic-rich sediment. The concept mostly derives from studies of a few ancient sedimentary basins with numerous hydrothermal vent complexes (HTVCs) where craters appear to have formed across large areas of the seafloor at the same time, but good examples remain rare in strata younger than the Early Eocene. We present geophysical data documenting at least 150 large (km-scale) craters on the modern seafloor across ∼148,000 km2 of Scan Basin in the southern Scotia Sea, a remote region offshore Antarctica. Seismic and bathymetric information reveals the craters relate to vertical fluid pipes extending above dome-shaped forced folds and saucer-shaped igneous sills. Presumably, magmatic intrusions deform overlying sediment and produce thermogenic gas, where buoyant hydrothermal fluids migrate upwards from sill flanks through V-shaped gas chimneys to the seafloor. Fluid expulsion, driven by excess pore pressure, enhances vertical conduits and creates collapse structures on the seafloor. Age estimates for sill emplacement and crater formation come from correlations of seismic reflectors with bore hole data collected on IODP Expedition 382. Sills intruded into sediment at least two times, first about 12–13 Ma (Middle Miocene), which occurred with deep intrusions of stacked composite sills, and once about 0.9 Ma and associated with volcanism along Discovery Bank, which may have reactivated previous fluid venting. Crater reactivation has occurred since 0.9 Ma, although probably episodically. Importantly, at present-day, numerous craters related to sills and fluid pipes populate the seafloor above a young sedimentary basin, and the ocean and atmosphere are receiving massive quantities of 13C depleted carbon. The two phenomena are unrelated but, with changes in global climate and sedimentation, the craters could be filled simultaneously and give an impression in the rock record of rapid and coeval formation coincident with carbon emission. Interpretations of ancient HTVCs and their significance to global carbon cycling needs revision with consideration of modern seafloor regions with HTVCs, notably Scan Basin.
Article Number: 3139
Keywords: Scotiahavet; Sørishavet; chronostratigrafi; geologi; klimaendringer; marin geologi; vulkanologi

Automated krill body length estimation based on stereo camera images - Svantemann, Mette M; Krafft, Bjørn A; Thompson, Fletcher F; Zhang, Guosong; Krag, Ludvig A (ICES Journal of Marine Science, 2025)
The fishery for Antarctic krill (Euphausia superba) is the largest by tonnage in the Southern Ocean, and understanding its population dynamics is essential for the sustainable management of this fishery. The standard method for calculating Antarctic krill biomass relies on hydroacoustic survey data and incorporates krill body length data collected concurrently. Traditional scientific acoustic surveys involve manually measuring the body lengths of individual krill caught using fine- meshed nets or trawls along acoustic transects. This work is resource-demanding and could represent a source of human error. To address these challenges, we develop and test an alternative, more automated method for estimating krill body length data by employing an in-trawl stereo camera system. This system collects images that are automatically processed by a custom-trained machine learning model. The results from the machine learning model are then compared to manually measured krill subsampled from the total catch of the corresponding trawl hauls. We demonstrated the ability to extract body lengths from underwater images. However, our results highlighted uncertainties, which we propose addressing by incorporating more advanced camera technology and optimizing the observation section of the small-meshed two-layer krill trawl.
Article number: fsaf058
Keywords: Sørishavet; ekkolodd; fiskerier; fiskeriforvaltning; krill; marin biologi; plankton

Untangling the complexities of larval Antarctic krill overwintering success under climate change - Sylvester, Zephyr T; Veytia, Devi; Bahl, Alexis A; Bahlburg, Dominik; Benkort, Deborah; Bestley, Sophie; Cagdas, Bulut; Cleary, Alison C; Constable, Andrew; Corney, Stuart; Fach, Bettina A; Hellessey, Nicole; et al. (ICES Journal of Marine Science, 2025)
Antarctic krill (Euphausia superba) are integral to Southern Ocean pelagic ecosystems. Winters with extensive sea ice have been linked to high post-larval krill recruitment the following spring, suggesting that sea ice plays a critical role in larval overwinter survival. As the ocean warms and sea ice declines under climate change, understanding the mechanisms linking sea ice and krill recruitment is increasingly urgent. To address this, we developed a qualitative network model (QNM) that integrates evidence-based and hypothesized interactions to explore larval overwinter survival and growth under future climate scenarios in the southwest Atlantic sector. Our model highlights habitat-specific impacts, with substantial declines predicted for the North Antarctic Peninsula continental shelf due to reduced autumn primary productivity and warming. In contrast, survival may improve in open-ocean habitats under cooler scenarios that enhance sea-ice-associated processes, such as food availability and refuge. The inclusion of hypothesized mechanisms, such as sea-ice terraces providing refuge from predation, strengthened these conclusions and highlighted critical uncertainties, including the influence of glacial melt on food web dynamics. These findings demonstrate the value of QNMs in complementing quantitative approaches, offering a framework for identifying critical mechanisms, addressing knowledge gaps, and guiding future field and laboratory studies to improve predictions of krill responses to climate change.
Article Number: fsaf049
Keywords: Sørishavet; fiskerier; klimaendringer; krill; oseanografi; plankton

Impact of krill (Euphausia superba) meal on growth performance of aquatic animals: A meta-analysis and prospective directions - Tran, Hung Quang; Nguyen, Tram Thi; Prokešová, Markéta Dvořáková; Øverland, Margareth; Gasco, Laura; Kumar, Vikas; Van Doan, Hien; Stejskal, Vlastimil (Animal Nutrition, 2025)
Antarctic krill meal (KM) (Euphausia superba) as a substitute for fishmeal in aquatic animal diets is gaining popularity worldwide. A quantitative approach investigating the efficacy of using this protein on the production performance of aquatic animals remains widely limited. Here, we employed a meta-analysis to quantify the overall effects (Hedges’g [g] value effect size) of KM on the specific growth rate (SGR), feed conversion ratio (FCR), protein efficiency ratio (PER), and survival rate (SR) of several aquaculture species. A total of 22 records published during 2006 to 2022 from different countries, targeting 14 aquatic species, were employed in the present study. Overall, KM has a high nutritional value relative to fishmeal, particularly from the high protein and amino acid composition. Dietary KM significantly increased the overall effect size of SGR (g = 1.92) (P = 0.001); the positive effect was illustrated in marine species (g = 1.32 to 9.10) (P < 0.05) and sturgeon (Acipenser gueldenstaedtii) (g = 6.59) (P < 0.001). The overall g value for FCR (−2.42) was significantly improved compared to the control group (P < 0.001). The inclusion of KM in aquatic animal diets did not affect g value of PER (1.52, 95% confidence interval: −1.04 to 4.07) and survival rate (0.08, 95% confidence interval: −0.63 to 0.79) (P = 0.252 and 0.208, respectively). The meta-regression models indicated that SGR of rainbow trout (Oncorhynchus mykiss) was significantly correlated with dietary KM by a positive linear model (P = 0.022). The cod and sturgeon (A. gueldenstaedtii) appeared to efficiently utilize krill-containing diets as illustrated by a negative linear model (P = 0.011 and P = 0.024, respectively) between dietary KM and FCR. Dietary KM positively correlated with PER for Atlantic cod (P = 0.021). Our meta-analysis highlighted the significant outcome of KM in diets for aquaculture species by reducing pressure on forage fish from marine resources and sparing edible foods. Specifically, including KM significantly reduced economic fish-in fish-out (eFIFO) in four taxa—the top forage fish consumers (P < 0.05): marine fish, salmon, shrimp, and trout. The meta-analysis revealed the decreased food-competition feedstuff in diets for important aquaculture species (P < 0.05) fed dietary KM. The outlook for efficient use of KM from marine resources in aquafeeds was elucidated in the present work.
Keywords: Sørishavet; akvakultur; fiskerier; krill; marin biologi; marin økologi; plankton

Impact of Ocean, Sea Ice or Atmosphere Initialization on Seasonal Prediction of Regional Antarctic Sea Ice - Xiu, Yongwu; Wang, Yiguo; Luo, Hao; Garcia-Oliva, Lilian; Yang, Qinghua (Journal of Advances in Modeling Earth Systems, 2025)
Dynamical modeling is widely utilized for Antarctic sea ice prediction. However, the relative impact of initializing different model components remains unclear. We compare three sets of hindcasts of the Norwegian Climate Prediction Model (NorCPM), which are initialized by ocean, ocean/sea-ice, or atmosphere data and referred to as the OCN, OCNICE, and ATM hindcasts hereafter. The seasonal cycle of sea ice extent (SIE) in the ATM reanalysis shows a slightly better agreement with observations than the OCN and OCNICE reanalyzes. The trends of sea ice concentration (SIC) in the OCN and OCNICE reanalyzes compare well to observations, but the ATM reanalysis is poor over the western Antarctic. The OCNICE reanalysis yields the most accurate estimation of sea ice variability, while the OCN and ATM reanalyzes are comparable. Evaluation of the hindcasts reveals the predictive skill varies with region and season. Austral winter SIE of the western Antarctic can be skillfully predicted 12 months ahead, while the predictive skill in the eastern Antarctic is low. Austral winter SIE predictability can be largely attributed to high sea surface temperature predictability, thanks to skillful initialization of ocean heat content. The ATM hindcast from July or October performs best due to the effective initialization of sea-ice thickness, which enhances prediction skills until early austral summer via its long memory. Meanwhile, the stratosphere-troposphere coupling contributes to the prediction of springtime. The comparable skill between the OCN and OCNICE hindcasts implies limited benefits from SIC data on prediction when using ocean data.
Publisher: John Wiley & Sons, Ltd Article number: e2024MS004382
Keywords: Sørishavet; atmosfæren; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Extended seasonal prediction of Antarctic sea ice concentration using ANTSIC-UNet - Yang, Z.; Liu, J.; Song, M.; Hu, Y.; Yang, Q.; Fan, K.; Graversen, R. G.; Zhou, L. (The Cryosphere, 2025)
Antarctic sea ice has experienced rapid change in recent years, with the total sea ice extent abruptly decreasing after a period of gradual increase from the late 1970s until 2014. Accurate long-term predictions of Antarctic sea ice concentration by dynamical or machine learning models are crucial for supporting the expanding activities in the Southern Ocean, related to for instance scientific research, tourism and fisheries. However, dynamical models often face difficulties in accurately predicting Antarctic sea ice due to limited representations of air-ice-sea interactions, especially on seasonal timescales and during the summer months. In addition, existing deep learning approaches typically rely on historical sea ice data, neglecting the complex interactions between sea ice and other climate variables, and lack interpretability of the underlying physical processes. Moreover, little attention has been paid to extended seasonal forecasts, and systematic evaluations of the predictive skill during extreme years remain scarce. To address these challenges and gaps, we here develop a deep learning model (named ANTSIC-UNet), trained by multiple climate variables, and evaluate its skill for extended up-to-six-months seasonal prediction of Antarctic sea ice concentration. We compare the predictive skill of ANTSIC-UNet in the Pan- and regional Antarctic with two benchmark models (a linear trend and an anomaly persistence model) and a dynamical model (SEAS5). In terms of root-mean-square error (RMSE) of sea ice concentration and integrated ice-edge error (IIEE), ANTSIC-UNet shows much better skills relative to the other models for the extended seasonal prediction, especially for the extreme events in recent years. Sea ice prediction errors increase with lead time, and are smaller during autumn and winter than in summer. The Pacific and Indian Oceans show accurate prediction performance at the sea ice edge during summer, and ANTSIC-UNet provides high predictive skill in capturing the interannual variability of Pan-Antarctic and regional sea ice extent anomalies. In addition, we quantify the importance of variables through a post-hoc interpretation method. This analysis suggests that the ANTSIC-UNet prediction at short lead times is sensitive to sea surface temperature, radiative flux, and atmospheric circulation in addition to sea ice conditions. At longer lead times, zonal wind in the stratosphere appears to be an important influencing factor for the prediction. Building on these findings, we further demonstrate that incorporating physical constraints into deep learning models potentially leads to a gain in the accuracy of the Antarctic sea ice edge prediction on extended seasonal timescales.
Publisher: Copernicus Publications
Keywords: Sørishavet; havis; klimamodeller; klimatologi; kryosfæren; maskinlæring; oseanografi; sjøis

Spatial Variations of Atmospheric Alkylated Polycyclic Aromatic Hydrocarbons across the Western Pacific to the Southern Ocean: Unexpected Increasing Deposition - Zhu, Fu-Jie; Lu, Xi-Mei; Jia, Jing-Wen; Zhang, Xue; Xing, De-Feng; Cai, Ming-Hong; Kallenborn, Roland; Li, Yi-Fan; Muir, Derek C. G.; Zhang, Zi-Feng; Zhang, Xianming (Environmental Science & Technology, 2025)
Spatial variations of atmospheric alkylated polycyclic aromatic hydrocarbons (Alk-PAHs) are key to understanding their long-range atmospheric transport (LRAT). However, limited Alk-PAHs data have hindered their LRAT characterizations on a global scale. In this study, 49 Alk-PAHs were measured in the atmospheric samples collected across the Western Pacific to the Southern Ocean. The summed concentration of 39 frequently detected Alk-PAHs (Σ39Alk-PAHs) was 25.8 ± 25.3 ng m–3. The concentrations of Σ39Alk-PAHs significantly declined with the decrease in latitude (°N). Higher concentrations (55.8 ± 33.8 ng m–3) were linked to continental air mass compared to oceanic/Antarctica air mass (17.0 ± 13.6 ng m–3), highlighting continental emissions as the primary source of marine atmospheric Alk-PAHs. An unexpected increase in the G/P partitioning ratio (KP) was found in samples farther away from the continent, which cannot be explained by the influence of temperature on the partitioning process. Deposition analysis suggested that gaseous concentrations and the G/P partitioning largely influenced deposition patterns. Hypothetical scenario analysis indicated that increased KP under snowy conditions could enhance the total Alk-PAH deposition. These findings emphasize the need for accurate characterization of partitioning and deposition processes when studying the global fate of Alk-PAHs, particularly in remote and polar regions.
Publisher: American Chemical Society
Keywords: Sørishavet; atmosfæren; biokjemi; forurensning; kjemi; miljøgifter

Observation of wave propagation over 1,000 km into Antarctica winter pack ice - Nose, Takehiko; Katsuno, Tomotaka; Waseda, Takuji; Ushio, Shuki; Rabault, Jean; Kodaira, Tsubasa; Voermans, Joey (Coastal Engineering Journal, 2024)
A drifting wave-ice buoy (Medusa-766) was deployed at the Lützow-Holm Bay (LHB) marginal ice zone in Antarctica during the 63rd Japanese Antarctic Research Expedition to study the wave influence on the unstable LHB fast ice. Medusa-766 survived the Antarctic winter as it was located deep in the ice cover with the shortest distance to the ice-free Southern Ocean over 1,000?km; at this time, there was evidence of 8-cm-height wave signal at the buoy position. Using the the ECMWF?s reanalysis wave data, we show that the incoming waves were likely 4-m waves that were generated by an extratropical cyclone in the Southern Ocean. Wave-induced ice breakup potential for this event could extend hundreds of kilometres into the ice field. When Medusa-766 was in LHB in the summer months, it did not detect sizable wave energy despite the low sea ice concentration extent even during on-ice wave events. Understanding the wave attenuation characteristics is needed to elucidate the ocean wave effect to the unstable LHB fast ice. The success of Medusa-766 demonstrates the robustness of the general design and the high sensitivity of the sensor used, which is promising for future LHB wave?ice interaction research.
Publisher: Taylor & Francis
Keywords: Sørishavet; havis; isshelf

Microplastics in Southern Ocean sea ice: a pan-Antarctic perspective - Anna Kelly; Thomas Rodemann; Klaus M. Meiners; Heidi J. Auman; Sebastien Moreau; Francois Fripiat; Bruno Dellile; Delphine Lannuzel (Water Emerging Contaminants & Nanoplastics, 2024)
Microplastic (MP; plastic particles < 5 mm) pollution is pervasive in the marine environment, including remote polar environments. This study provides the first pan-Antarctic survey of MP pollution in Southern Ocean sea ice by analyzing sea ice cores from several diverse Antarctic regions. Abundance, chemical composition, and particle size data were obtained from 19 archived ice core samples. The cores were melted, filtered, and chemically analyzed using Fourier-transform infrared spectroscopy and 4,090 MP particles were identified. Nineteen polymer types were found across all samples, with an average concentration of 44.8 (± 50.9) particles·L-1. Abundance and composition varied with ice type and geographical location. Pack ice exhibited significantly higher particle concentrations than landfast ice, suggesting open ocean sources of pollution. Winter sea ice cores had significantly more MPs than spring and summer-drilled cores, suggesting ice formation processes play a role in particle incorporation. Smaller particles dominated across samples. Polyethylene (PE) and polypropylene (PP) were the most common polymers, mirroring those most identified across marine habitats. Higher average MP concentrations in developing sea ice during autumn and winter, contrasting lower levels observed in spring and summer, suggest turbulent conditions and faster growth rates are likely responsible for the increased incorporation of particles. Southern Ocean MP contamination likely stems from both local and distant sources. However, the circulation of deep waters and long-range transport likely contribute to the accumulation of MPs in regional gyres, coastlines, and their eventual incorporation into sea ice. Additionally, seasonal sea ice variations likely influence regional polymer compositions, reflecting the MP composition of the underlying waters.
Keywords: Sørishavet; forurensning; havis; iskjerner; mikroplast; sjøis

Field comparison of Antarctic krill (Euphausia superba) backscatter and aggregation types using NORTEK and SIMRAD echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Cutter, George R.; Macaulay, Gavin J. (ICES Journal of Marine Science, 2024)
Temporal distributions of Antarctic krill (Euphausia superba) density and aggregation types were characterized and compared using Nortek Signature100 and SIMRAD Wideband Autonomous Transceiver (WBAT) upward-looking echosounders. Noise varied between the two echosounders. With the Signature100, it was necessary to correct data for background, transient, and impulse noises, while the WBAT data needed to be corrected for background noise only. For selected regions with no visible backscatter, the signal-to-noise ratio of Sv values (i.e. the ratio between the signal and the background noise level) did not vary between the two echosounders. Surface echo backscatter was similar during similar time periods. Descriptive metrics were used to quantify spatial and temporal krill vertical distributions: volume backscatter, mean depth, center of mass, inertia, equivalent area, aggregation index, and proportion occupied. Krill backscatter density differed between the two instruments but was detected at similar mean depths. Krill aggregations were identified at each mooring location and classified in three types based on morphological characteristics. Each type of aggregation shape differed at the two spatially separated moorings, while the acoustic density of each aggregation type was similar. The Signature100 detected a lower number of krill aggregations (n = 133) compared to the WBAT (n = 707). Although both instruments can be used for autonomous deployment and sampling of krill over extended periods, there is a strong caveat for the use of the Signature100 due to significant differences in noise characteristics and krill detection.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; marin biologi; plankton

Characterizing Antarctic air-breathing predator dive patterns on a common prey base from stationary echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Macaulay, Gavin J. (Polar Science, 2024)
Diving patterns of air-breathing predators were monitored from three moored subsurface upward-looking echosounders. Complete and partial dive profiles were visible on active acoustic records as echoes that started and/or returned to the surface. Dive metrics: maximum dive depths, durations, and wiggle count were measured and angles, distances, and velocities, were calculated at each site. Dive shapes ‘U’, ‘V’ and ‘W’ were derived using the number of wiggles and the percentage of dive bottom time. Dive profiles were classified into four types with type 1 dives being short in total duration and distance, low velocities, small angles, shallow, and linked to ‘U’ and ‘W’ shapes. Type 2 dives were short in distance, had low velocities, shallow depths, and were linked to ‘V’ dives. Dive types 3 and 4 had higher velocities, larger angles, longer total durations, and were deeper than types 1 and 2. Observed dive types could correspond to travelling, exploring, and foraging predator behaviors. Significant predator-prey overlaps occurred with predator dive profile counts correlated with krill aggregation thickness, density, and depth. This study demonstrates the utility of using stationary active acoustics to identify predator dive profiles with a simultaneous characterization of the potential prey field.
Article number: 100974
Keywords: Deceptionøya; Sør-Shetlandsøyene; Sørishavet; batymetri; hydroakustikk; marin biologi; marine økosystemer; oseanografi

Seasonal acoustic presence of marine mammals at the South Orkney Islands, Scotia Sea - Åsvestad, Linn; Ahonen, Heidi; Menze, Sebastian; Lowther, Andrew; Lindstrøm, Ulf; Krafft, Bjørn A. (Royal Society Open Science, 2024)
Increased knowledge about marine mammal seasonal distribution and species assemblage from the South Orkney Islands waters is needed for the development of management regulations of the commercial fishery for Antarctic krill (Euphausia superba) in this region. Passive acoustic monitoring (PAM) data were collected during the autumn and winter seasons in two consecutive years (2016, 2017), which represented highly contrasting environmental conditions due to the 2016 El Niño event. We explored differences in seasonal patterns in marine mammal acoustic presence between the two years in context of environmental cues and climate variability. Acoustic signals from five baleen whale species, two pinniped species and odontocete species were detected and separated into guilds. Although species diversity remained stable over time, the ice-avoiding and ice-affiliated species dominated before and after the onset of winter, respectively, and thus demonstrating a shift in guild composition related to season. Herein, we provide novel information about local marine mammal species diversity, community structure and residency times in a krill hotspot. Our study also demonstrates the utility of PAM data and its usefulness in providing new insights into the marine mammal habitat use and responses to environmental conditions, which are essential knowledge for the future development of a sustainable fishery management in a changing ecosystem.
_eprint: https://royalsocietypublishing.org/doi/pdf/10.1098/rsos.230233
Keywords: Sørishavet; marin biologi; pattedyr; zoologi

Sources of low-frequency variability in observed Antarctic sea ice - Bonan, D. B.; Dörr, J.; Wills, R. C. J.; Thompson, A. F.; Årthun, M. (The Cryosphere, 2024)
Antarctic sea ice has exhibited significant variability over the satellite record, including a period of prolonged and gradual expansion, as well as a period of sudden decline. A number of mechanisms have been proposed to explain this variability, but how each mechanism manifests spatially and temporally remains poorly understood. Here, we use a statistical method called low-frequency component analysis to analyze the spatiotemporal structure of observed Antarctic sea ice concentration variability. The identified patterns reveal distinct modes of low-frequency sea ice variability. The leading mode, which accounts for the large-scale, gradual expansion of sea ice, is associated with the Interdecadal Pacific Oscillation and resembles the observed sea surface temperature trend pattern that climate models have trouble reproducing. The second mode is associated with the central Pacific El Niño–Southern Oscillation (ENSO) and the Southern Annular Mode and accounts for most of the sea ice variability in the Ross Sea. The third mode is associated with the eastern Pacific ENSO and Amundsen Sea Low and accounts for most of the pan-Antarctic sea ice variability and almost all of the sea ice variability in the Weddell Sea. The third mode is also related to periods of abrupt Antarctic sea ice decline that are associated with a weakening of the circumpolar westerlies, which favors surface warming through a shoaling of the ocean mixed layer and decreased northward Ekman heat transport. Broadly, these results suggest that climate model biases in long-term Antarctic sea ice and large-scale sea surface temperature trends are related to each other and that eastern Pacific ENSO variability is a key ingredient for abrupt Antarctic sea ice changes.
Publisher: Copernicus Publications
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Glacial–interglacial Circumpolar Deep Water temperatures during the last 800 000 years: estimates from a synthesis of bottom water temperature reconstructions - Chandler, D. M.; Langebroek, Petra M. (Clim. Past, 2024)
Future climate and sea level projections depend sensitively on the response of the Antarctic Ice Sheet to ocean-driven melting and the resulting freshwater fluxes into the Southern Ocean. Circumpolar Deep Water (CDW) transport across the Antarctic continental shelf and into cavities beneath ice shelves is increasingly recognised as a crucial heat source for ice shelf melt. Quantifying past changes in the temperature of CDW is therefore of great benefit for modelling ice sheet response to past warm climates, for validating paleoclimate models, and for putting recent and projected changes in CDW temperature into context. Here we compile the available bottom water temperature reconstructions representative of CDW over the past 800 kyr. Estimated interglacial warming reached anomalies of +0.6 +/- 0.4 degrees C (MIS 11) and +0.5 +/- 0.5 degrees C (MIS 5) relative to present. Glacial cooling typically reached anomalies of ca. -1.5 to -2 degrees C, therefore maintaining positive thermal forcing for ice shelf melt even during glacials in the Amundsen Sea region of West Antarctica. Despite high variance amongst a small number of records and poor (4 kyr) temporal resolution, we find persistent and close relationships between our estimated CDW temperature and Southern Ocean sea surface temperature, Antarctic surface air temperature, and global deep-water temperature reconstructions at glacial-cycle timescales. Given the important role that CDW plays in connecting the world's three main ocean basins and in driving Antarctic Ice Sheet mass loss, additional temperature reconstructions targeting CDW are urgently needed to increase temporal and spatial resolution and to decrease uncertainty in past CDW temperatures - whether for use as a boundary condition, for model validation, or for understanding past oceanographic changes.
Publisher: Copernicus Publications
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Shackletons svanesang, Shackleton-Rowett-ekspedisjonen 1921-22 - Chojecki, Jan (Polarboken, 2024)
Keywords: Sørishavet; ekspedisjoner; historie

Observations of the Antarctic Slope Current in the Southeastern Weddell Sea: A Bottom-Enhanced Current and Its Seasonal Variability - Darelius, Elin; Fer, Ilker; Janout, Markus; Daae, Kjersti; Steiger, Nadine (Journal of Geophysical Research: Oceans, 2024)
Abstract The Antarctic Slope Front and the associated Antarctic Slope Current dynamically regulate the exchanges of heat across the continental shelf break around Antarctica. Where the front is weak, relatively warm deep waters reach the ice shelf cavities, contributing to basal melting and ultimately affecting sea level rise. Here, we present new 2017?2021 records from two moorings deployed on the upper continental slope (530 and 738 m depth) just upstream of the Filchner Trough in the southeastern Weddell Sea. The structure and seasonal variability of the frontal system in this region, central to the inflow of warm water toward the large Filchner-Ronne Ice Shelf, is previously undescribed. We use the records to describe the mean state and the seasonal variability of the regional hydrography and the southern part of the Antarctic Slope Current. We find that (a) the current is, contrary to previous assumptions, bottom-enhanced, (b) the isotherms slope upwards toward the shelf break, and more so for warmer isotherms, and (c) the monthly mean thermocline depth is shallowest in February-March and deepest in May-June while (d) the current is strongest in April-June. On monthly timescales, we show that (e) positive temperature anomalies of the de-seasoned records are associated with weaker-than-average currents. We propose that the upward-sloping isotherms are linked to the local topography and conservation of potential vorticity. Our results contribute to the understanding of how warm ocean waters propagate southward and potentially affect basal melt rates at the Filchner-Ronne Ice Shelf.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020666
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi

Southern Ocean sea ice, icebergs, and meteorological data from maritime sources for the period 1929 to 1940 - Divine, Dmitry V.; Divina, Svetlana; Bjørge, Ole Edvard; Isaksson, Elisabeth; Jølle, Harald Dag; Stokkeland, Ivar; Vasquez Guzman, Mariela; Wilkinson, Sally; Wilkinson, Clive (Geoscience Data Journal, 2024)
Maritime historical documentary sources of weather and state of sea surface including sea ice can aid in filling a known climate knowledge gap for the Southern Ocean and Antarctica for the first half of the 20th century. This study presents a data set of marine climate, sea ice and icebergs recovered from a collection of logbooks from mainly Norwegian whaling factory ships that operated in the Southern Ocean during 1929-1940. The data set comprises some 8000 weather and 4000 sea ice/open sea records from austral summers of the study period. This paper further discusses the structure and content of most common Norwegian maritime documentary sources of the period along with the practices of logging information relevant for the study, such as time keeping, positioning and making weather observations. An emphasis was made on recovery of notes on sea ice and icebergs and their interpretation in terms of WMO categories of sea ice concentration. Data, including ship-related metadata from all individual documents are homogenized and structured to a common machine-readable format that simplifies its ingestion into relevant climate data depositories.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; hvalfangst; isberg; klima; meteorologi; sjøis; skipsloggbøker

Observed water-mass characteristics and circulation off Prydz Bay, East Antarctica - Foppert, Annie; Bestley, Sophie; Shadwick, Elizabeth H.; Klocker, Andreas; Vives, Clara R.; Liniger, Guillaume; Westwood, Karen J. (Frontiers in Marine Science, 2024)
Circulation and water masses in the greater Prydz Bay region were surveyed in the austral summer 2021 (January-March) during the ‘Trends in Euphausiids off Mawson, Predators and Oceanography’ (TEMPO) experiment, and are described in this paper. The Southern Antarctic Circumpolar Current Front is found in the northern part of the survey area, generally near 63-64°S, whereas the Southern Boundary Front is located between 64 and 65.5°S. The westward flowing Antarctic Slope Front (ASF) is found in the southern part of the survey area near the continental slope on most transects. Highest concentrations of oxygen (> 300 µmol kg−1) are found in shelf waters at stations in Prydz Bay, south of 67°S along 75°E, whereas the lowest oxygen values are found in the Circumpolar Deep Water layer, with an average of roughly 215 µmol kg−1. North of the northern extension of the ASF, surface mixed layers are between 20 and 60 m deep. Mixed layers tend to deepen slightly in the northern part of the survey, generally increasing north of 64°S where the ocean has been ice-free the longest. We find evidence of upwelling of waters into the surface layers, based on temperature anomaly, particularly strong along 80°E. Enhanced variability of biogeochemical properties - nutrients, DIC, DO - in the AASW layer is driven by a combination of sea-ice and biological processes. Antarctic Bottom Water, defined as water with neutral density > 28.3 kg m-3, was sampled at all the offshore full-depth stations, with a colder/fresher variety along western transects and a warmer/saltier variety in the east. Newly formed Antarctic Bottom Water – the coldest, freshest, and most recently ventilated – is mostly found in the deep ocean along 65°E, in the base of the Daly Canyon.
Keywords: AABW; Sørishavet; klimatologi; oseanografi; vannmasser

An Assessment of Subseasonal Prediction Skill of the Antarctic Sea Ice Edge - Gao, Yuchun; Xiu, Yongwu; Nie, Yafei; Luo, Hao; Yang, Qinghua; Zampieri, Lorenzo; Lv, Xianqing; Uotila, Petteri (Journal of Geophysical Research: Oceans, 2024)
Abstract In this study, the subseasonal Antarctic sea ice edge prediction skill of the Copernicus Climate Change Service (C3S) and Subseasonal to Seasonal (S2S) projects was evaluated by a probabilistic metric, the spatial probability score (SPS). Both projects provide subseasonal to seasonal scale forecasts of multiple coupled dynamical systems. We found that predictions by individual dynamical systems remain skillful for up to 38 days (i.e., the ECMWF system). Regionally, dynamical systems are better at predicting the sea ice edge in the West Antarctic than in the East Antarctic. However, the seasonal variations of the prediction skill are partly system-dependent as some systems have a freezing-season bias, some had a melting-season bias, and some had a season-independent bias. Further analysis reveals that the model initialization is the crucial prerequisite for skillful subseasonal sea ice prediction. For those systems with the most realistic initialization, the model physics dictates the propagation of initialization errors and, consequently, the temporal length of predictive skill. Additionally, we found that the SPS-characterized prediction skill could be improved by increasing the ensemble size to gain a more realistic ensemble spread. Based on the C3S systems, we constructed a multi-model forecast from the above principles. This forecast consistently demonstrated a superior prediction skill compared to individual dynamical systems or statistical observation-based benchmarks. In summary, our results elucidate the most important factors (i.e., the model initialization and the model physics) affecting the currently available subseasonal Antarctic sea ice prediction systems and highlighting the opportunities to improve them significantly.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; sjøis

Museomics analyses inform about Channichthys icefish species diversity - Garmann-Aarhus, Benedicte; Nikolaeva, Ekaterina; Desvignes, Thomas; Straube, Nicolas; Matschiner, Michael (bioRxiv, 2024)
The rapid diversification of notothenioid fishes in the waters surrounding the Antarctic continent is a prime example of the process of adaptive radiation. Within around 10 million years, Antarctic notothenioids have diversified into over 100 species with a broad range of lifestyles and ecological adaptations. However, the exact number of species within this radiation has long been unclear. Particularly challenging is the taxonomy of the genus Channichthys, for which between one and nine species have been recognized by different authors. The putative species from this genus are known from a limited number of representative specimens, of which most were sampled decades ago. Here, we investigated the mitochondrial genomes of museum specimens representing the four recently recognized species Unicorn Icefish (C. rhinoceratus), Red Icefish (C. rugosus), Sailfish Pike (C. velifer), and Charcoal Icefish (C. panticapaei), complemented by morphological analyses. All analyzed specimens were collected in the 1960s and 1970s and fixed in formaldehyde, and their DNA has thus been heavily degraded. Applying ancient-DNA protocols for DNA extraction and single-stranded library preparation, we were nevertheless able to obtain sufficient endogenous DNA to reconstruct the mitochondrial genomes of one specimen of each species. These mitochondrial genome sequences were nearly identical for the three specimens assigned to Unicorn Icefish, Red Icefish, and Sailfish Pike, while greater mitochondrial divergence was observed for the Charcoal Icefish specimens. We discuss possible explanations of the contrast between these molecular results and the recognizable morphological variation found among the four species, and recommend that at least the Charcoal Icefish be included the list of valid icefish and notothenioid species.Competing Interest StatementThe authors have declared no competing interest.
Article Number: 32
Keywords: Sørishavet; fisker; genetisk analyse; marin biologi; morfologi; taksonomi; zoologi; økologi

Machine learning applied to species occurrence and interactions: the missing link in biodiversity assessment and modelling of Antarctic plankton distribution - Grillo, Marco; Schiaparelli, Stefano; Durazzano, Tiziana; Guglielmo, Letterio; Granata, Antonia; Huettmann, Falk (Ecological Processes, 2024)
Background: Plankton is the essential ecological category that occupies the lower levels of aquatic trophic networks, representing a good indicator of environmental change. However, most studies deal with distribution of single spe- cies or taxa and do not take into account the complex of biological interactions of the real world that rule the ecologi- cal processes. Results: This study focused on analyzing Antarctic marine phytoplankton, mesozooplankton, and microzooplankton, examining their biological interactions and co-existences. Field data yielded 1053 biological interaction values, 762 coexistence values, and 15 zero values. Six phytoplankton assemblages and six copepod species were selected based on their abundance and ecological roles. Using 23 environmental descriptors, we modelled the distribution of taxa to accurately represent their occurrences. Sampling was conducted during the 2016–2017 Italian National Antarctic Programme (PNRA) ‘P-ROSE’ project in the East Ross Sea. Machine learning techniques were applied to the occurrence data to generate 48 predictive species distribution maps (SDMs), producing 3D maps for the entire Ross Sea area. These models quantitatively predicted the occurrences of each copepod and phytoplankton assemblage, providing crucial insights into potential variations in biotic and trophic interactions, with significant implications for the man- agement and conservation of Antarctic marine resources. The Receiver Operating Characteristic (ROC) results indi- cated the highest model efficiency, for Cyanophyta (74%) among phytoplankton assemblages and Paralabidocera antarctica (83%) among copepod communities. The SDMs revealed distinct spatial heterogeneity in the Ross Sea area, with an average Relative Index of Occurrence values of 0.28 (min: 0; max: 0.65) for phytoplankton assemblages and 0.39 (min: 0; max: 0.71) for copepods. Conclusion: The results of this study are essential for a science-based management for one of the world’s most pris- tine ecosystems and addressing potential climate-induced alterations in species interactions. Our study emphasizes the importance of considering biological interactions in planktonic studies, employing open access and machine learning for measurable and repeatable distribution modelling, and providing crucial ecological insights for informed conservation strategies in the face of environmental change.
Article number: 56 (2024)
Keywords: Rosshavet; Sørishavet; biodiversitet; fytoplankton; marin biologi

Drivers of phytoplankton distribution, abundance and community composition off East Antarctica, from 55-80°E (CCAMLR Division 58.4.2 East) - Heidemann, Asta C.; Westwood, Karen J.; Foppert, Annie; Wright, Simon W.; Klocker, Andreas; Vives, Clara R.; Wotherspoon, Simon; Bestley, Sophie (Frontiers in Marine Science, 2024)
Southern Ocean phytoplankton form the base of the Antarctic food web, influencing higher trophic levels through biomass and community structure. We examined phytoplankton distribution and abundance in the Indian Sector of the Southern Ocean during austral summer as part a multidisciplinary ecosystem survey: Trends in Euphausiids off Mawson, Predators and Oceanography (TEMPO, 2021). Sampling covered six meridional transects from 55-80°E, and from 62°S or 63°S to the ice edge. To determine phytoplankton groups, CHEMTAX analysis was undertaken on pigments measured using HPLC. Diatoms were the dominant component of phytoplankton communities, explaining 56% of variation in chlorophyll a (Chl a), with haptophytes also being a major component. Prior to sampling the sea ice had retreated in a south-westerly direction, leading to shorter ice-free periods in the west (< 44 days, ≤65°E) compared to east (> 44 days, ≥70°E), inducing a strong seasonal effect. The east was nutrient limited, indicated by low-iron forms of haptophytes, and higher silicate:nitrate drawdown ratios (5.1 east vs 4.3 west), pheophytin a (phaeo) concentrations (30.0 vs 18.4 mg m-2) and phaeo:Chl a ratios (1.06 vs 0.53). Biological influences were evident at northern stations between 75-80°E, where krill “super-swarms” and feeding whales were observed. Here, diatoms were depleted from surface waters likely due to krill grazing, as indicated by high phaeo:Chl a ratios (> 0.75), and continued presence of haptophytes, associated with inefficient filtering or selective grazing by krill. Oceanographic influences included deeper mixed layers reducing diatom biomass, and a bloom to the north of the southern Antarctic Circumpolar Current Front in the western survey area thought to be sinking as waters flowed from west to east. Haptophytes were influenced by the Antarctic Slope Front with high-iron forms prevalent to the south only, showing limited iron transfer from coastal waters. Cryptophytes were associated with meltwater, and greens (chlorophytes + prasinophytes) were prevalent below the mixed layer. The interplay of seasonal, biological and oceanographic influences on phytoplankton populations during TEMPO had parallels with processes observed in the BROKE and BROKE-West voyages conducted 25 and 15 years earlier, respectively. Our research consolidates understanding of the krill ecosystem to ensure sustainable management in East Antarctic waters.
Keywords: Sørishavet; fytoplankton; krill; marin biologi; marine økosystemer; oseanografi; phytoplankton

Ocean warming as a trigger for irreversible retreat of the Antarctic ice sheet - Hill, Emily A.; Gudmundsson, G. Hilmar; Chandler, David M. (Nature Climate Change, 2024)
Warmer ocean conditions could impact future ice loss from Antarctica due to their ability to thin and reduce the buttressing of laterally confined ice shelves. Previous studies highlight the potential for a cold to warm ocean regime shift within the sub-shelf cavities of the two largest Antarctic ice shelves—the Filchner–Ronne and Ross. However, how this impacts upstream ice flow and mass loss has not been quantified. Here using an ice sheet model and an ensemble of ocean-circulation model sub-shelf melt rates, we show that transition to a warm state in those ice shelf cavities leads to a destabilization and irreversible grounding line retreat in some locations. Once this ocean shift takes place, ice loss from the Filchner–Ronne and Ross catchments is greatly accelerated, and conditions begin to resemble those of the present-day Amundsen Sea sector—responsible for most current observed Antarctic ice loss—where this thermal shift has already occurred.
Keywords: Amundsenhavet; Antarktis; Sørishavet; global oppvarming; innlandsis; klimaendringer; klimatologi

Stepwise Oligocene–Miocene breakdown of subpolar gyres and strengthening of the Antarctic Circumpolar Current - Hoem, F. S.; van den Broek, K.; López-Quirós, A.; van de Lagemaat, S. H. A.; Bohaty, S. M.; Hillenbrand, C.-D.; Larter, R. D.; van Peer, T. E.; Brinkhuis, H.; Sangiorgi, F.; Bijl, P. K. (J. Micropalaeontol., 2024)
Through the Cenozoic (66–0 Ma), the dominant mode of ocean surface circulation in the Southern Ocean transitioned from two large subpolar gyres to circumpolar circulation with a strong Antarctic Circumpolar Current (ACC) and complex ocean frontal system. Recent investigations in the southern Indian and Pacific oceans show warm Oligocene surface water conditions with weak frontal systems that started to strengthen and migrate northwards during the late Oligocene. However, due to the paucity of sedimentary records and regional challenges with traditional proxy methods, questions remain about the southern Atlantic oceanographic transition from gyral to circumpolar circulation, with associated development of frontal systems and sea ice cover in the Weddell Sea. Our ability to reconstruct past Southern Ocean surface circulation and the dynamic latitudinal positions of the frontal systems has improved over the past decade. Specifically, increased understanding of the modern ecologic affinity of organic-walled dinoflagellate cyst (dinocyst) assemblages from the Southern Ocean has improved reconstructions of distinct past oceanographic conditions (sea surface temperature, salinity, nutrients, and sea ice) using downcore assemblages from marine sediment records. Here we present new late Oligocene to latest Miocene (∼ 26–5 Ma) dinocyst assemblage data from marine sediment cores in the southwestern Atlantic Ocean (International Ocean Discovery Program (IODP) Site U1536, Ocean Drilling Program (ODP) Site 696 and piston cores from Maurice Ewing Bank). We compare these to previously published latest Eocene–latest Miocene (∼ 37–5 Ma) dinocyst assemblage records and sea surface temperature (SST) reconstructions available from the SW Atlantic Ocean in order to reveal oceanographic changes as the Southern Ocean gateways widen and deepen. The observed dinocyst assemblage changes across the latitudes suggest a progressive retraction of the subpolar gyre and southward migration of the subtropical gyre in the Oligocene–early Miocene, with strengthening of frontal systems and progressive cooling since the middle Miocene (∼ 14 Ma). Our data are in line with the timing of the removal of bathymetric and geographic obstructions in the Drake Passage and Tasmanian Gateway regions, which enhanced deep-water throughflow that broke down gyral circulation into the Antarctic circumpolar flow. Although the geographic and temporal coverage of the data is relatively limited, they provide a first insight into the surface oceanographic evolution of the late Cenozoic southern Atlantic Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; Sørishavsstrømmen; Weddellhavet; mikropaleontologi; oseanografi

Revisiting Winter Southern Ocean CO2 Uptake Based on CALIPSO Observations - Huang, Hao; Zhang, Ke; Zhang, Zhaoru; Smith Jr., Walker; He, Jianfeng; Liu, Na; Le, Chengfeng (Geophysical Research Letters, 2024)
The absorption of atmospheric carbon dioxide (CO2) in the Southern Ocean represents a critical component of the global oceanic carbon budget. Previous assessments of air-sea carbon flux variations and long-term trends in polar regions during winter have faced limitations due to scarce field data and the lack of ocean color satellite imagery, causing uncertainties in estimating CO2 flux estimation. This study utilized the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation satellite to construct a continuous 16-year (2006?2021) time series of sea surface partial pressure of CO2 (pCO2) in the Southern Ocean. Our findings revealed that the polar region in South Ocean acts as a carbon sink in winter, with CO2 flux of ?30 TgC in high-latitude areas (South of 50°S). This work highlights the efficacy of active remote sensing for monitoring sea surface pCO2 and contributes insights into the dynamic carbonate systems of the Southern Ocean.
Publisher: John Wiley & Sons, Ltd Article Number: e2024GL108335
Keywords: Sørishavet; karbon syklus; karbondioksid; klimaendringer; oseanografi

Sensitivity of the stock assessment for the Antarctic krill fishery to time-varying natural and fishing mortality - Johannessen, Elling Deehr; Krafft, Bjørn A.; Donovan, Carl R.; Wiff, Rodrigo; Caneco, Bruno; Lowther, Andrew (Fisheries Management and Ecology, 2024)
The stock assessment model for the Antarctic krill fishery is a population model operating on daily timesteps, which permits modeling within-year patterns of some population dynamics. We explored the effects of including within-year patterns in natural and fishing mortality on catch limits of krill, by incorporating temporal presence of key predator species and contemporary temporal trends of the fishing fleet. We found that inclusion of within-year variation in natural and fishing mortalities increased catch limits. Fishing mortality had a greater effect than natural mortality despite differences in top-down predation on krill, and potentially increased catch limits by 24% compared to the baseline model. Additionally, the stock assessment model allowed a higher catch limit when fishing was during peak summer months than autumn. Number of days with active fishing was negatively related to precautionary catch limits. Future stock assessments should incorporate contemporary spatiotemporal fishing trends and consider implementing additional ecosystem components into the model.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; fiskeriforvaltning; krill; marin økologi; marine økosystemer; plankton

SMOS-derived Antarctic thin sea ice thickness: data description and validation in the Weddell Sea - Kaleschke, L.; Tian-Kunze, X.; Hendricks, S.; Ricker, R. (Earth Syst. Sci. Data, 2024)
Accurate satellite measurements of the thickness of Antarctic sea ice are urgently needed but pose a particular challenge. The Antarctic data presented here were produced using a method to derive the sea ice thickness from 1.4 GHz brightness temperatures previously developed for the Arctic, with only modified auxiliary data. The ability to observe the thickness of thin sea ice using this method is limited to cold conditions, meaning it is only reasonable during the freezing period, typically March to October. The Soil Moisture and Ocean Salinity (SMOS) level-3 sea ice thickness product contains estimates of the sea ice thickness and its uncertainty up to a thickness of about 1 m. The sea ice thickness is provided as a daily average on a polar stereographic projection grid with a sample resolution of 12.5 km, while the SMOS brightness temperature data used have a footprint size of about 35–40 km in diameter. Data from SMOS have been available since 2010, and the mission's operation has been extended to continue until at least the end of 2025. Here we compare two versions of the SMOS Antarctic sea ice thickness product which are based on different level-1 input data (v3.2 based on SMOS L1C v620 and v3.3 based on SMOS L1C 724). A validation is performed to generate a first baseline reference for future improvements of the retrieval algorithm and synergies with other sensors. Sea ice thickness measurements to validate the SMOS product are particularly rare in Antarctica, especially during the winter season and for the valid range of thicknesses. From the available validation measurements, we selected datasets from the Weddell Sea that have varying degrees of representativeness: Helicopter-based EM Bird (HEM), Surface and Under-Ice Trawl (SUIT), and stationary Upward-Looking Sonars (ULS). While the helicopter can measure hundreds of kilometres, SUIT's use is limited to distances of a few kilometres and thus only captures a small fraction of an SMOS footprint. Compared to SMOS, the ULS are point measurements and multi-year time series are necessary to enable a statistically representative comparison. Only four of the ULS moorings have a temporal overlap with SMOS in the year 2010. Based on selected averaged HEM flights and monthly ULS climatologies, we find a small mean difference (bias) of less than 10 cm and a root mean square deviation of about 20 cm with a correlation coefficient R > 0.9 for the valid sea ice thickness range between 0 and about 1 m. The SMOS sea ice thickness showed an underestimate of about 40 cm with respect to the less representative SUIT validation data in the marginal ice zone. Compared with sea ice thickness outside the valid range, we find that SMOS strongly underestimates the real values, which underlines the need for combination with other sensors such as altimeters. In summary, the overall validity of the SMOS sea ice thickness for thin sea ice up to a thickness of about 1 m has been demonstrated through validation with multiple datasets. To ensure the quality of the SMOS product, an independent regional sea ice extent index was used for control. We found that the new version, v3.3, is slightly improved in terms of completeness, indicating fewer missing data. However, it is worth noting that the general characteristics of both datasets are very similar, also with the same limitations.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; sjøis

Radar internal reflection horizons from multisystem data reflect ice dynamic and surface accumulation history along the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica - Koch, Inka; Drews, Reinhard; Franke, Steven; Jansen, Daniela; Oraschewski, Falk Marius; Muhle, Leah Sophie; Višnjević, Vjeran; Matsuoka, Kenichi; Pattyn, Frank; Eisen, Olaf (Journal of Glaciology, 2024)
Ice shelves, which regulate ice flow from the Antarctic ice sheet towards the ocean, are shaped by spatiotemporal patterns of surface accumulation, surface/basal melt and ice dynamics. Therefore, an ice dynamic and accumulation history are imprinted in the internal ice stratigraphy, which can be imaged by radar in the form of internal reflection horizons (IRHs). Here, IRHs were derived from radar data combined across radar platforms (airborne and ground-based) in coastal eastern Dronning Maud Land (East Antarctica), comprising three ice rises and adjacent two ice shelves. To facilitate interpretation of dominant spatiotemporal patterns of processes shaping the local IRH geometry, traced IRHs are classified into three different types (laterally continuous, discontinuous or absent/IRH-free). Near-surface laterally continuous IRHs reveal local accumulation patterns, reflecting the mean easterly wind direction, and correlate with surface slopes. Areas of current and past increased ice flow and internal deformation are marked by discontinuous or IRH-free zones, and can inform about paleo ice-stream dynamics. The established IRH datasets extend continent-wide mapping efforts of IRHs to an important and climatically sensitive ice marginal region of Antarctica and are ready for integration into ice-flow models to improve predictions of Antarctic ice drainage.
Edition: 2023/12/12 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; teknologi

ALBATROSS: Advancing Southern Ocean tide modelling with high resolution and enhanced bathymetry - Le Merle, Eva; Belot, Carole; Fouchet, Ergane; Cancet, Mathilde; Andersen, Ole Baltazar; Lyard, Florent; Moholdt, Geir; Tsamados, Michel; El Hajj, Mahmoud; Maton, Josephine; Benveniste, Jérôme; Restano, Marco (Polar Science, 2024)
The knowledge of bathymetry and ocean tides plays a pivotal role at the crossroads of various scientific fields, especially in the Polar regions. Its significance extends to ocean circulation modeling and understanding the coupled dynamical response of the ocean, sea-ice and ice-sheet systems. In the Southern Ocean, conventional satellite altimetry measurements are rare below the 66° parallel. Hydrodynamic models are thus useful tools to provide spatially continuous information about ocean tides. However, the accuracy of ocean tide models around the Antarctic continent is currently limited by the quality of bathymetry. Recent reprocessing of decade-long CryoSat-2 data has facilitated a new computation of bathymetry around Antarctica, bringing innovative information on bathymetry gradients. This, combined with new compilations of bathymetry, ice draft, coastline, and grounding line datasets in ice-shelf regions, allows improving models and knowledge of ocean tides in the Southern Ocean. We developed a new high-resolution tidal model that implements the improved bathymetry data and includes data assimilation of satellite-altimetry tidal retrievals computed from CryoSat-2, filling the gap between the 66°S-limited coverage of the TOPEX-Jason suite missions and the Antarctic coast. Comparisons with tidal estimates derived from tide gauge measurements showed very good consistencies with an RMSE of 3 cm.
Article number: 101124
Keywords: Sørishavet; batymetri; geofysikk

Phytoplankton bloom distribution and succession driven by sea-ice melt in the Kong Håkon VII Hav - Lenss, Megan; Moreau, Sebastien; Hattermann, Tore; Wiktor, Jozef; Różańska, Magdalena; Claeys, Philippe; Brion, Natacha; Chierici, Melissa; Fransson, Agneta; Campbell, Karley (Elementa: Science of the Anthropocene, 2024)
The existence of ice-edge phytoplankton blooms in the Southern Ocean is well described, yet direct observations of the mechanisms of phytoplankton bloom development following seasonal sea-ice melt remain scarce. This study constrains such responses using biological and biogeochemical datasets collected along a coastal-to-offshore transect that bisects the receding sea-ice zone in the Kong Håkon VII Hav (off the coast of Dronning Maud Land). We documented that the biogeochemical growing conditions for phytoplankton vary on a latitudinal gradient of sea-ice concentration, where increased sea-ice melting creates optimal conditions for growth with increased light availability and potentially increased iron supply. The zones of the study area with the least ice cover were associated with diatom dominance, the greatest chlorophyll a concentrations, net community production, and dissolved inorganic carbon drawdown, as well as lower sea surface fugacity of CO2. Together, these associations imply higher potential for an oceanic CO2 sink due, at least in part, to more advanced bloom phase and/or larger bloom magnitude stemming from a relatively longer period of light exposure, as compared to the more ice-covered zones in the study area. From stable oxygen isotope fractions, sea-ice meltwater fractions were highest in the open ocean zone and meteoric meltwater fractions were highest in the coastal and polynya zones, suggesting that potential iron sources may also change on a latitudinal gradient across the study area. Variable phytoplankton community compositions were related to changing sea-ice concentrations, with a typical species succession from sympagic flagellate species (Pyramimonas sp. and Phaeocystis antarctica) to pelagic diatoms (e.g., Dactyliosolen tenuijunctus) observed across the study area. These results fill a spatiotemporal gap in the Southern Ocean, as sea-ice melting plays a larger role in governing phytoplankton bloom dynamics in the future Southern Ocean due to changing sea-ice conditions caused by anthropogenic global warming.
Article Number: 00122
Keywords: Sørishavet; biogeokjemi; fytoplankton; havis; oseanografi; sjøis

Diversity, toxicity, and distribution of potentially toxic diatoms in Antarctic waters––With description of Pseudo-nitzschia meridionalis sp. nov. and P. glacialis sp. nov. - Lundholm, Nina; Christensen, Anneliese L.; Olesen, Anna K.J.; Beszteri, Bánk; Eggers, Sarah Lena; Krock, Bernd; Altenburger, Andreas (Harmful Algae, 2024)
Diatoms of the genus Pseudo-nitzschia, known for their potential toxicity, are integral to the phytoplankton community of the Southern Ocean, which surrounds Antarctica. Despite their ecological importance, the diversity and toxicity of Pseudo-nitzschia in this region remain underexplored. Globally, these diatoms are notorious for forming harmful algal blooms in temperate and tropical waters, causing significant impacts on marine life, ecosystems, and coastal economies. However, detailed information on the diversity, morphology, and toxicity of Pseudo-nitzschia species in Antarctic waters is limited, with molecular characterizations of these species being particularly scarce. During three research expeditions to the Southern Ocean, monoclonal strains of Pseudo-nitzschia were isolated and cultivated. Stored samples from a fourth expedition, the Brategg expedition, were used to complete the description of particularly P. turgidula. Through electron microscopy and molecular analysis, two novel species were identified—Pseudo-nitzschia meridionalis sp. nov. and Pseudo-nitzschia glacialis sp. nov.—alongside the previously described species P. subcurvata, P. turgiduloides, and P. turgidula. Toxin assays revealed no detectable levels of domoic acid in P. turgiduloides, P. turgidula, P. meridionalis sp. nov. and P. glacialis sp. nov. Conversely, P. subcurvata was reported in a related study to produce domoic acid and its isomer, isodomoic acid C. These findings emphasize the need for comprehensive research on the phytoplankton of Antarctic waters, which is currently a largely uncharted domain. With the looming threat of climate change, understanding the dynamics of potentially harmful algal populations in this region is becoming increasingly critical.
Article Number: 102724
Keywords: Rosshavet; Sørishavet; alger; biodiversitet; diatomeer; fytoplankton; marin biologi

The case for a Framework for UnderStanding Ice-Ocean iNteractions (FUSION) in the Antarctic-Southern Ocean system - McCormack, Felicity S.; Cook, Sue; Goldberg, Daniel N.; Nakayama, Yoshihiro; Seroussi, Hélène; Nias, Isabel; An, Lu; Slater, Donald; Hattermann, Tore (Elementa: Science of the Anthropocene, 2024)
We are in a period of rapidly accelerating change across the Antarctic continent and Southern Ocean, with land ice loss leading to sea level rise and multiple other climate impacts. The ice-ocean interactions that dominate the current ice loss signal are a key underdeveloped area of knowledge. The paucity of direct and continuous observations leads to high uncertainty in the glaciological, oceanographic and atmospheric fields required to constrain ice-ocean interactions, and there is a lack of standardised protocols for reconciling observations across different platforms and technologies and modelled outputs. Funding to support observational campaigns is under increasing pressure, including for long-term, internationally coordinated monitoring plans for the Antarctic continent and Southern Ocean. In this Practice Bridge article, we outline research priorities highlighted by the international ice-ocean community and propose the development of a Framework for UnderStanding Ice-Ocean iNteractions (FUSION), using a combined observational-modelling approach, to address these issues. Finally, we propose an implementation plan for putting FUSION into practice by focusing first on an essential variable in ice-ocean interactions: ocean-driven ice shelf melt.
Article number: 00036
Keywords: Antarktis; Sørishavet; glasiologi; innlandsis; klimamodeller; klimatologi; oseanografi

Miocene ice sheet dynamics and sediment deposition in the central Ross Sea, Antarctica - McKay, Robert; Cockrell, Jay; Shevenell, Amelia E.; Laberg, Jan Sverre; Burns, Julianne; Patterson, Molly; Kim, Sunghan; Naish, Tim; Harwood, David; Levy, Richard; Marschalek, James; van de Flierdt, Tina; et al. (GSA Bulletin, 2024)
Drill cores from the Antarctic continental shelf are essential for directly constraining changes in past Antarctic Ice Sheet extent. Here, we provide a sedimentary facies analysis of drill cores from International Ocean Discovery Program (IODP) Site U1521 in the Ross Sea, which reveals a unique, detailed snapshot of Antarctic Ice Sheet evolution between ca. 18 Ma and 13 Ma. We identify distinct depositional packages, each of which contains facies successions that are reflective of past baseline shifts in the presence or absence of marine-terminating ice sheets on the outermost Ross Sea continental shelf. The oldest depositional package (>18 Ma) contains massive diamictites stacked through aggradation and deposited in a deep, actively subsiding basin that restricted marine ice sheet expansion on the outer continental shelf. A slowdown in tectonic subsidence after 17.8 Ma led to the deposition of progradational massive diamictites with thin mudstone beds/laminae, as several large marine-based ice sheet advances expanded onto the mid- to outer continental shelf between 17.8 Ma and 17.4 Ma. Between 17.2 Ma and 15.95 Ma, packages of interbedded diamictite and diatom-rich mudstone were deposited during a phase of highly variable Antarctic Ice Sheet extent and volume. This included periods of Antarctic Ice Sheet advance near the outer shelf during the early Miocene Climate Optimum (MCO)—despite this being a well-known period of peak global warmth between ca. 17.0 Ma and 14.6 Ma. Conversely, there were periods of peak warmth within the MCO during which diatom-rich mudstones with little to no ice-rafted debris were deposited, which indicates that the Antarctic Ice Sheet was greatly reduced in extent and had retreated to a smaller terrestrial-terminating ice sheet, most notably between 16.3 Ma and 15.95 Ma. Post-14.2 Ma, diamictites and diatomites contain unambiguous evidence of subglacial shearing in the core and provide the first direct, well-dated evidence of highly erosive marine ice sheets on the outermost continental shelf during the onset of the Middle Miocene Climate Transition (MMCT; 14.2–13.6 Ma). Although global climate forcings and feedbacks influenced Antarctic Ice Sheet advances and retreats during the MCO and MMCT, we propose that this response was nonlinear and heavily influenced by regional feedbacks related to the shoaling of the continental shelf due to reduced subsidence, sediment infilling, and local sea-level changes that directly influenced oceanic influences on melting at the Antarctic Ice Sheet margin. Although intervals of diatom-rich muds and diatomite indicating open-marine interglacial conditions still occurred during (and following) the MMCT, repeated advances of marine-based ice sheets since that time have resulted in widespread erosion and overdeepening in the inner Ross Sea, which has greatly enhanced sensitivity to marine ice sheet instability since 14.2 Ma.
Keywords: Rosshavet; Sørishavet; geologi; oseanografi; paleoklimatologi

KRILLSCAN: An automated open-source software for processing and analysis of echosounder data from the Antarctic krill fishery - Menze, Sebastian; Macaulay, Gavin J.; Zhang, Guosong; Lowther, Andrew D.; Krafft, Bjørn A. (Fisheries Management and Ecology, 2024)
Krillscan software was developed to automatically process echosounder data and achieve an accelerated and transparent analysis of backscatter data that allows calculation of target biomass. Herein, the fishery for Antarctic krill (Euphausia superba, Henceforth Krill) was used as a case study to develop the approach. Implementation of a sustainable management strategy for the krill fishery is complicated by a lack of regularly updated krill abundance data on spatiotemporal scales of the fishery. To increase krill biomass data availability, automatic echosounder data processing and swarm detection software was tested against traditional manual scrutinization with LSSS software and agreed with only minor offsets in estimated nautical area scattering coefficients. In addition to automatic processing and data transfer, Krillscan also has a graphical user interface to supervise automatic krill swarm detection. Echogram size can be compressed up to 100 times and raw data are processed faster than generated, thereby enabling near-real time analysis and data transfer. Compressed data can be transmitted online to allow fishing vessels to conduct surveys without having scientific personnel with special expertise on board.
Publisher: John Wiley & Sons, Ltd Article number: e12739
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; plankton

Antarctic sonobuoy surveys for blue whales from 2006-2021 reveal contemporary distribution, changes over time, and paths to further our understanding of their distribution and biology - Miller, Brian S.; Andrews-Goff, Virginia; Barlow, Jay; Bell, Elanor; Calderan, Susannah; Double, Michael C.; Gedamke, Jason; Kelly, Nat; Laverick, Sarah; Leaper, Russell; Miller, Elanor J.; Reeve, Kym; et al. (Frontiers in Marine Science, 2024)
Seven passive acoustic surveys for marine mammal sounds were conducted by deploying sonobuoys along ship tracks during Antarctic voyages spanning years 2006-2021. These surveys included nearly 330° of longitude throughout Antarctic (south of 60°S) and sub-Antarctic (between 50-60°S) latitudes. Here, we summarise the presence of calls from critically endangered Antarctic blue whales (Balaenoptera musculus intermedia) detected on all seven of these surveys. We describe and compare the spatial distribution of detections of three different types of Antarctic blue whale calls: unit-A, Z-calls, and D-calls. Three sets of voyages partially overlapped spatially but in different years, providing three regions (Indian Sector, Dumont d’Urville Sea, Ross Sea) to investigate differences over time for these three different call types. The proportion of sonobuoys with calls present was significantly higher in the more recent years for seven of the 15 combinations of years, regions, and call type. The proportion of sonobuoys with calls present was significantly lower only for one of the 15 combinations (unit A in the Ross Sea between 2015 vs 2017), and not significantly different for the remaining seven pairwise comparisons. We discuss possible explanations for these observations including: differences in probability of detection, whale behaviour, whale distribution, and abundance. These explanations are not mutually exclusive and cannot yet be resolved without application of complex analytical methods and collection of additional data. Lastly, we discuss future work that could help clarify the contributions of each of these potential drivers of acoustic detection. We propose continued acoustic data collection, application of new analytical methods, and collection of other synergistic data from Antarctic blue whales on their feeding grounds as a basis for future work on this species. This could provide a cost effective and holistic means of monitoring their status after the effects of 20th century industrial whaling, as well as their responses to natural and anthropogenic changes to their main prey, Antarctic krill, and a changing climate.
Keywords: Sørishavet; hvaler; hydroakustikk; marin biologi

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Section: Perspectives
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Pertierra, Luis R.; Varliero, Gilda; Barbosa, Andrés; Biersma, Elisabeth M.; Convey, Peter; Chown, Steven L.; Cowan, Don; De Los Rios, Asunción; Escribano-Alvarez, Pablo; Fontaneto, Diego; Fraser, Ceridwen; Harris, Mathew; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.
Publisher: Pensoft Publishers
Keywords: Antarktis; Sørishavet; biodiversitet; database; fauna; flora; mikroorganismer

Combined physical and biogeochemical assessment of mesoscale eddy parameterisations in ocean models: Eddy-induced advection at eddy-permitting resolutions - Ruan, X.; Couespel, D.; Lévy, M.; Li, J.; Mak, J.; Wang, Y. (Ocean Modelling, 2024)
Ocean general circulation models at the eddy-permitting regime are known to under-resolve the mesoscale eddy activity and associated eddy-mean interaction. Under-resolving the mesoscale eddy field has consequences for the resulting mean state, affecting the modelled ocean circulation and biogeochemical responses, and impacting the quality of climate projections. There is an ongoing debate on whether and how a parameterisation should be utilised in the eddy-permitting regime. Focusing on the Gent–McWilliams (GM) based parameterisations, it is known that, on the one hand, not utilising a parameterisation leads to insufficient eddy feedback and results in biases. On the other hand, utilising a parameterisation leads to double-counting of the eddy feedback, and introduces other biases. A recently proposed approach, known as splitting, modifies the way GM-based schemes are applied in eddy-permitting regimes, and has been demonstrated to be effective in an idealised Southern Ocean channel model. In this work, we evaluate whether the splitting approach can lead to improvements in the physical and biogeochemical responses in an idealised double gyre model. Compared with a high resolution mesoscale eddy resolving model truth, the use of the GM-based GEOMETRIC parameterisation together with splitting in the eddy-permitting regime leads to broad improvements in the control pre-industrial scenario and an idealised climate change scenario, over models with and models without the GM-based GEOMETRIC parameterisation active. While there are still some deficiencies, particularly in the subtropical region where the transport is too weak and may need momentum re-injection to reduce the biases, the present work provides further evidence in support of using the splitting procedure together with a GM-based parameterisation in ocean general circulation models at eddy-permitting resolutions.
Article number: 102396
Keywords: Sørishavet; havstrømmer; klimaendringer; oseanografi

Identifying prey capture events of a free-ranging marine predator using bio-logger data and deep learning - Schoombie, Stefan; Jeantet, Lorène; Chimienti, Marianna; Sutton, Grace J.; Pistorius, Pierre A.; Dufourq, Emmanuel; Lowther, Andrew D.; Oosthuizen, W. Chris (Royal Society Open Science, 2024)
Marine predators are integral to the functioning of marine ecosystems, and their consumption requirements should be integrated into ecosystem-based management policies. However, estimating prey consumption in diving marine predators requires innovative methods as predator-prey interactions are rarely observable. We developed a novel method, validated by animal-borne video, that uses tri-axial acceleration and depth data to quantify prey capture rates in chinstrap penguins (Pygoscelis antarctica). These penguins are important consumers of Antarctic krill (Euphausia superba), a commercially harvested crustacean central to the Southern Ocean food web. We collected a large data set (n = 41 individuals) comprising overlapping video, accelerometer and depth data from foraging penguins. Prey captures were manually identified in videos, and those observations were used in supervised training of two deep learning neural networks (convolutional neural network (CNN) and V-Net). Although the CNN and V-Net architectures and input data pipelines differed, both trained models were able to predict prey captures from new acceleration and depth data (linear regression slope of predictions against video-observed prey captures = 1.13; R2 approximate to 0.86). Our results illustrate that deep learning algorithms offer a means to process the large quantities of data generated by contemporary bio-logging sensors to robustly estimate prey capture events in diving marine predators.
Publisher: Royal Society
Keywords: Sørishavet; biologging; krill; marin biologi; marin zoologi; marine økosystemer; pingviner; plankton

Observed Pathways and Interannual Variability of the Warm Inflow Onto the Continental Shelf in the Southern Weddell Sea - Steiger, N.; Sallée, J. B.; Darelius, Elin; Janout, Markus; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2024)
Model projections suggest that the continental shelf in the southern Weddell Sea may experience a shift from today's near-freezing temperature to a much warmer state, where warm water floods the shelf and basal melt rates beneath the Filchner Ronne Ice Shelf increase dramatically. Today, the Filchner Trough serves as a conduit for the southward flow of Warm Deep Water (WDW) during summer and, thus, requires continuous monitoring of its hydrographic conditions. An extensive network of moorings was installed at key sites along the inflow pathway from 2017 to 2021, to expand on existing mooring records starting in 2014. The moorings complemented with under-ice profiling floats reveal two inflow pathways, where WDW enters along the eastern flank of the Filchner Trough as well as through a smaller trough east of there. Within the observed period, 2017 and 2018 feature anomalously warm inflows. The inflow is regulated by the heaving of isopycnals over the continental slope, and the southward propagation toward Filchner Ice Shelf is two times faster during these warm years. Furthermore, the warm years coincide with low summer sea ice concentration, which enhances surface stratification through increased freshwater input and modifies sea ice-ocean stresses that both act to lift the warm water layer and increase the temperatures on the continental shelf. Finally, the recent record low sea ice conditions around the Antarctic emphasize the importance of our findings and raise concerns regarding a potentially increasing presence of WDW on the southern Weddell Sea shelf.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; havis; isshelf; oseanografi; sjøis

The Southern Ocean sea-ice ecosystem is important to humans - Steiner, Nadja; Eronen-Rasimus, Eeva; Falardeau, Marianne; Moreau, Sebastien; Steiner, Finn (Frontiers for young minds, 2024)
Did you know that ecosystems support the wellbeing of humans by simply existing? An ecosystem describes the living things in an area, their interactions, and their environment. The ways that ecosystems benefit the wellbeing of humans are called ecosystem services. There are several types of ecosystem services: supporting (they support animals and their homes), provisioning (they provide food and other materials), cultural (they support our hobbies and cultural activities, such as tourism and arts), or regulating (they regulate our climate, for example by taking up carbon dioxide). Understanding the importance of an ecosystem through its ecosystem services helps guide decisions regarding the environment, such as how much fishing or ship traffic should be allowed in an area, or if an area or species should be protected. In this article, we describe the specific ecosystem services of the sea ice and Southern Ocean around Antarctica.
Article number : 1046644
Keywords: Sørishavet; havis; marine økosystemer; populærvitenskap; sjøis; økosystemer

Suppression of Mesoscale Eddy Mixing by Topographic PV Gradients - Sterl, Miriam F.; LaCasce, Joseph H.; Groeskamp, Sjoerd; Nummelin, Aleksi; Isachsen, Pål E.; Baatsen, Michiel L. J. (Journal of Physical Oceanography, 2024)
Oceanic mesoscale eddy mixing plays a crucial role in Earth’s climate system by redistributing heat, salt, and carbon. For many ocean and climate models, mesoscale eddies still need to be parameterized. This is often done via an eddy diffusivity K , which sets the strength of turbulent downgradient tracer fluxes. A well-known effect is the modulation of K in the presence of background potential vorticity (PV) gradients, which suppresses cross-PV gradient mixing. Topographic slopes can induce such suppression through topographic PV gradients. However, this effect has received little attention, and topographic effects are often not included in parameterizations for K . In this study, we show that it is possible to describe the effect of topography on K analytically in a barotropic framework, using a simple stochastic representation of eddy–eddy interactions. We obtain an analytical expression for the depth-averaged K as a function of the bottom slope, which we validate against diagnosed eddy diffusivities from a numerical model. The obtained analytical expression can be generalized to any constant barotropic PV gradient. Moreover, the expression is consistent with empirical parameterizations for eddy diffusivity over topography from previous studies and provides a physical rationalization for these parameterizations. The new expression helps to understand how eddy diffusivities vary across the ocean, and thus how mesoscale eddies impact ocean mixing processes.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Sørishavet; klimamodeller; oseanografi

Geographical distribution of close kin in southern right whales on feeding grounds - Takahashi, Megumi; Førland, Brage; Pastene, Luis A.; Skaug, Hans J. (PLOS ONE, 2024)
This study investigated the close kinship structure of southern right whales on feeding grounds during austral summer seasons. The study was based on biopsy samples of 171 individual whales, which were genotyped with 14 microsatellite DNA loci. Kinship was investigated by using the LOD (Log Odds) score, a relatedness index for a pair of genotypes. Based on a cut-off point of LODPO > 6, which was chosen to balance false positives and negatives, a total of 28 dyads were inferred. Among these, 25 were classified as parent-offspring pairs. Additional genetic (mitochondrial DNA haplotypes) and biological (estimated body length, sex) data were used to provide additional information on the inferred close kin pairs. The elapsed time between sampling varied from 0 (close kin detected in the same austral summer season) to 17 years. All the kin pairs occurred within the Antarctic Indo sector (85°-135°E) and no pair occurred between whales within and outside of this sector. Six pairs were between individuals in high (Antarctic) and lower latitudes. Results of the present analysis on kinship are consistent with the views that whales in the Indo sector of the Antarctic are related with the breeding ground in Southwest Australia, and that whales from this population can occupy different feeding grounds. The present study has the potential to contribute to the conservation of the southern right whales through the monitoring of important population parameters such as population sizes and growth rate, in addition to assist the interpretation of stock structure derived from standard population genetic analyses.
Publisher: Public Library of Science
Keywords: Sørishavet; genetikk; hvaler; marin biologi; zoogeografi

Swirls and scoops: Ice base melt revealed by multibeam imagery of an Antarctic ice shelf - Wåhlin, Anna; Alley, Karen E.; Begeman, Carolyn; Hegrenæs, Øyvind; Yuan, Xiaohan; Graham, Alastair G. C.; Hogan, Kelly; Davis, Peter E. D.; Dotto, Tiago S.; Eayrs, Clare; Hall, Robert A.; Holland, David M.; et al. (Science Advances, 2024)
Knowledge gaps about how the ocean melts Antarctica's ice shelves, borne from a lack of observations, lead to large uncertainties in sea level predictions. Using high-resolution maps of the underside of Dotson Ice Shelf, West Antarctica, we reveal the imprint that ice shelf basal melting leaves on the ice. Convection and intermittent warm water intrusions form widespread terraced features through slow melting in quiescent areas, while shear-driven turbulence rapidly melts smooth, eroded topographies in outflow areas, as well as enigmatic teardrop-shaped indentations that result from boundary-layer flow rotation. Full-thickness ice fractures, with bases modified by basal melting and convective processes, are observed throughout the area. This new wealth of processes, all active under a single ice shelf, must be considered to accurately predict future Antarctic ice shelf melt. A unique dataset from beneath an Antarctic ice shelf shows a varied icescape created by differential melt mechanisms.
Publisher: American Association for the Advancement of Science Article number: eadn9188
Keywords: Sørishavet; brehylle; havstrømmer; isbrem; oseanografi

Highly stratified mid-Pliocene Southern Ocean in PlioMIP2 - Weiffenbach, J. E.; Dijkstra, H. A.; von der Heydt, A. S.; Abe-Ouchi, A.; Chan, W.-L.; Chandan, D.; Feng, R.; Haywood, A. M.; Hunter, S. J.; Li, X.; Otto-Bliesner, B. L.; Peltier, W. R.; et al. (Clim. Past, 2024)
During the mid-Pliocene warm period (mPWP; 3.264–3.025 Ma), atmospheric CO2 concentrations were approximately 400 ppm, and the Antarctic Ice Sheet was substantially reduced compared to today. Antarctica is surrounded by the Southern Ocean, which plays a crucial role in the global oceanic circulation and climate regulation. Using results from the Pliocene Model Intercomparison Project (PlioMIP2), we investigate Southern Ocean conditions during the mPWP with respect to the pre-industrial period. We find that the mean sea surface temperature (SST) warming in the Southern Ocean is 2.8 °C, while global mean SST warming is 2.4 °C. The enhanced warming is strongly tied to a dramatic decrease in sea ice cover over the mPWP Southern Ocean. We also see a freshening of the ocean (sub)surface, driven by an increase in precipitation over the Southern Ocean and Antarctica. The warmer and fresher surface leads to a highly stratified Southern Ocean that can be related to weakening of the deep abyssal overturning circulation. Sensitivity simulations show that the decrease in sea ice cover and enhanced warming is largely a consequence of the reduction in the Antarctic Ice Sheet. In addition, the mPWP geographic boundary conditions are responsible for approximately half of the increase in mPWP SST warming, sea ice loss, precipitation, and stratification increase over the Southern Ocean. From these results, we conclude that a strongly reduced Antarctic Ice Sheet during the mPWP has a substantial influence on the state of the Southern Ocean and exacerbates the changes that are induced by a higher CO2 concentration alone. This is relevant for the long-term future of the Southern Ocean, as we expect melting of the western Antarctic Ice Sheet in the future, an effect that is not currently taken into account in future projections by Coupled Model Intercomparison Project (CMIP) ensembles.
Publisher: Copernicus Publications
Keywords: Sørishavet; geologi; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Gross Primary Production of Antarctic Landfast Sea Ice: A Model-Based Estimate - Wongpan, Pat; Meiners, K. M.; Vancoppenolle, M.; Fraser, A. D.; Moreau, Sebastien; Saenz, B. T.; Swadling, K. M.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2024)
Much of the Antarctic coast is covered by seasonal landfast sea ice (fast ice), which serves as an important habitat for ice algae. Fast-ice algae provide a key early season food source for pelagic and benthic food webs, and contribute to biogeochemical cycling in Antarctic coastal ecosystems. Summertime fast ice is undergoing a decline, leading to more seasonal fast ice with unknown impacts on interconnected Earth system processes. Our understanding of the spatiotemporal variability of Antarctic fast ice, and its impact on polar ecosystems is currently limited. Evaluating the overall productivity of fast-ice algae has historically been hampered by limitations in observations and models. By linking new fast-ice extent maps with a one-dimensional sea-ice biogeochemical model, we provide the first estimate of the spatio-seasonal variability of Antarctic fast-ice algal gross primary production (GPP) and its annual primary production on a circum-Antarctic scale. Experiments conducted for the 2005?2006 season provide a mean fast ice-algal production estimate of 2.8 Tg C/y. This estimate represents about 12% of overall Southern Ocean sea-ice algae production (estimated in a previous study), with the mean fast-ice algal production per area being 3.3 times higher than that of pack ice. Our Antarctic fast-ice GPP estimates are probably underestimated in the Ross Sea and Weddell Sea sectors because the sub-ice platelet layer habitats and their high biomass are not considered.
Publisher: John Wiley & Sons, Ltd Article Number: e2024JC021348
Keywords: Sørishavet; alger; biogeokjemi; geofysikk; havis; oseanografi; sjøis

Re-evaluating winter carbon sink in Southern Ocean by recovering MODIS-Aqua chlorophyll-a product at high solar zenith angles - Zhang, Ke; Zhang, Zhaoru; He, Jianfeng; Smith, Walker O.; Liu, Na; Le, Chengfeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)
Satellite ocean color observations are extensively utilized in global carbon sink evaluation. However, the valid coverage of chlorophyll-a concentration (Chla, mg m−3) measurements from these observations is severely limited during autumn and winter in high latitude oceans. The high solar zenith angle (SZA) stands as one of the primary contributors to the reduced quality of Chla products in the high-latitude Southern Ocean during these seasons. This study addresses this challenge by employing a random forest-based regression ensemble (RFRE) method to enhance the quality of Moderate Resolution Imaging Spectroradiometer (MODIS) Chla products affected by high SZA conditions. The RFRE model incorporates the color index (CI), band-ratio index (R), SZA, sensor zenith angle (senz), and Rayleigh-corrected reflectance at 869 nm (Rrc(869)) as predictors. The results indicate that the RFRE model significantly increased the MODIS observed Chla coverage (1.03 to 3.24 times) in high-latitude Southern Ocean regions to the quality of standard Chla products. By applying the recovered Chla to re-evaluate the carbon sink in South Ocean, results showed that the Southern Ocean’s ability to absorb carbon dioxide (CO2) in winter has been underestimated (5.9–18.6 Tg C year−1) in previous assessments. This study underscores the significance of improving the Chla products for a more accurate estimation of winter carbon sink in the Southern Ocean.
Keywords: Sørishavet; fjernmåling; fotogrammetri; karbon syklus; karbondioksid; oseanografi

Dynamic Response to Ice Shelf Basal Meltwater Relevant to Explain Observed Sea Ice Trends Near the Antarctic Continental Shelf - Huneke, Wilma G. C.; Hobbs, William R.; Klocker, Andreas; Naughten, Kaitlin A. (Geophysical Research Letters, 2023)
Abstract Observed Antarctic sea ice trends up to 2015 have a distinct regional and seasonal pattern, with a loss during austral summer and autumn in the Bellingshausen and Amundsen Seas, and a year-round increase in the Ross Sea. Global climate models generally failed to reproduce the magnitude of sea ice trends implying that the models miss relevant mechanisms. One possible mechanism is basal meltwater, which is generally not included in the current generation of climate models. Previous work on the effects of meltwater on sea ice has focused on thermodynamic processes. However, local freshening also leads to dynamic changes, affecting ocean currents through geostrophic balance. Using a coupled ocean/sea-ice/ice-shelf model, we demonstrate that basal melting can intensify coastal currents in West Antarctica and the westward transport of sea ice. This change in transport results in sea ice anomalies consistent with observations, and may explain the disparity between climate models and observations.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; havis; oseanografi

Deep Convection as the Key to the Transition From Eocene to Modern Antarctic Circumpolar Current - Xing, Qianjiang; Klocker, Andreas; Munday, David; Whittaker, Joanne (Geophysical Research Letters, 2023)
From the Eocene (?50 million years ago) to today, Southern Ocean circulation has evolved from the existence of two ocean gyres to the dominance of the Antarctic Circumpolar Current (ACC). It has generally been thought that the opening of Southern Ocean gateways in the late Eocene, in addition to the alignment of westerly winds with these gateways or the presence of the Antarctic ice sheet, was a sufficient requirement for the transition to an ACC of similar strength to its modern equivalent. Nevertheless, models representing these changes produce a much weaker ACC. Here we show, using an eddying ocean model, that the missing ingredient in the transition to a modern ACC is deep convection around the Antarctic continent. This deep convection is caused by cold temperatures and high salinities due to sea-ice production around the Antarctic continent, leading to both the formation of Antarctic Bottom Water and a modern-strength ACC.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; oseanografi

Macronutrient biogeochemistry in Antarctic land-fast sea ice: Insights from a circumpolar data compilation - Henley, Sian F.; Cozzi, Stefano; Fripiat, François; Lannuzel, Delphine; Nomura, Daiki; Thomas, David N.; Meiners, Klaus M.; Vancoppenolle, Martin; Arrigo, Kevin; Stefels, Jacqueline; van Leeuwe, Maria; Moreau, Sebastien; et al. (Marine Chemistry, 2023)
Antarctic sea ice plays an important role in Southern Ocean biogeochemistry and mediating Earth's climate system. Yet our understanding of biogeochemical cycling in sea ice is limited by the availability of relevant data over sufficient temporal and spatial scales. Here we present a new publicly available compilation of macronutrient concentration data from Antarctic land-fast sea ice, covering the full seasonal cycle using datasets from around Antarctica, as well as a smaller dataset of macronutrient concentrations in adjacent seawater. We show a strong seasonal cycle whereby nutrient concentrations are high during autumn and winter, due to supply from underlying surface waters, and then are utilised in spring and summer by mixed ice algal communities consisting of diatoms and non-siliceous species. Our data indicate some degree of nutrient limitation of ice algal primary production, with silicon limitation likely being most prevalent, although uncertainties remain around the affinities of sea-ice algae for each nutrient. Remineralisation of organic matter and nutrient recycling drive substantial accumulations of inorganic nitrogen, phosphate and to a lesser extent silicic acid in some ice cores to concentrations far in excess of those in surface waters. Nutrient supply to fast ice is enhanced by brine convection, platelet ice accumulation and incorporation into the ice matrix, and under-ice tidal currents, whilst nutrient adsorption to sea-ice surfaces, formation of biofilms, and abiotic mineral precipitation and dissolution can also influence fast-ice nutrient cycling. Concentrations of nitrate, ammonium and silicic acid were generally higher in fast ice than reported for Antarctic pack ice, and this may support the typically observed higher algal biomass in fast-ice environments.
Keywords: Sørishavet; alger; havis; kjemi; marin biologi

Quantifying circumpolar summer habitat for Antarctic krill and Ice krill, two key species of the Antarctic marine ecosystem - Merkel, B; Trathan, P; Thorpe, S; Murphy, E J; Pehlke, H; Teschke, K; Griffith, G P (ICES Journal of Marine Science, 2023)
Antarctic krill (Euphausia superba) and Ice krill (Euphausia crystallorophias) are key species within Southern Ocean marine ecosystems. Given their importance in regional food webs, coupled with the uncertain impacts of climate change, the on-going recovery of krill-eating marine mammals, and the expanding commercial fishery for Antarctic krill, there is an increasing need to improve current estimates of their circumpolar habitat distribution. Here, we provide an estimate of the austral summer circumpolar habitat distribution of both species using an ensemble of habitat models and updated environmental covariates. Our models were able to resolve the segregated habitats of both species. We find that extensive potential habitat for Antarctic krill is mainly situated in the open ocean and concentrated in the Atlantic sector of the Southern Ocean, while Ice krill habitat was concentrated more evenly around the continent, largely over the continental shelf. Ice krill habitat was mainly predicted by surface oxygen concentration and water column temperature, while Antarctic krill was additionally characterized by mixed layer depth, distance to the continental shelf edge, and surface salinity. Our results further improve understanding about these key species, helping inform sustainable circumpolar management practices.
Keywords: Sørishavet; krill; marin biologi

Perspectives on the economic and political history of the Ross Sea - Basberg, Bjørn L.; Lintott, Bryan (The Polar Journal, 2023)
The paper analyses the economic and political history of the Ross Sea, where exploration, science, commercial exploitation, politics and adventure became highly interlinked and interwoven. Expedition accounts and the extensive literature on Antarctic history and politics inform the contextual aspects. The archives of the Norwegian whaling company A/S Rosshavet, established in 1923, and the United States of America and New Zealand archival material from the 1950s are key sources. From the first whaling season onwards, the impact of Antarctic whaling, and later scientific bases, highlights and illustrates the tensions between Antarctic commerce, territorial claims and international politics.
Publisher: Routledge
Keywords: Sørishavet; historie; hvalfangst; politikk; økonomi

Slowdown of Antarctic Bottom Water export driven by climatic wind and sea-ice changes - Zhou, Shenjie; Meijers, Andrew J. S.; Meredith, Michael P.; Abrahamsen, E. Povl; Holland, Paul R.; Silvano, Alessandro; Sallée, Jean-Baptiste; Østerhus, Svein (Nature Climate Change, 2023)
Antarctic Bottom Water (AABW) is pivotal for oceanic heat and carbon sequestrations on multidecadal to millennial timescales. The Weddell Sea contributes nearly a half of global AABW through Weddell Sea Deep Water and denser underlying Weddell Sea Bottom Water that form on the continental shelves via sea-ice production. Here we report an observed 30% reduction of Weddell Sea Bottom Water volume since 1992, with the largest decrease in the densest classes. This is probably driven by a multidecadal reduction in dense-water production over southern continental shelf associated with a >40% decline in the sea-ice formation rate. The ice production decrease is driven by northerly wind trend, related to a phase transition of the Interdecadal Pacific Oscillation since the early 1990s, superposed by Amundsen Sea Low intrinsic variability. These results reveal key influences on exported AABW to the Atlantic abyss and their sensitivity to large-scale, multidecadal climate variability.
Keywords: Sørishavet; havis; oseanografi

Monitoring persistent organic chemicals in Antarctica in support of global chemical policy: a horizon scan of priority actions and challenges - Bengtson Nash, Susan; Bohlin-Nizzetto, Pernilla; Galban-Malagon, Cristobal; Corsolini, Simonetta; Cincinelli, Alessandra; Lohmann, Rainer (The Lancet Planetary Health, 2023)
Summary Global production and emission of chemicals exceeds societal capacities for assessment and monitoring. This situation calls for improved chemical regulatory policy frameworks and increased support for expedited decision making within existing frameworks. The polar regions of the Earth represent unique sentinel areas for the study of global chemical behaviour, and data arising from these areas can strengthen existing policy frameworks. However, chemical pollution research and monitoring in the Antarctic is underdeveloped, with geopolitical complexities and the absence of legal recognition of international chemical policy serving to neutralise progress made in other global regions. This Personal View represents a horizon scan by the action group Input Pathways of Persistent Organic Pollutants to Antarctica, of the Scientific Committee for Antarctic Research. Four priority research and research facilitation gaps are outlined, with recommendations for Antarctica Treaty parties for strategic action against these priorities.
Keywords: Antarktis; Sørishavet; forskning; forvaltning; helse; miljøgifter

Wind-driven upwelling of iron sustains dense blooms and food webs in the eastern Weddell Gyre - Moreau, Sebastien; Hattermann, Tore; de Steur, Laura; Kauko, Hanna M.; Ahonen, Heidi; Ardelan, Murat; Assmy, Philipp; Chierici, Melissa; Descamps, Sebastien; Dinter, Tilman; Falkenhaug, Tone; Fransson, Agneta; et al. (Nature Communications, 2023)
The Southern Ocean is a major sink of anthropogenic CO2 and an important foraging area for top trophic level consumers. However, iron limitation sets an upper limit to primary productivity. Here we report on a considerably dense late summer phytoplankton bloom spanning 9000 km2 in the open ocean of the eastern Weddell Gyre. Over its 2.5 months duration, the bloom accumulated up to 20 g C m−2 of organic matter, which is unusually high for Southern Ocean open waters. We show that, over 1997–2019, this open ocean bloom was likely driven by anomalies in easterly winds that push sea ice southwards and favor the upwelling of Warm Deep Water enriched in hydrothermal iron and, possibly, other iron sources. This recurring open ocean bloom likely facilitates enhanced carbon export and sustains high standing stocks of Antarctic krill, supporting feeding hot spots for marine birds and baleen whales.
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton

Observational evidence for on-shelf heat transport driven by dense water export in the Weddell Sea - Darelius, Elin; Daae, Kjersti; Dundas, Vår; Fer, Ilker; Hellmer, Hartmut H.; Janout, Markus; Nicholls, Keith W.; Sallée, Jean-Baptiste; Østerhus, Svein (Nature Communications, 2023)
The transport of oceanic heat towards the Antarctic continental margin is central to the mass balance of the Antarctic Ice Sheet. Recent modeling efforts challenge our view on where and how the on-shelf heat flux occurs, suggesting that it is largest where dense shelf waters cascade down the continental slope. Here we provide observational evidence supporting this claim. Using records from moored instruments, we link the downslope flow of dense water from the Filchner overflow to upslope and on-shelf flow of warm water.
Keywords: Sørishavet; oseanografi

Physical and Biogeochemical Properties of Rotten East Antarctic Summer Sea Ice - Corkill, M.; Moreau, S.; Janssens, J.; Fraser, A. D.; Heil, P.; Tison, J.-L.; Cougnon, E. A.; Genovese, C.; Kimura, N.; Meiners, K. M.; Wongpan, P.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2023)
Sea ice forms a barrier to the exchange of energy, gases, moisture and particles between the ocean and atmosphere around Antarctica. Ice temperature, salinity and the composition of ice crystals determine whether a particular slab of sea ice is habitable for microorganisms and permeable to exchanges between the ocean and atmosphere, allowing, for example, carbon dioxide (CO2) from the atmosphere to be absorbed or outgassed by the ocean. Spring sea ice can have high concentrations of algae and absorb atmospheric CO2. In the summer of 2016?2017 off East Antarctica, we found decayed and porous granular ice layers in the interior of the ice column, which showed high algal pigment concentrations. The maximum chlorophyll a observed in the interior of the ice column was 67.7 ?g/L in a 24% porous granular ice layer between 0.8 and 0.9 m depth in 1.7 m thick ice, compared to an overall mean sea-ice chlorophyll a (± one standard deviation) of 13.5 ± 21.8 ?g/L. We also found extensive surface melting, with instances of snow meltwater apparently percolating through the ice, as well as impermeable superimposed ice layers that had refrozen along with melt ponds on top of the ice. With future warming, the structures we describe here could occur earlier and/or become more persistent, meaning that sea ice would be more often characterized by patchy permeability and interior ice algal accumulations.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; havis; isfjell

Genomics of cold adaptations in the Antarctic notothenioid fish radiation - Bista, Iliana; Wood, Jonathan M. D.; Desvignes, Thomas; McCarthy, Shane A.; Matschiner, Michael; Ning, Zemin; Tracey, Alan; Torrance, James; Sims, Ying; Chow, William; Smith, Michelle; Oliver, Karen; et al. (Nature Communications, 2023)
Numerous novel adaptations characterise the radiation of notothenioids, the dominant fish group in the freezing seas of the Southern Ocean. To improve understanding of the evolution of this iconic fish group, here we generate and analyse new genome assemblies for 24 species covering all major subgroups of the radiation, including five long-read assemblies. We present a new estimate for the onset of the radiation at 10.7 million years ago, based on a time-calibrated phylogeny derived from genome-wide sequence data. We identify a two-fold variation in genome size, driven by expansion of multiple transposable element families, and use the long-read data to reconstruct two evolutionarily important, highly repetitive gene family loci. First, we present the most complete reconstruction to date of the antifreeze glycoprotein gene family, whose emergence enabled survival in sub-zero temperatures, showing the expansion of the antifreeze gene locus from the ancestral to the derived state. Second, we trace the loss of haemoglobin genes in icefishes, the only vertebrates lacking functional haemoglobins, through complete reconstruction of the two haemoglobin gene clusters across notothenioid families. Both the haemoglobin and antifreeze genomic loci are characterised by multiple transposon expansions that may have driven the evolutionary history of these genes.
Article number: 3412
Keywords: Sørishavet; fisker; marin biologi; zoologi

Reduced Deep Convection and Bottom Water Formation Due To Antarctic Meltwater in a Multi-Model Ensemble - Chen, Jia-Jia; Swart, Neil C.; Beadling, Rebecca; Cheng, Xuhua; Hattermann, Tore; Jüling, André; Li, Qian; Marshall, John; Martin, Torge; Muilwijk, Morven; Pauling, Andrew G.; Purich, Ariaan; et al. (Geophysical Research Letters, 2023)
Abstract The additional water from the Antarctic ice sheet and ice shelves due to climate-induced melt can impact ocean circulation and global climate. However, the major processes driving melt are not adequately represented in Coupled Model Intercomparison Project phase 6 (CMIP6) models. Here, we analyze a novel multi-model ensemble of CMIP6 models with consistent meltwater addition to examine the robustness of the modeled response to meltwater, which has not been possible in previous single-model studies. Antarctic meltwater addition induces a substantial weakening of open-ocean deep convection. Additionally, Antarctic Bottom Water warms, its volume contracts, and the sea surface cools. However, the magnitude of the reduction varies greatly across models, with differing anomalies correlated with their respective mean-state climatology, indicating the state-dependency of the climate response to meltwater. A better representation of the Southern Ocean mean state is necessary for narrowing the inter-model spread of response to Antarctic meltwater.
Publisher: John Wiley & Sons, Ltd Article number: e2023GL106492
Keywords: Sørishavet; klimamodeller; oseanografi

Historical occurrence of Antarctic icebergs within mercantile shipping routes and the exceptional events of the 1890s - Headland, Robert Keith; Hughes, Nicholas Edward; Wilkinson, Jeremy Paul (Journal of Glaciology, 2023)
A major consideration for maritime activity in the Southern Hemisphere is the northern limit of icebergs, or the Southern Ocean Limit Of Known Ice (SOLOKI). This analysis of historical reports of icebergs during Southern Hemisphere voyages from 1687 to 1933 provides a basis for examination of their geographical and chronological occurrence during ~250 years. The analyses use tabulated data from 742 voyages and other reports from many sources, some including first-person descriptions. While these data are dependent on icebergs being reported by mariners, as well as the variable frequency of voyages, they demonstrate distinct periods of exceptional frequency of icebergs occurring in certain localities, particularly the far South Atlantic. Based upon historical records the evidence suggests unprecedented numbers of icebergs were present in southern shipping channels in the 1890s. When these historical observations are combined with modern iceberg drift trajectories, their possible origin can be elucidated. Owing to the numbers of icebergs seen and their geographical spread, our results suggest that this was possibly the largest near-synchronous calvings in the last 300 years, and the northernmost extent of the SOLOKI.
Keywords: Sørishavet; glasiologi; isfjell

Assessing the viability of estimating baleen whale abundance from tourist vessels - Henderson, Angus Fleetwood; Hindell, Mark Andrew; Wotherspoon, Simon; Biuw, Martin; Lea, Mary-Anne; Kelly, Nat; Lowther, Andrew Damon (Frontiers in Marine Science, 2023)
Many populations of southern hemisphere baleen whales are recovering and are again becoming dominant consumers in the Southern Ocean. Key to understanding the present and future role of baleen whales in Southern Ocean ecosystems is determining their abundance on foraging grounds. Distance sampling is the standard method for estimating baleen whale abundance but requires specific logistic requirements which are rarely achieved in the remote Southern Ocean. We explore the potential use of tourist vessel-based sampling as a cost-effective solution for conducting distance sampling surveys for baleen whales in the Southern Ocean. We used a dataset of tourist vessel locations from the southwest Atlantic sector of the Southern Ocean and published knowledge from Southern Ocean sighting surveys to determine the number of tourist vessel voyages required for robust abundance estimates. Second, we simulated the abundance and distributions of four baleen whale species for the study area and sampled them with both standardized line transect surveys and non-standardized tourist vessel-based surveys, then compared modeled abundance and distributions from each survey to the original simulation. For the southwest Atlantic, we show that 12-22 tourist vessel voyages are likely required to estimate abundance for humpback and fin whales, with relative estimates for blue, sei, Antarctic minke, and southern right whales. Second, we show tourist vessel-based surveys outperformed standardized line transect surveys at reproducing simulated baleen whale abundances and distribution. These analyses suggest tourist vessel-based surveys are a viable method for estimating baleen whale abundance in remote regions. For the southwest Atlantic, the relatively cost-effective nature of tourist vessel-based survey and regularity of tourist vessel voyages could allow for annual and intra-annual estimates of abundance, a fundamental improvement on current methods, which may capture spatiotemporal trends in baleen whale movements on forging grounds. Comparative modeling of sampling methods provided insights into the behavior of general additive model-based abundance modeling, contributing to the development of detailed guidelines of best practices for these approaches. Through successful engagement with tourist company partners, this method has the potential to characterize abundance across a variety of marine species and spaces globally, and deliver high-quality scientific outcomes relevant to management organizations.
Keywords: Sørishavet; kval; marin biologi

The stability of present-day Antarctic grounding lines – Part 1: No indication of marine ice sheet instability in the current geometry - Hill, E. A.; Urruty, B.; Reese, R.; Garbe, J.; Gagliardini, O.; Durand, G.; Gillet-Chaulet, F.; Gudmundsson, G. H.; Winkelmann, R.; Chekki, M.; Chandler, D.; Langebroek, P. M. (The Cryosphere, 2023)
Theoretical and numerical work has shown that under certain circumstances grounding lines of marine-type ice sheets can enter phases of irreversible advance and retreat driven by the marine ice sheet instability (MISI). Instances of such irreversible retreat have been found in several simulations of the Antarctic Ice Sheet. However, it has not been assessed whether the Antarctic grounding lines are already undergoing MISI in their current position. Here, we conduct a systematic numerical stability analysis using three state-of-the-art ice sheet models: Úa, Elmer/Ice, and the Parallel Ice Sheet Model (PISM). For the first two models, we construct steady-state initial configurations whereby the simulated grounding lines remain at the observed present-day positions through time. The third model, PISM, uses a spin-up procedure and historical forcing such that its transient state is close to the observed one. To assess the stability of these simulated states, we apply short-term perturbations to submarine melting. Our results show that the grounding lines around Antarctica migrate slightly away from their initial position while the perturbation is applied, and they revert once the perturbation is removed. This indicates that present-day retreat of Antarctic grounding lines is not yet irreversible or self-sustained. However, our accompanying paper (Part 2, Reese et al., 2023a) shows that if the grounding lines retreated further inland, under present-day climate forcing, it may lead to the eventual irreversible collapse of some marine regions of West Antarctica.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Edition: 2023/10/18 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

Warming beneath an East Antarctic ice shelf due to increased subpolar westerlies and reduced sea ice - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Auger, Matthis; Nøst, Ole Anders; Moholdt, Geir (Nature Geoscience, 2023)
Understanding how climate change influences ocean-driven melting of the Antarctic ice shelves is one of the greatest challenges for projecting future sea level rise. The East Antarctic ice shelf cavities host cold water masses that limit melting, and only a few short-term observational studies exist on what drives warm water intrusions into these cavities. We analyse nine years of continuous oceanographic records from below Fimbulisen and relate them to oceanic and atmospheric forcing. On monthly time scales, warm inflow events are associated with weakened coastal easterlies reducing downwelling in front of the ice shelf. Since 2016, however, we observe sustained warming, with inflowing Warm Deep Water temperatures reaching above 0 °C. This is concurrent with an increase in satellite-derived basal melt rates of 0.62 m yr−1, which nearly doubles the basal mass loss at this relatively cold ice shelf cavity. We find that this transition is linked to a reduction in coastal sea ice cover through an increase in atmosphere–ocean momentum transfer and to a strengthening of remote subpolar westerlies. These results imply that East Antarctic ice shelves may become more exposed to warmer waters with a projected increase of circum-Antarctic westerlies, increasing this region’s relevance for sea level rise projections.
Keywords: Sørishavet; glasiologi; oseanografi

Antarctic sea-ice low resonates in the ecophysiology of humpback whales - Nash, Susan Bengtson; Groβ, Jasmin; Castrillon, Juliana; Casa, Maria Valeria; Luche, Greta Dalle; Meager, Justin; Ghosh, Ruma; Eggebo, June; Bohlin-Nizzetto, Pernilla (Science of The Total Environment, 2023)
The past six years have been marked by some of the most dramatic climatic events observed in the Antarctic region in recent history, commencing with the 2017 sea-ice extreme low. The Humpback Whale Sentinel Programme is a circum-polar biomonitoring program for long term surveillance of the Antarctic sea-ice ecosystem. It has previously signalled the extreme La Niña event of 2010/11, and it was therefore of interest to assess the capacity of existing biomonitoring measures under the program to detect the impacts of 2017 anomalous climatic events. Six ecophysiological markers of population adiposity, diet, and fecundity were targeted, as well as calf and juvenile mortality via stranding records. All indicators, with the exception of bulk stable isotope dietary tracers, indicated a negative trend in 2017, whilst C and N bulk stable isotopes appeared to indicate a lag phase resulting from the anomalous year. The collation of multiple biochemical, chemical, and observational lines of evidence via a single biomonitoring platform provides comprehensive information for evidence-led policy in the Antarctic and Southern Ocean region.
Keywords: Sørishavet; bioovervåking; havis; klimaendringer; knølhvaler; marine økosystemer; miljøgifter; økofysiologi

Large-scale seabird community structure along oceanographic gradients in the Scotia Sea and northern Antarctic Peninsula - Ollus, Victoria Marja Sofia; Biuw, Martin; Lowther, Andrew; Fauchald, Per; Deehr Johannessen, John Elling; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C.; Oosthuizen, W. Chris; Lindstrøm, Ulf (Frontiers in Marine Science, 2023)
Introduction: The Scotia Sea and Antarctic Peninsula are warming rapidly and changes in species distribution are expected. In predicting habitat shifts and considering appropriate management strategies for marine predators, a community-level understanding of how these predators are distributed is desirable. Acquiring such data, particularly in remote areas, is often problematic given the cost associated with the operation of research vessels. Here we use cruise vessels as sampling platforms to explore seabird distribution relative to habitat characteristics. Methods: Data on seabird at-sea distribution were collected using strip-transect counts throughout the Antarctic Peninsula and Scotia Sea in the austral summer of 2019-2020. Constrained correspondence analysis (CCA) and generalized additive models (GAM) were used to relate seabird community composition, density, and species richness to environmental covariates. Results: Species assemblages differed between oceanographic areas, with sea surface temperature and distance to coast being the most important predictors of seabird distribution. Our results further revealed a geographic separation of distinct communities rather than hotspot regions in the study area in summer. Discussion: These findings highlight the importance of large-scale environmental characteristics in shaping seabird community structure, presumably through underlying prey distribution and interspecific interactions. The present study contributes to the knowledge of seabird distribution and habitat use as well as the baseline for assessing the response of Antarctic seabird communities to climate warming. We argue that cruise vessels, when combined with structured research surveys, can provide a cost-effective additional tool for the monitoring of community and ecosystem level changes.
Keywords: Antarktis; Sørishavet; marin biologi; marin zoologi; marine økosystemer; sjøfugler

Quantifying dissolution rates of Antarctic icebergs in open water - Orheim, Olav; Giles, A. Barry; Jacka, T. H. (Jo); Moholdt, Geir (Annals of Glaciology, 2023)
At any one time 130 000 icebergs are afloat in the Southern Ocean; 97% of these are too small to be registered in current satellite-based databases, yet the melting of these small icebergs provides a major input to the Southern Ocean. We use a unique set of visual size observations of 53 000 icebergs in the South Atlantic Ocean, the SCAR International Iceberg Database, to derive average iceberg dissolution rates. Fracture into two parts is the dominant dissolution process for tabular icebergs, with an average half-life of 30 days for icebergs <4 km length and 60 days for larger icebergs. Complete shatter producing many icebergs <1 km length is rare. A side attrition rate of 0.23 m d−1 combined with drift speed of 6 km d−1, or any proportional change in both numbers fits the observed changes in iceberg distribution. The largest injection into the Southern Ocean of fresh water and any iceberg-transported material takes place in a ~2.3 × 10⁶ km2 zone extending east-northeast from the Antarctic Peninsula to the Greenwich meridian. The iceberg contribution to salinities and temperatures, with maximum contribution north of the Weddell Sea, differs in some regions, from those indicated by tracking large icebergs.
Edition: 2023/05/03 Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi; iceberg calving; isfjell; oseanografi

Antarctic iceberg distribution revealed through three decades of systematic ship-based observations in the SCAR International Iceberg Database - Orheim, Olav; Giles, A. Barry; Moholdt, Geir; (Jo) Jacka, T. H.; Bjørdal, Are (Journal of Glaciology, 2023)
In 1981, the Scientific Committee on Antarctic Research endorsed a program for ship-based collection of Antarctic iceberg data, to be coordinated by the Norwegian Polar Institute (NPI). From the austral summers 1982/1983 to 1997/1998, icebergs were recorded from most, and up to 2009/10 by fewer research vessels. The NPI database makes up 80% of the SCAR International Iceberg Database presented here, the remainder being Australian National Antarctic Research Expedition observations. The database contains positions of 374 142 icebergs resulting from 34 662 observations. Within these, 298 235 icebergs are classified into different size categories. The ship-based data are particularly useful because they include systematic observations of smaller icebergs not covered by current satellite-based datasets. Here, we assess regional and seasonal variations in iceberg density and total quantities, we identify drift patterns and exit zones from the continent, and we discuss iceberg dissolution rates and calving rates. There are significant differences in the extent of icebergs observed over the 30 plus years of observations, but much of these can be ascribed to differences in observation density and location. In the summer, Antarctic icebergs >10 m in length number ~130 000 of which 1000 are found north of the Southern Ocean boundary.
Edition: 2022/10/03 Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; database; glasiologi; isfjell

The stability of present-day Antarctic grounding lines – Part 2: Onset of irreversible retreat of Amundsen Sea glaciers under current climate on centennial timescales cannot be excluded - Reese, R.; Garbe, J.; Hill, E. A.; Urruty, B.; Naughten, K. A.; Gagliardini, O.; Durand, G.; Gillet-Chaulet, F.; Gudmundsson, G. H.; Chandler, D.; Langebroek, P. M.; Winkelmann, R. (The Cryosphere, 2023)
Observations of ocean-driven grounding-line retreat in the Amundsen Sea Embayment in Antarctica raise the question of an imminent collapse of the West Antarctic Ice Sheet. Here we analyse the committed evolution of Antarctic grounding lines under the present-day climate. To this aim, we first calibrate a sub-shelf melt parameterization, which is derived from an ocean box model, with observed and modelled melt sensitivities to ocean temperature changes, making it suitable for present-day simulations and future sea level projections. Using the new calibration, we run an ensemble of historical simulations from 1850 to 2015 with a state-of-the-art ice sheet model to create model instances of possible present-day ice sheet configurations. Then, we extend the simulations for another 10 000 years to investigate their evolution under constant present-day climate forcing and bathymetry. We test for reversibility of grounding-line movement in the case that large-scale retreat occurs. In the Amundsen Sea Embayment we find irreversible retreat of the Thwaites Glacier for all our parameter combinations and irreversible retreat of the Pine Island Glacier for some admissible parameter combinations. Importantly, an irreversible collapse in the Amundsen Sea Embayment sector is initiated at the earliest between 300 and 500 years in our simulations and is not inevitable yet – as also shown in our companion paper (Part 1, Hill et al., 2023). In other words, the region has not tipped yet. With the assumption of constant present-day climate, the collapse evolves on millennial timescales, with a maximum rate of 0.9 mm a−1 sea-level-equivalent ice volume loss. The contribution to sea level by 2300 is limited to 8 cm with a maximum rate of 0.4 mm a−1 sea-level-equivalent ice volume loss. Furthermore, when allowing ice shelves to regrow to their present geometry, we find that large-scale grounding-line retreat into marine basins upstream of the Filchner–Ronne Ice Shelf and the western Siple Coast is reversible. Other grounding lines remain close to their current positions in all configurations under present-day climate.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Southern ocean carbon and heat impact on climate - Sallée, J. B.; Abrahamsen, E. P.; Allaigre, C.; Auger, M.; Ayres, H.; Badhe, R.; Boutin, J.; Brearley, J. A.; de Lavergne, C.; ten Doeschate, A. M. M.; Droste, E. S.; du Plessis, M. D.; et al. (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2023)
The Southern Ocean greatly contributes to the regulation of the global climate by controlling important heat and carbon exchanges between the atmosphere and the ocean. Rates of climate change on decadal timescales are therefore impacted by oceanic processes taking place in the Southern Ocean, yet too little is known about these processes. Limitations come both from the lack of observations in this extreme environment and its inherent sensitivity to intermittent processes at scales that are not well captured in current Earth system models. The Southern Ocean Carbon and Heat Impact on Climate programme was launched to address this knowledge gap, with the overall objective to understand and quantify variability of heat and carbon budgets in the Southern Ocean through an investigation of the key physical processes controlling exchanges between the atmosphere, ocean and sea ice using a combination of observational and modelling approaches. Here, we provide a brief overview of the programme, as well as a summary of some of the scientific progress achieved during its first half. Advances range from new evidence of the importance of specific processes in Southern Ocean ventilation rate (e.g. storm-induced turbulence, sea–ice meltwater fronts, wind-induced gyre circulation, dense shelf water formation and abyssal mixing) to refined descriptions of the physical changes currently ongoing in the Southern Ocean and of their link with global climate. This article is part of a discussion meeting issue ‘Heat and carbon uptake in the Southern Ocean: the state of the art and future priorities’.
_eprint: https://royalsocietypublishing.org/doi/pdf/10.1098/rsta.2022.0056
Keywords: Sørishavet; atmosfæren; havis; klimaforskning; oseanografi

Observing Antarctic Bottom Water in the Southern Ocean - Silvano, Alessandro; Purkey, Sarah; Gordon, Arnold L.; Castagno, Pasquale; Stewart, Andrew L.; Rintoul, Stephen R.; Foppert, Annie; Gunn, Kathryn L.; Herraiz-Borreguero, Laura; Aoki, Shigeru; Nakayama, Yoshihiro; Naveira Garabato, Alberto C.; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.
Keywords: Sørishavet; oseanografi

Absence of photophysiological response to iron addition in autumn phytoplankton in the Antarctic sea-ice zone - Singh, A.; Fietz, S.; Thomalla, S. J.; Sanchez, N.; Ardelan, M. V.; Moreau, S.; Kauko, H. M.; Fransson, A.; Chierici, M.; Samanta, S.; Mtshali, T. N.; Roychoudhury, A. N.; et al. (Biogeosciences, 2023)
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton

The Southern Ocean Freshwater Input from Antarctica (SOFIA) Initiative: scientific objectives and experimental design - Swart, Neil C.; Martin, Torge; Beadling, Rebecca; Chen, Jia-Jia; Danek, Christopher; England, Matthew H.; Farneti, Riccardo; Griffies, Stephen M.; Hattermann, Tore; Hauck, Judith; Haumann, F. Alexander; Jüling, André; et al. (Geoscientific Model Development, 2023)
As the climate warms, the grounded ice sheet and floating ice shelves surrounding Antarctica are melting and releasing additional freshwater into the Southern Ocean. Nonetheless, almost all existing coupled climate models have fixed ice sheets and lack the physics required to represent the dominant sources of Antarctic melt. These missing ice dynamics represent a key uncertainty that is typically unaccounted for in current global climate change projections. Previous modelling studies that have imposed additional Antarctic meltwater have demonstrated regional impacts on Southern Ocean stratification, circulation, and sea ice, as well as remote changes in atmospheric circulation, tropical precipitation, and global temperature. However, these previous studies have used widely varying rates of freshwater forcing, have been conducted using different climate models and configurations, and have reached differing conclusions on the magnitude of meltwater–climate feedbacks. The Southern Ocean Freshwater Input from Antarctica (SOFIA) initiative brings together a team of scientists to quantify the climate system response to Antarctic meltwater input along with key aspects of the uncertainty. In this paper, we summarize the state of knowledge on meltwater discharge from the Antarctic ice sheet and ice shelves to the Southern Ocean and explain the scientific objectives of our initiative. We propose a series of coupled and ocean–sea ice model experiments, including idealized meltwater experiments, historical experiments with observationally consistent meltwater input, and future scenarios driven by meltwater inputs derived from stand-alone ice sheet models. Through coordinating a multi-model ensemble of simulations using a common experimental design, open data archiving, and facilitating scientific collaboration, SOFIA aims to move the community toward better constraining our understanding of the climate system response to Antarctic melt.
Keywords: Sørishavet; geovitenskap; havnivåstigning; klimaendringer; klimamodeller; oseanografi

Linking timescale-dependent Antarctic sea ice kinematic observations to ice thickness - Tian, Tian R.; Fraser, Alexander D.; Lavergne, Thomas; Fiddes, Sonya L.; Zhao, Chen; Heil, Petra (Remote Sensing of Environment, 2023)
Sea ice kinematics impacts the global ocean–atmosphere system in numerous ways: modification of albedo, ice cover, and ice mass; heat transmission between atmosphere and ocean; and ice thickness distribution. Such research is often conducted using in situ and remotely-sensed observations of ice motion. In recent work, an ice motion product generated from overlapping sections of multiple individual swath pairs – the so-called swath-to-swath (S2S) approach – has been favourably evaluated by buoys in the Arctic. This new product is better able to represent drifting buoy trajectories, however, it has yet to be applied to ice kinematics research. In this study, we investigate the Antarctic sea ice differential kinematic parameters (DKPs) represented by divergence and maximum shear rate computed from the new S2S ice motion product, and compare these with the daily-map (DM)-derived DKP magnitudes. Results indicate that S2S-derived DKP magnitudes are highly timescale-dependent and well represented by an exponential relationship. Furthermore, the exponential DKP curve parameters in this work are shown to correspond well to ice thickness, thus enabling a new class of Antarctic ice thickness proxy observations. This technique lays the groundwork for the possibility of new proxy measurement of ice thickness back to at least 1991, when the high-accuracy S2S measurements of ice motion become available.
Article number: 113813
Keywords: Sørishavet; fysikk; havis

BVLOS UAV missions for vegetation mapping in maritime Antarctic - Zmarz, Anna; Karlsen, Stein Rune; Kycko, Marlena; Korczak-Abshire, Małgorzata; Gołębiowska, Izabela; Karsznia, Izabela; Chwedorzewska, Katarzyna (Frontiers in Environmental Science, 2023)
Polar areas are among the regions where climate change occurs faster than on most of the other areas on Earth. To study the effects of climate change on vegetation, there is a need for knowledge on its current status and properties. Both classic field observation methods and remote sensing methods based on manned aircraft or satellite image analysis have limitations. These include high logistic operation costs, limited research areas, high safety risks, direct human impact, and insufficient resolution of satellite images. Fixed-wing unmanned aerial vehicle beyond the visual line of sight (UAV BVLOS) missions can bridge the scale gap between field-based observations and full-scale airborne or satellite surveys. In this study the two operations of the UAV BVLOS, at an altitude of 350 m ASL, have been successfully performed in Antarctic conditions. Maps of the vegetation of the western shore of Admiralty Bay (King George Island, South Shetlands, Western Antarctic) that included the Antarctic Specially Protected Area No. 128 (ASPA 128) were designed. The vegetation in the 7.5 km2 area was mapped in ultra-high resolution (<5 cm and DEM of 0.25 m GSD), and from the Normalized Difference Vegetation Index (NDVI), four broad vegetation units were extracted: “dense moss carpets” (covering 0.14 km2, 0.8% of ASPA 128), “Sanionia uncinata moss bed” (0.31 km2, 1.7% of ASPA 128), “Deschampsia antarctica grass meadow” (0.24 km2, 1.3% of ASPA 128), and “Deschampsia antarctica–Usnea antarctica heath” (1.66 km2, 9.4% of ASPA 128). Our results demonstrate that the presented UAV BVLOS–based surveys are time-effective (single flight lasting 2.5 h on a distance of 300 km) and cost-effective when compared to classical field-based observations and are less invasive for the ecosystem. Moreover, unmanned airborne vehicles significantly improve security, which is of particular interest in polar region research. Therefore, their development is highly recommended for monitoring areas in remote and fragile environments.
Keywords: Sørishavet; kartlegging; logistikk; teknologi; vegetasjon

Southern Ocean biogenic blooms freezing-in Oligocene colder climates - Hochmuth, Katharina; Whittaker, Joanne M.; Sauermilch, Isabel; Klocker, Andreas; Gohl, Karsten; LaCasce, Joseph H. (Nature Communications, 2022)
Crossing a key atmospheric CO2 threshold triggered a fundamental global climate reorganisation ~34 million years ago (Ma) establishing permanent Antarctic ice sheets. Curiously, a more dramatic CO2 decline (~800–400 ppm by the Early Oligocene(~27 Ma)), postdates initial ice sheet expansion but the mechanisms driving this later, rapid drop in atmospheric carbon during the early Oligocene remains elusive and controversial. Here we use marine seismic reflection and borehole data to reveal an unprecedented accumulation of early Oligocene strata (up to 2.2 km thick over 1500 × 500 km) with a major biogenic component in the Australian Southern Ocean. High-resolution ocean simulations demonstrate that a tectonically-driven, one-off reorganisation of ocean currents, caused a unique period where current instability coincided with high nutrient input from the Antarctic continent. This unrepeated and short-lived environment favoured extreme bioproductivity and enhanced sediment burial. The size and rapid accumulation of this sediment package potentially holds ~1.067 × 1015 kg of the ‘missing carbon’ sequestered during the decline from an Eocene high CO2-world to a mid-Oligocene medium CO2-world, highlighting the exceptional role of the Southern Ocean in modulating long-term climate.
Keywords: Sørishavet; geologi; glasiologi; klimaendringer; sedimenter

Regional sea-level highstand triggered Holocene ice sheet thinning across coastal Dronning Maud Land, East Antarctica - Suganuma, Yusuke; Kaneda, Heitaro; Mas e Braga, Martim; Ishiwa, Takeshige; Koyama, Takushi; Newall, Jennifer C.; Okuno, Jun’ichi; Obase, Takashi; Saito, Fuyuki; Rogozhina, Irina; Andersen, Jane Lund; Kawamata, Moto; et al. (Communications Earth & Environment, 2022)
The East Antarctic Ice Sheet stores a vast amount of freshwater, which makes it the single largest potential contributor to future sea-level rise. However, the lack of well-constrained geological records of past ice sheet changes impedes model validation, hampers mass balance estimates, and inhibits examination of ice loss mechanisms. Here we identify rapid ice-sheet thinning in coastal Dronning Maud Land from Early to Middle Holocene (9000–5000 years ago) using a deglacial chronology based on in situ cosmogenic nuclide surface exposure dates from central Dronning Maud Land, in concert with numerical simulations of regional and continental ice-sheet evolution. Regional sea-level changes reproduced from our refined ice-load history show a highstand at 9000–8000 years ago. We propose that sea-level rise and a concomitant influx of warmer Circumpolar Deep Water triggered ice shelf breakup via the marine ice sheet instability mechanism, which led to rapid thinning of upstream coastal ice sheet sectors.
Keywords: Antarktis; Sørishavet; glasiologi; havis; havnivå; isshelf

Genomic insights into the secondary aquatic transition of penguins - Cole, Theresa L.; Zhou, Chengran; Fang, Miaoquan; Pan, Hailin; Ksepka, Daniel T.; Fiddaman, Steven R.; Emerling, Christopher A.; Thomas, Daniel B.; Bi, Xupeng; Fang, Qi; Ellegaard, Martin R.; Feng, Shaohong; et al. (Nature Communications, 2022)
Penguins lost the ability to fly more than 60 million years ago, subsequently evolving a hyper-specialized marine body plan. Within the framework of a genome-scale, fossil-inclusive phylogeny, we identify key geological events that shaped penguin diversification and genomic signatures consistent with widespread refugia/recolonization during major climate oscillations. We further identify a suite of genes potentially underpinning adaptations related to thermoregulation, oxygenation, diving, vision, diet, immunity and body size, which might have facilitated their remarkable secondary transition to an aquatic ecology. Our analyses indicate that penguins and their sister group (Procellariiformes) have the lowest evolutionary rates yet detected in birds. Together, these findings help improve our understanding of how penguins have transitioned to the marine environment, successfully colonizing some of the most extreme environments on Earth.
Keywords: Sørishavet; evolusjon; fylogenetikk; ornitologi; pingviner

Plastic occurrence, sources, and impacts in Antarctic environment and biota - Caruso, Gabriella; Bergami, Elisa; Singh, Neelu; Corsi, Ilaria (Water Biology and Security, 2022)
Several studies have documented that plastic pollution is affecting one of the most remote and pristine regions of our planet, Antarctica. Plastics of different size and polymeric composition have been retrieved in Antarctic sea ice, surface waters and sediments, with microplastics (mostly fibers) found both in terrestrial and marine organisms. Such evidence raises concerns about potential detrimental effects on biodiversity and ecosystem functions. The present review aims to report the most up-to-date knowledge on occurrence and distribution of plastic pollution in the Antarctic environment and biota including interaction with microorganisms, potential sources, and its impact on Antarctic biota. Our understanding of plastic pollution in this polar region will help us define the human footprint in Antarctica and predict future ecological risks.
Keywords: Sørishavet; forurensning; plastpartikler; økotoksikologi

Characterization of fin whale song off the Western Antarctic Peninsula - Wood, Megan; Širović, Ana (PLOS ONE, 2022)
Song is produced by a variety of terrestrial and marine animals and is particularly common among baleen whales. Fin whale (Balaenoptera physalus) song is comprised of relatively simple 20 Hz pulses produced at regular intervals. The timing of these intervals, in addition to the presence and frequency of overtones, appears to be unique to each population. The purpose of this study was to characterize Western Antarctic Peninsula fin whale song and describe temporal pattern variations in song type and occurrence. Recordings were collected in the area from 2001–2004 and again 2014–2016. One song type was identified with a primary inter-pulse interval (IPI) of approximately 14 s and secondary IPI of 12.5 s. This song occurred in three pattern variants: singlet, doublet, and long triplet. The interval between pulses increased by 1.5 s between recording periods while the frequency of the overtones decreased from 89 Hz to 86 Hz. Song was never recorded in August and while it was recorded at other times in some years, it was consistently present in recordings from April through June across all years. While multiple pattern variants were present each year, singlets were generally the most prevalent variant. Doublets and triplets occurred from February through June, with highest levels of variants in February. In later years the triplet variant presence increased and in 2016 it comprised 53% of recorded song bouts. Further research is needed to understand the reasons why song changes over time and to examine the feasibility of using song to delineate and identify populations.
Publisher: Public Library of Science
Keywords: Sørishavet; kval; marin biologi

Xenobiotic metabolism and its physiological consequences in high-Antarctic Notothenioid fishes - Strobel, Anneli; Lille-Langøy, Roger; Segner, Helmut; Burkhardt-Holm, Patricia; Goksøyr, Anders; Karlsen, Odd André (Polar Biology, 2022)
The Antarctic ecosystem is progressively exposed to anthropogenic contaminants, such as polycyclic aromatic hydrocarbons (PAHs). So far, it is largely unknown if PAHs leave a mark in the physiology of high-Antarctic fish. We approached this issue via two avenues: first, we examined the functional response of the aryl hydrocarbon receptor (Ahr), which is a molecular initiating event of many toxic effects of PAHs in biota. Chionodraco hamatus and Trematomus loennbergii served as representatives for high-Antarctic Notothenioids, and Atlantic cod, Gadus morhua as non-polar reference species. We sequenced and cloned the Ahr ligand binding domain (LBD) of the Notothenioids and deployed a GAL4-based luciferase reporter gene assay expressing the Ahr LBD. Benzo[a]pyrene (BaP), beta-naphthoflavone and chrysene were used as ligands for the reporter gene assay. Second, we investigated the energetic costs of Ahr activation in isolated liver cells of the Notothenioids during acute, non-cytotoxic BaP exposure. In the reporter assay, the Ahr LBD of Atlantic cod and the Antarctic Notothenioids were activated by the ligands tested herein. In the in vitro assays with isolated liver cells of high-Antarctic Notothenioids, BaP exposure had no effect on overall respiration, but caused shifts in the respiration dedicated to protein synthesis. Thus, our study demonstrated that high-Antarctic fish possess a functional Ahr that can be ligand-activated in a concentration-dependent manner by environmental contaminants. This is associated with altered cost for cellular protein synthesis. Future studies have to show if the toxicant-induced activation of the Ahr pathway may lead to altered organism performance of Antarctic fish.
Keywords: Sørishavet; fisker; marin zoologi; marinbiologi

Oppdagelsen av Shackletons Endurance: fremtidig beskyttelse eller plyndring? / av redaksjonen - Barr, Susan; Gjertz, Ian; Mehlum, Fridtjof (Polarboken, 2022)
Kunngjøringen 9. mars 2022 om oppdagelsen av Ernest Shackletons skip Endurance vekket omfattende interesse. Skipet står oppreist på kjølen rundt 3000 meter under stedet der det i 1915 ble presset ned under trykket av den antarktiske isen. Vraket synes å være i forbausende god stand. Medieomtaler indikerer at det faktum at vrakområdet er anerkjent somet fredet kulturminne under Antarktistraktaten gjorde at ingenting ble rørt eller fjernet. Det ble kun fotodokumentert fra passende avstand. Denne ansvarsfulle tilnærmingen må berømmes.
Keywords: Endurance (skip); Sørishavet; kulturminner

Strong and lasting impacts of past global warming on baleen whales and their prey - Cabrera, Andrea A; Schall, Elena; Bérubé, Martine; Anderwald, Pia; Bachmann, Lutz; Berrow, Simon; Best, Peter B; Clapham, Phillip J; Cunha, Haydée A.; Dalla Rosa, Luciano; Dias, Carolina; Findlay, Kenneth P.; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real-time effects into their long-term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long-term responses of natural populations to periods with global warming. The effects of this post-LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large-scale climate fluctuations during the post-LGM affected baleen whales and their prey, we conducted an extensive, large-scale analysis of the long-term effects of the post-LGM warming on abundance and inter-ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome-wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post-LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean-wide expansions and decreases in abundance that were initiated by the post-LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long-lasting impacts of global warming on marine fauna.
Keywords: Sørishavet; klimaendringer; marin biologi; polarområdene

The Impact of a Southern Ocean Cyclonic Eddy on Mesopelagic Micronekton - Della Penna, Alice; Llort, Joan; Moreau, Sebastien; Patel, Ramkrushnbhai; Kloser, Rudy; Gaube, Peter; Strutton, Peter; Boyd, Philip W (Journal of Geophysical Research: Oceans, 2022)
Mesoscale eddies shape the foraging ecology of predators such as marine mammals and seabirds. A growing number of animal tracking studies show that predators alter their swimming, diving, and foraging behavior within mesoscale eddies. However, little is known about how Southern Ocean eddies influence the distribution of mesopelagic micronekton (fish, squid, and crustaceans), which are major prey items of megafauna. Studies in other oceanic regions have found that eddies can influence the abundance and community composition of micronekton. Here, we analyze acoustic observations from a 14-day survey of a cyclonic mesoscale eddy, its surrounding waters, and the Polar Frontal Zone (PFZ) waters where the eddy formed. We report and interpret spatial patterns of acoustic backscatter at 18 and 75 kHz, proxies indicating combined changes in species, size, and abundance of micronekton. We find that the vertical distribution of acoustic backscatter matched the underwater light conditions characteristic of the eddy core, periphery, and surrounding waters, at scales smaller than 10 km. The median water-column integrated acoustic backscatter values in the eddy core were only half of those measured in the Sub-Antarctic Zone waters surrounding the eddy, but similar to those measured in the PFZ, where the eddy originated 27 days prior. These results suggest that, as for physical and chemical tracers, the eddy maintained its biological characteristics from its source waters creating a unique habitat compared to its surroundings.
Keywords: Sørishavet; marin biologi; oseanografi

Reviews and syntheses: A framework to observe, understand and project ecosystem response to environmental change in the East Antarctic Southern Ocean - Gutt, Julian; Arndt, Stefanie; Barnes, David Keith Alan; Bornemann, Horst; Brey, Thomas; Eisen, Olaf; Flores, Hauke; Griffiths, Huw; Haas, Christian; Hain, Stefan; Hattermann, Tore; Held, Christoph; et al. (Biogeosciences (Online), 2022)
Systematic long-term studies on ecosystem dynamics are largely lacking from the East Antarctic Southern Ocean, although it is well recognized that they are indispensable to identify the ecological impacts and risks of environmental change. Here, we present a framework for establishing a long-term cross-disciplinary study on decadal timescales. We argue that the eastern Weddell Sea and the adjacent sea to the east, off Dronning Maud Land, is a particularly well suited area for such a study, since it is based on findings from previous expeditions to this region. Moreover, since climate and environmental change have so far been comparatively muted in this area, as in the eastern Antarctic in general, a systematic long-term study of its environmental and ecological state can provide a baseline of the current situation, which will be important for an assessment of future changes from their very onset, with consistent and comparable time series data underpinning and testing models and their projections. By establishing an Integrated East Antarctic Marine Research (IEAMaR) observatory, long-term changes in ocean dynamics, geochemistry, biodiversity, and ecosystem functions and services will be systematically explored and mapped through regular autonomous and ship-based synoptic surveys. An associated long-term ecological research (LTER) programme, including experimental and modelling work, will allow for studying climate-driven ecosystem changes and interactions with impacts arising from other anthropogenic activities. This integrative approach will provide a level of long-term data availability and ecosystem understanding that are imperative to determine, understand, and project the consequences of climate change and support a sound science-informed management of future conservation efforts in the Southern Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; klimaendringer; miljøendringer; økosystemer

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Edition: 2022/12/02 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern

Intra-season variations in distribution and abundance of humpback whales in the West Antarctic Peninsula using cruise vessels as opportunistic platforms - Johannessen, John Elling Deehr; Biuw, Martin; Lindstrøm, Ulf; Ollus, Victoria Marja Sofia; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C; Oosthuizen, Wessel Chris; Lowther, Andrew (Ecology and Evolution, 2022)
Fine-scale knowledge of spatiotemporal dynamics in cetacean distribution and abundance throughout the Western Antarctic Peninsula (WAP) is sparse yet essential for effective ecosystem-based management (EBM). Cruise vessels were used as platforms of opportunity to collect data on the distribution and abundance of humpback whales (Megaptera novaeangliae) during the austral summer of 2019/2020 in a region that is also important for the Antarctic krill (Euphausia superba) fishery, to assess potential spatiotemporal interactions for future use in EBM. Data were analyzed using traditional design-based line transect methodology and spatial density surface hurdle models fitted using a set of physical environmental covariates to estimate the abundance and distribution of whales in the area, and to describe their temporal dynamics. Our results indicate a rapid increase in humpback whale abundance in the Bransfield and Gerlache Straits through December, reaching a stable abundance by mid-January. The distribution of humpback whales appeared to change from a patchier distribution in the northern Gerlache Strait to a significantly concentrated presence in the central Gerlache and southern Bransfield Straits, followed by a subsequent dispersion throughout the area. Abundance estimates agreed well with previous literature, increasing from approximately 7000 individuals in 2000 to a peak of 19,107 in 2020. Based on these estimates, we project a total krill consumption of between 1.4 and 3.7 million tons based on traditional and contemporary literature on per capita krill consumption of whales, respectively. When taken in the context of krill fishery catch data in the study area, we conclude that there is minimal spatiotemporal overlap between humpback whales and fishery activity during our study period of November–January. However, there is potential for significant interaction between the two later in the feeding season, but cetacean survey efforts need to be extended into late season in order to fully characterize this potential overlap.
Keywords: Sørishavet; hvaler; marin biologi

Bycatch in the Antarctic krill (Euphausia superba) trawl fishery - Krafft, Bjørn A.; Lowther, Andrew; Krag, Ludvig A. (Fisheries Management and Ecology, 2022)
Bycatch of nontarget species can contribute to overfishing and slow efforts to rebuild fish stocks. Controlling bycatch is fundamental to sustainable fishing and maintaining healthy populations of target species. The Antarctic krill (Euphausia superba) fishery is the largest volume fishery in the Southern Ocean. Understanding the significance of bycatch and its diversity is critical to managing this keystone species. Registered bycatch data from the Antarctic krill fishery in the southwest Atlantic sector of the Southern Ocean were analysed. Observers collected data following an internationally agreed method during the 2010–2020 fishing seasons, with a 20 (± 9) % coverage of fishing activity of Total catch of Antarctic krill which increased from 200,000 tonnes to 450,000 tonnes, with the greatest increase over the last 3 years. Except in 2010 (2.2%), the bycatch ratio was stable and ranged 0.1–0.3%. Fish dominated the bycatch, followed by tunicates and other crustaceans. Observer coverage was high, and bycatch levels were generally low across gear types. Given that accurate information on bycatch is important for sustaining developing fisheries, maintaining high observer coverage of this fishery will be important for detecting impacts from a warming climate and for moving back into historical fishing grounds.
Keywords: Sørishavet; fiskeri; krill; plankton

A review of the scientific knowledge of the seascape off Dronning Maud Land, Antarctica - Lowther, Andrew; von Quillfeldt, Cecilie; Assmy, Philipp; De Steur, Laura; Descamps, Sebastien; Divine, Dmitry; Elvevold, Synnøve; Forwick, Matthias; Fransson, Agneta; Fraser, Alexander; Gerland, Sebastian; Granskog, Mats; et al. (Polar Biology, 2022)
Despite the exclusion of the Southern Ocean from assessments of progress towards achieving the Convention on Biological Diversity (CBD) Strategic Plan, the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) has taken on the mantle of progressing efforts to achieve it. Within the CBD, Aichi Target 11 represents an agreed commitment to protect 10% of the global coastal and marine environment. Adopting an ethos of presenting the best available scientific evidence to support policy makers, CCAMLR has progressed this by designating two Marine Protected Areas in the Southern Ocean, with three others under consideration. The region of Antarctica known as Dronning Maud Land (DML; 20°W to 40°E) and the Atlantic sector of the Southern Ocean that abuts it conveniently spans one region under consideration for spatial protection. To facilitate both an open and transparent process to provide the vest available scientific evidence for policy makers to formulate management options, we review the body of physical, geochemical and biological knowledge of the marine environment of this region. The level of scientific knowledge throughout the seascape abutting DML is polarized, with a clear lack of data in its eastern part which is presumably related to differing levels of research effort dedicated by national Antarctic programmes in the region. The lack of basic data on fundamental aspects of the physical, geological and biological nature of eastern DML make predictions of future trends difficult to impossible, with implications for the provision of management advice including spatial management. Finally, by highlighting key knowledge gaps across the scientific disciplines our review also serves to provide guidance to future research across this important region.
Keywords: Dronning Maud Land; Sørishavet; biofysikk; biogeokjemi; biologi; oseanografi

Distribution and export of particulate organic carbon in East Antarctic coastal polynyas - Ratnarajah, Lavenia; Puigcorbé, Viena; Moreau, Sébastien; Roca-Martí, Montserrat; Janssens, Julie; Corkill, Matthew; Duprat, Luis; Genovese, Cristina; Lieser, Jan; Masqué, Pere; Lannuzel, Delphine (Deep Sea Research Part I: Oceanographic Research Papers, 2022)
Polynyas represent regions of enhanced primary production because of the low, or absent, sea-ice cover coupled with the proximity of nutrient sources. However, studies throughout the Southern Ocean suggest elevated primary production does not necessarily result in increased carbon export. Three coastal polynyas in East Antarctica and an off-shelf region were visited during the austral summer from December 2016 to January 2017 to examine the vertical distribution and concentration of particulate organic carbon (POC). Carbon export was also examined using thorium-234 (234Th) as a proxy at two of the polynyas. Our results show that concentrations and integrated POC stocks were higher within the polynyas compared to the off-shelf sites. Within the polynyas, vertical POC concentrations were higher in the Mertz and Ninnis polynyas compared to the Dalton polynya. Similarly, higher carbon export was measured in the diatom-dominated Mertz polynya, where large particles (>53 μm) represented a significant fraction of the particulate 234Th and POC (average 50% and 39%, respectively), compared to the small flagellate-dominated Dalton polynya, where almost all the particulate 234Th and POC were found in the smaller size fraction (1–53 μm). The POC to Chlorophyll-a ratios suggest that organic matter below the mixed layer in the polynyas consisted largely of fresh phytoplankton at this time of the year. In combination with a parallel study on phytoplankton production at these sites, we find that increased primary production at these polynyas does lead to greater concentrations and export of POC and a higher POC export efficiency.
Keywords: Sørishavet; marin biologi; oseanografi

Allometric relationships of ecologically important Antarctic and Arctic zooplankton and fish species - Schaafsma, Fokje L.; David, Carmen L.; Kohlbach, Doreen; Ehrlich, Julia; Castellani, Giulia; Lange, Benjamin A.; Vortkamp, Martina; Meijboom, André; Fortuna-Wünsch, Anna; Immerz, Antonia; Cantzler, Hannelore; Klasmeier, Apasiri; et al. (Polar Biology, 2022)
Allometric relationships between body properties of animals are useful for a wide variety of purposes, such as estimation of biomass, growth, population structure, bioenergetic modelling and carbon flux studies. This study summarizes allometric relationships of zooplankton and nekton species that play major roles in polar marine food webs. Measurements were performed on 639 individuals of 15 species sampled during three expeditions in the Southern Ocean (winter and summer) and 2374 individuals of 14 species sampled during three expeditions in the Arctic Ocean (spring and summer). The information provided by this study fills current knowledge gaps on relationships between length and wet/dry mass of understudied animals, such as various gelatinous zooplankton, and of animals from understudied seasons and maturity stages, for example, for the krill Thysanoessa macrura and larval Euphausia superba caught in winter. Comparisons show that there is intra-specific variation in length–mass relationships of several species depending on season, e.g. for the amphipod Themisto libellula. To investigate the potential use of generalized regression models, comparisons between sexes, maturity stages or age classes were performed and are discussed, such as for the several krill species and T. libellula. Regression model comparisons on age classes of the fish E. antarctica were inconclusive about their general use. Other allometric measurements performed on carapaces, eyes, heads, telsons, tails and otoliths provided models that proved to be useful for estimating length or mass in, e.g. diet studies. In some cases, the suitability of these models may depend on species or developmental stages.
Keywords: Sørishavet; biomasse; dyreplankton; fisker; marin biologi; marin økologi; polarområdene; zooplankton

Evaluation of an emergent feature of sub-shelf melt oscillations from an idealized coupled ice sheet–ocean model using FISOC (v1.1) – ROMSIceShelf (v1.0) – Elmer/Ice (v9.0) - Zhao, Chen; Gladstone, Rupert; Galton-Fenzi, Benjamin Keith; Gwyther, David; Hattermann, Tore (Geosci. Model Dev., 2022)
Changes in ocean-driven basal melting have a key influence on the stability of ice shelves, the mass loss from the ice sheet, ocean circulation, and global sea level rise. Coupled ice sheet–ocean models play a critical role in understanding future ice sheet evolution and examining the processes governing ice sheet responses to basal melting. However, as a new approach, coupled ice sheet–ocean systems come with new challenges, and the impacts of solutions implemented to date have not been investigated. An emergent feature in several contributing coupled models to the 1st Marine Ice Sheet–Ocean Model Intercomparison Project (MISOMIP1) was a time-varying oscillation in basal melt rates. Here, we use a recently developed coupling framework, FISOC (v1.1), to connect the modified ocean model ROMSIceShelf (v1.0) and ice sheet model Elmer/Ice (v9.0), to investigate the origin and implications of the feature and, more generally, the impact of coupled modeling strategies on the simulated basal melt in an idealized ice shelf cavity based on the MISOMIP setup. We found the spatial-averaged basal melt rates (3.56 m yr−1) oscillated with an amplitude ∼0.7 m yr−1 and approximate period of ∼6 years between year 30 and 100 depending on the experimental design. The melt oscillations emerged in the coupled system and the standalone ocean model using a prescribed change of cavity geometry. We found that the oscillation feature is closely related to the discretized ungrounding of the ice sheet, exposing new ocean, and is likely strengthened by a combination of positive buoyancy–melt feedback and/or melt–geometry feedback near the grounding line, and the frequent coupling of ice geometry and ocean evolution. Sensitivity tests demonstrate that the oscillation feature is always present, regardless of the choice of coupling interval, vertical resolution in the ocean model, tracer properties of cells ungrounded by the retreating ice sheet, or the dependency of friction velocities to the vertical resolution. However, the amplitude, phase, and sub-cycle variability of the oscillation varied significantly across the different configurations. We were unable to ultimately determine whether the feature arises purely due to numerical issues (related to discretization) or a compounding of multiple physical processes amplifying a numerical artifact. We suggest a pathway and choices of physical parameters to help other efforts understand the coupled ice sheet–ocean system using numerical models.
Publisher: Copernicus Publications
Keywords: Antarktis; Sørishavet; glasiologi; havnivåstigning; innlandsis; oseanografi

Observed interannual changes beneath Filchner-Ronne Ice Shelf linked to large-scale atmospheric circulation - Hattermann, Tore; Nicholls, Keith W.; Hellmer, Hartmut H.; Davis, Peter E. D.; Janout, Markus A.; Østerhus, Svein; Schlosser, Elisabeth; Rohardt, Gerd; Kanzow, Torsten (Nature Communications, 2021)
Floating ice shelves are the Achilles’ heel of the Antarctic Ice Sheet. They limit Antarctica’s contribution to global sea level rise, yet they can be rapidly melted from beneath by a warming ocean. At Filchner-Ronne Ice Shelf, a decline in sea ice formation may increase basal melt rates and accelerate marine ice sheet mass loss within this century. However, the understanding of this tipping-point behavior largely relies on numerical models. Our new multi-annual observations from five hot-water drilled boreholes through Filchner-Ronne Ice Shelf show that since 2015 there has been an intensification of the density-driven ice shelf cavity-wide circulation in response to reinforced wind-driven sea ice formation in the Ronne polynya. Enhanced southerly winds over Ronne Ice Shelf coincide with westward displacements of the Amundsen Sea Low position, connecting the cavity circulation with changes in large-scale atmospheric circulation patterns as a new aspect of the atmosphere-ocean-ice shelf system.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf; meteorologi; oseanografi

Multi-decadal trends in Antarctic sea-ice extent driven by ENSO–SAM over the last 2,000 years - Crosta, Xavier; Etourneau, Johan; Orme, Lisa C; Dalaiden, Quentin; Campagne, Philippine; Swingedouw, Didier; Goosse, Hugues; Massé, Guillaume; Miettinen, Arto; McKay, Robert M; Dunbar, Robert B; Escutia, Carlota; et al. (Nature Geoscience, 2021)
Antarctic sea ice has paradoxically become more extensive over the past four decades despite a warming climate. The regional expression of this trend has been linked to changes in vertical redistribution of ocean heat and large-scale wind-field shifts. However, the short length of modern observations has hindered attempts to attribute this trend to anthropogenic forcing or natural variability. Here, we present two new decadal-resolution records of sea ice and sea surface temperatures that document pervasive regional climate heterogeneity in Indian Antarctic sea-ice cover over the last 2,000 years. Data assimilation of our marine records in a climate model suggests that the reconstructed dichotomous regional conditions were driven by the multi-decadal variability of the El Niño Southern Oscillation and Southern Annular Mode (SAM). For example, during an El Niño/SAM– combination, the northward sea-ice transport was reduced while heat advection from the subtropics to the Southern Ocean increased, which resulted in reduced sea-ice extent in the Indian sector as sea ice was compacted along the Antarctic coast. Our results therefore indicate that natural variability is large in the Southern Ocean and suggest that it has played a crucial role in the recent sea-ice trends and their decadal variability in this region.
Keywords: Sørishavet; havis; klimaendringer; klimamodeller; sjøis

Decline in body condition in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean during the 1990s - Cunen, Céline; Walløe, Lars; Konishi, Kenji; Hjort, Nils Lid (Polar Biology, 2021)
Keywords: Sørishavet; hvaler; krill; marin biologi

Sea-ice habitat minimizes grazing impact and predation risk for larval Antarctic krill - David, Carmen L; Schaafsma, Fokje L; van Franeker, Jan A; Pakhomov, Evgeny A; Hunt, Brian P V; Lange, Benjamin A; Castellani, Giulia; Brandt, Angelika; Flores, Hauke (Polar Biology, 2021)
Survival of larval Antarctic krill (Euphausia superba) during winter is largely dependent upon the presence of sea ice as it provides an important source of food and shelter. We hypothesized that sea ice provides additional benefits because it hosts fewer competitors and provides reduced predation risk for krill larvae than the water column. To test our hypothesis, zooplankton were sampled in the Weddell-Scotia Confluence Zone at the ice-water interface (0–2 m) and in the water column (0–500 m) during August–October 2013. Grazing by mesozooplankton, expressed as a percentage of the phytoplankton standing stock, was higher in the water column (1.97 ± 1.84%) than at the ice-water interface (0.08 ± 0.09%), due to a high abundance of pelagic copepods. Predation risk by carnivorous macrozooplankton, expressed as a percentage of the mesozooplankton standing stock, was significantly lower at the ice-water interface (0.83 ± 0.57%; main predators amphipods, siphonophores and ctenophores) than in the water column (4.72 ± 5.85%; main predators chaetognaths and medusae). These results emphasize the important role of sea ice as a suitable winter habitat for larval krill with fewer competitors and lower predation risk. These benefits should be taken into account when considering the response of Antarctic krill to projected declines in sea ice. Whether reduced sea-ice algal production may be compensated for by increased water column production remains unclear, but the shelter provided by sea ice would be significantly reduced or disappear, thus increasing the predation risk on krill larvae.
Keywords: Sørishavet; krill; marin biologi; zooplankton

Svarthamaren seabirds, sentinels of the Southern Ocean - Descamps, Sébastien; Moreau, Sébastien; Tarroux, Arnaud; Lorensten, Svein-Håkon; Bustnes, Jan-Ove; Yoccoz, Nigel G; Borgå, Katrine; Carravieri, Alice; Patrick, Samantha (Fram forum, 2021)
Keywords: Sørishavet; forurensning; klimaendringer; marin biologi; marine økosystemer; miljøendringer; observasjoner; ornitologi; sjøfugler; zoologi; økologi

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Handley, Jonathan; Rouyer, Marie-Morgane; Pearmain, Elizabeth J; Warwick-Evans, Victoria; Teschke, Katharina; Hinke, Jefferson T; Lynch, Heather; Emmerson, Louise; Southwell, Colin; Griffith, Gary; Cárdenas, César A; Franco, Aldina M A; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.
Keywords: Antarktis; Sørishavet; biodiversitet; klimaendringer; marin biologi; miljøvern

FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea - Janout, Markus A; Hellmer, Hartmut H; Hattermann, Tore; Huhn, Oliver; Sültenfuss, Jürgen; Østerhus, Svein; Stulic, Lukrecia; Ryan, Svenja; Schröder, Michael; Kanzow, Torsten (Journal of Geophysical Research: Oceans, 2021)
The Filchner-Ronne Ice Shelf (FRIS) is characterized by moderate basal melt rates due to the near-freezing waters that dominate the wide southern Weddell Sea continental shelf. We revisited the region in austral summer 2018 with detailed hydrographic and noble gas surveys along FRIS. The FRIS front was characterized by High Salinity Shelf Water (HSSW) in Ronne Depression, Ice Shelf Water (ISW) on its eastern flank, and an inflow of modified Warm Deep Water (mWDW) entering through Central Trough. Filchner Trough was dominated by Ronne HSSW-sourced ISW, likely forced by a recently intensified circulation beneath FRIS due to enhanced sea ice production in the Ronne polynya since 2015. Glacial meltwater fractions and tracer-based water mass dating indicate two separate ISW outflow cores, one hugging the Berkner slope after a two-year travel time, and the other located in the central Filchner Trough following a ∼six year-long transit through the FRIS cavity. Historical measurements indicate the presence of two distinct modes, in which water masses in Filchner Trough were dominated by either Ronne HSSW-derived ISW (Ronne-mode) or more locally derived Berkner-HSSW (Berkner-mode). While the dominance of these modes has alternated on interannual time scales, ocean densities in Filchner Trough have remained remarkably stable since the first surveys in 1980. Indeed, geostrophic velocities indicated outflowing ISW-cores along the trough's western flank and onto Berkner Bank, which suggests that Ronne-ISW preconditions Berkner-HSSW production. The negligible density difference between Berkner- and Ronne-mode waters indicates that each contributes cold dense shelf waters to protect FRIS against inflowing mWDW.
Keywords: Sørishavet; Weddellhavet; oseanografi; vannmasser

Evaluation of Three Numerical Weather Prediction Models for the Weddell Sea Region for the Austral Winter 2013 - Jonassen, Marius O; Nygård, Tiina; Vihma, Timo (Journal of Geophysical Research: Atmospheres, 2021)
It is widely recognized that numerical weather prediction (NWP) results for the Antarctic are relatively poor compared to the mid-latitudes. In this study, we evaluate output from three operational NWP systems: the ECMWF, Global Forecast System (GFS) and Antarctic Mesoscale Prediction System (AMPS), for the Austral winter (June-August) of 2013 for the Weddell Sea region, paying special attention to regional patterns of error statistics. This is the first evaluation of NWP systems over the Southern Ocean that also addresses the accuracy of forecasted vertical profiles. In the evaluation, we use data from land- and ship-based automatic weather stations (AWS) and radiosoundings. While the ECMWF and AMPS forecasts are on average biased cold and dry near the surface, the GFS forecasts are on average biased warm and moist. The near-surface wind speed is on average overestimated by the AMPS forecasts, whereas it is slightly underestimated by the forecasts of the other two NWP systems. Among the variables investigated, all three NWP systems forecast the near-surface specific humidity most accurately, followed by the temperature and then the wind speed. The forecast quality for the near-surface and upper-air wind speed degrades the most rapidly with increasing lead time, compared to the other variables. ECMWF is the overall best NWP system when compared against both the near-surface and upper-air observations, followed by AMPS and then GFS. The generally poorest model performance is found in locations with complex terrain along the coast of the Antarctic continent, and the best over the ocean.
Keywords: Sørishavet; Weddellhavet; geofysikk; meteorologi

Phenology and Environmental Control of Phytoplankton Blooms in the Kong Håkon VII Hav in the Southern Ocean - Kauko, Hanna M; Hattermann, Tore; Ryan-Keogh, Thomas; Singh, Asmita; de Steur, Laura; Fransson, Agneta; Chierici, Melissa; Falkenhaug, Tone; Hallfredsson, Elvar H; Bratbak, Gunnar; Tsagaraki, Tatiana; Berge, Terje; et al. (Frontiers in Marine Science, 2021)
Knowing the magnitude and timing of pelagic primary production is important for ecosystem and carbon sequestration studies, in addition to providing basic understanding of phytoplankton functioning. In this study we use data from an ecosystem cruise to Kong Håkon VII Hav, in the Atlantic sector of the Southern Ocean, in March 2019 and more than two decades of satellite-derived ocean color to study phytoplankton bloom phenology. During the cruise we observed phytoplankton blooms in different bloom phases. By correlating bloom phenology indices (i.e., bloom initiation and end) based on satellite remote sensing to the timing of changes in environmental conditions (i.e., sea ice, light, and mixed layer depth) we studied the environmental factors that seemingly drive phytoplankton blooms in the area. Our results show that blooms mainly take place in January and February, consistent with previous studies that include the area. Sea ice retreat controls the bloom initiation in particular along the coast and the western part of the study area, whereas bloom end is not primarily connected to sea ice advance. Light availability in general is not appearing to control the bloom termination, neither is nutrient availability based on the autumn cruise where we observed non-depleted macronutrient reservoirs in the surface. Instead, we surmise that zooplankton grazing plays a potentially large role to end the bloom, and thus controls its duration. The spatial correlation of the highest bloom magnitude with marked topographic features indicate that the interaction of ocean currents with sea floor topography enhances primary productivity in this area, probably by natural fertilization. Based on the bloom timing and magnitude patterns, we identified five different bloom regimes in the area. A more detailed understanding of the region will help to highlight areas with the highest relevance for the carbon cycle, the marine ecosystem and spatial management. With this gained understanding of bloom phenology, it will also be possible to study potential shifts in bloom timing and associated trophic mismatch caused by environmental changes.
Keywords: Sørishavet; fytoplankton; havis; marin biologi; marine økosystemer; miljøendringer; planteplankton; sjøis

Antarctic krill (Euphausia superba) exhibit positive phototaxis to white LED light - Krafft, Bjørn A; Krag, Ludvig A (Polar Biology, 2021)
Keywords: Sørishavet; fototaxis; krill; marin biologi; plankton

Standing stock of Antarctic krill (Euphausia superba Dana, 1850) (Euphausiacea) in the Southwest Atlantic sector of the Southern Ocean, 2018–19 - Krafft, Bjørn A; Macaulay, Gavin J; Skaret, Georg; Knutsen, Tor; Bergstad, Odd A; Lowther, Andrew; Huse, Geir; Fielding, Sophie; Trathan, Philip; Murphy, Eugene; Choi, Seok-Gwan; Chung, Sangdeok; et al. (Journal of Crustacean Biology, 2021)
Estimates of the distribution and density of Antarctic krill (Euphausia superba Dana, 1850) were derived from a large-scale survey conducted during the austral summer in the Southwest Atlantic sector of the Southern Ocean and across the Scotia Sea in 2018–19, the ‘2018–19 Area 48 Survey’. Survey vessels were provided by Norway, the Association of Responsible Krill harvesting companies and Aker BioMarine AS, the United Kingdom, Ukraine, Republic of Korea, and China. Survey design followed the transects of the Commission for the Conservation of Antarctic Marine Living Resources synoptic survey, carried out in 2000 and from regular national surveys performed in the South Atlantic sector by the U.S., China, Republic of Korea, Norway, and the U.K. The 2018–19 Area 48 Survey represents only the second large-scale survey performed in the area and this joint effort resulted in the largest ever total transect line (19,500 km) coverage carried out as one single exercise in the Southern Ocean. We delineated and integrated acoustic backscatter arising from krill swarms to produce distribution maps of krill areal biomass density and standing stock (biomass) estimates. Krill standing stock for the Area 48 was estimated to be 62.6 megatonnes (mean density of 30 g m–2 over 2 million km2) with a sampling coefficient variation of 13%. The highest mean krill densities were found in the South Orkney Islands stratum (93.2 g m–2) and the lowest in the South Georgia Island stratum (6.4 g m–2). The krill densities across the strata compared to those found during the previous survey indicate some regional differences in distribution and biomass. It is currently not possible to assign any such differences or lack of differences between the two survey datasets to longer term trends in the environment, krill stocks or fishing pressure.
Keywords: Sørishavet; krill; marin biologi; marine økosystemer; plankton

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Antarctic krill Euphausia superba: spatial distribution, abundance, and management of fisheries in a changing climate - McBride, Margaret M; Schram Stokke, Olav; Renner, Angelika H H; Krafft, Bjørn A; Bergstad, Odd A; Biuw, Martin; Lowther, Andrew D; Stiansen, Jan E (Marine Ecology Progress Series, 2021)
Antarctic krill Euphausia superba, a keystone species in the Southern Ocean, is highly relevant for studying effects of climate-related shifts on management systems. Krill provides a key link between primary producers and higher trophic levels and supports the largest regional fishery. Any major perturbation in the krill population would have severe ecological and economic ramifications. We review the literature to determine how climate change, in concert with other environmental changes, alters krill habitat, affects spatial distribution/abundance, and impacts fisheries management. Findings recently reported on the effects of climate change on krill distribution and abundance are inconsistent, however, raising questions regarding methods used to detect changes in density and biomass. One recent study reported a sharp decline in krill densities near their northern limit, accompanied by a poleward contraction in distribution in the Southwest Atlantic sector. Another recent study found no evidence of long-term decline in krill density or biomass and reported no evidence of a poleward shift in distribution. Moreover, with predicted decreases in phytoplankton production, vertical foraging migrations to the seabed may become more frequent, also impacting krill production and harvesting. Potentially cumulative impacts of climate change further compound the management challenge faced by CCAMLR, the organization responsible for conservation of Antarctic marine living resources: to detect changes in the abundance, distribution, and reproductive performance of krill and krill-dependent predator stocks and to respond to such change by adjusting its conservation measures. Based on CCAMLR reports and documents, we review the institutional framework, outline how climate change has been addressed within this organization, and examine the prospects for further advances toward ecosystem risk assessment and an adaptive management system.
Keywords: Sørishavet; fiskeri; klimaendringer; marin biologi; zooplankton; økosystemer

Southern Ocean Food Web Modelling: Progress, Prognoses, and Future Priorities for Research and Policy Makers - McCormack, Stacey A; Melbourne-Thomas, Jessica; Trebilco, Rowan; Griffith, Gary; Hill, Simeon L; Hoover, Carie; Johnston, Nadine M; Marina, Tomás I; Murphy, Eugene J; Pakhomov, Evgeny A; Pinkerton, Matt; Plagányi, Éva; et al. (Frontiers in Ecology and Evolution, 2021)
Globally important services are supported by Southern Ocean ecosystems, underpinned by the structure, function, and dynamics of complex interconnected and regionally distinctive food webs. These food webs vary in response to a combination of physical and chemical processes that alter productivity, species composition and the relative abundance and dynamics of organisms. Combined with regional and seasonal variability, climate-induced changes and human activities have and are expected to continue to drive important structural and functional changes to Southern Ocean food webs. However, our current understanding of food web structure, function, status, and trends is patchy in space and time, and methods for systematically assessing and comparing community-level responses to change within and across regional and temporal scales are not well developed. Insights gained from food web modelling studies—ranging from theoretical analyses of ecosystem resilience and adaptation, to qualitative and quantitative descriptions of the system—can assist in resolving patterns of energy flow and the ecological mechanisms that drive food web structure, function, and responses to drivers (such as fishing and climate change). This understanding is required to inform robust management strategies to conserve Southern Ocean food webs and the ecosystem services they underpin in the face of change. This paper synthesises the current state of knowledge regarding Southern Ocean pelagic food webs, highlighting the distinct regional food web characteristics, including key drivers of energy flow, dominant species, and network properties that may indicate system resilience. In particular, the insights, gaps, and potential integration of existing knowledge and Southern Ocean food web models are evaluated as a basis for developing integrated food web assessments that can be used to test the efficacy of alternative management and policy options. We discuss key limitations of existing models for assessing change resulting from various drivers, summarise priorities for model development and identify that significant progress could be made to support policy by advancing the development of food web models coupled to projected biogeochemical models, such as in Earth System models.
Keywords: Sørishavet; marin biologi; marine økosystemer

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Variability of Sea-Air Carbon Dioxide Flux in Autumn Across the Weddell Gyre and Offshore Dronning Maud Land in the Southern Ocean - Ogundare, Margaret Ojone; Fransson, Agneta; Chierici, Melissa; Joubert, Warren R.; Roychoudhury, Alakendra N. (Frontiers in Marine Science, 2021)
Sea surface fugacity of carbon dioxide (fCO2ssw) was measured across the Weddell gyre and the eastern sector in the Atlantic Southern Ocean in autumn. During the occupation between February and April 2019, the region of the study transect was a potential ocean CO2 sink. A net CO2 flux (FCO2) of −6.2 (± 8; sink) mmol m–2 d–1 was estimated for the entire study region, with the largest average CO2 sink of −10.0 (± 8) mmol m–2 d–1 in the partly ice-covered Astrid Ridge (AR) region near the coast at 68°S and −6.1 (± 8) mmol m–2d–1 was observed in the Maud Rise (MR) region. A CO2 sink was also observed south of 66°S in the Weddell Sea (WS). To assess the main drivers describing the variability of fCO2ssw, a correlation model using fCO2 and oxygen saturation was considered. Spatial distributions of the fCO2 saturation/O2 saturation correlations, described relative to the surface water properties of the controlling variables (chlorophyll a, apparent oxygen utilization (AOU), sea surface temperature, and sea surface salinity) further constrained the interplay of the processes driving the fCO2ssw distributions. Photosynthetic CO2 drawdown significantly offsets the influence of the upwelling of CO2-rich waters in the central Weddell gyre and enhanced the CO2 sink in the region. FCO2 of −6.9 mmol m–2 d–1 estimated for the Weddell gyre in this study was different from FCO2 of −2.5 mmol m–2 d–1 in autumn estimated in a previous study. Due to low CO2 data coverage during autumn, limited sea-air CO2 flux estimates from direct sea-surface CO2 observations particularly for the Weddell gyre region are available with which to compare the values estimated in this study. This highlights the importance of increasing seasonal CO2 observations especially during autumn/winter to improving the seasonal coverage of flux estimates in the seasonal sea ice-covered regions of the Southern Ocean.
Keywords: Sørishavet; karbondioksid; kjemi

Evidence for the Impact of Climate Change on Primary Producers in the Southern Ocean - Pinkerton, Matthew H; Boyd, Philip W; Deppeler, Stacy; Hayward, Alex; Höfer, Juan; Moreau, Sebastien (Frontiers in Ecology and Evolution, 2021)
Within the framework of the Marine Ecosystem Assessment for the Southern Ocean (MEASO), this paper brings together analyses of recent trends in phytoplankton biomass, primary production and irradiance at the base of the mixed layer in the Southern Ocean and summarises future projections. Satellite observations suggest that phytoplankton biomass in the mixed-layer has increased over the last 20 years in most (but not all) parts of the Southern Ocean, whereas primary production at the base of the mixed-layer has likely decreased over the same period. Different satellite models of primary production (Vertically Generalised versus Carbon Based Production Models) give different patterns and directions of recent change in net primary production (NPP). At present, the satellite record is not long enough to distinguish between trends and climate-related cycles in primary production. Over the next 100 years, Earth system models project increasing NPP in the water column in the MEASO northern and Antarctic zones but decreases in the Subantarctic zone. Low confidence in these projections arises from: (1) the difficulty in mapping supply mechanisms for key nutrients (silicate, iron); and (2) understanding the effects of multiple stressors (including irradiance, nutrients, temperature, pCO_2, pH, grazing) on different species of Antarctic phytoplankton. Notwithstanding these uncertainties, there are likely to be changes to the seasonal patterns of production and the microbial community present over the next 50–100 years and these changes will have ecological consequences across Southern Ocean food-webs, especially on key species such as Antarctic krill and silverfish.
Keywords: Sørishavet; biogeokjemi; fytoplankton; klimaendringer; marine økosystemer; phytoplankton

Internal Ocean Dynamics Control the Long-Term Evolution of Weddell Sea Polynya Activity - Rheinlænder, Jonathan W.; Smedsrud, Lars H.; Nisanciouglu, Kerim H. (Frontiers in Climate, 2021)
Open-ocean polynyas effectively couple the ocean and atmosphere through large ice-free areas within the sea-ice cover, release vast quantities of oceanic heat, and impact deep ocean ventilation. Changes in polynya activity, particularly in the Weddell Sea, may be key to longer time-scale climate fluctuations, feedbacks and abrupt change. While changes in the occurrence of Weddell Sea polynyas are generally attributed to changes in the atmospheric surface forcing, the role of internal ocean dynamics for polynya variability is not well-resolved. In this study we employ a global coupled ocean-sea ice model with a repeating annual atmospheric cycle to explore changes in Weddell Sea water mass properties, stratification and ocean circulation driven by open-ocean polynyas. During the 1300-year long simulation, two large polynyas occur in the central Weddell Sea. Our results suggest that Weddell polynyas may be triggered without inter-annual changes in the atmospheric forcing. This highlights the role of ocean processes in preconditioning and triggering open-ocean polynyas on multi-centennial time-scales. The simulated polynyas form due to internal ocean-sea ice dynamics associated with a slow build-up and subsequent release of subsurface heat. A strong stratification and weak vertical mixing is necessary for building the subsurface heat reservoir. Once the water column turns unstable, enhanced vertical mixing of warm and saline waters into the surface layer causes efficient sea ice melt and the polynya appears. Subsequent, vigorous deep convection is maintained through upwelling of warm deep water leading to enhanced bottom water formation. We find a cessation of simulated deep convection and polynya activity due to long-term cooling and freshening of the subsurface heat reservoir. As subsurface waters in the Southern Ocean are now becoming warmer and saltier, we speculate that larger and more persistent Weddell polynyas could become more frequent in the future.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; polynja; sjøis

Icebreaking polar class research vessels: New Antarctic fleet capabilities - Rogan-Finnemore, Michelle; Ojeda, Miguel; Paz Acosta, Jorge Manuel; Bretel, Patrice; Browne, Nick; Flått, Stig; Shuoren, Wang; Sliester, Randolph (Polar Record, 2021)
Supporting Antarctic scientific investigation is the job of the national Antarctic programmes, the government entities charged with delivering their countries’ Antarctic research strategies. This requires sustained investment in people, innovative technologies, Antarctic infrastructures, and vessels with icebreaking capabilities. The recent endorsement of the International Maritime Organization (IMO) Polar Code (2015) means that countries must address challenges related to an ageing icebreaking vessel fleet. Many countries have recently invested in and begun, or completed, builds on new icebreaking Polar research vessels. These vessels incorporate innovative technologies to increase fuel efficiency, to reduce noise output, and to address ways to protect the Antarctic environment in their design. This paper is a result of a Council of Managers of National Antarctic Programs (COMNAP) project on new vessel builds which began in 2018. It considers the recent vessel builds of Australia’s RSV Nuyina, China’s MV Xue Long 2, France’s L’Astrolabe, Norway’s RV Kronprins Haakon, Peru’s BAP Carrasco, and the United Kingdom’s RRS Sir David Attenborough. The paper provides examples of purposeful consideration of science support requirements and environmental sustainability in vessel designs and operations.
Publisher: Cambridge University Press
Keywords: Sørishavet; skipsfart; teknologi

Antarctic icebergs reorganize ocean circulation during Pleistocene glacials - Starr, Aidan; Hall, Ian R.; Barker, Stephen; Rackow, Thomas; Zhang, Xu; Hemming, Sidney R.; van der Lubbe, H. J. L.; Knorr, Gregor; Berke, Melissa A.; Bigg, Grant R.; Cartagena-Sierra, Alejandra; Jiménez-Espejo, Francisco J.; et al. (Nature, 2021)
The dominant feature of large-scale mass transfer in the modern ocean is the Atlantic meridional overturning circulation (AMOC). The geometry and vigour of this circulation influences global climate on various timescales. Palaeoceanographic evidence suggests that during glacial periods of the past 1.5 million years the AMOC had markedly different features from today1; in the Atlantic basin, deep waters of Southern Ocean origin increased in volume while above them the core of the North Atlantic Deep Water (NADW) shoaled2. An absence of evidence on the origin of this phenomenon means that the sequence of events leading to global glacial conditions remains unclear. Here we present multi-proxy evidence showing that northward shifts in Antarctic iceberg melt in the Indian–Atlantic Southern Ocean (0–50° E) systematically preceded deep-water mass reorganizations by one to two thousand years during Pleistocene-era glaciations. With the aid of iceberg-trajectory model experiments, we demonstrate that such a shift in iceberg trajectories during glacial periods can result in a considerable redistribution of freshwater in the Southern Ocean. We suggest that this, in concert with increased sea-ice cover, enabled positive buoyancy anomalies to ‘escape’ into the upper limb of the AMOC, providing a teleconnection between surface Southern Ocean conditions and the formation of NADW. The magnitude and pacing of this mechanism evolved substantially across the mid-Pleistocene transition, and the coeval increase in magnitude of the ‘southern escape’ and deep circulation perturbations implicate this mechanism as a key feedback in the transition to the ‘100-kyr world’, in which glacial–interglacial cycles occur at roughly 100,000-year periods.
Keywords: Sørishavet; havstrømmer; isfjell; paleoklimatologi; paleoseanografi

Climate change impacts on sea-ice ecosystems and associated ecosystem services - Steiner, Nadja S; Bowman, Jeff; Campbell, Karley; Chierici, Melissa; Eronen-Rasimus, Eeva; Falardeau, Marianne; Flores, Hauke; Fransson, Agneta; Herr, Helena; Insley, Stephen J; Kauko, Hanna M; Lannuzel, Delphine; et al. (Elementa: Science of the Anthropocene, 2021)
A rigorous synthesis of the sea-ice ecosystem and linked ecosystem services highlights that the sea-ice ecosystem supports all 4 ecosystem service categories, that sea-ice ecosystems meet the criteria for ecologically or biologically significant marine areas, that global emissions driving climate change are directly linked to the demise of sea-ice ecosystems and its ecosystem services, and that the sea-ice ecosystem deserves specific attention in the evaluation of marine protected area planning. The synthesis outlines (1) supporting services, provided in form of habitat, including feeding grounds and nurseries for microbes, meiofauna, fish, birds and mammals (particularly the key species Arctic cod, Boreogadus saida, and Antarctic krill, Euphausia superba, which are tightly linked to the sea-ice ecosystem and transfer carbon from sea-ice primary producers to higher trophic level fish, mammal species and humans); (2) provisioning services through harvesting and medicinal and genetic resources; (3) cultural services through Indigenous and local knowledge systems, cultural identity and spirituality, and via cultural activities, tourism and research; (4) (climate) regulating services through light regulation, the production of biogenic aerosols, halogen oxidation and the release or uptake of greenhouse gases, for example, carbon dioxide. The ongoing changes in the polar regions have strong impacts on sea-ice ecosystems and associated ecosystem services. While the response of sea-ice–associated primary production to environmental change is regionally variable, the effect on ice-associated mammals and birds is predominantly negative, subsequently impacting human harvesting and cultural services in both polar regions. Conservation can help protect some species and functions. However, the key mitigation measure that can slow the transition to a strictly seasonal ice cover in the Arctic Ocean, reduce the overall loss of sea-ice habitats from the ocean, and thus preserve the unique ecosystem services provided by sea ice and their contributions to human well-being is a reduction in carbon emissions.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer

An ocean of possibilities: antarctic petrel's foraging in the Southern Ocean - Tarroux, Arnaud; Fauchald, Per; Varpe, Øystein; Yoccoz, Nigel G; Descamps, Sébastien (Fram forum, 2021)
Keywords: Sørishavet; fôring; marin biologi; observasjoner; ornitologi; petreller; sjøfugler; zoologi

Remote assessment of the fate of phytoplankton in the Southern Ocean sea-ice zone - Moreau, Sébastien; Boyd, Philip W.; Strutton, Peter G. (Nature Communications, 2020)
In the Southern Ocean, large-scale phytoplankton blooms occur in open water and the sea-ice zone (SIZ). These blooms have a range of fates including physical advection, downward carbon export, or grazing. Here, we determine the magnitude, timing and spatial trends of the biogeochemical (export) and ecological (foodwebs) fates of phytoplankton, based on seven BGC-Argo floats spanning three years across the SIZ. We calculate loss terms using the production of chlorophyll—based on nitrate depletion—compared with measured chlorophyll. Export losses are estimated using conspicuous chlorophyll pulses at depth. By subtracting export losses, we calculate grazing-mediated losses. Herbivory accounts for ~90% of the annually-averaged losses (169 mg C m−2 d−1), and phytodetritus POC export comprises ~10%. Furthermore, export and grazing losses each exhibit distinctive seasonality captured by all floats spanning 60°S to 69°S. These similar trends reveal widespread patterns in phytoplankton fate throughout the Southern Ocean SIZ.
Keywords: Sørishavet; marin biologi; plankton; økologi

Meridional Ocean Carbon Transport - Aldama-Campino, Aitor; Fransner, Filippa; Ödalen, Malin; Groeskamp, Sjoerd; Yool, Andrew; Döös, Kristofer; Nycander, Jonas (Global Biogeochemical Cycles, 2020)
The ocean's ability to take up and store CO2 is a key factor for understanding past and future climate variability. However, qualitative and quantitative understanding of surface-to-interior pathways, and how the ocean circulation affects the CO2 uptake, is limited. Consequently, how changes in ocean circulation may influence carbon uptake and storage and therefore the future climate remains ambiguous. Here we quantify the roles played by ocean circulation and various water masses in the meridional redistribution of carbon. We do so by calculating streamfunctions defined in dissolved inorganic carbon (DIC) and latitude coordinates, using output from a coupled biogeochemical-physical model. By further separating DIC into components originating from the solubility pump and a residual including the biological pump, air-sea disequilibrium, and anthropogenic CO2, we are able to distinguish the dominant pathways of how carbon enters particular water masses. With this new tool, we show that the largest meridional carbon transport occurs in a pole-to-equator transport in the subtropical gyres in the upper ocean. We are able to show that this pole-to-equator DIC transport and the Atlantic meridional overturning circulation (AMOC)-related DIC transport are mainly driven by the solubility pump. By contrast, the DIC transport associated with deep circulation, including that in Antarctic bottom water and Pacific deep water, is mostly driven by the biological pump. As these two pumps, as well as ocean circulation, are widely expected to be impacted by anthropogenic changes, these findings have implications for the future role of the ocean as a climate-buffering carbon reservoir.
Keywords: Sørishavet; biogeokjemi; bunnvann; karbon syklus; karbondioksid; klimatologi; oseanografi; vannmasser

Global biogeography of marine amphipod crustaceans: latitude, regionalization, and beta diversity - Arfianti, Tri; Costello, Mark J (Marine Ecology Progress Series, 2020)
Studying the biogeography of amphipod crustaceans is of interest because they play an important role at lower trophic levels in ecosystems. Because they lack a planktonic larval stage, it has been hypothesized that marine benthic amphipod crustaceans may have short dispersal distances, high endemicity, and spatial turnover in species composition, and consequently high global species richness. In this study, we examined over 400000 distribution records of 4876 amphipod species, and identified 12 regions of endemicity. The number and percent of endemic species peaked at 30°-35°S and coincided with 3 of these regions of high endemicity: Australia, New Zealand, and southern Africa. Pelagic species of marine amphipod crustaceans were more cosmopolitan than benthic species. The latitudinal patterns of richness (alpha, gamma, and ES50) and species turnover were at least bimodal. Most occurrence records and greater alpha and gamma richness were in mid-latitudes, reflecting sampling bias. Both ES50 and beta diversity had similar richness in the tropics, mid-latitudes, and on the Antarctic shelf around 70°S. These 2 indices exhibited a sharp dip in the deep Southern Ocean at 55°S. ES50 peaked at 30°-35°S and a small dip was apparent near the equator at 5°-10°N. Beta diversity was driven mostly by turnover rather than nestedness. These findings support the need for conservation in each realm of species endemicity and for amphipods, particularly in Antarctica and the coastal mid-latitudes (30°-35°S) of the Southern Hemisphere. KEYWORDS: Endemicity · Latitudinal gradients · Conservation · Species richness · Species turnover
Keywords: Sørishavet; biogeografi; crustacea; krepsdyr; marin biologi; marine økosystemer; zoogeografi

CO2 Increase Experiments Using the CESM: Relationship to Climate Sensitivity and Comparison of CESM1 to CESM2 - Bacmeister, Julio; Hannay, Cecile; Medeiros, Brian; Gettelman, Andrew; Neale, Richard; Fredriksen, Hege-Beate; Lipscomb, William H; Simpson, Isla; Bailey, David; Holland, Marika; Lindsay, Keith; Otto-Bliesner, Bette (Journal of Advances in Modeling Earth Systems, 2020)
We examine the response of the Community Earth System Model Versions 1 and 2 (CESM1 and CESM2) to abrupt quadrupling of atmospheric CO2 concentrations (4xCO2) and to 1% annually increasing CO2 concentrations (1%CO2). Different estimates of equilibrium climate sensitivity (ECS) for CESM1 and CESM2 are presented. All estimates show that the sensitivity of CESM2 has increased by 1.5 K or more over that of CESM1. At the same time the transient climate response (TCR) of CESM1 and CESM2 derived from 1%CO2 experiments has not changed significantly—2.1 K in CESM1 and 2.0 K in CESM2. Increased initial forcing as well as stronger shortwave radiation feedbacks are responsible for the increase in ECS seen in CESM2. A decomposition of regional radiation feedbacks and their contribution to global feedbacks shows that the Southern Ocean plays a key role in the overall behavior of 4xCO2 experiments, accounting for about 50% of the total shortwave feedback in both CESM1 and CESM2. The Southern Ocean is also responsible for around half of the increase in shortwave feedback between CESM1 and CESM2, with a comparable contribution arising over tropical ocean. Experiments using a thermodynamic slab-ocean model (SOM) yield estimates of ECS that are in remarkable agreement with those from fully coupled Earth system model (ESM) experiments for the same level of CO2 increase. Finally, we show that the similarity of TCR in CESM1 and CESM2 masks significant regional differences in warming that occur in the 1%CO2 experiments for each model.
Keywords: Sørishavet; atmosfæren; fysikk; karbondioksid; klimaendringer; klimagasser; klimamodeller; klimatologi; menneskelig påvirkning; meteorologi; skyer

Signature of Ocean Warming at the Mixed Layer Base - Clément, Louis; McDonagh, Elaine L; Marzocchi, Alice; Nurser, A J George (Geophysical Research Letters, 2020)
The warming climate influences the ocean by changing its wind-driven dynamics and by inputting extra heat. This study analyzes the warming where temperature anomalies penetrate the ocean interior, that is, by focusing on the winter mixed layer base. This allows to distinguish regions where ocean circulation contributes to warm anomalies from locations where density-compensated temperature anomalies locally enter the ocean along isopycnals. Multidecadal (1980–2018) local temperature trends from a hydrographic data set are examined at the winter mixed layer base and partitioned into components relating to isopycnal movement (heave) and change along isopycnals (spice). Subtropical gyres and western boundary currents show warming larger than the global average that mostly projects onto heave. This is the result of the strengthening of the circulation in the Southern Hemisphere subtropical gyres and is related to both wind-driven changes and Southern Ocean warming. Subtropical regions of surface salinity maxima are influenced by warm anomalies along isopycnals.
Keywords: Sørishavet; havet; havstrømmer; klimaendringer; oppvarming; oseanografi

Necessary Conditions for Warm Inflow Toward the Filchner Ice Shelf, Weddell Sea - Daae, Kjersti; Hattermann, Tore; Darelius, Elin Maria K; Mueller, Rachael D; Naughten, Kaitlin A; Timmermann, Ralph; Hellmer, Hartmut H (Geophysical Research Letters, 2020)
Understanding changes in Antarctic ice shelf basal melting is a major challenge for predicting future sea level. Currently, warm Circumpolar Deep Water surrounding Antarctica has limited access to the Weddell Sea continental shelf; consequently, melt rates at Filchner-Ronne Ice Shelf are low. However, large-scale model projections suggest that changes to the Antarctic Slope Front and the coastal circulation may enhance warm inflows within this century. We use a regional high-resolution ice shelf cavity and ocean circulation model to explore forcing changes that may trigger this regime shift. Our results suggest two necessary conditions for supporting a sustained warm inflow into the Filchner Ice Shelf cavity: (i) an extreme relaxation of the Antarctic Slope Front density gradient and (ii) substantial freshening of the dense shelf water. We also find that the on-shelf transport over the western Weddell Sea shelf is sensitive to the Filchner Trough overflow characteristics.
Keywords: Sørishavet; Weddellhavet; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Från kallt till varmt - norsk oceanografisk forskning i Weddelhavet, Antarktis - Darelius, Elin Maria K; Foldvik, Arne (Det norske videnskaps-akademi, 2020)
Keywords: Sørishavet; Weddellhavet; oseanografi

Antarctic petrels ‘on the ice rocks’: wintering strategy of an Antarctic seabird - Delord, Karine; Kato, Akiko; Tarroux, Arnaud; Orgeret, Florian; Cotté, Cedric; Ropert-Coudert, Yan; Cherel, Yves; Descamps, Sébastien (Royal Society Open Science, 2020)
There is a paucity of information on the foraging ecology, especially individual use of sea-ice features and icebergs, over the non-breeding season in many seabird species. Using geolocators and stable isotopes, we defined the movements, distribution and diet of adult Antarctic petrels Thalassoica antarctica from the largest known breeding colony, the inland Svarthamaren, Antarctica. More specifically, we examined how sea-ice concentration and free-drifting icebergs affect the distribution of Antarctic petrels. After breeding, birds moved north to the marginal ice zone (MIZ) in the Weddell sector of the Southern Ocean, following its northward extension during freeze-up in April, and they wintered there in April–August. There, the birds stayed predominantly out of the water (60–80% of the time) suggesting they use icebergs as platforms to stand on and/or to rest. Feather δ15N values encompassed one full trophic level, indicating that birds fed on various proportions of crustaceans and fish/squid, most likely Antarctic krill Euphausia superba and the myctophid fish Electrona antarctica and/or the squid Psychroteuthis glacialis. Birds showed strong affinity for the open waters of the northern boundary of the MIZ, an important iceberg transit area, which offers roosting opportunities and rich prey fields. The strong association of Antarctic petrels with sea-ice cycle and icebergs suggests the species can serve, year-round, as a sentinel of environmental changes for this remote region.
Keywords: Sørishavet; Weddellhavet; biologi; geolokalisering; havis; isberg; isfjell; klimaendringer; miljøendringer; ornitologi; petreller; sjøfugler; sjøis; økologi

Atmospheric and Oceanographic Signatures in the Ice Shelf Channel Morphology of Roi Baudouin Ice Shelf, East Antarctica, Inferred From Radar Data - Drews, Reinhard; Schannwell, Clemens; Ehlers, Todd A; Gladstone, Rupert; Pattyn, Frank; Matsuoka, Kenichi (Journal of Geophysical Research: Earth Surface, 2020)
Ice shelves around Antarctica can provide back stress for outlet glaciers and control ice sheet mass loss. They often contain narrow bands of thin ice termed ice shelf channels. Ice shelf channel morphology can be interpreted through surface depressions and exhibits junctions and deflections from flowlines. Using ice flow modeling and radar, we investigate ice shelf channels in the Roi Baudouin Ice Shelf. These are aligned obliquely to the prevailing easterly winds. In the shallow radar stratigraphy, syncline and anticline stacks occur beneath the upwind and downwind side, respectively. The structures are horizontally and vertically coherent, except near an ice shelf channel junction where patterns change structurally with depth. Deeper layers truncate near basal incisions. Using ice flow modeling, we show that the stratigraphy is ∼9 times more sensitive to atmospheric variability than to oceanic variability. This is due to the continual adjustment toward flotation. We propose that syncline-anticline pairs in the shallow stratigraphy are caused by preferential snow deposition on the windward side and wind erosion at the downwind side. This drives downwind deflection of ice shelf channels of several meters per year. The depth variable structures indicate formation of an ice shelf channel junction by basal melting. We conclude that many ice shelf channels are seeded at the grounding line. Their morphology farther seaward is shaped on different length scales by ice dynamics, the ocean, and the atmosphere. These processes act on finer (subkilometer) scales than are captured by most ice, atmosphere, and ocean models, yet the dynamics of ice shelf channels may have broader implications for ice shelf stability.
Keywords: Sørishavet; brehylle; geofysikk; glasiologi; innlandsis; isbrem; isshelf

Nutrient Distribution in East Antarctic Summer Sea Ice: A Potential Iron Contribution From Glacial Basal Melt - Duprat, Luis; Corkill, Matthew; Genovese, Cristina; Townsend, Ashley T; Moreau, Sébastien; Meiners, Klaus M; Lannuzel, Delphine (Journal of Geophysical Research: Oceans, 2020)
Antarctic sea ice can incorporate high levels of iron (Fe) during its formation and has been suggested as an important source of this essential micronutrient to Southern Ocean surface waters during the melt season. Over the last decade, a limited number of studies have quantified the Fe pool in Antarctic sea ice, with a focus on late winter and spring. Here we study the distribution of operationally defined dissolved and particulate Fe from nine sites sampled between Wilkes Land and King George V Land during austral summer 2016/2017. Results point toward a net heterotrophic sea-ice community, consistent with the observed nitrate limitation (<1 μM). We postulate that the recycling of the high particulate Fe pool in summer sea ice supplies sufficient (∼3 nM) levels of dissolved Fe to sustain ice algal growth. The remineralization of particulate Fe is likely favored by high concentrations of exopolysaccharides (113–16,290 μg xeq L−1) which can serve as a hotspot for bacterial activity. Finally, results indicate a potential relationship between glacial meltwater discharged from the Moscow University Ice Shelf and the occurrence of Fe-rich (∼4.3 μM) platelet ice in its vicinity. As climate change is expected to result in enhanced Fe-rich glacial discharge and changes in summer sea-ice extent and quality, the processes influencing Fe distribution in sea ice that persists into summer need to be better constrained.
Keywords: Sørishavet; alger; fytoplankton; havis; klimaendringer; marin biologi; oseanografi; sjøis

Characteristics of ice rises and ice rumples in Dronning Maud Land and Enderby Land, Antarctica - Goel, Vikram; Matsuoka, Kenichi; Berger, Cesar Deschamps; Lee, Ian; Dall, Jørgen; Forsberg, René (Journal of Glaciology, 2020)
Ice rises and rumples, locally grounded features adjacent to ice shelves, are relatively small yet play significant roles in Antarctic ice dynamics. Their roles generally depend upon their location within the ice shelf and the stage of the ice-sheet retreat or advance. Large, long-stable ice rises can be excellent sites for deep ice coring and paleoclimate study of the Antarctic coast and the Southern Ocean, while small ice rises tend to respond more promptly and can be used to reveal recent changes in regional mass balance. The coasts of Dronning Maud Land (DML) and Enderby Land in East Antarctica are abundant with these features. Here we review existing knowledge, presenting an up-to-date status of research in these regions with focus on ice rises and rumples. We use regional datasets (satellite imagery, surface mass balance and ice thickness) to analyze the extent and surface morphology of ice shelves and characteristic timescales of ice rises. We find that large parts of DML have been changing over the past several millennia. Based on our findings, we highlight ice rises suitable for drilling ice cores for paleoclimate studies as well as ice rises suitable for deciphering ice dynamics and evolution in the region.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; isshelf

Full-Depth Global Estimates of Ocean Mesoscale Eddy Mixing From Observations and Theory - Groeskamp, Sjoerd; LaCasce, Joseph H; McDougall, Trevor J; Rogé, Marine (Geophysical Research Letters, 2020)
Mixing by mesoscale eddies profoundly impacts climate and ecosystems by redistributing and storing dissolved tracers such as heat and carbon. Eddy mixing is parameterized in most numerical models of the ocean and climate. To reduce known sensitivity to such parameterizations, observational estimates of mixing are needed. However, logistical and technological limitations obstruct our ability to measure global time-varying mixing rates. Here, we extend mixing length theory with mean-flow suppression theory, and first surface modes, to estimate mixing from readily available observational-based climatological data, of salinity, temperature, pressure, and eddy kinetic energy at the sea surface. The resulting full-depth global maps of eddy mixing can reproduce the few available direct estimates and confirm the importance of mean-flow suppression of mixing. The results also emphasize the significant effect of eddy surface intensification and its relation to the vertical density stratification. These new insights in mixing dynamics will improve future mesoscale eddy mixing parameterizations.
Keywords: Sørishavet; geovitenskap; havet; klimatologi; polarområdene; vannvirvler; økosystemer

Supercooled Southern Ocean Waters - Haumann, F Alexander; Moorman, Ruth; Riser, Stephen C; Smedsrud, Lars H; Maksym, Ted; Wong, Annie P S; Wilson, Earle A; Drucker, Robert; Talley, Lynne D; Johnson, Kenneth S; Key, Robert M; Sarmiento, Jorge L (Geophysical Research Letters, 2020)
In cold polar waters, temperatures sometimes drop below the freezing point, a process referred to as supercooling. However, observational challenges in polar regions limit our understanding of the spatial and temporal extent of this phenomenon. We here provide observational evidence that supercooled waters are much more widespread in the seasonally ice-covered Southern Ocean than previously reported. In 5.8% of all analyzed hydrographic profiles south of 55°S, we find temperatures below the surface freezing point (“potential” supercooling), and half of these have temperatures below the local freezing point (“in situ” supercooling). Their occurrence doubles when neglecting measurement uncertainties. We attribute deep coastal-ocean supercooling to melting of Antarctic ice shelves and surface-induced supercooling in the seasonal sea-ice region to wintertime sea-ice formation. The latter supercooling type can extend down to the permanent pycnocline due to convective sinking plumes—an important mechanism for vertical tracer transport and water-mass structure in the polar ocean.
Keywords: Sørishavet; havis; hydrografi; isbrem; isshelf; oseanografi; polarområdene; sjøis; superkjøling

The Role of Tides in Ocean-Ice Shelf Interactions in the Southwestern Weddell Sea - Hausmann, Ute; Sallée, Jean-Baptiste; Jourdain, Nicolas; Mathiot, Pierre; Rousset, Clément; Madec, Gurvan; Deshayes, Julie; Hattermann, Tore (Journal of Geophysical Research: Oceans, 2020)
To investigate the role of tides in Weddell Sea ocean-ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean-sea ice model configuration, with time-varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner-Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time-varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold-cavity regime. The resulting systematic tide-driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr−1). In addition, tides also increase the melt-induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open-ocean southwestern continental shelf, characterized by overall freshening and small year-round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; havis; isbrem; isshelf; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis; tidevann

Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A; Reisinger, Ryan R; Ropert-Coudert, Yan; Hückstädt, Luis A; Trathan, Philip N; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L; Costa, Daniel P; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature, 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change1,2. Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer; miljøvern; overvåking

High-resolution distributed vertical strain and velocity from repeat borehole logging by optical televiewer: Derwael Ice Rise, Antarctica - Hubbard, Bryn; Philippe, Morgane; Pattyn, Frank; Drews, Reinhard; Young, Tun Jan; Bruyninx, Carine; Bergeot, Nicolas; Fjøsne, Karen; Tison, Jean-Louis (Journal of Glaciology, 2020)
Direct measurements of spatially distributed vertical strain within ice masses are scientifically valuable but challenging to acquire. We use manual marker tracking and automatic cross correlation between two repeat optical televiewer (OPTV) images of an ~100 m-long borehole at Derwael Ice Rise (DIR), Antarctica, to reconstruct discretised, vertical strain rate and velocity at millimetre resolution. The resulting profiles decay with depth, from −0.07 a−1 at the surface to ~−0.002 a−1 towards the base in strain and from −1.3 m a−1 at the surface to ~−0.5 m a−1 towards the base in velocity. Both profiles also show substantial local variability. Three coffee-can markers installed at different depths into adjacent boreholes record consistent strain rates and velocities, although averaged over longer depth ranges and subject to greater uncertainty. Measured strain-rate profiles generally compare closely with output from a 2-D ice-flow model, while the former additionally reveal substantial high-resolution variability. We conclude that repeat OPTV borehole logging represents an effective means of measuring distributed vertical strain at millimetre scale, revealing high-resolution variability along the uppermost ~100 m of DIR, Antarctica.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Antarctic minke whales find ice gaps along the ice edge in foraging grounds of the Indo-Pacific sector (60° E and 140° E) of the Southern Ocean - Konishi, Kenji; Isoda, Tatsuya; Bando, Takeharu; Minamikawa, Shingo; Kleivane, Lars (Polar Biology, 2020)
Keywords: Sørishavet; forskning; hvaler; krill; marin biologi; næring

Rødt gull i sør - Krafft, Bjørn (Polarboken, 2020)
Keywords: Sørishavet; fiskeri; zoologi

Coherent Seasonal Acceleration of the Weddell Sea Boundary Current System Driven by Upstream Winds - Le Paih, Nicolas; Hattermann, Tore; Boebel, Olaf; Kanzow, Torsten; Lüpkes, Christof; Rohardt, Gerd; Strass, Volker; Herbette, Steven (Journal of Geophysical Research: Oceans, 2020)
The Weddell Sea is of global importance in the formation of dense bottom waters associated with sea ice formation and ocean-ice sheet interaction occurring on the shelf areas. In this context, the Weddell Sea boundary current system (BCS) presents a major conduit for transporting relatively warm water to the Weddell Sea ice shelves and for exporting some modified form of Wedell Sea deep and bottom waters into the open ocean. This study investigates the downstream evolution of the structure and the seasonality of the BCS along the Weddell Sea continental slope, combining ocean data collected for the past two decades at three study locations. The interannual-mean geostrophic flow, which follows planetary potential vorticity contours, shifts from being surface intensified to bottom intensified along stream. The shift occurs due to the densification of water masses and the decreasing surface stress that occurs westward, toward the Antarctic Peninsula. A coherent along-slope seasonal acceleration of the barotropic flow exists, with maximum speed in austral autumn and minimum speed in austral summer. The barotropic flow significantly contributes to the seasonal variability in bottom velocity along the tip of the Antarctic Peninsula. Our analysis suggests that the winds on the eastern/northeastern side of the gyre determines the seasonal acceleration of the barotropic flow. In turn, they might control the export of Weddell Sea Bottom Water on seasonal time scales. The processes controlling the baroclinic seasonality of the flow need further investigation.
Keywords: Sørishavet; Weddellhavet; batymetri; havstrømmer; innlandsis; kontinentalmargin; oseanografi

Calving Event Led to Changes in Phytoplankton Bloom Phenology in the Mertz Polynya, Antarctica - Liniger, Guillaume; Strutton, Peter G.; Lannuzel, Delphine; Moreau, Sebastien (Journal of Geophysical Research: Oceans, 2020)
Polynyas are subject to variability in winds and ocean circulation and are important sites of ecological productivity. In February 2010, the B09B iceberg collided with the Mertz Glacier Tongue (MGT), calving a 78 × 40-km giant iceberg which modified the icescape and primary productivity of the Mertz polynya. In this study, we use satellite ocean color and sea ice concentration to investigate the variability, trends, and drivers of phytoplankton blooms in the Mertz polynya since 1997. During the bloom, over 21 years, we found (i) a later ice retreat time, (ii) an increase in sea ice concentration, (iii) a decrease in open-water period, (iv) a later bloom start, and (v) a decrease in bloom duration. Our results suggest that major postcalving changes in the physical characteristics of the polynya, mainly its icescape, are the primary drivers of phytoplankton phenology. More specifically, the MGT calving event resulted in significant seasonal and regional changes, with higher eastern chl-a and mean summer chl-a postcalving. While satellite data are useful to study long-term variability in these inhospitable areas, they only focus on the ocean surface and are obscured by ice and clouds. Additional subsurface parameters from seal tags, gliders and moorings in the southernmost polar regions would strengthen our comprehension of phytoplankton and physical changes in ocean dynamics that may have far-reaching consequences, from global circulation to carbon export.
Keywords: Sørishavet; fytoplankton; havsirkulasjon; isbre; kalving; marin biologi; marine økosystemer; oseanografi; polynja

Distribution and source of glycerol dialkyl glycerol tetraethers (GDGTs) and the applicability of GDGT-based temperature proxies in surface sediments of Prydz Bay, East Antarctica - Liu, Ruijuan; Han, Zhengbing; Zhao, Jun; Zhang, Haifeng; Li, Dong; Ren, Jianye; Pan, Jianming; Zhang, Haisheng (Polar Research, 2020)
Reliable records of Southern Ocean seawater palaeotemperatures are important because this region plays a significant role in regulating global climate change. Biomarkers such as GDGT-based indices have been effectively used to reconstruct seawater temperatures. We analysed the composition and distribution of iGDGTs, OH-GDGTs and brGDGTs and calculated GDGT-based temperature indices in surface sediments from Prydz Bay, East Antarctica. Our results showed that iGDGTs, OH-GDGTs and brGDGTs are all produced in situ, with iGDGTs and OH-GDGTs mostly synthesized by Thaumarchaeota. Concentrations of iGDGTs, OH-GDGTs and brGDGTs showed similar spatial distributions and decreased from the continental shelf towards the deep ocean. The highest concentrations were in the inner bay, which is attributed to a combination of (1) bathymetry that reduces water exchange, (2) the Prydz Bay Gyre stabilizing the upper water column and (3) sea ice that releases archaea and bacteria. Among the temperature indices based on iGDGTs, OH-GDGTs and combinations therein, those based on OH-GDGTs showed the strongest correlation with seawater temperature. Some OH-GDGT-based indices (e.g., OH-0/OHs, OH-1/OHs, OH-2/OHs and RI-OH′) exhibited a stronger correlation with annual subsurface ocean temperature (100–200 m), which may be related to archaeal habitats and production mechanisms. Our study suggests that RI-OH′ and OH-0/OHs could be used as indicators of annual subsurface ocean temperature in Antarctic marginal seas.
Keywords: Sørishavet; arkebakterier; batymetri; biomarkører; klimaendringer; oseanografi; sjøvann; temperatur; økosystemer

Pathogen surveillance in Southern Ocean pinnipeds - Núñez-Egido, Sandra; Lowther, Andrew; Nymo, Ingebjørg H.; Klein, Jörn; Breines, Eva M.; Tryland, Morten (Polar Research, 2020)
Knowledge of the health status and potential effect of disease outbreaks among Southern Ocean fauna may be decisive for its conservation. We assessed the exposure and infection of Antarctic fur seals (Arctocephalus gazella, AFS) and Southern elephant seals (Mirounga leonine, SES) to parapoxvirus, Phocid alphaherpesvirus-1 (PhHV-1), smooth Brucella spp. and Toxoplasma gondii. AFS (n = 65) serum and swab samples, and SES (n = 13) serum samples from the sub–Antarctic island of Bouvetøya (54°25’S, 03°22’E) were collected during two austral summers (2014/15, 2017/18). Three polymerase chain reaction (PCR) tests amplifying the DNA polymerase, B2L and GIF parapoxvirus genomic regions were performed, investigating DNA from mucosal swab samples. The glycoprotein B gene was targeted to detect PhHV-1 viral DNA. Sera were assayed for T. gondii and smooth Brucella spp. antibodies with indirect enzyme-linked immunosorbent assays. Parapoxvirus PCR amplicons of the expected size were generated in two of the 29 AFS pups (nasal swabs, 2014/15), targeting the B2L (n = 2) and DNA polymerase (n = 1) genes, whereas the GIF PCR did not amplify target sequences. The PCR amplicons were sequenced and blasted in GenBank, revealing highest similarity with a seal parapoxvirus, confirming the presence of the virus in AFS for the first time. No PhHV-1 amplicons were generated, and antibodies against T. gondii or smooth Brucella spp. were not detected. Our data indicate that these seals are host for parapoxvirus but are neither exposed to smooth Brucella spp. nor T. gondii. Evidence of PhHV-1 shedding was not detected.
Keywords: Bouvetøya; Sørishavet; epidemiologi; fylogenetikk; infeksjon; marin biologi; marin zoologi; pelsseler; pinnipedier; serologi; sjøelefanter; virologi

Antarctic Futures: An Assessment of Climate-Driven Changes in Ecosystem Structure, Function, and Service Provisioning in the Southern Ocean - Rogers, Alex David; Frinault, Betina A V; Barnes, D K A; Bindoff, Nathaniel Lee; Downie, Rod; Ducklow, Hugh W; Friedlaender, A S; Hart, T; Hill, Simeon; Hofmann, E E; Linse, Katrin; McMahon, Clive R; et al. (Annual Review of Marine Science, 2020)
In this article, we analyze the impacts of climate change on Antarctic marine ecosystems. Observations demonstrate large-scale changes in the physical variables and circulation of the Southern Ocean driven by warming, stratospheric ozone depletion, and a positive Southern Annular Mode. Alterations in the physical environment are driving change through all levels of Antarctic marine food webs, which differ regionally. The distributions of key species, such as Antarctic krill, are also changing. Differential responses among predators reflect differences in species ecology. The impacts of climate change on Antarctic biodiversity will likely vary for different communities and depend on species range. Coastal communities and those of sub-Antarctic islands, especially range-restricted endemic communities, will likely suffer the greatest negative consequences of climate change. Simultaneously, ecosystem services in the Southern Ocean will likely increase. Such decoupling of ecosystem services and endemic species will require consideration in the management of human activities such as fishing in Antarctic marine ecosystems.
Keywords: Sørishavet; biodiversitet; klimaendringer; marine økosystemer; miljøpåvirkning

The retrospective analysis of Antarctic tracking data project - Ropert-Coudert, Yan; Van de Putte, Anton P; Reisinger, Ryan R; Bornemann, Horst; Charrassin, Jean-Benoît; Costa, Daniel P; Danis, Bruno; Hückstädt, Luis A; Jonsen, Ian D; Lea, Mary-Anne; Thompson, David; Torres, Leigh G; et al. (Scientific Data, 2020)
The Retrospective Analysis of Antarctic Tracking Data (RAATD) is a Scientific Committee for Antarctic Research project led jointly by the Expert Groups on Birds and Marine Mammals and Antarctic Biodiversity Informatics, and endorsed by the Commission for the Conservation of Antarctic Marine Living Resources. RAATD consolidated tracking data for multiple species of Antarctic meso- and top-predators to identify Areas of Ecological Significance. These datasets and accompanying syntheses provide a greater understanding of fundamental ecosystem processes in the Southern Ocean, support modelling of predator distributions under future climate scenarios and create inputs that can be incorporated into decision making processes by management authorities. In this data paper, we present the compiled tracking data from research groups that have worked in the Antarctic since the 1990s. The data are publicly available through biodiversity.aq and the Ocean Biogeographic Information System. The archive includes tracking data from over 70 contributors across 12 national Antarctic programs, and includes data from 17 predator species, 4060 individual animals, and over 2.9 million observed locations.
Keywords: Antarktis; Sørishavet; biologi; økologi; økosystem

Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner-Ronne Ice Shelf in 2017 - Ryan, Svenja; Hellmer, Hartmut H; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael (Geophysical Research Letters, 2020)
The Filchner-Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open-ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline.
Keywords: Sørishavet; Weddellhavet; batymetri; brehylle; geofysikk; havis; isbrem; kontinentalsokkel; oseanografi; sjøis; smelting

Modeling of the Influence of Sea Ice Cycle and Langmuir Circulation on the Upper Ocean Mixed Layer Depth and Freshwater Distribution at the West Antarctic Peninsula - Schultz, Cristina; Doney, Scott C.; Zhang, Weifeng Gordon; Regan, Heather; Holland, Paul R.; Meredith, Michael P.; Stammerjohn, Sharon (Journal of Geophysical Research: Oceans, 2020)
The Southern Ocean is chronically undersampled due to its remoteness, harsh environment, and sea ice cover. Ocean circulation models yield significant insight into key processes and to some extent obviate the dearth of data; however, they often underestimate surface mixed layer depth (MLD), with consequences for surface water-column temperature, salinity, and nutrient concentration. In this study, a coupled circulation and sea ice model was implemented for the region adjacent to the West Antarctic Peninsula, a climatically sensitive region which has exhibited decadal trends towards higher ocean temperature, shorter sea ice season, and increasing glacial freshwater input, overlain by strong interannual variability. Hindcast simulations were conducted with different air-ice drag coefficients and Langmuir circulation parameterizations to determine the impact of these factors on MLD. Including Langmuir circulation deepened the surface mixed layer, with the deepening being more pronounced in the shelf and slope regions. Optimal selection of an air-ice drag coefficient also increased modeled MLD by similar amounts and had a larger impact in improving the reliability of the simulated MLD interannual variability. This study highlights the importance of sea ice volume and redistribution to correctly reproduce the physics of the underlying ocean, and the potential of appropriately parameterizing Langmuir circulation to help correct for biases towards shallow MLD in the Southern Ocean. The model also reproduces observed freshwater patterns in the West Antarctic Peninsula during late summer and suggests that areas of intense summertime sea ice melt can still show net annual freezing due to high sea ice formation during the winter.
Keywords: Sørishavet; havis; klimatologi; langmuirsirkulasjon; oseanografi; sjøis

Foraging tactics in dynamic sea-ice habitats affect individual state in a long-ranging seabird - Tarroux, Arnaud; Cherel, Yves; Fauchald, Per; Kato, Akiko; Love, Oliver P; Ropert-Coudert, Yan; Spreen, Gunnar; Varpe, Øystein; Weimerskirch, Henri; Yoccoz, Nigel G; Zahn, Sandrine; Descamps, Sébastien (Functional Ecology, 2020)
Abstract Individual heterogeneity in diet and foraging behaviour is common in wild animal populations, and can be a strong determinant of how populations respond to environmental changes. Within populations, variation in foraging behaviour and the occurrence of individual tactics in relation to resources distribution can help explain differences in individual fitness, and ultimately identify important factors affecting population dynamics. We examined how foraging behaviour and habitat during the breeding period related to the physiological state of a long-ranging seabird adapted to sea ice, the Antarctic petrel Thalassoica antarctica. Firstly, using GPS tracking and state-switching movement modelling (hidden Markov models) on 124 individual birds, we tested for the occurrence of distinct foraging tactics within our study population. Our results highlight a large variation in the movement and foraging behaviour of a very mobile seabird, and delineate distinct foraging tactics along a gradient from foraging in dense pack ice to foraging in open water. Secondly, we investigated the effects of these foraging tactics on individual state at return from a foraging trip. We combined movement data with morphometric and physiological measurements of a suite of plasma metabolites that provided a general picture of a bird's individual state. Foraging in denser sea ice was associated with lower gain in body mass during brooding, as well as lower level of energy acquisition (plasma triacylglycerol) during both brooding and incubation. We found no clear relationship between the foraging tactic in relation to sea ice and the energetic stress (changes in plasma corticosterone), energetic balance (β-hydroxybutyrate) or trophic level (δ15N). However, a shorter foraging range was related to both the energetic balance (positively) and the trophic level (negatively). Our results highlight a diverse range of foraging tactics in relation to sea ice in Antarctic petrels. While the various foraging tactics do not seem to strongly alter energetic balance, they may affect other aspects of Antarctic petrels' physiology. Future changes in sea-ice habitats can thus be expected to have an impact on the individual state of seabirds such as Antarctic petrels, which could ultimately affect their population dynamics. Nonetheless, strong individual heterogeneity in the use of sea-ice habitats by a typical pagophilic species might strengthen its resilience to environmental changes and in particular to forecasted sea-ice loss. A free Plain Language Summary can be found within the Supporting Information of this article.
Keywords: Sørishavet; fôring; havis; marin biologi; miljøendringer; observasjoner; ornitologi; petreller; sjøfugler; sjøis; smelting; zoologi

Microcontinents and Continental Fragments Associated With Subduction Systems - van den Broek, Joost M; Gaina, Carmen (Tectonics, 2020)
Microcontinents and continental fragments are small pieces of continental crust that are surrounded by oceanic lithosphere. Although classically associated with passive margin formation, here we present several preserved microcontinents and continental fragments associated with subduction systems. They are located in the Coral Sea, South China Sea, central Mediterranean and Scotia Sea regions, and a “proto-microcontinent,” in the Gulf of California. Reviewing the tectonic history of each region and interpreting a variety of geophysical data allows us to identify parameters controlling the formation of microcontinents and continental fragments in subduction settings. All these tectonic blocks experienced long, complex tectonic histories with an important role for developing inherited structures. They tend to form in back-arc locations and separate from their parent continent by oblique or rotational kinematics. The separated continental pieces and associated marginal basins are generally small and their formation is quick (<50 Myr). Microcontinents and continental fragments formed close to large continental masses tend to form faster than those created in systems bordered by large oceanic plates. A common triggering mechanism for their formation is difficult to identify, but seems to be linked with rapid changes of complex subduction dynamics. The young ages of all contemporary pieces found in situ suggest that microcontinents and continental fragments in these settings are short lived. Although presently the amount of in-situ subduction-related microcontinents is meager (an area of 0.56% and 0.28% of global, non-cratonic, continental crustal area and crustal volume, respectively), through time microcontinents contributed to terrane amalgamation and larger continent formation.
Keywords: Sørishavet; batymetri; geofysikk; geologi; geovitenskap; litosfæren; tektonikk

Sea Ice CO2 Dynamics Across Seasons: Impact of Processes at the Interfaces - Van der Linden, Fanny; Tison, Jean-Louis; Champenois, Willy; Moreau, Sébastien; Carnat, Gauthier; Kotovitch, Marie; Fripiat, François; Deman, Florian; Roukaerts, Arnout; Dehairs, Frank; Wauthy, Sarah; Lourenço, Antonio; et al. (Journal of Geophysical Research: Oceans, 2020)
Winter to summer CO2 dynamics within landfast sea ice in McMurdo Sound (Antarctica) were investigated using bulk ice pCO2 measurements, air-snow-ice CO2 fluxes, dissolved inorganic carbon (DIC), total alkalinity (TA), and ikaite saturation state. Our results suggest depth-dependent biotic and abiotic controls that led us to discriminate the ice column in three layers. At the surface, winter pCO2 supersaturation drove CO2 release to the atmosphere while spring-summer pCO2 undersaturation led to CO2 uptake most of the time. CO2 fluxes showed a diel pattern superimposed upon this seasonal pattern which was potentially assigned to either ice skin freeze-thaw cycles or diel changes in net community production. In the ice interior, the pCO2 decrease across the season was driven by physical processes, mainly independent of the autotrophic and heterotrophic phases. Bottom sea ice was characterized by a massive biomass build-up counterintuitively associated with transient heterotrophic activity and nitrate plus nitrite accumulation. This inconsistency is likely related to the formation of a biofilm. This biofilm hosts both autotrophic and heterotrophic activities at the bottom of the ice during spring and may promote calcium carbonate precipitation.
Keywords: Sørishavet; biofilm; biomasse; geokjemi; karbon syklus; karbondioksid; landfast havis; landfast sjøis; oseanografi

Diversity and community structure of bacterioplankton in surface waters off the northern tip of the Antarctic Peninsula - Cao, Shunan; He, Jianfeng; Zhang, Fang; Lin, Ling; Gao, Yuan; Zhou, Qiming (Polar Research, 2019)
Global climate change is significantly affecting marine life off the northern tip of the Antarctic Peninsula, but little is known about microbial ecology in this area. The main goal of this study was to investigate the bacterioplankton community structure in surface waters using pyrosequencing and to determine factors influencing this community. Pelagibacterales and Rhodobacterales (Alphaproteobacteria), Oceanospirillales and Alteromonadales (Gammaproteobacteria), and Flavobacteriales (Bacteroidetes) were the core taxa in our samples, and the five most relatively abundant genera were Pelagibacter, Polaribacter, Octadecabacter, group HTCC2207 and Sulfitobacter. Although nutrients and chlorophyll a (chl a) contributed more to bacterioplankton community structure than water masses or depth, only 30.39% of the variance could be explained by the investigated environmental factors, as revealed by RDA and pRDA. No significant difference with respect to nutrients and chl a was observed among water masses or depth, as indicated by ANOVA. Furthermore, significant correlations among the dominant bacterial genera were more common than correlations between dominant genera and environmental factors, as revealed by Spearman analysis. We conclude that nutrients and chl a become homogeneous and that interpopulation interactions may have a central role in influencing the bacterial community structure in surface waters off the northern tip of the Antarctic Peninsula during the summer.
Keywords: Sørishavet; bakterier; bakterioplankton; fytoplankton; klimaendringer; marin biologi; plankton; pyrosekvensering; zooplankton

Ecological niche modelling of cold-water corals in the Southern Ocean (N Antarctic), present distribution and future projections due to temperature changes - Chaabani, Safa; López-González, Pablo J; Casado-Amezua, Pilar; Pehlke, Hendrik; Weber, Lukas; Martínez-Baraldés, Irene; Jerosch, Kerstin (Marine Ecology Progress Series, 2019)
An urgent necessity to understand the effect of climatic change on scleractinian cold-water coral (CWC) ecosystems has arisen due to increasing ocean warming and acidification over the last decades. Here, presence-absence records of 12 scleractinian CWC species from research expeditions and the literature were compiled and merged with model-generated pseudo-absence data and 14 environmental variables. The best-fitting results of 9 species distribution models (SDMs) were combined to an ensemble habitat suitability model for CWCs in the northern Southern Ocean (Weddell Sea and Antarctic Peninsula) by means of the open-source R package "biomod2". Furthermore, 2 future scenarios of increasing bottom sea temperature were used to investigate the spatial response of scleractinians to temperature change. The resulting (current scenario) potential ecological niches were evaluated with good to excellent statistical measures. The results predict that present areas of highest probability of CWC occurrence are around the Antarctic Peninsula, South Orkney Islands and Queen Maud Land, with preference to geomorphic features such as seamounts. The distribution of CWC habitats is mainly driven by distance to coast and ice shelves, bathymetry, benthic calcium carbonate, and temperature. Under warming conditions, CWCs are predicted to expand their distribution range by 6 and 10% in 2037 and 2150, respectively, compared to the present distribution. The future models using increased bottom temperature revealed a stable CWC distribution for most parts of the study area. However, habitat shifts are expected to the Filchner Trough region, the adjacent continental shelves, as well as to the eastern side of the Antarctic Peninsula. KEYWORDS: Scleractinian coral · Ensemble models · Environmental change · Habitat suitability model · Spatial distribution · Weddell Sea. Antarctica
Keywords: Sørishavet; Weddellhavet; batymetri; biodiversitet; global oppvarming; klimaendringer; marin biologi; miljøendringer; oseanografi; økosystemer

Prey differences drive local genetic adaptation in Antarctic fur seals - Cleary, Alison C; Bester, Marthán; Forcada, Jaume; Goebel, Michael; Goldsworthy, Simon D; Guinet, Christophe; Hoffman, Joseph I; Kovacs, Kit M; Lydersen, Christian; Lowther, Andrew D (Marine Ecology Progress Series, 2019)
Antarctic fur seal (Arctocephalus gazella) colonies are found on sub-Antarctic islands around the continent. These islands experience a range of conditions in terms of physical and biological habitat, creating a natural laboratory to investigate local genetic adaptation. One striking habitat difference is in the availability of Euphausia superba krill as prey, which has led to A. gazella exhibiting a range of diets. A. gazella in some colonies consume exclusively krill, while their conspecifics in other colonies feed mainly on fish and consume few to no krill. To investigate potential adaptations to these different prey fields, reduced representation genome sequencing was conducted on A. gazella from the 8 major colonies. Twenty-seven genomic regions exhibiting signatures of natural selection were identified. Two of these genomic regions were clearly associated with seals living in krill-dominated areas or those in fish-dominated areas. Twenty-two additional genomic regions under selection showed a pattern consistent with prey differences as the driver of selection after historical migrations from krill-dominated habitats where lineages evolved to present krill-poor habitat areas were taken into account. Only 1 of the genomic regions identified appeared to be explained by any other environmental variable analysed (depth). Genomic regions under prey-driven selection included genes associated with regulation of gene expression, skeletal development, and lipid metabolism. Adaptation to local prey has implications for spatial management of this species and for the potential impacts of climate- or harvest-driven reductions in krill abundance on these seals. KEY WORDS: Arctocephalus gazella · Double digest restriction-site associated DNA sequencing · ddRAD · Diet · Euphausia superba · Natural selection
Keywords: Bouvetøya; Sørishavet; genetikk; krill; marin biologi; pelsseler; plankton; zoologi; økosystemer

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Two species of Lumbricillus (Enchytraeidae, Annelida) new to Antarctica - Lee, Jeounghee; Klinth, Mårten J; Jung, Jongwoo (Polar Research, 2019)
The intertidal fauna of the Antarctic Peninsula has a relatively high species diversity, due to its warmer environment compared to other parts of Antarctica. Marine oligochaetes are, in general, one of the most diverse and ecologically important benthic organism groups, at least in the littoral zone. Antarctica has been one of the least studied areas with regard to oligochaete diversity. Here we report two Lumbricillus species (Lumbricillus antarcticus Stephenson, 1932 and Lumbricillus sejongensis sp. nov.) new to Antarctica, found in a tidal pool on the Barton Peninsula, King George Island. The diversity of this genus remains poorly known for Antarctica and the Subantarctic islands, and what we know is based on a few patchy studies.
Keywords: Sørishavet; belteormer; bentiske organismer; biodiversitet; fauna; marin biologi; tidevann

The life cycle of small- to medium-sized icebergs in the Amundsen Sea Embayment - Mazur, Aleksandra K.; Wåhlin, Anna K.; Kalén, Ola (Polar Research, 2019)
An object-based method for automatic iceberg detection has been applied to Advanced Synthetic Aperture Radar images in the Amundsen Sea Embayment (ASE), Antarctica. The images were acquired between 1 January 2006 and 8 April 2012 under varying meteorological, oceanographic and sea-ice conditions. During this time period, the icebergs were counted (average 1370 ± 50) and their surface area was estimated (average 1537.5 km2). The average surface area was about 2.5 times larger than the annual calved area (620 km2), indicating that the average iceberg age in the ASE is about 2.5 years, which was confirmed by observed residence times based on drift tracks. Most of the ASE icebergs were less than 1500 m long, and almost 90% of them were smaller than 2 km2. The proportion of small- and medium-sized icebergs (84.4%) was significantly higher than in the open ocean, where large icebergs (>10 km2) account for nearly the whole iceberg surface area. The opposite was true for the freshly calved icebergs in the ASE. The data indicate that the creation of icebergs in the ASE is dominated by steady small- to medium-scale calving from ice shelves fringing the embayment. In addition, rare calving events of giant icebergs occur on a decadal timescale. There is also some import of icebergs from the Bellingshausen Sea further east along the coast, in particular after large calving events there.
Keywords: Amundsenhavet; Sørishavet; batymetri; fjernmåling; havis; hydrologi; isberg; isbrem; isfjell; kalving; oseanografi; sjøis

Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas - Moreau, Sebastien; Lannuzel, Delphine; Janssens, J.; Arroyo, Mar; Corkill, M; Cougnon, Eva; Genovese, C.; Legresy, Benoit; Lenton, Andrew; Puigcorbe, V.; Ratnarajah, L.; Rintoul, Steve; et al. (Journal of Geophysical Research: Oceans, 2019)
In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2. Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a)/m2, respectively) and net community production (5.3 and 4.6 mol C/m2, respectively) were approximately 3 times those measured in the Dalton polynya (average of 122 mg Chl a/m2 and 1.8 mol C/m2). Phytoplankton communities also differed between the polynyas. Diatoms were thriving in the Mertz and Ninnis polynyas but not in the Dalton polynya, where Phaeocystis antarctica dominated. These strong regional differences were explored using physiological, biological, and physical parameters. The most likely drivers of the observed higher productivity in the Mertz and Ninnis were the relatively shallow inflow of iron-rich modified Circumpolar Deep Water onto the shelf as well as a very large sea ice meltwater contribution. The productivity contrast between the three polynyas could not be explained by (1) the input of glacial meltwater, (2) the presence of Ice Shelf Water, or (3) stratification of the mixed layer. Our results show that physical drivers regulate the productivity of polynyas, suggesting that the response of biological productivity and carbon export to future change will vary among polynyas.
Keywords: Sørishavet; biomasse; brehylle; fytoplankton; havis; isbrem; isshelf; marin biologi; oseanografi; polynja; sjøis

Two-Timescale Carbon Cycle Response to an AMOC Collapse - Nielsen, Søren B; Jochum, Markus; Pedro, Joel B; Eden, Carsten; Nuterman, Roman (Paleoceanography and Paleoclimatology, 2019)
Atmospheric CO2 concentrations (pCO2) varied on millennial timescales in phase with Antarctic temperature during the last glacial period. A prevailing view has been that carbon release and uptake by the Southern Ocean dominated this millennial-scale variability in pCO2. Here, using Earth System Model experiments with an improved parameterization of ocean vertical mixing, we find a major role for terrestrial and oceanic carbon releases in driving the pCO2 trend. In our simulations, a change in Northern Hemisphere insolation weakens the Atlantic Meridional Overturning Circulation (AMOC) leading to increasing pCO2 and Antarctic temperatures. The simulated rise in pCO2 is caused in equal parts by increased CO2 outgassing from the global ocean due to a reduced biological activity and changed ventilation rates, and terrestrial carbon release as a response to southward migration of the Intertropical Convergence Zone. The simulated terrestrial release of carbon could explain stadial declines in organic carbon reservoirs observed in recent ice core δ13C measurements. Our results show that parallel variations in Antarctic temperature and pCO2 do not necessitate that the Southern Ocean dominates carbon exchange; instead, changes in carbon flux from the global ocean and land carbon reservoirs can explain the observed pCO2 (and δ13C) changes.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; paleoklimatologi; paleoseanografi; temperatur

Groundwater discharge to the western Antarctic coastal ocean - Null, Kimberly A; Corbett, D Reide; Crenshaw, Jared; Peterson, Richard N; Peterson, Leigha E; Lyons, W Berry (Polar Research, 2019)
Submarine groundwater discharge (SGD) measurements have been limited along the Antarctic coast, although groundwater discharge is becoming recognized as an important process in the Antarctic. Quantifying this meltwater pathway is important for hydrologic budgets, ice mass balances and solute delivery to the coastal ocean. Here, we estimate the combined discharge of subglacial and submarine groundwater to the Antarctic coastal ocean. SGD, including subglacial and submarine groundwater, is quantified along the WAP at the Marr Glacier terminus using the activities of naturally occurring radium isotopes (223Ra, 224Ra). Estimated SGD fluxes from a 224Ra mass balance ranged from (0.41 ± 0.14)×104 and (8.2 ± 2.3)×104m3 d−1. Using a salinity mass balance, we estimate SGD contributes up to 32% of the total freshwater to the coastal environment near Palmer Station. This study suggests that a large portion of the melting glacier may be infiltrating into the bedrock and being discharged to coastal waters along the WAP. Meltwater infiltrating as groundwater at glacier termini is an important solute delivery mechanism to the nearshore environment that can influence biological productivity. More importantly, quantifying this meltwater pathway may be worthy of attention when predicting future impacts of climate change on retreat of tidewater glaciers.
Keywords: Sørishavet; biologi; geologi; grunnvann; hydrologi; isbreer; klimaendringer; tidevann

GlobSed: Updated Total Sediment Thickness in the World's Oceans - Straume, Eivind O; Gaina, Carmen; Medvedev, Sergei; Hochmuth, Katharina; Gohl, Karsten; Whittaker, Joanne; Abdul Fattah, R; Doornenbal, J C; Hopper, John R (Geochemistry, Geophysics, Geosystems, 2019)
We present GlobSed, a new global 5-arc-minute total sediment thickness grid for the world's oceans and marginal seas. GlobSed covers a larger area than previously published global grids and incorporates updates for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions, which results in a 29.7% increase in estimated total oceanic sediment volume. We use this new global grid and a revised global oceanic lithospheric age grid to assess the relationship between the total sediment thickness and age of the underlying oceanic lithosphere and its latitude. An analytical approximation model is used to mathematically describe sedimentation trends in major oceanic basins and to allow paleobathymetric reconstructions at any given geological time. This study provides a much-needed update of the sediment thickness distribution of the world oceans and delivers a model for sedimentation rates on oceanic crust through time that agrees well with selected drill data used for comparison.
Keywords: Sørishavet; batymetri; litosfæren; marin geofysikk; marin geologi; sedimenter; sedimentologi

Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines - Sun, Sainan; Hattermann, Tore; Pattyn, Frank; Nicholls, Keith W; Drews, Reinhard; Berger, Sophie (Geophysical Research Letters, 2019)
The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase-sensitive radio-echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results suggest an intricate mechanism in which topographic waves control the seasonal melt rate variability near the grounding line. This mechanism has not been considered before and has the potential to enhance local melt rates without advecting different water masses. As topographic waves seem to strengthen in a stratified ocean, the freshening of Antarctic surface water, predicted by observations and models, is likely to increase future basal melting in this area.
Keywords: Sørishavet; glasiologi; isshelf; klimatologi; oseanografi; smelting; vannmasser

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Surface heat budget in the Southern Ocean from 42°S to the Antarctic marginal ice zone: four atmospheric reanalyses versus icebreaker Aurora Australis measurements - Yu, Lisan; Jin, Xiangze; Schulz, Eric W (Polar Research, 2019)
Surface heat fluxes from four atmospheric reanalyses in the Southern Ocean are evaluated using air–sea measurements obtained from the Aurora Australis during off-winter seasons in 2010–12. The icebreaker tracked between Hobart, Tasmania (ca. 42°S), and the Antarctic continent, providing in situ benchmarks for the surface energy budget change in the Subantarctic Southern Ocean (58–42°S) and the eastern Antarctic marginal ice zone (MIZ, 68–58°S). We find that the reanalyses show a high-level agreement among themselves, but this agreement reflects a universal bias, not a “truth.” Downward shortwave radiation (SW↓) is overestimated (warm biased) and downward longwave radiation (LW↓) is underestimated (cold biased), an indication that the cloud amount in all models is too low. The ocean surface in both regimes shows a heat gain from the atmosphere when averaged over the seven months (October–April). However, the ocean heat gain in reanalyses is overestimated by 10–36 W m−2 (80–220%) in the MIZ but underestimated by 6–20 W m−2 (7–25%) in the Subantarctic. The biases in SW↓ and LW↓ cancel out each other in the MIZ, causing the surface heat budget to be dictated by the underestimation bias in sensible heat loss. These reanalyses biases affect the surface energy budget in the Southern Ocean by meaningfully affecting the timing of the seasonal transition from net heat gain to net heat loss at the surface and the relative strength of SW↓ at different regimes in summer, when the length-of-day effect can lead to increased SW↓ at high latitudes.
Keywords: Sørishavet; havis; klima; meteorologi; oseanografi

Signals from the south; humpback whales carry messages of Antarctic sea-ice ecosystem variability - Bengtson Nash, Susan M; Castrillon, Juliana; Eisenmann, Pascale; Fry, Brian; Shuker, Jon D; Cropp, Roger A; Dawson, Amanda; Bignert, Anders; Bohlin-Nizzetto, Pernilla; Waugh, Courtney A; Polkinghorne, Bradley J; Dalle Luche, Greta; et al. (Global Change Biology, 2018)
Abstract Southern hemisphere humpback whales (Megaptera novaeangliae) rely on summer prey abundance of Antarctic krill (Euphausia superba) to fuel one of the longest-known mammalian migrations on the planet. It is hypothesized that this species, already adapted to endure metabolic extremes, will be one of the first Antarctic consumers to show measurable physiological change in response to fluctuating prey availability in a changing climate; and as such, a powerful sentinel candidate for the Antarctic sea-ice ecosystem. Here, we targeted the sentinel parameters of humpback whale adiposity and diet, using novel, as well as established, chemical and biochemical markers, and assembled a time trend spanning 8 years. We show the synchronous, inter-annual oscillation of two measures of humpback whale adiposity with Southern Ocean environmental variables and climate indices. Furthermore, bulk stable isotope signatures provide clear indication of dietary compensation strategies, or a lower trophic level isotopic change, following years indicated as leaner years for the whales. The observed synchronicity of humpback whale adiposity and dietary markers, with climate patterns in the Southern Ocean, lends strength to the role of humpback whales as powerful Antarctic sea-ice ecosystem sentinels. The work carries significant potential to reform current ecosystem surveillance in the Antarctic region.
Keywords: Sørishavet; havis; hvaler; marin biologi; marine økosystemer; plankton; sjøis; stabile isotoper

Variable Melt Production Rate of the Kerguelen HotSpot Due To Long-Term Plume-Ridge Interaction - Bredow, Eva; Steinberger, Bernhard (Geophysical Research Letters, 2018)
For at least 120 Myr, the Kerguelen plume has distributed enormous amounts of magmatic rocks over various igneous provinces between India, Australia, and Antarctica. Previous attempts to reconstruct the complex history of this plume have revealed several characteristics that are inconsistent with properties typically associated with plumes. To explore the geodynamic behavior of the Kerguelen hotspot, and in particular address these inconsistencies, we set up a regional viscous flow model with the mantle convection code ASPECT. Our model features complex time-dependent boundary conditions in order to explicitly simulate the surrounding conditions of the Kerguelen plume. We show that a constant plume influx can result in a variable magma production rate if the plume interacts with nearby spreading ridges and that a dismembered plume, multiple plumes, or solitary waves in the plume conduit are not required to explain the fluctuating magma output and other unusual characteristics attributed to the Kerguelen hotspot.
Keywords: Den antarktiske kontinentalplaten; Sørishavet; geodynamiske modeller; geovitenskap; plategrenser; platetektonikk; tektoniske plater; vulkaner

Response of Antarctic sea-ice algae to an experimental decrease in pH: a preliminary analysis from chlorophyll fluorescence imaging of melting ice - Castrisios, Katerina; Martin, Andrew; Müller, Marius N; Kennedy, Fraser; McMinn, Andrew; Ryan, Ken G (Polar Research, 2018)
Microorganisms confined to annual sea ice in the Southern Ocean are exposed to highly variable oxygen and carbonate chemistry dynamics because of the seasonal increase in biomass and limited exchange with the underlying water column. For sea-ice algae, physiological stress is likely to be exacerbated when the ice melts; however, variation in carbonate speciation has rarely been monitored during this important state-transition. Using pulse amplitude modulated fluorometry (Imaging-PAM, Walz), we documented in situ changes in the maximum quantum yield of photosystem II ( F v / F m ) of sea-ice algae melting out into seawater with initial pH values ranging from 7.66 to 6.39. Although the process of ice-melt elevated seawater pH by 0.2–0.55 units, we observed a decrease in F v / F m between 0.02 and 0.06 for each unit drop in pH during real-time fluorescence imaging. These results are considered preliminary but provide context for including carbonate chemistry monitoring in the design of future sea ice state-transition experiments. Imaging-PAM is a reliable technology for determining F v / F m , but is of limited use for obtaining additional photosynthetic parameters when imaging melting ice.
Keywords: Sørishavet; alger; fotosyntese; fysiologi; havis; karbonatkjemi; marin biologi; sjøis; økofysiologi

Feeding by Antarctic krill Euphausia superba in the West Antarctic Peninsula: differences between fjords and open waters - Cleary, Alison C; Durbin, Edward G; Casas, Maria C (Marine Ecology Progress Series, 2018)
Antarctic krill Euphausia superba are key components of Antarctic ecosystems, serving as the major prey item for most of the megafauna in the region. Coastal fjords along the West Antarctic Peninsula have been identified as biological hotspots, areas in which high biomasses of both E. superba and their megafauna predators are consistently observed. We investigated feeding by E. superba in fjords and adjacent open waters of the West Antarctic Peninsula. Next generation sequencing of stomach contents from 174 krill indicated a diverse diet, with broad patterns consistent with previous understanding of E. superba feeding. Diatom sequence reads were frequent and abundant, indicating a largely diatom-based diet, while the occasional presence of high abundances of copepod sequence reads suggests carnivory supplemented the diet. Striking differences were observed between the stomach contents of krill collected in fjords and those of krill collected in adjacent open waters. Chaetoceros spp. diatoms made up 71% of the stomach contents sequences of krill collected in fjords, but less than 10% of the stomach contents sequences of krill collected in open waters. These differences could not be explained by differences in the surface water phytoplankton communities, as in both open waters and fjords Chaetoceros spp. made up less than 10% of the surface water sequence read assemblages. These feeding differences highlight the importance of taking into account regional differences in krill feeding when considering E. superba’s roles in Southern Ocean ecosystems, and suggest krill in fjords may make use of vertical structure in phytoplankton assemblages.
Keywords: Sørishavet; biomasse; fytoplankton; krill; marin biologi; oseanografi; zoologi; økosystemer

Wind Stress Mediated Variability of the Filchner Trough Overflow, Weddell Sea - Daae, Kjersti Birkeland; Darelius, Elin Maria K; Fer, Ilker; Østerhus, Svein; Ryan, Svenja (Journal of Geophysical Research: Oceans, 2018)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Seasonal Outflow of Ice Shelf Water Across the Front of the Filchner Ice Shelf, Weddell Sea, Antarctica - Darelius, Elin Maria K; Sallée, Jean-Baptiste (Geophysical Research Letters, 2018)
Keywords: Sørishavet; Weddellhavet; bunnvann; isfront; isshelf; oseanografi

Ice-rise stratigraphy reveals changes in surface mass balance over the last millennia in Dronning Maud Land - Goel, Vikram; Martín, Carlos; Matsuoka, Kenichi (Journal of Glaciology, 2018)
We use ice flow modelling to simulate the englacial stratigraphy of Blåskimen Island, an ice rise in Dronning Maud Land and elucidate the evolution of this data-sparse region. We apply a thermo-mechanically coupled Elmer/Ice model to a profile along flowlines and through the ice-rise summit, where surface mass balance (SMB), flow velocity and ice stratigraphy were recently measured. We conclude that: (i) the ice rise is presently thickening at a rate of 0.5~0.6 m ice equivalent per year (mieq a−1), which is twice an earlier estimate using the field data and the input–output method; (ii) present thickening started 20–40 years in the past, before which the ice rise was in a steady state; (iii) SMB contrast between the upwind and downwind slopes was stronger than the present value by ~23% (or 0.15 mieq a−1) prior to ~1100 years ago. Since then, this contrast has been decreasing overall. We surmise that these SMB changes are likely a result of synoptic-scale atmospheric changes, rather than local atmospheric changes controlled by local ice topography. Our technique effectively assimilates geophysical data, avoiding the complexity of ice flow beneath the ice divide. Thus, it could be applied to other ice rises to elucidate the recent glacial retreat.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Di(2-ethylhexyl) adipate (DEHA) detection in Antarctic krill (Euphasia superba Dana) - Han, Xiangning; Liu, Daicheng (Polar Research, 2018)
In this reported study, a novel high-performance thin-layer chromatography (HPTLC) method was developed for the detection and quantification of the toxic substance di(2-ethylhexyl) adipate (DEHA) in Antarctic krill. This procedure was based on the extraction of DEHA by ultrasonic solvent extraction with anhydrous ethanol, silica-gel column chromatographic separation, HPTLC detection and quantification using petroleum ether/ethyl acetate/ acetone/glacial acetic acid (29:1:0.5:2d*, v/v/v/v) as the developing solvent and bromine thymol blue solution as the chromogenic agent. The content of DEHA in freeze-dried Antarctic krill was found to be ca. 0.63 ± 0.05 mg/g. The structure of DEHA in the Antarctic krill was subsequently determined by gas chromatography–mass spectrometry (GC-MS) and infrared chromatography, which verified the presence of this compound in the krill. The HPTLC method exhibited excellent accuracy, with a recovery of 97.1–101.6% and good precision with a relative standard deviation of 2.47–4.90%. The DEHA in Antarctic krill oil was extracted by n-hexane and detected using the same method described above, which verified that DEHA was also present in krill oil at a concentration of ca. 2.16 ± 0.08 mg/g. The presence of DEHA in kill oil is very concerning because of its demonstrated harmful ecotoxicity, and since Antarctic krill is the key link in the food chain in the Antarctic coastal marine ecosystem. The adverse effects of DEHA on Antarctic krill and the source of DEHA will be explored in future research.
Keywords: Sørishavet; krill; marin forurensning; plankton; plastpartikler; økotoksikologi; økotoksiner

A Model-Based Evaluation of the Inverse Gaussian Transit-Time Distribution Method for Inferring Anthropogenic Carbon Storage in the Ocean - He, Yan-Chun; Tjiputra, Jerry; Langehaug, Helene R.; Jeansson, Emil; Gao, Yongqi; Schwinger, Jörg; Olsen, Are (Journal of Geophysical Research: Oceans, 2018)
The Inverse Gaussian approximation of transit time distribution method (IG-TTD) is widely used to infer the anthropogenic carbon (Cant) concentration in the ocean from measurements of transient tracers such as chlorofluorocarbons (CFCs) and sulfur hexafluoride (SF6). Its accuracy relies on the validity of several assumptions, notably (i) a steady state ocean circulation, (ii) a prescribed age tracer saturation history, e.g., a constant 100% saturation, (iii) a prescribed constant degree of mixing in the ocean, (iv) a constant surface ocean air-sea CO2 disequilibrium with time, and (v) that preformed alkalinity can be sufficiently estimated by salinity or salinity and temperature. Here, these assumptions are evaluated using simulated “model-truth” of Cant. The results give the IG-TTD method a range of uncertainty from 7.8% to 13.6% (11.4 Pg C to 19.8 Pg C) due to above assumptions, which is about half of the uncertainty derived in previous model studies. Assumptions (ii), (iv) and (iii) are the three largest sources of uncertainties, accounting for 5.5%, 3.8% and 3.0%, respectively, while assumptions (i) and (v) only contribute about 0.6% and 0.7%. Regionally, the Southern Ocean contributes the largest uncertainty, of 7.8%, while the North Atlantic contributes about 1.3%. Our findings demonstrate that spatial-dependency of , and temporal changes in tracer saturation and air-sea CO2 disequilibrium have strong compensating effect on the estimated Cant. The values of these parameters should be quantified to reduce the uncertainty of IG-TTD; this is increasingly important under a changing ocean climate.
Keywords: Sørishavet; antropogenisk CO2; fossilt brensel; karbondioksid; karbonlagring; klimaendringer; klimatologi

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

Observations of Ice Nucleating Particles Over Southern Ocean Waters - McCluskey, Christina S; Hill, Thomas C J; Humphries, Ruhi S; Rauker, Anne M; Moreau, Sebastien; Strutton, P G; Chambers, Scott Dudley; Williams, Alastair G; McRobert, I; Ward, J; Keywood, Melita D; Harnwell, J; et al. (Geophysical Research Letters, 2018)
A likely important feature of the poorly understood aerosol-cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations (nINPs) were measured during a ship campaign that occurred south of Australia (down to 53°S) in March–April 2016. Ocean surface chlorophyll a concentrations ranged from 0.11 to 1.77 mg/m3, and nINPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m−3 at −20 °C. The INP population included organic heat-stable material, with contributions from heat-labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses.
Keywords: Sørishavet; atmosfæren; iskjerner; iskrystaller; klimatologi; marin organisk aerosol; meteorologi; skyer

Chinstrap penguin population genetic structure: one or more populations along the Southern Ocean? - Mura-Jornet, Isidora; Pimentel, Carolina; Dantas, Gisele P M; Petry, Maria Virginia; González-Acuña, Daniel; Barbosa, Andrés; Lowther, Andrew D; Kovacs, Kit M; Poulin, Elie; Vianna, Juliana A (BMC Evolutionary Biology, 2018)
Keywords: Bouvetøya; Sørishavet; fugler; genetikk; marin biologi; ornitologi; pingviner

Net Community Production in the Southern Ocean: Insights From Comparing Atmospheric Potential Oxygen to Satellite Ocean Color Algorithms and Ocean Models - Nevison, Cynthia; Munro, David; Lovenduski, Nicole; Cassar, Nicolas; Keeling, Ralph; Krummel, Paul; Tjiputra, Jerry (Geophysical Research Letters, 2018)
The contribution of oceanic net community production (NCP) to the observed seasonal cycle in atmospheric potential oxygen (APO) is estimated at Cape Grim, Tasmania. The resulting APONCP signal is compared to satellite and ocean model-based estimates of POC export and NCP across the Southern Ocean. The satellite products underestimate the amplitude of the observed APONCP seasonal cycle by more than a factor of 2. Ocean models suggest two reasons for this underestimate: (1) Current satellite products substantially underestimate the magnitude of NCP in early spring. (2) Seasonal O2 outgassing is supported in large part by storage of carbon in DOC and living biomass. More DOC observations are needed to help evaluate this latter model prediction. Satellite products could be improved by developing seasonally dependent relationships between remote sensing chlorophyll data and in situ NCP, recognizing that the former is a measure of mass, the latter of flux.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; karboneksport; marin biologi; oseanografi

Multi-temporal variation of the Ross Sea Polynya in response to climate forcings - Park, Jinku; Kim, Hyun-Cheol; Kidwell, Autumn; Hwang, Jihyun (Polar Research, 2018)
The multi-temporal scales of two physical characteristics (areas and occurrence time) of the Ross Sea Polynya (RSP) in Antarctica were analysed using a sea-ice concentration data set (1979–2014) derived from the Scanning Multichannel Microwave Radiometer, the Special Sensor Microwave Imager and Sensor Microwave Imager Sounder. Then, the Ensemble Empirical Mode Decomposition (EEMD) was applied to the data sets to decompose signals into finite numbers of intrinsic mode functions and a residual mode: long time trend. This approach allowed us to understand the long-term variability of the RSP area and occurrence in response to atmospheric forcing through teleconnections between low and high latitudes by comparing the Nino3.4 and Southern Annular Mode (SAM) indices. The nonlinear trend of the RSP areas derived from the EEMD residual had an upward trending shift in the early 1990s and was fairly consistent with the nonlinear trend of Nino3.4. However, the trend of RSP occurrence time progressively increased and had a significant effect on the long time scale. The trend of the RSP area is significantly correlated (+0.98) with the ratio of the trend of the meridional to zonal wind components related with the nonlinearity of Nino3.4, suggesting that meridional wind stress dominated the changes of the polynya area in the Ross Sea. In addition, the nonlinear trends between the SAM and RSP occurrence time show a strong positive correlation, contributing to the earlier onset of polynya expansion and delayed connection with the open ocean owing to enhanced southerly winds.
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; polynja; sjøis; sørlig oscillasjon

Planktonic food web structure at SSTF and PF in the Indian sector of the Southern Ocean during austral summer 2011 - Pillai, H U K; Anilkumar, N; Achuthankutty, C T; Mendes, C R; Sabu, P; Jayalakshmi, K V; Devi, C R Asha; Dessai, Deepti; George, Jenson; Pavithran, Sini; Hari Devi, C K; Tripathy, S C; et al. (Polar Research, 2018)
This study aims to describe the planktonic food web structure with respect to phytoplankton biomass (chlorophyll a ) and prevailing environmental conditions at the South Subtropical Front (SSTF) and the Polar Front (PF) in the Indian sector of the Southern Ocean. Sampling was carried out at each front for 72 hrs, at 6-hr intervals, during the austral summer 2011. Considerable variations were observed in the hydrography between these two fronts. A strong temperature minimum layer was observed at the PF. Although the surface primary production and chlorophyll a values showed similar trends at both the fronts, the water column values of these parameters showed major disparities. The phytoplankton composition also revealed marked difference between the fronts. A deep chlorophyll maximum concordant with the upper limit of the temperature minimum layer was prominent at the PF. The microzooplankton abundance at the SSTF was twice as high as at the PF. The mesozooplankton biovolume and population density also showed considerable variations between these fronts. Noticeable diel variations were observed in the surface mesozooplankton biovolumes at both the fronts and the copepod Pleuromamma gracilis showed active diel vertical migration at SSTF. Both the grazing and senescence indices showed significant variations between these fronts, suggesting a disparity in the ecological efficiency of the two regions. The variability observed in the plankton community structure with respect to the hydrography and the biological components measured suggests that a multivorous food web at the SSTF and a conventional food web at the PF prevailed during the period of study.
Keywords: Sørishavet; biomasse; fytoplankton; hydrografi; marin biologi; zooplankton; økosystemer

Increasing temperature may shift availability of euphausiid prey in the Southern Ocean - Richerson, Kate; Driscoll, Ryan; Mangel, Marc (Marine Ecology Progress Series, 2018)
Climate change is predicted to affect Southern Ocean biota in complex ways. Euphausiids play a crucial role in the trophodynamics of the ecosystem, and their status under future environmental scenarios is the subject of much concern. Thysanoessa macrura is the most widely distributed, numerically abundant, and ubiquitous euphausiid south of the Polar Front and may be an underappreciated prey species. T. macrura is eurythermic and may be better able to tolerate warming ocean temperatures in comparison to the more stenothermic Antarctic krill Euphausia superba. We use temperature-dependent growth models and biomass per recruit to investigate how the availability of this euphausiid to predators may change under a range of temperature scenarios. We contrast this with the availability of E. superba and find that, under some ranges of temperature change, increasing T. macrura growth may be able to partially compensate for decreasing E. superba growth in terms of biomass available for predators. However, in spite of its considerable biomass, other aspects of this species, such as its size and habitat, may limit its potential to replace E. superba in the diet of many predators. KEYWORDS: Thysanoessa macrura · Euphausia superba · Growth · Temperature · Climate change · Krill predators · Southern Ocean · Euphausiids · Modeling
Keywords: Sørishavet; biomasse; havoppvarming; klimaendringer; krill; marin biologi; marine økosystemer; miljøendringer; plankton

A New Bathymetry for the Southeastern Filchner-Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History - Rosier, Sebastian H R; Hofstede, Coen; Brisbourne, Alex Mark; Hattermann, Tore; Nicholls, Keith William; Davis, Peter E D; Anker, Paul; Hillenbrand, Claus-Dieter; Smith, Andrew M; Corr, Hugh F (Journal of Geophysical Research: Oceans, 2018)
The Filchner-Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub-ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo-ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub-ice shelf melt rates.
Keywords: Sørishavet; batymetri; brehylle; innlandsis; isbrem; isshelf; klima; oseanografi; tidevann

Remarkable structural resistance of a nanoflagellate-dominated plankton community to iron fertilization during the Southern Ocean experiment LOHAFEX - Schulz, Isabelle; Montresor, Marina; Klaas, Christine; Assmy, Philipp; Wolzenburg, Sina; Gauns, Mangesh; Sarkar, Amit; Thiele, Stefan; Wolf-Gladrow, Dieter; Naqvi, Wajih; Smetacek, Victor (Marine Ecology Progress Series, 2018)
The genesis of phytoplankton blooms and the fate of their biomass in iron-limited, high-nutrient-low-chlorophyll regions can be studied under natural conditions with ocean iron fertilization (OIF) experiments. The Indo-German OIF experiment LOHAFEX was carried out over 40 d in late summer 2009 within the cold core of a mesoscale eddy in the productive south-west Atlantic sector of the Southern Ocean. Silicate concentrations were very low, and phytoplankton biomass was dominated by autotrophic nanoflagellates (ANF) in the size range 3-10 µm. As in all previous OIF experiments, the phytoplankton responded to iron fertilization by increasing the maximum quantum yield (Fv/Fm) and cellular chlorophyll levels. Within 3 wk, chlorophyll levels tripled and ANF biomass doubled. With the exception of some diatoms and dinoflagellates, the biomass levels of all other groups of the phyto- and protozooplankton (heterotrophic nanoflagellates, dinoflagellates and ciliates) remained remarkably stable throughout the experiment both inside and outside the fertilized patch. We attribute the unusually high biomass attained and maintained by ANF to the absence of their grazers, the salps, and to constraints on protozooplankton grazers by heavy predation exerted by the large copepod stock. The resistance to change of the ecosystem structure over 38 d after fertilization, indicated by homogeneity at regional and temporal scales, suggests that it was locked into a stable, mature state that had evolved in the course of the seasonal cycle. The LOHAFEX bloom provides a case study of a resistant/robust dynamic equilibrium between auto- and heterotrophic ecosystem components resulting in low vertical flux both inside and outside the patch despite high biomass levels. KEYWORDS: Antarctic · Protists · Fe-limitation · Si-limitation · Ecology-biogeochemistry relationship · Carbon:chlorophyll ratios · Ecosystem stability
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; økologi; økosystemer

Abnormal gonads in the Antarctic toothfish (Dissostichus mawsoni Norman, 1937 [Perciformes: Nototheniidae]): the first record and histological description - Zhukova, Kristina A; Gordeev, Ilya I; Kuznetsova, Elena N (Polar Research, 2018)
This paper describes the morphology and histology of abnormal gonads in Antarctic toothfish (Dissostichus mawsoni) and the possibility of intersexuality and senescence of some individuals. Two old (approximately 25 years) and large (184–185 cm) specimenswith abnormal gonadswere caught in the Antarctic during commercial fishing for toothfish and studied using histological methods. Although D. mawsoni is well-known and extensively studied, this is the first study dealing with abnormal gonads in the species. The histological analysis revealed that the gonads of the first specimen contained both male and female germ cells (ovotestis), the testicular and ovarian tissues being separated by a thick layer of connective tissue. The female portion was composed of secondary vitellogenic oocytes, primary vitellogenic, cortical alveolar and primary growth oocytes, while the testes contained cysts of spermatogonia and primary spermatocyte. The gonads of the second specimen were small, filiform and showed massive growth of the connective tissue, which occupied almost the entire gonad; a few spermatogonia without visible cystswere found. This study extends our understanding of sexual development in Antarctic toothfish, documenting the possibility of long-term interruptions in the reproductive cycle of this species.
Keywords: Sørishavet; fisker; gonader; histologi; marin biologi; morfologi; oseanografi; reproduksjon

Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Publisher: Routledge
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Ontogenetic changes in the feeding strategy of Lepidonotothen nudifrons (Pisces, Nototheniidae) off the South Shetland Islands and the Antarctic Peninsula - Blasina, Gabriela; Cazorla, Andrea Lopez; Antoni, Mariana Deli; Bruno, Daniel; Delpiani, Matías; Díaz de Astarloa, Juan Martín (Polar Research, 2017)
The diet and feeding strategy of Lepidonotothen nudifrons off the South Shetland Islands and the Antarctic Peninsula, as well as their variation in relation to ontogenetic stage (juvenile– adult) and sampling area, were determined by stomach contents analysis. Additionally, the trophic level of this species was estimated to determine its position within the Antarctic food web. Out of 247 specimens with prey in their stomachs, 144 were caught near the South Shetland Islands and 103 off the Antarctic Peninsula. Ontogenetic changes in the trophic ecology of L. nudifrons were observed in both areas and were mainly related to a decrease of copepods and an increase of euphausiids in the diet. The diet of juveniles from the South Shetland Islands was characterized by the dominance of calanoid copepods, followed by isopods and amphipods, whereas diet off the Antarctic Peninsula was dominated by amphipods and cyclopoid copepods. The diet in adults was dominated by amphipods and euphausiids in both areas. The specialization of individual predators on different prey types was observed when considering the whole population of L. nudifrons, but when ontogenetic stages were considered separately it showed a more mixed feeding strategy, with different dominant prey for each class. Although the trophic level increased with fish size, L. nudifrons can be classified as secondary consumer throughout its lifespan.
Keywords: Sørishavet; amfipoder; copepoder; euphausiacea; fauna; fisker; isopoder; marin zoologi; økosystemer

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi

Microplastic in the surface waters of the Ross Sea (Antarctica): Occurrence, distribution and characterization by FTIR - Cincinelli, Alessandra; Scopetani, Costanza; Chelazzi, David; Lombardini, Emilia; Martellini, Tania; Katsoyiannis, Athanasios; Fossi, Maria Cristina; Corsolini, Simonetta (Chemosphere, 2017)
This is the first survey to investigate the occurrence and extent of microplastic (MPs) contamination in sub surface waters collected near-shore and off-shore the coastal area of the Ross Sea (Antarctica). Moreover, a non-invasive method to analyze MPs, consisting in filtration after water sampling and analysis of the dried filter through Fourier Transform Infrared Spectroscopy (FTIR) 2D Imaging, using an FPA detector, was proposed. The non-invasiveness of analytical set-up reduces potential bias and allows subsequent analysis of the filter sample for determination of other classes of contaminants. MPs ranged from 0.0032 to 1.18 particle per m3 of seawater, with a mean value of 0.17 ± 0.34 particle m−3, showing concentrations lower than those found in the oceans worldwide. MPs included fragments (mean 71.9 ± 21.6%), fibers (mean 12.7 ± 14.3%), and others (mean 15.4 ± 12.8%). The presence of different types of MPs was confirmed by FTIR spectroscopy, with predominant abundance of polyethylene and polypropylene. The potential environmental impact arising from scientific activities, such as marine activities for scientific purposes, and from the sewage treatment plant, was also evidenced.
Keywords: Rosshavet; Sørishavet; forurensning; mikroplast; miljøgifter

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

A global ocean climatology of preindustrial and modern ocean δ13C - Eide, Marie; Olsen, Are; Ninnemann, Ulysses S; Johannessen, Truls (Global Biogeochemical Cycles, 2017)
We present a global ocean climatology of dissolved inorganic carbon δ13C (‰) corrected for the 13C-Suess effect, preindustrial δ13C. This was constructed by first using Olsen and Ninnemann's (2010) back-calculation method on data from 25 World Ocean Circulation Experiment cruises to reconstruct the preindustrial δ13C on sections spanning all major oceans. Next, we developed five multilinear regression equations, one for each major ocean basin, which were applied on the World Ocean Atlas data to construct the climatology. This reveals the natural δ13C distribution in the global ocean. Compared to the modern distribution, the preindustrial δ13C spans a larger range of values. The maxima, of up to 1.8‰, occurs in the subtropical gyres of all basins, in the upper and intermediate waters of the North Atlantic, as well as in mode waters with a Southern Ocean origin. Particularly strong gradients occur at intermediate depths, revealing a strong potential for using δ13C as a tracer for changes in water mass geometry at these levels. Further, we identify a much tighter relationship between δ13C and apparent oxygen utilization (AOU) than between δ13C and phosphate. This arises because, in contrast to phosphate, AOU and δ13C are both partly reset when waters are ventilated in the Southern Ocean and underscore that δ13C is a highly robust proxy for past changes in ocean oxygen content and ocean ventilation. Our global preindustrial δ13C climatology is openly accessible and can be used, for example, for improved model evaluation and interpretation of sediment δ13C records.
Keywords: Sørishavet; klimatologi; uorganisk karbon; vannmasser

Spring phenology shapes the spatial foraging behavior of Antarctic petrels - Fauchald, Per; Tarroux, Arnaud; Tveraa, Torkild; Cherel, Yves; Ropert-Coudert, Yan; Kato, Akiko; Love, Oliver P; Varpe, Øystein; Descamps, Sébastien (Marine Ecology Progress Series, 2017)
In polar seas, the seasonal melting of ice triggers the development of an open-waterecosystem characterized by short-lived algal blooms, the grazing and development of zooplank-ton, and the influx of avian and mammalian predators. Spatial heterogeneity in the timing of icemelt generates temporal variability in the development of these events across the habitat, offeringa natural framework to assess how foraging marine predators respond to the spring phenology.We combined 4 yr of tracking data of Antarctic petrels Thalassoica antarcticawith synopticremote-sensing data on sea ice and chlorophyll ato test how the development of melting ice andprimary production drive Antarctic petrel foraging. Cross-correlation analyses of first-passagetime revealed that Antarctic petrels utilized foraging areas with a spatial scale of 300 km. Theseareas changed position or disappeared within 10 to 30 d and showed no spatial consistency amongyears. Generalized additive model (GAM) analyses suggested that the presence of foraging areaswas related to the time since ice melt. Antarctic petrels concentrated their search effort in meltingareas and in areas that had reached an age of 50 to 60 d from the date of ice melt. We found nosignificant relationship between search effort and chlorophyll aconcentration. We suggest thatthese foraging patterns were related to the vertical distribution and profitability of the main prey,the Antarctic krill Euphausia superba. Our study demonstrates that the annual ice melt in theSouthern Ocean shapes the development of a highly patchy and elusive food web, underscoringthe importance of flexible foraging strategies among top predators. KEY WORDS: Area-restricted search · Euphausia superba· Marginal ice zone · Phytoplanktonbiomass · Procellariiformes · Sea ice dynamics · Southern Ocean · Thalassoica antarctica
Keywords: Sørishavet; Weddellhavet; biologi; biomasse; fenologi; fytoplankton; fôring; havis; klima; petreller; sjøis; smelting; økosystemer

Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica - Goel, Vikram; Brown, Joel; Matsuoka, Kenichi (The Cryosphere, 2017)
The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below the current sea level. Shallow radar-detected isochrones dated with a firn core reveal that the surface mass balance is higher on the south-eastern (upwind) slope than on the north-western (downwind) slope by ∼ 37 %, and this pattern has persisted for at least the past decade. Moreover, arches in radar stratigraphy suggest that the summit of the ice rise has been stable for ∼ 600 years. Ensemble estimates of the mass balance using the input–output method show that this ice rise has thickened by 0.12–0.37 m ice equivalent per year over the past decade.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Channelized Melting Drives Thinning Under a Rapidly Melting Antarctic Ice Shelf - Gourmelen, Noel; Goldberg, Dan N; Snow, Kate; Henley, Sian F; Bingham, Robert G; Kimura, Satoshi; Hogg, Anna E; Shepherd, Andrew; Mouginot, Jeremie; Lenaerts, Jan T M; Ligtenberg, Stefan R M; van de Berg, Willem Jan (Geophysical Research Letters, 2017)
Ice shelves play a vital role in regulating loss of grounded ice and in supplying freshwater to coastal seas. However, melt variability within ice shelves is poorly constrained and may be instrumental in driving ice shelf imbalance and collapse. High-resolution altimetry measurements from 2010 to 2016 show that Dotson Ice Shelf (DIS), West Antarctica, thins in response to basal melting focused along a single 5 km-wide and 60 km-long channel extending from the ice shelf's grounding zone to its calving front. If focused thinning continues at present rates, the channel will melt through, and the ice shelf collapse, within 40–50 years, almost two centuries before collapse is projected from the average thinning rate. Our findings provide evidence of basal melt-driven sub-ice shelf channel formation and its potential for accelerating the weakening of ice shelves.
Keywords: Sørishavet; glasiologi; havnivå; innlandsis; isbrem; isshelf; smelting

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

Om C.A. Larsen og starten på pelagisk hvalfangst - Iversen, Ragnar (Skipet, 2017)
Keywords: Sørishavet; historie; hvalfangst

Oceanographic Controls on the Variability of Ice-Shelf Basal Melting and Circulation of Glacial Meltwater in the Amundsen Sea Embayment, Antarctica - Kimura, Satoshi; Jenkins, Adrian; Regan, Heather; Holland, Paul R; Assmann, Karen M; Whitt, Daniel B; Van Wessem, Melchoir; van de Berg, Willem Jan; Reijmer, Carleen H; Dutrieux, Pierre (Journal of Geophysical Research: Oceans, 2017)
Ice shelves in the Amundsen Sea Embayment have thinned, accelerating the seaward flow of ice sheets upstream over recent decades. This imbalance is caused by an increase in the ocean-driven melting of the ice shelves. Observations and models show that the ocean heat content reaching the ice shelves is sensitive to the depth of thermocline, which separates the cool, fresh surface waters from warm, salty waters. Yet the processes controlling the variability of thermocline depth remain poorly constrained. Here we quantify the oceanic conditions and ocean-driven melting of Cosgrove, Pine Island Glacier (PIG), Thwaites, Crosson, and Dotson ice shelves in the Amundsen Sea Embayment from 1991 to 2014 using a general circulation model. Ice-shelf melting is coupled to variability in the wind field and the sea-ice motions over the continental shelf break and associated onshore advection of warm waters in deep troughs. The layer of warm, salty waters at the calving front of PIG and Thwaites is thicker in austral spring (June–October) than in austral summer (December–March), whereas the seasonal cycle at the calving front of Dotson is reversed. Furthermore, the ocean-driven melting in PIG is enhanced by an asymmetric response to changes in ocean heat transport anomalies at the continental shelf break: melting responds more rapidly to increases in ocean heat transport than to decreases. This asymmetry is caused by the inland deepening of bathymetry and the glacial meltwater circulation around the ice shelf.
Keywords: Amundsenhavet; Sørishavet; batymetri; brehylle; glasiologi; isbrem; ismeltvann; isshelf; klimatologi; oseanografi

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

Molluscan assemblages associated with Gigartina beds in the Strait of Magellan and the South Shetland Islands (Antarctica): a comparison of composition and abundance - Rosenfeld, Sebastián; Aldea, Cristian; Ojeda, Jaime; Marambio, Johanna; Hüne, Mathias; Troncoso, Jesús S; Mansilla, Andrés (Polar Research, 2017)
In this paper we evaluated the composition and abundance of molluscs associated with beds of the red algae Gigartina, located in the South Shetland Islands (Antarctic Peninsula) and the Strait of Magellan (southern Chile). During the summer season of 2013, samples were obtained by scuba diving using a 0.25 m2 quadrat, arranged randomly within the bed. We extracted a total of 15 quadrats per sampling site. For Antarctic Peninsula beds the most abundant species were the bivalve Lissarca miliaris (233 individuals) and the gastropod Laevilacunaria antarctica (94 individuals), while for Strait of Magellan beds the most abundant species was the polyplacophoran Callochiton puniceus (36 individuals). Comparative analysis between the two molluscan assemblages showed significant differences in the faunal composition between the Antarctic Peninsula and Strait of Magellan (f = 64.474; p = 0.0001). Therefore, molluscs reported in both areas are characteristic of their respective biogeographic area. Finally, Gigartina species play an important role in the formation of patterns of abundance and diversity of the communities associated with them.
Keywords: Sørishavet; alger; biodiversitet; biogeokjemi; bløtdyr; havbunnen; muslinger; snegler

Seasonal cycle of hydrography on the eastern shelf of the Filchner Trough, Weddell Sea, Antarctica - Ryan, Svenja; Hattermann, Tore; Darelius, Elin Maria K; Schröder, Michael (Journal of Geophysical Research: Oceans, 2017)
Keywords: Sørishavet; Weddellhavet; hydrografi; isshelf; kontinentalsokkel; kontinentalsokler

Potential chemical defenses of Antarctic benthic organisms against marine bacteria - Sacristán-Soriano, Oriol; Angulo-Preckler, Carlos; Vázquez, Jennifer; Avila, Conxita (Polar Research, 2017)
The continental shelf of Antarctica harbours rich suspension-feeding macroinvertebrate communities that are continuously exposed to large populations of free-living microbes. To avoid settlement or fouling by undesirable microorganisms that could cause infection or collapse filter-feeding systems, these macroinvertebrates might regulate the epibiotic microbial mat through chemical interactions. In Antarctic chemical ecology, the antibacterial roles of natural products remain mostly unknown. A necessary first step is to identify organisms that produce compounds with potential ecological relevance. For that reason, we tested the crude organic extracts of 116 taxa of Antarctic benthic organisms for antibacterial activity against a panel of seven strains of marine bacteria. Nine out of 11 phyla tested had antibacterial properties. However, inhibitory activity was quite selective and species-specific. These patterns suggest that Antarctic benthic organisms may produce diverse bioactive metabolites with different antibacterial activities or, alternatively, those contrasting profiles may be shaped by environmental and biological interactions acting at a small spatial scale. The reasons of such selectivity remain to be further investigated and may contribute to the identification of bioactive compounds with pharmaceutical applications.
Keywords: Sørishavet; alger; biodiversitet; biologi; fauna; kjemisk; kontinentalsokkel; makrovirvelløse dyr; mikrober; mikroorganismer; økologi

Geomorphic and shallow-acoustic investigation of an Antarctic Peninsula fjord system using high-resolution ROV and shipboard geophysical observations: Ice dynamics and behaviour since the Last Glacial Maximum - García, Marga; Dowdeswell, J.A.; Noormets, R.; Hogan, K.A.; Evans, J.; Ó Cofaigh, C.; Larter, R.D. (Quaternary Science Reviews, 2016)
Detailed bathymetric and sub-bottom acoustic observations in Bourgeois Fjord (Marguerite Bay, Antarctic Peninsula) provide evidence on sedimentary processes and glacier dynamics during the last glacial cycle. Submarine landforms observed in the 50 km-long fjord, from the margins of modern tidewater glaciers to the now ice-distal Marguerite Bay, are described and interpreted. The landforms are grouped into four morpho-sedimentary systems: (i) glacial advance and full-glacial; (ii) subglacial and ice-marginal meltwater; (iii) glacial retreat and neoglaciation; and (iv) Holocene mass-wasting. These morpho-sedimentary systems have been integrated with morphological studies of the Marguerite Bay continental shelf and analysed in terms of the specific sedimentary processes and/or stages of the glacial cycle. They demonstrate the action of an ice-sheet outlet glacier that produced drumlins and crag-and-tail features in the main and outer fjord. Meltwater processes eroded bedrock channels and ponds infilled by fine-grained sediments. Following the last deglaciation of the fjord at about 9000 yr BP, subsequent Holocene neoglacial activity involved minor readvances of a tidewater glacier terminus in Blind Bay. Recent stillstands and/or minor readvances are inferred from the presence of a major transverse moraine that indicates grounded ice stabilization, probably during the Little Ice Age, and a series of smaller landforms that reveal intermittent minor readvances. Mass-wasting processes also affected the walls of the fjord and produced scars and fan-shaped deposits during the Holocene. Glacier-terminus changes during the last six decades, derived from satellite images and aerial photographs, reveal variable behaviour of adjacent tidewater glaciers. The smaller glaciers show the most marked recent retreat, influenced by regional physiography and catchment-area size.
Keywords: Antarctic Peninsula; Antarktis; Fjord systems; Geomorphology; Glacial sedimentary processes; Last Glacial Maximum; ROV-Derived bathymetry; Sørishavet; batymetri; geomorfologi

Winter distribution and size structure of Antarctic krill Euphausia superba populations in-shore along the West Antarctic Peninsula - Cleary, Alison C; Durbin, Edward G; Casas, Maria C; Zhou, Meng (Marine Ecology Progress Series, 2016)
Antarctic krill Euphausia superba are a key component of food webs in the maritime West Antarctic Peninsula, and their life history is tied to the seasonal cycles of sea ice and primary production in the region. Previous work has shown a general in-shore migration of krill in winter in this region; however, the very near-shore has not often been sampled as part of these surveys. We investigated distribution, abundance, and size structure of krill in 3 fjordic bays along the peninsula, and in the adjacent Gerlache Strait area using vertically stratified MOCNESS net tows and ADCP acoustic biomass estimates. Krill abundance was high within bays, with net estimated densities exceeding 60 krill m-3, while acoustic estimates were an order of magnitude higher. Krill within bays were larger than krill in the Gerlache Strait. Within bays, krill aggregations were observed near the seafloor during the day with aggregations extending to the sediment interface, and exhibited diel vertical migration higher into the water column at night. We suggest these high winter krill abundances within fjords are indicative of an active seasonal migration by krill in the peninsula region. Potential drivers for such a migration include reduced advective losses and costs, and availability of sediment food resources within fjords. Seasonally near-shore krill may also affect stock and recruitment assessments and may have implications for managing the krill fishery in this area. KEYWORDS: Euphausiid · Abundance · Diel vertical migration · DVM · WAP · Fjord.
Keywords: Sørishavet; biomasse; hydrografi; krill; marin biologi; oseanografi; zooplankton

At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Akiko, Kato; Krafft, Bjørn A; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS One, 2016)
Kommersielle fiskerier kan påvirke marine økosystemer og bestander av topp-predatorer som sjøfugl. I Sørishavet foregår et ekstensivt fiske etter Antarktisk krill (Euphausia superba), og dette er antatt å øke. En sammenligning av fordeling og uttak hos fiskeriene og tilsvarende hos topp-predatorene er nødvendig for å forutsi fiskerirelaterte påvirkninger på krillavhengige predatorer. I dette studiet kartla vi næringssøksområdene hos Antarktispetrell (Thalassoica antarctica) som hekker i verdens største koloni (Svarthammaren, Dronning Maud land) over en treårsperiode. Vi fant at det romlige overlappet mellom krillfiskerier og næringssøkende Antarktispetrell generelt var lite. Konkurranse mellom Antarktispetrell og krill-fiskerier er for tiden neglisjerbart, men kan øke hvis fiskeriet etter krill øker.
Keywords: Dronning Maud Land; Sørishavet; fiskeriforvaltning; krill; marinbiologi; ornitologi; økosystem

Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

Parasites of the Antarctic toothfish (Dissostichus mawsoni Norman, 1937) (Perciformes, Nototheniidae) in the Pacific sector of the Antarctic - Gordeev, Ilya I; Sokolov, Sergey G (Polar Research, 2016)
The Antarctic toothfish (Dissostichus mawsoni Norman, 1937) is one of the main target species of commercial fisheries in the Antarctic. It is an endemic and is found along the shelf of Antarctica, as well as on the slopes of seamounts, underwater elevations and islands in the sub-Antarctic. It feeds on a variety of fish and cephalopods and can be an intermediate/paratenic host of some helminthes, whose final hosts are whales, seals, large rays and sharks. This article presents new data on toothfish infection in the Pacific sector of the Antarctic. Specimens were examined during commercial longline fishing in the Ross Sea and the Amundsen Sea in January–February 2013. Fourteen species of parasites were found using standard parasitological methods and genetic analysis. Keywords: Toothfish; parasites; Antarctic fisheries; CCAMLR; infection; Southern Ocean.
Keywords: Rosshavet; Sørishavet; fiskeri; infeksjon; parasitter; parasittologi

Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C; Firing, Yvonne (Journal of Geophysical Research: Oceans, 2016)
Ice shelves around Antarctica are vulnerable to an increase in ocean-driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice-shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice-shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation-rate-based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin-Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting.
Keywords: Sørishavet; batymetri; brehylle; isbrem; isshelf; klimatologi; målinger; oseanografi; smeltevann; vannmasser

Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present-day performance and future projection - Nevison, Cynthia; Manizza, Manfredi; Keeling, Ralph; Stephens, Britton; Bent, Jonathan; Dunne, John P; Ilyina, Tatiana; Long, Matthew; Resplandy, Laure; Tjiputra, Jerry; Yukimoto, Seiji (Geophysical Research Letters, 2016)
Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2 + 1.1 CO2) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air-sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present-day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; meteorologi; oseanografi

Scleractinian corals recorded in the Argentinean Antarctic expeditions between 2012 and 2014, with comments on Flabellum (Flabellum) areum Cairns, 1982 - Schejter, Laura; Bremec, Claudia S; Cairns, Stephen D (Polar Research, 2016)
In this contribution, we provide a list of the scleractinian corals recorded during the Argentinean Antarctic expeditions on board the oceanographic vessel Puerto Deseado (Argentina) in the austral summers in 2012, 2013 and 2014. The identified taxa consist of six solitary species (Flabellum impensum, F. flexuosum, F. areum, Caryophyllia antarctica, Paraconotrochus antarcticus and Javania antarctica), recorded from 19 sampling sites located off the Antarctic Peninsula and South Shetland and South Orkney islands. We also update the information of F. areum, previously known only from south-west Atlantic waters, extending its distribution range to Antarctic waters and its upper bathymetric range to 218 m. Keywords: cold-water corals; Antarctica; range extension; bathymetric range extension; Scleractinia.
Keywords: Sørishavet; ekspedisjoner; koraller; marin zoologi; oseanografi

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Publisher: Routledge
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi

Pacific-Atlantic Circumpolar Deep Water coupling during the last 500 ka - Ullermann, Johannes; Lamy, Frank; Ninnemann, Ulysses; Lembke-Jene, Lester; Gersonde, Rainer; Tiedemann, Ralf (Paleoceanography, 2016)
Investigating the interbasin deepwater exchange between the Pacific and Atlantic Oceans over glacial-interglacial climate cycles is important for understanding circum-Antarctic Southern Ocean circulation changes and their impact on the global Meridional Overturning Circulation. We use benthic foraminiferal δ13C records from the southern East Pacific Rise to characterize the δ13C composition of Circumpolar Deep Water in the South Pacific, prior to its transit through the Drake Passage into the South Atlantic. A comparison with published South Atlantic deepwater records from the northern Cape Basin suggests a continuous water mass exchange throughout the past 500 ka. Almost identical glacial-interglacial δ13C variations imply a common deepwater evolution in both basins suggesting persistent Circumpolar Deep Water exchange and homogenization. By contrast, deeper abyssal waters occupying the more southern Cape Basin and the southernmost South Atlantic have lower δ13C values during most, but not all, stadial periods. We conclude that these values represent the influence of a more southern water mass, perhaps Antarctic Bottom Water (AABW). During many interglacials and some glacial periods, the gradient between Circumpolar Deep Water and the deeper southern Cape Basin bottom water disappears suggesting either no presence of AABW or indistinguishable δ13C values of both water masses.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; klimatologi; oseanografi; paleoseanografi

Advancements in decadal climate predictability: The role of nonoceanic drivers - Bellucci, Alessio; Haarsma, Rein; Bellouin, Nicolas; Booth, Ben B; Cagnazzo, Chiara; van den Hurk, Bart; Keenlyside, Noel; Koenigk, Torben; Massonnet, François; Materia, Stefano; Weiss, M (Reviews of Geophysics, 2015)
We review recent progress in understanding the role of sea ice, land surface, stratosphere, and aerosols in decadal-scale predictability and discuss the perspectives for improving the predictive capabilities of current Earth system models (ESMs). These constituents have received relatively little attention because their contribution to the slow climatic manifold is controversial in comparison to that of the large heat capacity of the oceans. Furthermore, their initialization as well as their representation in state-of-the-art climate models remains a challenge. Numerous extraoceanic processes that could be active over the decadal range are proposed. Potential predictability associated with the aforementioned, poorly represented, and scarcely observed constituents of the climate system has been primarily inspected through numerical simulations performed under idealized experimental settings. The impact, however, on practical decadal predictions, conducted with realistically initialized full-fledged climate models, is still largely unexploited. Enhancing initial-value predictability through an improved model initialization appears to be a viable option for land surface, sea ice, and, marginally, the stratosphere. Similarly, capturing future aerosol emission storylines might lead to an improved representation of both global and regional short-term climatic changes. In addition to these factors, a key role on the overall predictive ability of ESMs is expected to be played by an accurate representation of processes associated with specific components of the climate system. These act as “signal carriers,” transferring across the climatic phase space the information associated with the initial state and boundary forcings, and dynamically bridging different (otherwise unconnected) subsystems. Through this mechanism, Earth system components trigger low-frequency variability modes, thus extending the predictability beyond the seasonal scale.
Keywords: Sørishavet; geofysikk; havis; klimaendringer; klimamodeller; meteorologi; polarområdene; sjøis

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Publisher: Nøtterøy historielag
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Application of remotely piloted aircraft systems in observing the atmospheric boundary layer over Antarctic sea ice in winter - Jonassen, Marius O; Tisler, Priit; Altstädter, Barbara; Scholtz, Andreas; Vihma, Timo; Lampert, Astrid; König-Langlo, Gert; Lüpkes, Christof (Polar Research, 2015)
The main aim of this paper is to explore the potential of combining measurements from fixed- and rotary-wing remotely piloted aircraft systems (RPAS) to complement data sets from radio soundings as well as ship and sea-ice-based instrumentation for atmospheric boundary layer (ABL) profiling. This study represents a proof-of-concept of RPAS observations in the Antarctic sea-ice zone. We present first results from the RV Polarstern Antarctic winter expedition in the Weddell Sea in June–August 2013, during which three RPAS were operated to measure temperature, humidity and wind; a fixed-wing small unmanned meteorological observer (SUMO), a fixed-wing meteorological mini-aerial vehicle, and an advanced mission and operation research quadcopter. A total of 86 RPAS flights showed a strongly varying ABL structure ranging from slightly unstable temperature stratification near the surface to conditions with strong surface-based temperature inversions. The RPAS observations supplement the regular upper air soundings and standard meteorological measurements made during the campaign. The SUMO and quadcopter temperature profiles agree very well and, excluding cases with strong temperature inversions, 70% of the variance in the difference between the SUMO and quadcopter temperature profiles can be explained by natural, temporal, temperature fluctuations. Strong temperature inversions cause the largest differences, which are induced by SUMO’s high climb rates and slow sensor response. Under such conditions, the quadcopter, with its slower climb rate and faster sensor, is very useful in obtaining accurate temperature profiles in the lowest 100 m above the sea ice. Keywords: Remotely piloted aircraft systems; unmanned aerial vehicles; Weddell Sea; polar meteorology; Antarctic; boundary layer meteorology.
Keywords: Sørishavet; Weddellhavet; fjernstyrte flysystemer; havis; meteorologi; målinger; observasjoner; sjøis; ubemannede luftfartøyer

A roadmap for Antarctic and Southern Ocean science for the next two decades and beyond - Kennicutt, M.C.; Chown, S.L.; Cassano, J.J.; Liggett, D.; Peck, L.S.; Massom, R.; Rintoul, S.R.; Storey, J.; Vaughan, D.G.; Wilson, T.J.; Allison, I.; Ayton, J.; et al. (Antarctic Science, 2015)
Antarctic and Southern Ocean science is vital to understanding natural variability, the processes that govern global change and the role of humans in the Earth and climate system. The potential for new knowledge to be gained from future Antarctic science is substantial. Therefore, the international Antarctic community came together to ‘scan the horizon’ to identify the highest priority scientific questions that researchers should aspire to answer in the next two decades and beyond. Wide consultation was a fundamental principle for the development of a collective, international view of the most important future directions in Antarctic science. From the many possibilities, the horizon scan identified 80 key scientific questions through structured debate, discussion, revision and voting. Questions were clustered into seven topics: i) Antarctic atmosphere and global connections, ii) Southern Ocean and sea ice in a warming world, iii) ice sheet and sea level, iv) the dynamic Earth, v) life on the precipice, vi) near-Earth space and beyond, and vii) human presence in Antarctica. Answering the questions identified by the horizon scan will require innovative experimental designs, novel applications of technology, invention of next-generation field and laboratory approaches, and expanded observing systems and networks. Unbiased, non-contaminating procedures will be required to retrieve the requisite air, biota, sediment, rock, ice and water samples. Sustained year-round access to Antarctica and the Southern Ocean will be essential to increase winter-time measurements. Improved models are needed that represent Antarctica and the Southern Ocean in the Earth System, and provide predictions at spatial and temporal resolutions useful for decision making. A co-ordinated portfolio of cross-disciplinary science, based on new models of international collaboration, will be essential as no scientist, programme or nation can realize these aspirations alone.
Edition: 2014/09/18 Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; forskning; teknologi

An Antarctic krill (Euphausia superba) hotspot: population characteristics, abundance and vertical structure explored from a krill fishing vessel - Krafft, Bjørn Arne; Skaret, Georg; Knutsen, Tor (Polar Biology, 2015)
Keywords: Sørishavet; krill; marin biologi; plankton; zooplankton

Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

The potential response of the hydrate reservoir in the South Shetland Margin, Antarctic Peninsula, to ocean warming over the 21st century - Marín-Moreno, Hector; Giustiniani, Michela; Tinivella, Umberta (Polar Research, 2015)
In the South Shetland Margin (SSM), Antarctic Peninsula, a bottom-simulating reflector indicates the presence of hydrate between ca. 500 and 3000 m water depth (mwd). The cold seabed temperatures allow hydrate stability at shallower water depths. During the past five decades, the Antarctic Peninsula has been warming up faster than any other part of the Southern Hemisphere, and long-term ocean warming could affect the stability of the SSM hydrate reservoir at shallow waters. Here, we model the transient response of the SSM hydrate reservoir between 375 and 450 mwd to ocean warming for the period 1958–2100. For the period 1958–2010, seabed temperatures are given by oceanographic measurements in the area, and for 2010–2100 by two temperature scenarios represented by the observed trends for the periods 1960–2010 (0.0034°C y−1) and 1980–2010 (0.023°C y−1). Our results show no hydrate-sourced methane emissions for an ocean warming rate at the seabed of 0.0034 °C y−1. For a rate of 0.023°C y−1, emissions start in 2028 at 375 mwd and extend to 442 mwd at an average rate of about 0.91 mwd y−1, releasing ca. 1.13×103 mol y−1 of methane per metre along the margin by 2100. These emissions originate from dissociation at the top of the hydrate layer, a physical process that steady-state modelling cannot represent. Our results are speculative on account of the lack of direct evidence of a shallow water hydrate reservoir, but they illustrate that the SSM is a key area to observe the effects of ocean warming-induced hydrate dissociation in the coming decades. Keywords: Hydrate; ocean warming; methane emissions; transient modelling; South Shetland Margin; Antarctic Peninsula.
Keywords: Sørishavet; geofysikk; havbunnen; havoppvarming; metanutslipp; oseanografi

Antarctic ice rises and rumples: their properties and significance for ice-sheet dynamics and evolution - Matsuoka, Kenichi; Hindmarsh, Richard C A; Moholdt, Geir; Bentley, Michael J; Pritchard, Hamish D; Brown, Joel; Conway, Howard; Drews, Reinhard; Durand, Gaël; Goldberg, Daniel; Hattermann, Tore; Kingslake, Jonathan; et al. (Earth-Science Reviews, 2015)
Locally grounded features in ice shelves, called ice rises and rumples, play a key role buttressing discharge from the Antarctic Ice Sheet and regulating its contribution to sea level. Ice rises typically rise several hundreds of meters above the surrounding ice shelf; shelf flow is diverted around them. On the other hand, shelf ice flows across ice rumples, which typically rise only a few tens of meters above the ice shelf. Ice rises contain rich histories of deglaciation and climate that extend back over timescales ranging from a few millennia to beyond the last glacial maximum. Numerical model results have shown that the buttressing effects of ice rises and rumples are significant, but details of processes and how they evolve remain poorly understood. Fundamental information about the conditions and processes that cause transitions between floating ice shelves, ice rises and ice rumples is needed in order to assess their impact on ice-sheet behavior. Targeted high-resolution observational data are needed to evaluate and improve prognostic numerical models and parameterizations of the effects of small-scale pinning points on grounding-zone dynamics.
Keywords: Antarktis; Sørishavet; glasiologi; havis

Ozone-induced climate change propped up by the Southern Hemisphere oceanic front - Ogawa, Fumiaki; Omrani, Nour-Eddine; Nishii, Kazuaki; Nakamura, Hisashi; Keenlyside, Noel (Geophysical Research Letters, 2015)
The late twentieth century was marked by a significant summertime trend in the Southern Annular Mode (SAM), the dominant mode of tropospheric variability in the extratropical Southern Hemisphere (SH). This trend with poleward shifting tropospheric westerlies was attributed to downward propagation of stratospheric changes induced by ozone depletion. However, the role of the ocean in setting the SAM response to ozone depletion and its dynamical forcing remains unclear. Here we show, using idealized experiments with a state-of-the-art atmospheric model and analysis of Intergovernmental Panel on Climate Change climate simulations, that frontal sea surface temperature gradients in the midlatitude SH are critical for translating the ozone-induced stratospheric changes down to the surface. This happens through excitation of wave forcing, which controls the vertical connection of the tropospheric SAM with the stratosphere and shows the importance of internal tropospheric dynamics for stratosphere/troposphere coupling. Thus, improved simulation of oceanic fronts may reduce uncertainties in simulating SH ozone-induced climate changes.
Keywords: Sørishavet; geofysikk; havet; havstrømmer; klimaendringer; ozonhull; ozonlaget

First record of humpback anglerfish (Melanocetus johnsonii) (Melanocetidae) in Antarctic waters - Orlov, Alexei M.; Orlova, Svetlana Y.; Volkov, Alexander A.; Pelenev, Dmitry V. (Polar Research, 2015)
The first record of the humpback anglerfish (Melanocetus johnsonii) in Antarctic waters (Ross Sea) is documented. Species identification is confirmed by the structure of the escal bulb and analysis of the mitochondrial cytochrome oxidase subunit I (COI) gene. This record extends the known range of M. johnsonii by more than 1000 nm to the south. The taxonomic status of Melanocetus species in Antarctic waters is discussed. Keywords: Melanocetus sp.; new record; taxonomy; distribution; Ross Sea; Antarctic.
Keywords: Rosshavet; Sørishavet; fisker; genetisk analyse; marin zoologi; taksonomi; zoogeografi

Seismic signals from large, tabular icebergs drifting along the Dronning Maud Land coast, Antarctica, and their significance for iceberg monitoring - Pirli, Myrto; Matsuoka, Kenichi; Schweitzer, Johannes; Moholdt, Geir (Journal of Glaciology, 2015)
In this study, we analyze a large dataset of seismic signals, recorded by station TROLL in Dronning Maud Land, Antarctica. The signals, recorded in April–December 2012, came from sources near the edge of the ice shelves, at distances of 230–500 km from TROLL. The sources, which moved westward with time, could be associated with four large, tabular icebergs, drifting between 15° E and 8° W. Combining the seismological data with information from satellite remote sensing, we find that one-third of the signals can be attributed to individual icebergs. The trajectories of three of the associated icebergs are known through iceberg-tracking databases, whereas the fourth, a fragment of one of the other three, is untracked, and only scarce information is available from satellite imagery. The observed seismic signals exhibit a wide variety of frequency characteristics, from unstructured episodes to occurrences of iceberg harmonic tremor. Although we are not able to determine the exact cause of the signals, we classify them into five classes on a phenomenological basis. This study demonstrates the potential of regional seismic networks for iceberg monitoring as supplementary resources to information obtained with remote-sensing technologies.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; isfjell; teknologi

More than passive drifters: a stochastic dynamic model for the movement of Antarctic krill - Richerson, Kate; Watters, George M; Santora, Jarrod A; Schroeder, Isaac D; Mangel, Marc (Marine Ecology Progress Series, 2015)
Antarctic krill Euphausia superba are a key part of the marine food web and are the target of the largest fishery in the Southern Ocean. Although ecosystem and management models typically assume that krill are passive drifters, their relatively large size and strong swimming ability suggest that the active movement of krill may play an important role in their spatial distribution. Thus, active swimming behavior by krill may influence spatial structure of food web interactions (e.g. feeding behavior of seabirds and marine mammals) and regional commercial fishery activity. The objective of this work was to model the potential for active movement to affect krill distribution, and consequently growth, reproductive success, and survival. We used state-dependent life history theory, implemented by stochastic dynamic programming, in combination with spatial information on food availability, current velocity, temperature, and predation risk, to predict krill swimming behavior near the northern Antarctic Peninsula. We found that including active krill behavior resulted in distribution patterns that are associated with increased survival, growth, and reproductive success compared to a model that treats krill as passive drifters. The expected reproductive success of actively behaving krill was about 70% greater than that of passively diffusing krill, suggesting that there are strong selective pressures for active behavior along oceanic drift trajectories. This modeling framework will benefit assessments of new catch limits as krill fishing grounds are partitioned into smaller spatial management units. KEYWORDS: Euphausia superba · Behavior · Stochastic dynamic programming · Management · Advection · Southern Ocean
Keywords: Sørishavet; krill; marin biologi; oseanografi; plankton; økosystemer

Sessile macro-epibiotic community of solitary ascidians, ecosystem engineers in soft substrates of Potter Cove, Antarctica - Rimondino, Clara; Torre, Luciana; Sahade, Ricardo; Tatián, Marcos (Polar Research, 2015)
The muddy bottoms of inner Potter Cove, King George Island (Isla 25 de Mayo), South Shetlands, Antarctica, show a high density and richness of macrobenthic species, particularly ascidians. In other areas, ascidians have been reported to play the role of ecosystem engineers, as they support a significant number of epibionts, increasing benthic diversity. In this study, a total of 21 sessile macro-epibiotic taxa present on the ascidian species Corella antarctica Sluiter, 1905, Cnemidocarpa verrucosa (Lesson, 1830) and Molgula pedunculata Herdman, 1881 were identified, with Bryozoa being the most diverse. There were differences between the three ascidian species in terms of richness, percent cover and diversity of sessile macro-epibionts. The morphological characteristics of the tunic surface, the available area for colonization (and its relation with the age of the basibiont individuals) and the pH of the ascidian tunic seem to explain the observed differences. Recent environmental changes in the study area (increase of suspended particulate matter caused by glaciers retreat) have been related to observed shifts in the benthic community structure, negatively affecting the abundance and distribution of the studied ascidian species. Considering the diversity of sessile macro-epibionts found on these species, the impact of environmental shifts may be greater than that estimated so far. Keywords: Sessile macro-epibiont; ascidian; Antarctica; ecosystem- engineer.
Keywords: Sørishavet; bentiske organismer; biodiversitet; bryozoa; havbunnen; sekkdyr; økologi; økosystemer

Multi-frequency observations of seawater carbonate chemistry on the central coast of the western Antarctic Peninsula - Schram, Julie B; Schoenrock, Kathryn M; McClintock, James B; Amsler, Charles D; Angus, Robert A (Polar Research, 2015)
Assessments of benthic coastal seawater carbonate chemistry in Antarctica are sparse. The studies have generally been short in duration, during the austral spring/summer, under sea ice, or offshore in ice-free water. Herein we present multi-frequency measurements for seawater collected from the shallow coastal benthos on a weekly schedule over one year (May 2012–May 2013), daily schedule over three months (March–May 2013) and semidiurnal schedule over five weeks (March–April 2013). A notable pH increase (max pH = 8.62) occurred in the late austral spring/summer (November–December 2012), coinciding with sea-ice break-out and subsequent increase in primary productivity. We detected semidiurnal variation in seawater pH with a maximum variation of 0.13 pH units during the day and 0.11 pH units during the night. Daily variation in pH is likely related to biological activity, consistent with previous research. We calculated the variation in dissolved inorganic carbon (DIC) over each seawater measurement frequency, focusing on the primary DIC drivers in the Palmer Station region. From this, we estimated net biological activity and found it accounts for the greatest variations in DIC. Our seasonal data suggest that this coastal region tends to act as a carbon dioxide source during austral winter months and as a strong sink during the summer. These data characterize present-day seawater carbonate chemistry and the extent to which these measures vary over multiple time scales. This information will inform future experiments designed to evaluate the vulnerability of coastal benthic Antarctic marine organisms to ocean acidification. Keywords: Antarctica; aragonite; calcite; pH; seawater chemistry; total alkalinity.
Keywords: Sørishavet; analyser; havis; kjemisk; sjøis; sjøvann

Protists in the polar regions: comparing occurrence in the Arctic and Southern oceans using pyrosequencing - Wolf, Christian; Kilias, Estelle; Metfies, Katja (Polar Research, 2015)
In the ongoing discussion of the distribution of protists, whether they are globally distributed or endemic to one or both of the polar regions is the subject of heated debate. In this study, we compared next-generation sequencing data from the Arctic and the Southern oceans to reveal the extent of similarities and dissimilarities between the protist communities in the polar regions. We found a total overlap of operational taxonomic units (OTUs) between the two regions of 11.2%. On closer inspection of different taxonomic groups, the overlap ranged between 5.5% (haptophytes) and 14.5% (alveolates). Within the different groups, the proportion of OTUs occurring in both regions greatly differed between the polar regions. On the one hand, the overlap between these two regions is remarkable, given the geographical distance between them. On the other hand, one could expect a greater overlap of OTUs between these regions on account of the similar environmental conditions. The overlap suggests a connection between the polar regions for at least certain species or that the evolutionary divergence has been slow, relative to the timescales of isolation. The different proportions of common OTUs among the groups or regions may be a result of different life cycle strategies or environmental adaptations. Keywords: 18S rDNA; bipolar; next-generation sequencing; phytoplankton; polar regions; protist distribution.
Keywords: Sørishavet; fytoplankton; marin biologi; polarområdene; protoktister; pyrosekvensering; økosystemer

Reconstruction of changes in the Weddell Sea sector of the Antarctic Ice Sheet since the Last Glacial Maximum - Hillenbrand, Claus-Dieter; Bentley, Michael J.; Stolldorf, Travis D.; Hein, Andrew S.; Kuhn, Gerhard; Graham, Alastair G.C.; Fogwill, Christopher J.; Kristoffersen, Yngve; Smith, James. A.; Anderson, John B.; Larter, Robert D.; Melles, Martin; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
The Weddell Sea sector is one of the main formation sites for Antarctic Bottom Water and an outlet for about one fifth of Antarctica's continental ice volume. Over the last few decades, studies on glacial–geological records in this sector have provided conflicting reconstructions of changes in ice-sheet extent and ice-sheet thickness since the Last Glacial Maximum (LGM at ca 23–19 calibrated kiloyears before present, cal ka BP). Terrestrial geomorphological records and exposure ages obtained from rocks in the hinterland of the Weddell Sea, ice-sheet thickness constraints from ice cores and some radiocarbon dates on offshore sediments were interpreted to indicate no significant ice thickening and locally restricted grounding-line advance at the LGM. Other marine geological and geophysical studies concluded that subglacial bedforms mapped on the Weddell Sea continental shelf, subglacial deposits and sediments over-compacted by overriding ice recovered in cores, and the few available radiocarbon ages from marine sediments are consistent with major ice-sheet advance at the LGM. Reflecting the geological interpretations, different ice-sheet models have reconstructed conflicting LGM ice-sheet configurations for the Weddell Sea sector. Consequently, the estimated contributions of ice-sheet build-up in the Weddell Sea sector to the LGM sea-level low-stand of ∼130 m vary considerably. In this paper, we summarise and review the geological records of past ice-sheet margins and past ice-sheet elevations in the Weddell Sea sector. We compile marine and terrestrial chronological data constraining former ice-sheet size, thereby highlighting different levels of certainty, and present two alternative scenarios of the LGM ice-sheet configuration, including time-slice reconstructions for post-LGM grounding-line retreat. Moreover, we discuss consistencies and possible reasons for inconsistencies between the various reconstructions and propose objectives for future research. The aim of our study is to provide two alternative interpretations of glacial–geological datasets on Antarctic Ice-Sheet History for the Weddell Sea sector, which can be utilised to test and improve numerical ice-sheet models.
Keywords: Antarctica; Cosmogenic nuclide surface exposure age dating; Deglaciation; Geomorphology; Glacial history; Ice Shelf; Ice sheet; Last Glacial Maximum; Radiocarbon dating; Sea level; Sørishavet; Weddellhavet; geologi; geomorfologi; glasiologi

Thorbryn - en hvalbåts videverdige karriere - Basberg, Bjørn L (Norsk maritimt museum. Årbok, 2014)
Publisher: Norsk maritimt museum
Keywords: Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

A Nutritional-Toxicological Assessment of Antarctic Krill Oil versus Fish Oil Dietary Supplements - Bengtson Nash, Susan M; Schlabach, Martin; Nichols, Peter D (Nutrients, 2014)
Fish oil dietary supplements and complementary medicines are pitched to play a role of increasing strategic importance in meeting daily requirements of essential nutrients, such as long-chain (≥C20, LC) omega-3 polyunsaturated fatty acids and vitamin D. Recently a new product category, derived from Antarctic krill, has been launched on the omega-3 nutriceutical market. Antarctic krill oil is marketed as demonstrating a greater ease of absorption due to higher phospholipid content, as being sourced through sustainable fisheries and being free of toxins and pollutants; however, limited data is available on the latter component. Persistent Organic Pollutants (POP) encompass a range of toxic, man-made contaminants that accumulate preferentially in marine ecosystems and in the lipid reserves of organisms. Extraction and concentration of fish oils therefore represents an inherent nutritional-toxicological conflict. This study aimed to provide the first quantitative comparison of the nutritional (EPA and DHA) versus the toxicological profiles of Antarctic krill oil products, relative to various fish oil categories available on the Australian market. Krill oil products were found to adhere closely to EPA and DHA manufacturer specifications and overall were ranked as containing intermediate levels of POP contaminants when compared to the other products analysed. Monitoring of the pollutant content of fish and krill oil products will become increasingly important with expanding regulatory specifications for chemical thresholds.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; miljøgifter; plankton; toksikologi

Polynya dynamics drive primary production in the Larsen A and B embayments following ice shelf collapse - Cape, Mattias R.; Vernet, Maria; Kahru, Mati; Spreen, Gunnar (Journal of Geophysical Research: Oceans, 2014)
The climate-driven collapses of the Larsen A and B ice shelves have opened up new regions of the coastal Antarctic to the influence of sea ice resulting in increases in seasonal primary production. In this study, passive microwave remote sensing of sea ice concentration and satellite imagery of ocean color are employed to quantify the magnitude of and variability in open water area and net primary productivity (NPP) in the Larsen embayments between 1997 and 2011. Numerical model output provides context to analyze atmospheric forcing on the coastal ocean. Following ice shelf disintegration the embayments function as coastal, sensible heat polynyas. The Larsen A and B are as productive as other Antarctic shelf regions, with seasonally averaged daily NPP rates reaching 1232 and 1127 mg C m−2 d−1 and annual rates reaching 200 and 184 g C m−2 yr−1, respectively. A persistent cross-shelf gradient in NPP is present with higher productivity rates offshore, contrasting with patterns observed along the West Antarctic Peninsula. Embayment productivity is intimately tied to sea ice dynamics, with large interannual variability in NPP rates driven by open water area and the timing of embayment opening. Opening of the embayment is linked to periods of positive Southern Annular Mode and stronger westerlies, which lead to the vertical deflection of warm, maritime air over the peninsula and down the leeward side causing increases in surface air temperature and wind velocity. High productivity in these new polynyas is likely to have ramifications for organic matter export and marine ecosystem evolution.
Keywords: Sørishavet; brehylle; fjernmåling; fytoplankton; havis; isbrem; isshelf; klimaendringer; oseanografi; polynja; satellite bilder; sjøis

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

Commonness and rarity in the marine biosphere - Connolly, Sean R; MacNeil, M Aaron; Caley, M Julian; Knowlton, Nancy; Cripps, Ed; Hisano, Mizue; Thibaut, Loïc M; Bhattacharya, Bhaskar D; Benedetti-Cecchi, Lisandro; Brainard, Russell E; Brandt, Angelika; Bulleri, Fabio; et al. (Proceedings of the National Academy of Sciences, 2014)
Tests of biodiversity theory have been controversial partly because alternative formulations of the same theory seemingly yield different conclusions. This has been a particular challenge for neutral theory, which has dominated tests of biodiversity theory over the last decade. Neutral theory attributes differences in species abundances to chance variation in individuals’ fates, rather than differences in species traits. By identifying common features of different neutral models, we conduct a uniquely robust test of neutral theory across a global dataset of marine assemblages. Consistently, abundances vary more among species than neutral theory predicts, challenging the hypothesis that community dynamics are approximately neutral, and implicating species differences as a key driver of community structure in nature.Explaining patterns of commonness and rarity is fundamental for understanding and managing biodiversity. Consequently, a key test of biodiversity theory has been how well ecological models reproduce empirical distributions of species abundances. However, ecological models with very different assumptions can predict similar species abundance distributions, whereas models with similar assumptions may generate very different predictions. This complicates inferring processes driving community structure from model fits to data. Here, we use an approximation that captures common features of “neutral” biodiversity models—which assume ecological equivalence of species—to test whether neutrality is consistent with patterns of commonness and rarity in the marine biosphere. We do this by analyzing 1,185 species abundance distributions from 14 marine ecosystems ranging from intertidal habitats to abyssal depths, and from the tropics to polar regions. Neutrality performs substantially worse than a classical nonneutral alternative: empirical data consistently show greater heterogeneity of species abundances than expected under neutrality. Poor performance of neutral theory is driven by its consistent inability to capture the dominance of the communities’ most-abundant species. Previous tests showing poor performance of a neutral model for a particular system often have been followed by controversy about whether an alternative formulation of neutral theory could explain the data after all. However, our approach focuses on common features of neutral models, revealing discrepancies with a broad range of empirical abundance distributions. These findings highlight the need for biodiversity theory in which ecological differences among species, such as niche differences and demographic trade-offs, play a central role.
Keywords: Sørishavet; biodiversitet; biologi; marin økologi; marine økosystemer; polarområdene; zoologi

Three artotrogids (Crustacea: Copepoda: Siphonostomatoida) from the Ross Sea, Antarctica - Conradi, Mercedes (Polar Research, 2014)
The Artotrogidae, one of the most primitive of siphonostomatoid families, consists currently of 117 species in 21 genera. Most of these species (65%) are poorly or incompletely described since they have been rarely recorded in recent decades and, when encountered, have been found in very low numbers. During the 19th Italian Antarctic Expedition, with the RV Italica, to the Ross Sea in austral summer 2004, some artotrogid copepods were collected. This paper redescribes two species of artotrogid copepods, which are known only from the Southern Ocean, Neobradypontius neglectus and Cryptopontiuslatus, and describes for the first time a male of the genus Neobradypontius. Furthermore, a new species is described and added to Sestropontius, increasing the number of known species of this genus to three. The main discrepancies between the original descriptions and the specimens of the two species collected from the Ross Sea redescribed here were on the armature of the antennary exopod and leg 5. The new species, Sestropontius italicae, shares with its most similar congener, S. mckinnoni, the armature of the third endopodal segment of leg 1 and leg 2 and that of the third exopodal segment of leg 4. However, the segmentation of the antennae and the armature on the antennary exopod are different. Keywords: Antarctica; Artotrogidae; redescription; Neobradypontius; Sestropontius; Cryptopontius.
Keywords: Rosshavet; Sørishavet; copepoder; ekspedisjoner; hoppekreps; marin biologi; zoologi

Antarktis: inlandsis, shelf-is och stigande havsnivå - Darelius, Elin (Naturen, 2014)
I klimatsammanhang har strålkastarljuset länge varit riktade mot de känsliga polarområdena och smältande is. Bilder på isbjörnar som klamrar sig fast vid ett ensamt isflak figurerar varje höst i media när årets – ofta rekordlåga – minimum i utbredning av Arktisk havsis offentliggörs. Men nyligen har is-överskrifterna allt oftare kommit söderifrån, de har handlat om Antarktis, om shelf-is som smälter, om en stigande havsnivå och om möjligheten för att inlandsisen i Väst-Antarktis ska kollapsa.
Keywords: Sørishavet; brehylle; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R; Nicholls, Keith W (Journal of Geophysical Research: Oceans, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; hydrografi; isfront; isshelf

On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Fjerning av reinsdyr på Sør-Georgia: nok et avsluttet kapittel i norsk hvalfangsthistorie - Kilander, Carl Erik (Polarboken, 2014)
Keywords: Sørishavet; zoologi; økologi

Decrease in stomach contents in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Hakamada, Takashi; Kiwada, Hiroshi; Kitakado, Toshihide; Walløe, Lars (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; krill; marin biologi; observasjoner

High variability of climate and surface mass balance induced by Antarctic ice rises - Lenaerts, Jan T M; Joel, Brown.; Van Den Broeke, Michiel R; Matsuoka, Kenichi; Drews, Reinhard; Callens, Denis; Philippe, Morgane; Gorodetskaya, Irina V; Van Meijgaard, Erik; Reijmer, Carleen H; Pattyn, Frank; Van Lipzig, Nicole P M (Journal of Glaciology, 2014)
Ice rises play key roles in buttressing the neighbouring ice shelves and potentially provide palaeoclimate proxies from ice cores drilled near their divides. Little is known, however, about their influence on local climate and surface mass balance (SMB). Here we combine 12 years (2001–12) of regional atmospheric climate model (RACMO2) output at high horizontal resolution (5.5 km) with recent observations from weather stations, ground-penetrating radar and firn cores in coastal Dronning Maud Land, East Antarctica, to describe climate and SMB variations around ice rises. We demonstrate strong spatial variability of climate and SMB in the vicinity of ice rises, in contrast to flat ice shelves, where they are relatively homogeneous. Despite their higher elevation, ice rises are characterized by higher winter temperatures compared with the flat ice shelf. Ice rises strongly influence SMB patterns, mainly through orographic uplift of moist air on the upwind slopes. Besides precipitation, drifting snow contributes significantly to the ice-rise SMB. The findings reported here may aid in selecting a representative location for ice coring on ice rises, and allow better constraint of local ice-rise as well as regional ice-shelf mass balance.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Environmental influences on the at-sea behaviour of a major consumer, Mirounga leonina, in a rapidly changing environment - McIntyre, Trevor; Bornemann, Horst; de Bruyn, P J Nico; Reisinger, Ryan R; Steinhage, Daniel; Márquez, Maria E I; Bester, Marthán N; Plötz, Joachim (Polar Research, 2014)
Understanding the distribution and foraging ecology of major consumers within pelagic systems, specifically in relation to physical parameters, can be important for the management of bentho-pelagic systems undergoing rapid change associated with global climate change and other anthropogenic disturbances such as fishing (i.e., the Antarctic Peninsula and Scotia Sea). We tracked 11 adult male southern elephant seals (Mirounga leonina), during their five-month post-moult foraging migrations from King George Island (Isla 25 de Mayo), northern Antarctic Peninsula, using tags capable of recording and transmitting behavioural data and in situ temperature and salinity data. Seals foraged mostly within the Weddell–Scotia Confluence, while a few foraged along the western Antarctic Peninsula shelf of the Bellingshausen Sea. Mixed model outputs suggest that the at-sea behaviour of seals was associated with a number of environmental parameters, especially seafloor depth, sea-ice concentrations and the temperature structure of the water column. Seals increased dive bottom times and travelled at slower speeds in shallower areas and areas with increased sea-ice concentrations. Changes in dive depth and durations, as well as relative amount of time spent during the bottom phases of dives, were observed in relation to differences in overall temperature gradient, likely as a response to vertical changes in prey distribution associated with temperature stratification in the water column. Our results illustrate the likely complex influences of bathymetry, hydrography and sea ice on the behaviour of male southern elephant seals in a changing environment and highlight the need for region-specific approaches to studying environmental influences on behaviour. Keywords: Southern elephant seals; foraging ecology; satellite-relay data loggers; King George Island; Isla 25 de Mayo; at-sea behaviour.
Keywords: Sørishavet; batymetri; havis; klimaendringer; miljø; næring; seler; sjøis

Verification of a new NOAA/NSIDC passive microwave sea-ice concentration climate record - Meier, Walter N; Peng, Ge; Scott, Donna J; Savoie, Matt H (Polar Research, 2014)
A new satellite-based passive microwave sea-ice concentration product developed for the National Oceanic and Atmospheric Administration (NOAA) Climate Data Record (CDR) programme is evaluated via comparison with other passive microwave-derived estimates. The new product leverages two well-established concentration algorithms, known as the NASA Team and Bootstrap, both developed at and produced by the National Aeronautics and Space Administration (NASA) Goddard Space Flight Center (GSFC). The sea-ice estimates compare well with similar GSFC products while also fulfilling all NOAA CDR initial operation capability (IOC) requirements, including (1) self-describing file format, (2) ISO 19115-2 compliant collection-level metadata, (3) Climate and Forecast (CF) compliant file-level metadata, (4) grid-cell level metadata (data quality fields), (5) fully automated and reproducible processing and (6) open online access to full documentation with version control, including source code and an algorithm theoretical basic document. The primary limitations of the GSFC products are lack of metadata and use of untracked manual corrections to the output fields. Smaller differences occur from minor variations in processing methods by the National Snow and Ice Data Center (for the CDR fields) and NASA (for the GSFC fields). The CDR concentrations do have some differences from the constituent GSFC concentrations, but trends and variability are not substantially different. Keywords: Sea ice; Arctic and Antarctic oceans; climate data record; evaluation; passive microwave remote sensing.
Keywords: Sørishavet; evaluering; havis; klimaendringer; polarområdene; sjøis

Basal mass budget of Ross and Filchner-Ronne ice shelves, Antarctica, derived from Lagrangian analysis of ICESat altimetry - Moholdt, Geir; Padman, Laurie; Fricker, Helen Amanda (Journal of Geophysical Research: Earth Surface, 2014)
Traditional methods of deriving temporal variability of Antarctic ice-shelf elevation from satellite altimetry use a fixed (“Eulerian”) reference frame, where the measured changes include advection of ice thickness gradients between measurement epochs. We present a new method which removes advection effects by using an independent velocity field to compare elevations in a moving (“Lagrangian”) reference frame. Applying the technique to ICESat laser altimetry for the period 2003–2009 over the two largest Antarctic ice shelves, Ross and Filchner-Ronne, we show that the Lagrangian approach reduces the variability of derived elevation changes by about 50% compared to the Eulerian approach and reveals clearer spatial patterns of elevation change. The method simplifies the process of estimating basal mass budget from the residual of all other processes that contribute to ice-shelf elevation changes. We use field data and ICESat measurements over ice rises and the grounded ice sheet to account for surface accumulation and changes in firn air content, and remove the effect of ice-flow divergence using surface velocity and ice thickness data. The results show highest basal melt rates (>5 m a−1) near the deep grounding lines of major ice streams, but smaller melt rates (<5 m a−1) near the ice-shelf fronts are equally important to total meltwater production since they occur over larger areas. Integrating over the entire ice-shelf areas, we obtain basal mass budgets of −50 ± 64 Gt a−1 for Ross and −124 ± 66 Gt a−1 for Filchner-Ronne, with changes in firn air content as the largest error source.
Keywords: Sørishavet; batymetri; brehylle; geofysikk; innlandsis; isbrem; isshelf; oseanografi; satellite altimetri

Observations of cetaceans in the south-east Atlantic sector of the Southern Ocean, during summer 2008 - Nøttestad, Leif; Krafft, Bjørn; Søiland, Henrik; Skaret, Georg (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; marin biologi; observasjoner; oseanografi

Distribution of total alkalinity and pH in the Ross Sea (Antarctica) waters during austral summer 2008 - Rivaro, Paola; Messa, Roberta; Ianni, Carmela; Magi, Emanuele; Budillon, Giorgio (Polar Research, 2014)
Measurements of total alkalinity (AT) and pH were made in the Ross Sea in January–February 2008 in order to characterize the carbonate system in the Ross Sea and to evaluate the variability associated with different water masses. The main water masses of the Ross Sea, Antarctic Surface Water, High Salinity Shelf Water (HSSW), Deep Ice Shelf Water, Circumpolar Deep Water (CDW) and Antarctic Bottom Water, were identified on the basis of the physical and chemical data. In particular, the AT ranged between 2275 and 2374 µmol kg−1 with the lowest values in the surface waters (2275–2346 µmol kg−1), where the influence of the sea-ice melting and of the variability of the physical properties was significant. In the deep layers of the water column, the AT maxima were measured in correspondence to the preferential pathways of the spreading HSSW. The pH had variable values in the surface layer (7.890–8.033) with the highest values in Terra Nova Bay and Ross Sea polynyas. A low pH (7.969±0.025) traced the intrusion of the CDW in the Ross Sea shelf area. All samples revealed waters that were oversaturated with respect to both calcite and aragonite, but near corrosive levels of aragonite saturation state (Ω ca. 1.1–1.2) were associated with the entrainment of CDW over the slope. Aragonite undersaturation is of particular concern for the zooplankton species comprising to calcifying organisms such as pteropods. The partial pressure of CO2 at the sea surface was undersaturated with respect to the atmospheric value, particularly in Terra Nova Bay and the Ross Sea polynyas, but a large variability in the sea–air CO2 fluxes was observed associated with different responses in the strength of the biological and physical processes. Keywords: Total alkalinity; pH; saturation state; Terra Nova Bay polynya; Ross Sea.
Keywords: Rosshavet; Sørishavet; havis; hydrografi; hydrokjemi; kjemiske analyser; klimaendringer; kontinentalsokkel; sjøis; vannmasser; zooplankton

Hvalfangerkirken i Grytviken 100 år - Tokstad, Kjell (Polarboken, 2014)
Keywords: Sørishavet; bygninger; historie

Atmosphere–sea ice interaction in early summer in the Antarctic: evaluation and challenges of a regional atmospheric model - Valkonen, T.; Vihma, T.; Johansson, M. M.; Launiainen, J. (Quarterly Journal of the Royal Meteorological Society, 2014)
Antarctic sea ice areas have only been the main focus for a few studies combining observations and three-dimensional atmospheric model experiments. This study presents simulations over the Weddell Sea in early summer, applying the polar-optimized version of the Weather Research and Forecasting model (Polar WRF). The results are compared against observations from the drifting experiment Ice Station Polarstern, which took place on 28 November 2004?2 January 2005. The Polar WRF model showed good skill in simulating synoptic-scale variations. The diurnal cycles of surface variables were reproduced, but the amplitude was overestimated for most of the variables and the simulations were characterized by a cold temperature bias at night. The major challenges related to the modelling of the atmosphere over Antarctic sea ice were found to be associated with clouds, atmospheric boundary-layer processes and processes in the sea ice and snow layer. Temporal variations in the errors in cloud cover generated large errors in long-wave radiation fluxes. In the boundary layer, the overestimated downward sensible heat flux was partly compensated for by the underestimated downward long-wave radiation at the surface. The underestimated downward long-wave flux started to dominate as the stability increased and generated the cold temperature bias at the surface. Problems with the surface energy balance, as found in this study, could be reduced by applying more advanced schemes for snow and ice thermodynamics.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; meteorologi; sjøis

Atmospheric trace elements in aerosols observed over the Southern Ocean and coastal East Antarctica - Xu, Guojie; Gao, Yuan (Polar Research, 2014)
Atmospheric aerosol samples were collected over the Southern Ocean (SO) and coastal East Antarctica (CEA) during the austral summer of 2010/11. Samples were analysed for trace elements, including Na, Mg, K, Al, Fe, Mn, Ni, Cd and Se, by inductively coupled plasma mass spectrometry (ICP-MS). The mean atmospheric concentrations over the SO were 1100 ng m−3 for Na, 190 ng m−3 for Mg, 150 ng m−3 for Al, 14 ng m−3 for Fe, 0.46 ng m−3 for Mn and 0.25 ng m−3 for Se. Over CEA, the mean concentrations were 990 ng m−3 for Na, 180 ng m−3 for Mg, 190 ng m−3 for Al, 26 ng m−3 for Fe, 0.70 ng m−3 for Mn and 0.29 ng m−3 for Se. Particle size distributions, enrichment factors (EFs) and correlation analysis indicate that Na, Mg and K mainly came from the marine source, while Al, Fe and Mn were mainly from the crustal source, which also contributed to Mg and K over CEA. High EFs were associated with Ni, Cd and Se, suggesting likely contributions from mixed sources from the Antarctic continent, long-range transport, marine biogenic emissions and anthropogenic emissions. Sea-salt elements (Na, Mg, K) were mainly accumulated in the coarse mode, and crustal elements (Al, Fe, Mn) presented a bimodal size distribution pattern. Bioactive elements (Fe, Ni, Cd) were enriched in the fine mode, especially with samples collected over the SO, possibly affecting biogeochemical cycles in this oceanic region. Keywords: Southern Ocean; coastal East Antarctica; trace elements; size distribution; sources.
Keywords: Sørishavet; atmosfærisk aerosol; biogeokjemi; kjemiske analyser; meteorologi

Wind-driven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea - Zhou, Qiming; Hattermann, Tore; Nøst, Ole Anders; Biuw, Martin; Kovacs, Kit M; Lydersen, Christian (Journal of Geophysical Research: Oceans, 2014)
Abstract Solar heated, fresh Antarctic Surface Water (ASW) is a permanent feature along the Eastern Weddell Sea (EWS) coast in summer down to a depth of roughly 200 m. Recently, ASW has been observed beneath the Fimbul Ice Shelf, suggesting that it might play an important role in basal melting. We propose that wind-driven coastal downwelling is the main mechanism that spreads ASW beneath the ice shelf in this sector of Antarctica. We validate this hypothesis with observations, scaling analyses, and numerical modeling, along three principle lines: (i) data analyses of about 1500 salinity profiles collected by instrumented seals indicate that the observed freshening of the coastal water column is likely explained by the on-shore Ekman transport and subsequent downwelling of ASW; (ii) an analytical model of the coastal momentum balance indicates that wind-driven downwelling is capable of depressing the buoyant surface water to a depth similar to the ice shelf draft; and (iii) simulations from both idealized and regional eddy-resolving numerical ice shelf/ocean models support our proposition. Our main conclusion is that wind-driven spreading of ASW beneath the ice shelf occurs when downwelling exceeds the depth of the ice shelf base. Furthermore, our study adds to the understanding of the oceanic processes at the Antarctic Slope Front in the EWS, with possible implications for other sectors of Antarctica.
Keywords: Sørishavet; Weddellhavet; isbrem; isshelf; oseanografi; overflatevann; smelting; vannmasser; vannvirvler

Norske krav i Sørishavet - Utfordringer for Sjøforsvaret - Aase, Johnny Grøneng (Norsk Tidsskrift for Sjøvesen, 2013)
Norge gjorde i 2009 krav på økonomiske soner utenfor Bouvetøya og Dronning Maud Land. Slike krav fører i følge Lov om økonomiske soner med seg forpliktelser som over tid får konsekvenser for Sjøforsvaret. l den økonomiske sonen som ble erklært utenfor fastlands-Norge på 1970-tallet har det vært Kystvakten som har opprettholdt juridiksjon, overvåket miljøet og kontrollert fisket. Norske og utenlandsk fartøyer har alt begynt å fiske i norsk økonomisk sone utenfor Bouvetøya. Det foregår i dag en rivende utvikling av teknologi for gruvedrift på store havdyp. Statlige og kommersielle private aktører posisjonerer seg aktivt for å kunne utnytte naturressursene i Sørishavet. Denne forfatteren mener at det vil tvinge seg fram et behov for stedlig overvåkning, kontroll og miljøvern i de norske økonomiske sonene i Antarktis. Det eksisterer ingen robust søk- og redningstjeneste i Antarktis. Siden Norge har gjort territorielle krav har vi også en moralsk forpliktelse om å kunne komme skipbrudne og syke til unnsetning i disse områdene. Overvåkning og hevding av juridiksjon i slike store og fjerntliggende havområder vil bli komplisert og dyrt. Kystvakten har i dag verken fartøyer eller personell for å kunne utføre dette. Rundt 2020 vil de store kystvaktskipene Nordkapp, Senja og Andenes være rundt 40 år og nærme seg tidspunktet for utfasing. Klimaendringene fører til migrasjon av fisk nordover mot kaldere vann i Barentshavet, og det vil derfor bli behov for fiskeriinspeksjoner lenger nord enn i dag. Kystvakten trenger å anskaffe store erstatningsfartøy for Nordkapp-klassen, og ved prosjekteringen bør man ta høyde for at Norge også vil ha behov for en kystvaktkapasitet i Antarktis. For å redusere risikoen for over- eller feilinvesteringer vil jeg gjennomgå hvordan en allerede i dag kan benytte satellitter for å kartlegge skipstrafikken i de norske områdene i sør. Ut fra dette bakgrunnsmaterialet kan Forsvaret anslå hvor mange fartøyer som vil være nødvendig å ha i sør.
Publisher: Sjømilitære samfund
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; havrett; jus; miljøovervåking; miljøvern; naturressurser; økonomi

Eddy-Driven Exchange between the Open Ocean and a Sub–Ice Shelf Cavity - Årthun, Marius; Holland, Paul R; Nicholls, Keith William; Feltham, Daniel L (Journal of Physical Oceanography, 2013)
Keywords: Sørishavet; Weddellhavet; isshelf; oseanografi; sjøvirvler; vannvirvler

Thick-shelled, grazer-protected diatoms decouple ocean carbon and silicon cycles in the iron-limited Antarctic Circumpolar Current - Assmy, Philipp; Smetacek, Victor; Montresor, Marina; Klaas, Christine; Henjes, Joachim; Strass, Volker; Arrieta, Jesus M; Bathmann, Ulrich; Berg, Gry Mine; Breitbarth, Eike; Cisewski, Boris; Friedrichs, Lars; et al. (Proceedings of the National Academy of Sciences, 2013)
Diatoméer – alger med skall av silisium, som er helt avhengige av næringsstoffet silikat – dominerer fytoplankton oppblomstringer og spiller en nøkkelrolle i havets økosystemer og i global karbonsyklus. Vi viser hvordan forskjeller i økologiske karakteristikker av dominerende arter i Sørishavet, som ble observert under det in situ europeiske jerngjødslings eksperimentet (European Iron Fertilization Experiment - EIFEX), kan påvirke karbon og silisium syklusene i havet. Vi argumenterer for at økologien til tykkskallete diatomé arter, som er selektert for av sterk beiting fra kopepoder, tar opp silikat fremfor andre næringsstoffer i det dype Sørishavet og underliggende sedimenter. Fordi Sørishavet er en viktig sentral for oseanisk fordeling av næringsstoffer, selektivt opptak av silikat i dette havområdet begrenser oppblomstringene av diatoméer i andre deler av verdenshavene, noe som potensielt får konsekvenser for biotisk opptak av karbon i hele verdens havområder.
Keywords: Sørishavet; marinbiologi; oseanografi; plankton; økosystem

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

Antarktis-isen: større og dypere - Bjermeland, Monica (Klima: norsk magasin for klimaforskning, 2013)
De siste tiårene har isen i Antarktis økt litt i utbredelse. Men ikke fordi det er blitt kaldere der.
Keywords: Antarktis; Sørishavet; glasiologi; havis; is; klima

Dietary overlap in inshore notothenioid fish from the Danco Coast, western Antarctic Peninsula - Casaux, Ricardo; Barrera-Oro, Esteban (Polar Research, 2013)
We carried out a dietary overlap analysis between notothenioid species by examining the stomach contents of more than 900 specimens collected in a fish assemblage at the Danco Coast, western Antarctic Peninsula, in the summer of 2000. Prey reoccurrences among fish species were 32.2%, with krill Euphausia superba, salps and the gammaridean Prostebeingia longicornis the most reoccurring prey. The diet similarity between species pairs was lower than 55%, in accordance with similar fish assemblages in the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula. Whereas at those localities the higher prey overlap was between krill-feeding fish species, at the Danco Coast it was between Trematomus bernacchii and Lepidonotothen nudifrons, Notothenia coriiceps and Notothenia rossii, Notothenia coriiceps and Parachaenichthyis charcoti, and Trematomus newnesi and Notothenia rossii, which shared primarily gammaridean amphipods, algae, fish and krill, respectively. Krill is normally the main prey of fish in summer in inshore waters of the western Antarctic Peninsula, but its density in January/February 2000 was notably lower than in previous years. Therefore, at the Danco Coast, under conditions of krill shortage, most of the notothenioid species foraged more intensively on alternative prey, such as gammarideans, fish and algae. The difference between areas in the pattern of dietary overlap might be related to differences in prey availability between years and to the degree of competition for targeted prey. Keywords: Fish dietary overlap; notothenioid fish; Antarctic Peninsula.
Keywords: Sørishavet; fisker; forskning; krill; marin biologi; plankton; økosystemer

Tintinnid ciliates of Amundsen Sea (Antarctica) plankton communities - Dolan, John R; Yang, Eun Jin; Lee, Sang Hoon; Kim, Sun Young (Polar Research, 2013)
The Amundsen Sea has been described as one of the most productive and dynamic pelagic systems in Antarctica and is one of the least studied. Based on samples from 15 stations in the Amundsen Sea, we describe for the first time the composition of the tintinnid ciliate assemblage of the microzooplankton. We compared the species compositions of coastal polynya sites, where the phytoplankton communities are dominated by Phaeocystis, to those of the offshore deep water sites, which are dominated by diatoms. We found a total of 15 species. Polynya sites were dominated by a few species of tintinnids, mostly those endemic to the Southern Ocean. In contrast, the deep-water sites contained many widespread tintinnid species, which are known from a wide variety of systems as well as other areas of the Southern Ocean. We examined polymorphism known to characterize the Antarctic tintinnid species Cymatocylis affinis/convallaria and Codonellopsis gaussi. We found that the types or forms found appeared unrelated to the type of microplankton community, defined by the identity of the dominant phytoplankton taxa. However, the number of different morphotypes found at a site appeared related to the overall concentration of the species, suggesting that different morphologies, previously considered distinct species, may simply be developmental stages. Keywords: Zooplankton; microzooplankton; polynya; protists; Phaeocystis; diatoms.
Keywords: Sørishavet; diatomeer; fytoplankton; marin biologi; oseanografi; protoktister; zooplankton; økologi

Genetic characterization and life cycle of the diatom Fragilariopsis kerguelensis - Fuchs, Nike; Scalco, Eleonora; Kooistra, Wiebe; Assmy, Philipp; Montresor, Marina (European Journal of Phycology, 2013)
Diatoméen Fragilariopsis kerguelensis fra Sørishavet spiller en nøkkelrolle i marin silisium syklus fordi restene av celleveggene synker til havbunnen rundt Antarktis, hvor de bygger opp de største depotene av biologisk generert silisium i verden. Tomme skall av diatomeer har også blitt brukt som indikatorer/proksier for produksjonsregimer i geologisk fortid av mikro-paleontologer. For å bedre kunne beskrive og forstå biologien av denne arten fra Sørishavet har vi adressert dens genetiske identitet ved hjelp av molekylære markører, og for første gang vært i stand til å anslå kjønn til denne arten. Dette har ført til at vi har vært i stand til å kjøre et stort antall vellykkede parringseksperimenter. Vi har vært i stand til å avdekke det intrikate parringssystemet og livssyklus karakteristikker til F. kerguelensis og demonstrere at vi kun har å gjøre med én biologisk art. En bedre forståelse av livssyklus til F. kerguelensis burde hjelpe for tolkning av geologiske tidsserier for denne arten og belyse rollen miljøfaktorer kan ha for å regulere populasjoner av arten.
Keywords: Sørishavet; genetikk; marinbiologi; plankton

Tre kilder til smelting av Fimbulisen - Hattermann, Tore; Nøst, Ole A; Smedsrud, Lars H (Klima: norsk magasin for klimaforskning, 2013)
Soloppvarmet overflatevann er en sentral varmekilde som bidrar til smelting av isbremmen Fimbulisen i Dronning Maud Land.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Assessing the potential of calcium-based artificial ocean alkalinization to mitigate rising atmospheric CO2 and ocean acidification - Ilyina, Tatiana; Wolf-Gladrow, Dieter; Munhoven, Guy; Heinze, Christoph (Geophysical Research Letters, 2013)
Enhancement of ocean alkalinity using calcium compounds, e.g., lime has been proposed to mitigate further increase of atmospheric CO2 and ocean acidification due to anthropogenic CO2 emissions. Using a global model, we show that such alkalinization has the potential to preserve pH and the saturation state of carbonate minerals at close to today's values. Effects of alkalinization persist after termination: Atmospheric CO2 and pH do not return to unmitigated levels. Only scenarios in which large amounts of alkalinity (i.e., in a ratio of 2:1 with respect to emitted CO2) are added over large ocean areas can boost oceanic CO2 uptake sufficiently to avoid further ocean acidification on the global scale, thereby elevating some key biogeochemical parameters, e.g., pH significantly above preindustrial levels. Smaller-scale alkalinization could counteract ocean acidification on a subregional or even local scale, e.g., in upwelling systems. The decrease of atmospheric CO2 would then be a small side effect.
Keywords: Sørishavet; biogeokjemi; havalkalisering; klimatologi; meteorologi; modeller

Low frequency variability on the continental slope of the southern Weddell Sea - Jensen, Mari F; Fer, Ilker; Darelius, Elin (Journal of Geophysical Research: Oceans, 2013)
One-year long records of temperature, salinity, and currents show seasonally varying, energetic oscillations with a dominant period of approximately 35 h on the upper continental slope of the southern Weddell Sea. The data set is sampled by five moorings deployed on the slope of the Crary Fan, east of the main outflow site of the Filchner overflow plume. The characteristics of the observed oscillations are compared to idealized coastal trapped waves inferred from a numerical code. The variability at 35 h period is identified as mode 1 waves with wavelengths less than 200 km and group velocity opposing the phase speed, indicating energy propagation toward east. Filchner Depression and the nearby ridges on the slope are suggested as the generation site where the dynamics associated with the overflow plume can force the variability. Historical time series at the overflow site are revisited to identify the source of previously reported variability at 3 and 6 day time scales. Mode 2 waves at wavelengths of about 100 and 1000 km were found to bear resemblance to the 3 day and 6 day variability, respectively. The seasonal variation in the energy in the 35 h band shows small but significant correlation with the low frequency easterly winds. The presence of coastal trapped waves along the continental slope of the Weddell Sea can increase the heat exchange across the shelf break and affect the dense water production rates.
Keywords: Sørishavet; Weddellhavet; batymetri; bunnvann; geofysikk; havstrømmer; kelvinbølger; saltinnhold; temperatur måling

Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding - Nomura, Daiki; Granskog, Mats A; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen (Journal of Geophysical Research: Oceans, 2013)
In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface (Fflood) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m−2 d−1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow-air surface (Fsnow) and bare ice surface (Fice). The Fsnow/Fflood ratio decreased with increasing water equivalent of snow and superimposed-ice, suggesting that the properties of snow and superimposed-ice formation affect the magnitude of the CO2 flux. The Fsnow/Fflood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed-ice. Hence, snow cover properties and superimposed-ice play an important role in the CO2 fluxes across the sea ice-snow-atmosphere interface.
Keywords: Sørishavet; atmosfæren; gassutveksling; havis; karbondioksid; klimaendringer; klimatologi; meteorologi; polarområdene; sjøis

Microbial biogeography during austral summer 2007 in the surface waters around the South Shetland Islands, Antarctica - Olsen, Lasse Mork; Ardelan, Murat van; Hewes, Christopher D; Holm-Hansen, Osmund; Reiss, Christian; Bizsel, Nihayet; Sakshaug, Egil; Vadstein, Olav (Aquatic Microbial Ecology, 2013)
Recent studies have concluded that different water bodies in the ocean can contain different microbial communities. The goal of the present study was to determine if biogeographic patterns are present for aquatic microbes in waters which meet around the South Shetland Islands(SSI), Antarctica. Prokaryotic and eukaryotic marine microbial communities were monitored during the 2007 austral summer by use of polymerase chain reaction (PCR) and denaturing gradientgel electrophoresis (DGGE) of small subunit ribosomal DNA. Hydrographic properties, nutrients and chlorophyll a were also measured. There was an onshore to offshore gradient in temperature, salinity and iron concentration and a unimodal distribution of chlorophyll a concentration in rela-tion to the middle of this gradient that occurred near the SSI. The differences in microbial community structure among stations in the studied area were correlated with both geographical distance and environmental factors. For eukaryotes, the correlation was strongest for environment, where as it was strongest for geographical distance for the prokaryotes. Eukaryotic and prokaryotic community structures were highly correlated. Surface water from the Weddell Sea had a different community of eukaryotes than the water in the Antarctic Circumpolar Current in the Drake Passage, whereas the prokaryotic community was not significantly different. The area close to theSSI where the 2 water types mix had the highest chlorophyll concentration and significantly dif-ferent communities of eukaryotes and prokaryotes from both of the inflowing water types. These results suggest that the prokaryote community structure was more affected by productivity thanby environmental variables. KEY WORDS: Microbial biogeography. Microbial community. Natural iron enrichment. Southern Ocean.
Keywords: Sørishavet; biogeografi; marin biologi; mikroorganismer; oseanografi; overflatevann; økosystemer

New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, José Luis; Scioscia, Gabriela; Torres, Mónica Anilía; Dellabianca, Natalia Andrea (Polar Research, 2013)
During ship-based seabird surveys in the south Atlantic and Antarctica in the austral summers of 1994/95, 2009, 2010, 2011 and 2012, we documented at-sea distributions of Buller’s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), soft-plumaged petrel (Pterodroma mollis), Kerguelen petrel (Lugensa brevirostris) and great-winged petrel (Pterodroma macroptera). In some cases, sightings were considered as extralimital, but for other species updating their distributions in the literature seems warranted. Atlantic petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the distribution of this species has not been updated in the literature. The observations reported here will contribute to update the at-sea distributions of these species and to changes in their distributions. Keywords: Seabirds; Antarctica; South Atlantic Ocean; distribution.
Keywords: Antarktis; Sørishavet; marin zoologi; observasjoner; ornitologi; petreller; sjøfugler

Environmental conditions, particle flux and sympagic microalgal succession in spring before the sea-ice break-up in Adélie Land, East Antarctica - Riaux-Gobin, Catherine; Dieckmann, Gerhard S; Poulin, Michel; Neveux, Jacques; Labrune, Céline; Vétion, Gilles (Polar Research, 2013)
Data pertaining to environmental conditions, sympagic (sea ice) microalgal dynamics and particle flux were collected before the spring ice break-up 2001 in Pierre Lejay Bay, adjacent to the Dumont d'Urville Station, Petrel Island, East Antarctica. An array of two multiple sediment traps and a current meter was deployed for five weeks, from 8 November to 6 December 2001. The sea-ice chlorophyll a and particulate organic carbon (POC) averaged 0.6 mg l−1 (30 mg m−2) and 20 mg l−1 (1 g m−2) near the coast. The POC export flux that reached a maximum of 79 mg m−2 d−1 during the study period was high compared to the one for the Weddell Sea. The flux was homogeneous from the surface to 47 m depth and increased sharply 33 days before the effective ice break-up. A north-western progressive vector of currents (i.e., Lagrangian drift) in the sub-ice surface waters was demonstrated. Bottom ice, platelet ice and under-ice water at 5 m were characterized by differences in colonization and short-term succession of microalgae. Keywords: Land-fast ice; oceanic short-term regime; POM flux; sympagic communities; East Antarctica.
Keywords: Sørishavet; Weddellhavet; alger; fysisk oseanografi; geokjemi; havis; sjøis; sympagisk økologi

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Reproductive biology of the Antarctic ‘‘sea pen’’ Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae) - Servetto, Natalia; Torre, Luciana; Sahade, Ricardo (Polar Research, 2013)
The reproductive biology of the sea pen Malacobelemnon daytoni was studied at Potter Cove, South Shetland Islands, where it is one of the dominant species in shallow waters. Specimens collected at 15–22 m depth were examined by histological analysis. M. daytoni is gonochoristic and exhibited a sex ratio of 1:1. Oocyte sizes (>300 µm) and the absence of embryos or newly developed larvae in the colonies suggest that this species can have lecithotrophic larvae and experience external fertilization. This life strategy is in line with other members of the group and supports the hypothesis that this could be a phylogenetically fixed trait for pennatulids. It was observed that oocytes were generated by gastrodermic tissue and released to the longitudinal canal. Thereafter, they migrate along the canal until they reach maturity and are released by autozooids at the top of the colonies. This striking feature has not yet been reported for other pennatulaceans. Mature oocytes were observed from colonies of 15 mm in length, suggesting that sexual maturity can be reached rapidly. This is contrary to what is hypothesized for the vast majority of Antarctic benthic invertebrates, namely that rates of activities associated with development, reproduction and growth are almost universally very slow. This strategy may also explain the ecological success of M. daytoni in areas with high ice impact as in the shallow waters of Potter Cove.
Keywords: Sørishavet; bentos; havbunnen; marin biologi; nesledyr; reproduksjon

Observed variations in multidecadal Antarctic sea ice trends during 1979–2012 - Simpkins, Graham R; Ciasto, Laura M; England, Matthew H (Geophysical Research Letters, 2013)
The spatiotemporal sensitivity of Antarctic sea ice season length trends are examined using satellite-derived observations over 1979–2012. While the large-scale spatial structure of multidecadal trends has varied little during the satellite record, the magnitude of trends has undergone substantial weakening over the past decade. This weakening is particularly evident in the Ross and Bellingshausen Seas, where a ∼25–50% reduction is observed when comparing trends calculated over 1979–2012 and 1979–1999. Multidecadal trends in the Bellingshausen Sea are found to be dominated by variability over subdecadal time scales, particularly the rapid decline in season length observed between 1979 and 1989. In fact, virtually no trend is detectable when the first decade is excluded from trend calculations. In contrast, the sea ice expansion in the Ross Sea is less influenced by shorter-term variability, with trends shown to be more consistent at decadal time scales and beyond. Understanding these contrasting characteristics have implications for sea ice trend attribution.
Keywords: Sørishavet; havis; klimatologi; observasjoner; satellite bilder; sjøis

Sources and geographic heterogeneity of trace metals in the sediments of Prydz Bay, East Antarctica - Sun, Wei-Ping; Hu, Chuan-Yu; Weng, Huan-Xin; Han, Zheng-Bing; Shen, Chen; Pan, Jian-Ming (Polar Research, 2013)
In this study, we have determined the contents and distribution of zinc and cadmium in the surface sediments from Prydz Bay, East Antarctica. The main sources of the trace elements and their geographic heterogeneity, and the relation between Zn and Cd, are discussed based on the cluster analysis, principle component analysis and considerations of biogenic and lithogenic inputs. The results show that the contents of trace metals range from 34.6 to 96.6 mg kg-1 for Zn, and from 0.254 to 0.441 mg kg-1 for Cd. Calculations of the enrichment factor indicated no significant anthropogenic impact. Biogenic and lithogenic inputs are the main sources of trace metals. They are almost equal for Zn and Cd at the Amery Ice Shelf edge, while the continental shelf and deep ocean are dominated by biogenic inputs. The contribution of biogenic inputs is much higher for Zn than for Cd at the deep ocean. Calculations of biogenic trace metals revealed different relationships between biogenic Zn and biogenic Cd, which reflect the biological uptake by phytoplankton in the water column. Keywords: Trace elements; sources; enrichment factor; cluster analysis; principal component analysis; Antarctica.
Keywords: Sørishavet; fytoplankton; geografi; kjemiske analyser; kontinentalmargin; kontinentalsokkel; marin biologi; oseanografi; sedimenter; sedimentologi

Inorganic C utilization and C isotope fractionation by pelagic and sea ice algal assemblages along the Antarctic continental shelf - Tortell, Philippe D; Mills, Mathew M; Payne, Christopher D; Maldonado, Maria T; Chierici, Melissa; Fransson, Agneta; Alderkamp, Anne-Carlijn; Arrigo, Kevin R (Marine Ecology Progress Series, 2013)
Physiological characteristics of inorganic C uptake were examined in Southern Ocean ice algae and phytoplankton assemblages. Ice algal and phytoplankton assemblages were largely dominated by diatoms and Phaeocystis antarctica, and showed a high capacity for HCO3- utilization, with direct HCO3- transport accounting for ~60% of total inorganic C uptake. Extracellular carbonic anhydrase (eCA) was detectable in all samples, but with significantly lower activity in sea ice algae. Neither HCO3- transport nor eCA activity was related to the in situ partial pressure of CO2 (pCO2) or taxonomic composition of samples. The half-saturation constant (KS) for inorganic C ranged from ~100 to 5000 µM, and showed significantly more variability among sea ice algae than phytoplankton assemblages. For the phytoplankton assemblages, there were significant positive correlations between in situ pCO2 and KS (higher C substrate affinity in low pCO2 waters), and also between KS and maximum C uptake rates (Vmax). In contrast, KS and Vmax in sea-ice algal assemblages were not correlated to each other, or to any other measured variables. The C isotope composition of particulate organic carbon(δ13C-POC) in the phytoplankton assemblages showed modest variability (range -30 to -24.6‰) and was significantly correlated to the ratio of inferred growth rates (derived from Vmax) and in situ CO2 concentrations, but not to any measured C uptake parameters. δ13C-POC in sea ice algal samples (range -25.7 to -12.9‰) was significantly heavier than in the phytoplankton assemblages, and not correlated to any other variables. Our results provide evidence for the widespread occurrence of carbon-concentrating mechanisms in Southern Ocean sea ice algae and phytoplankton assemblages. KEYWORDS: Phytoplankton · Sea ice algae · Inorganic carbon uptake · HCO3- · Carbonic anhydrase
Keywords: Sørishavet; alger; biokjemi; diatomeer; fytoplankton; kjemiske analyser; kontinentalsokkel; marin biologi

Seasonal inflow of warm water onto the southern Weddell Sea continental shelf, Antarctica - Årthun, Marius; Nicholls, Keith William; Makinson, Keith; Fedak, Michael A; Boehme, Lars (Geophysical Research Letters, 2012)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Feeding grounds of the eastern South Pacific humpback whale population include the South Orkney Islands - Dalla Rosa, Luciano; Félix, Fernando; Stevick, Peter T; Secchi, Eduardo R; Allen, Judith M; Chater, Kim; Martin, Anthony R; Basso, Manuela (Polar Research, 2012)
This paper reports on two photo-identified humpback whales (Megaptera novaeangliae) that were sighted in different years in the proximity of the South Orkney Islands, at the boundary between the Scotia and Weddell seas (60o54.5’S – 46o40.4’W and 60o42.6’S – 45o33’W). One of the whales had been previously sighted off Ecuador, a breeding ground for the eastern South Pacific population. The other whale was subsequently resighted in Bransfield Strait, off the western Antarctic Peninsula, a well-documented feeding ground for the same population. These matches give support to a hypothesis that the area south of the South Orkney Islands is occupied by whales from the eastern South Pacific breeding stock. Consequently, we propose 40oW as a new longitudinal boundary between the feeding grounds associated with the eastern South Pacific and western South Atlantic breeding stocks. Keywords: Humpback whale; photo-identification; breeding stocks; migration; South Orkney Islands; Southern Ocean
Keywords: Rosshavet; Sørishavet; knølhvaler; marin zoologi; migrasjon; oseanografi

Aerosol-Mediated Transport and Deposition of Brominated Diphenyl Ethers to Antarctica - Dickhut, Rebecca M; Cincinelli, Alessandra; Cochran, Michele; Kylin, Henrik (Environmental Science & Technology, 2012)
Brominated diphenyl ethers (BDE47, 99, 100, and 209) were measured in air, snow and sea ice throughout western Antarctica between 2001 and 2007. BDEs in Antarctic air were predominantly associated with aerosols and were low compared to those in remote regions of the northern hemisphere, except in Marguerite Bay following the fire at Rothera research station in Sept 2001, indicating that this event was a local source of BDE209 to the Antarctic environment. Aerosol BDE47/100 reflects a mixture of commercial pentaBDE products; however, BDE99/100 is suggestive of photodegradation of BDE99 during long-range atmospheric transport (LRAT) in the austral summer. BDEs in snow were lower than predicted based on snow scavenging of aerosols indicating that atmospheric deposition events may be episodic. BDE47, -99, and -100 significantly declined in Antarctic sea ice between 2001 and 2007; however, BDE209 did not decline in Antarctic sea ice over the same time period. Significant losses of BDE99 and -100 from sea ice were recorded over a 19 day period in spring 2001 demonstrating that seasonal ice processes result in the preferential loss of some BDEs. BDE47/100 and BDE99/100 in sea ice samples reflect commercial pentaBDE products, suggesting that photodegradation of BDE99 is minimal during LRAT in the austral winter.
Publisher: American Chemical Society
Keywords: Antarktis; Sørishavet; atmosfæren; forurensning; miljøgifter; polarområdene

Southern Weddell Sea shelf edge geomorphology: Implications for gully formation by the overflow of high-salinity water - Gales, Jennifer A; Larter, Robert David; Mitchell, Neil; Hillenbrand, Claus-Dieter; Østerhus, Svein; Shoosmith, Deb R (Journal of Geophysical Research: Earth Surface, 2012)
Keywords: Sørishavet; Weddellhavet; forskning; geomorfologi; isshelf; oseanografi

Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Publisher: Inter-Research
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi

Deciphering the role of southern gateways and carbon dioxide on the onset of the Antarctic Circumpolar Current - Lefebvre, Vincent; Donnadieu, Yannick; Sepulchre, Pierre; Swingedouw, Didier; Zhang, Zhong-Shi (Paleoceanography, 2012)
Growth of Antarctic ice sheet during the Cenozoic 34 million years ago appears as a potential tipping point in the long term cooling trend that began 50 Ma ago. For decades, the onset of the Antarctic Circumpolar Current (ACC) following the opening of the Drake Passage and of the Tasman Seaway has been suggested as the main driver of the continental-scale Antarctic glaciation. However, recent modeling works emphasized that the Eocene/Oligocene atmospheric carbon dioxide (CO2) lowering could be the primary forcing of the Antarctic glaciation, questioning the ACC theory. Here, we investigate the response of the ACC to changes in CO2concentrations occurring from the late Eocene to the late Oligocene. We used a fully coupled atmosphere-ocean model (FOAM) with a mid-Oligocene geography. We find that the opening of southern oceanic gateways does not trigger the onset of the ACC for CO2typical of the late Eocene (>840 ppm). A cooler background climatic state such as the one prevalent at the end of the Oligocene is required to simulate a well-developed ACC. In this cold configuration, the intensified sea-ice development around Antarctica and the resulting brine formation lead to a strong latitudinal density gradient in the Southern Ocean favoring the compensation of the Ekman transport, and consequently the ACC. Our results imply that the ACC has acted as a feedback rather than as a driver of the global cooling.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; karbondioksid; klimatologi; paleogeografi

Radar characterization of the basal interface across the grounding zone of an ice-rise promontory in East Antarctica - Matsuoka, Kenichi; Pattyn, Frank; Callens, Denis; Conway, Howard (Annals of Glaciology, 2012)
Radar power returned from the basal interface along a 42 km long profile over an ice-rise promontory and the adjacent Roi Baudouin ice shelf, Dronning Maud Land, East Antarctica, is analyzed to infer spatial variations in basal reflectivity and hence the basal environment. Extracting basal reflectivity from basal returned power requires an englacial attenuation model. We estimate attenuation in two ways: (1) using a temperature-dependent model with input from thermomechanical ice-flow models; and (2) using a radar method that linearly approximates the geometrically corrected returned power with ice thickness. The two methods give different results. We argue that attenuation calculated using a modeled temperature profile is more robust than the widely used radar method, especially in locations where depth-averaged attenuation varies spatially or where the patterns of basal reflectivity correlate with the patterns of the ice thickness.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Review of A complete guide to Antarctic wildlife: birds and mammals of the Antarctic Continent and the Southern Ocean, by Hadoram Shirihai - Mehlum, Fridtjof (Polar Research, 2012)
This impressive book is an invaluable, fully illustrated, wildlife guide for tourists and scientists visiting the Southern Ocean and Antarctica.
Keywords: Antarktis; Sørishavet; bokanmeldelser; dyreliv; fugler; marin biologi; ornitologi; pattedyr; zoologi

Virvler øker smeltingen - Smedsrud, Lars H; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Kovacs, Kit M; Nøst, Ole A (Klima: norsk magasin for klimaforskning, 2012)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima; oseanografi

Chronostratigraphic framework for the IODP Expedition 318 cores from the Wilkes Land Margin: Constraints for paleoceanographic reconstruction - Tauxe, Lisa; Stickley, Catherine; Sugisaki, Saiko; Bijl, Peter K; Bohaty, S M; Brinkhuis, Henk; Escutia, Carlota; Flores, J A; Houben, A J P; Iwai, Masao; Jiménez-Espejo, Francisco J; McKay, Robert; et al. (Paleoceanography, 2012)
The Integrated Ocean Drilling Program Expedition 318 to the Wilkes Land margin of Antarctica recovered a sedimentary succession ranging in age from lower Eocene to the Holocene. Excellent stratigraphic control is key to understanding the timing of paleoceanographic events through critical climate intervals. Drill sites recovered the lower and middle Eocene, nearly the entire Oligocene, the Miocene from about 17 Ma, the entire Pliocene and much of the Pleistocene. The paleomagnetic properties are generally suitable for magnetostratigraphic interpretation, with well-behaved demagnetization diagrams, uniform distribution of declinations, and a clear separation into two inclination modes. Although the sequences were discontinuously recovered with many gaps due to coring, and there are hiatuses from sedimentary and tectonic processes, the magnetostratigraphic patterns are in general readily interpretable. Our interpretations are integrated with the diatom, radiolarian, calcareous nannofossils and dinoflagellate cyst (dinocyst) biostratigraphy. The magnetostratigraphy significantly improves the resolution of the chronostratigraphy, particularly in intervals with poor biostratigraphic control. However, Southern Ocean records with reliable magnetostratigraphies are notably scarce, and the data reported here provide an opportunity for improved calibration of the biostratigraphic records. In particular, we provide a rare magnetostratigraphic calibration for dinocyst biostratigraphy in the Paleogene and a substantially improved diatom calibration for the Pliocene. This paper presents the stratigraphic framework for future paleoceanographic proxy records which are being developed for the Wilkes Land margin cores. It further provides tight constraints on the duration of regional hiatuses inferred from seismic surveys of the region.
Keywords: Sørishavet; biostratigrafi; chronostratigrafi; magnetostratigrafi; paleoklimatologi; paleoseanografi; seismologi

Culturable heterotrophic bacteria from Potter Cove, Antarctica, and their hydrolytic enzymes production - Tropeano, Mauro; Coria, Silvia; Turjanski, Adrían; Cicero, Daniel; Bercovich, Andrés; Mac Cormack, Walter; Vázquez, Susana (Polar Research, 2012)
Affiliations of the dominant culturable bacteria isolated from Potter Cove, South Shetland Islands, Antarctica, were investigated together with their production of cold-active hydrolytic enzymes. A total of 189 aerobic heterotrophic bacterial isolates were obtained at 4°C and sorted into 63 phylotypes based on their amplified ribosomal DNA restriction analysis profiles. The sequencing of the 16S rRNA genes of representatives from each phylotype showed that the isolates belong to the phyla Proteobacteria (classes Alpha- and Gamma-proteobacteria), Bacteroidetes (class Flavobacteria), Actinobacteria (class Actinobacteria) and Firmicutes (class Bacilli). The predominant culturable group in the site studied belongs to the class Gammaproteobacteria, with 65 isolates affiliated to the genus Pseudoalteromonas and 58 to Psychrobacter. Among the 189 isolates screened, producers of amylases (9.5%), pectinases (22.8%), cellulases (14.8%), CM-cellulases (25.4%), xylanases (20.1%) and proteases (44.4%) were detected. More than 25% of the isolates produced at least one extracellular enzyme, with some of them producing up to six of the tested extracellular enzymatic activities. These results suggest that a high culturable bacterial diversity is present in Potter Cove and that this place represents a promising source of biomolecules. Keywords: Microbial enzymes; Antarctic bacteria; marine bacteria; cold enzymes; psychrophiles.
Keywords: Sørishavet; alger; bakterier; biodiversitet; marin biologi; sjøvann; økologi; økosystemer

Impact of increasing Antarctic ice-shelf melting on Southern Ocean hydrography - Wang, Caixin; Wang, Keguang (Journal of Glaciology, 2012)
Southern Ocean hydrography has undergone substantial changes in recent decades, concurrent with an increase in the rate of Antarctic ice-shelf melting (AISM). We investigate the impact of increasing AISM on hydrography through a twin numerical experiment, with and without AISM, using a global coupled sea-ice/ocean climate model. The difference between these simulations gives a qualitative understanding of the impact of increasing AISM on hydrography. It is found that increasing AISM tends to freshen the surface water, warm the intermediate and deep waters, and freshen and warm the bottom water in the Southern Ocean. Such effects are consistent with the recent observed trends, suggesting that increasing AISM is likely a significant contributor to the changes in the Southern Ocean. Our analyses indicate potential positive feedback between hydrography and AISM that would amplify the effect on both Southern Ocean hydrography and Antarctic ice-shelf loss caused by external factors such as changing Southern Hemisphere winds.
Keywords: Sørishavet; glasiologi; hydrografi

Environmental forcings of Paleogene Southern Ocean dinoflagellate biogeography - Bijl, Peter K; Pross, Jörg; Warnaar, Jeroen; Stickley, Catherine E; Huber, Matthew; Guerstein, Raquel; Houben, Alexander J P; Sluijs, Appy; Visscher, Henk; Brinkhuis, Henk (Paleoceanography, 2011)
Despite warm polar climates and low meridional temperature gradients, a number of different high-latitude plankton assemblages were, to varying extents, dominated by endemic species during most of the Paleogene. To better understand the evolution of Paleogene plankton endemism in the high southern latitudes, we investigate the spatiotemporal distribution of the fossil remains of dinoflagellates, i.e., organic-walled cysts (dinocysts), and their response to changes in regional sea surface temperature (SST). We show that Paleocene and early Eocene (∼65–50 Ma) Southern Ocean dinocyst assemblages were largely cosmopolitan in nature but that a distinct switch from cosmopolitan-dominated to endemic-dominated assemblages (the so-called “transantarctic flora”) occurred around the early-middle Eocene boundary (∼50 Ma). The spatial distribution and relative abundance patterns of this transantarctic flora correspond well with surface water circulation patterns as reconstructed through general circulation model experiments throughout the Eocene. We quantitatively compare dinocyst assemblages with previously published TEX86–based SST reconstructions through the early and middle Eocene from a key locality in the southwest Pacific Ocean, ODP Leg 189 Site 1172 on the East Tasman Plateau. We conclude that the middle Eocene onset of the proliferation of the transantarctic flora is not linearly correlated with regional SST records and that only after the transantarctic flora became fully established later in the middle Eocene, possibly triggered by large-scale changes in surface-ocean nutrient availability, were abundances of endemic dinocysts modulated by regional SST variations.
Keywords: Sørishavet; biogeografi; fossiler; paleobotanikk; paleoseanografi; plankton

Variability of nutrient and thermal structure in surface waters between New Zealand and Antarctica, October 2004-January 2005 - Campanelli, Alessandra; Massolo, Serena; Grilli, Federica; Marini, Mauro; Paschini, Elio; Rivaro, Paola; Artegiani, Antonio; Jacobs, Stanley S (Polar Research, 2011)
We describe the upper ocean thermal structure and surface nutrient concentrations between New Zealand and Antarctica along five transects that cross the Subantarctic Front, the Polar Front and the southern Antarctic Circumpolar Current front. The surface water thermal structure is coupled with variations in surface nutrient concentrations, making water masses identifiable by both temperature and nutrient ranges. In particular, a strong latitudinal gradient in orthosilicate concentration is centred at the Polar Front. On the earlier sections, which extend south-west from the Campbell Plateau, orthosilicate increases sharply southward from 10-15 to 50-55µmol l-1, between 58°S and 60°S, while surface temperature drops from 7°C to 2°C. Nitrate increases more regularly toward the south, with concentrations ranging from 10-12µmol l-1 at 54°S to 25-30µmol l-1 at 66°S. The same features are observed during the later transects between New Zealand and the Ross Sea, but the sharp silica and surface temperature gradients are shifted between 60°S and 64°S. Both temporal and spatial factors may influence the observed variability. The January transect suggests an uptake of silica, orthophosphate and nitrate between 63°S and 70°S over the intervening month, with an average depletion near 37%, 44% and 29%, respectively. An N/P apparent drawdown ratio of 8.8±4.1 and an Si/N apparent drawdown ratio >1 suggests this depletion results from a seasonal diatom bloom. A southward movement of the oceanic fronts between New Zealand and the Ross Sea relative to prior measurements is consistent with reports of recent warming and changes in the Antarctic Circumpolar Current. Keywords: Southern Ocean, nutrients, silica belt, Antarctic Circumpolar Current, expendable bathythermograph.
Keywords: Rosshavet; Sørishavet; fytoplankton; havstrømmer; næringsstoff; vannmasser; økosystemer

Antarctic bacterial isolates that produce cold-active extracellular proteases at low temperature but are active and stable at high temperature - Martínez-Rosales, Cecilia; Castro-Sowinski, Susana (Polar Research, 2011)
We report the isolation and identification of bacteria that produce extracellular cold-active proteases, obtained from water samples collected near the Uruguayan Antarctic Base on King George Island, South Shetlands. The bacteria belonged to the genera Pseudomonas (growth between 4 and 30°C) and Flavobacterium (growth between 4 and 18°C). In all cases, extracellular protease production was evident when reaching the stationary phase at 18 and 4ºC, but was not detected at 30ºC. The zymogram revealed the secretion of one extracellular protease per isolate, each with different relative electrophoretic mobility. The extracellular proteases produced at 4ºC showed thermal activity and stability at 30ºC. Both activity and stability at temperature higher that 10ºC have no physiological meaning because the isolates do not experience such temperatures in the Antarctic environment; however, the possible ecological value of cold-active and -stable extracellular proteases is discussed. Keywords: Antarctic, cold-active enzymes, protease.
Keywords: Sørishavet; bakterier; biokjemi; marin biologi; oseanografi

A comparison of the present and last interglacial periods in six Antarctic ice cores - Masson-Delmotte, Valerie; Buiron, Daphné; Ekaykin, Alexey Anatolievich; Frezzotti, M; Gallée, Hubert; Jouzel, Jean; Krinner, Gerhard; Landais, Amaelle; Motoyama, Hideaki; Oerter, Hans; Pol, K; Pollard, D; et al. (Clim. Past, 2011)
We compare the present and last interglacial periods as recorded in Antarctic water stable isotope records now available at various temporal resolutions from six East Antarctic ice cores: Vostok, Taylor Dome, EPICA Dome C (EDC), EPICA Dronning Maud Land (EDML), Dome Fuji and the recent TALDICE ice core from Talos Dome. We first review the different modern site characteristics in terms of ice flow, meteorological conditions, precipitation intermittency and moisture origin, as depicted by meteorological data, atmospheric reanalyses and Lagrangian moisture source diagnostics. These different factors can indeed alter the relationships between temperature and water stable isotopes. Using five records with sufficient resolution on the EDC3 age scale, common features are quantified through principal component analyses. Consistent with instrumental records and atmospheric model results, the ice core data depict rather coherent and homogenous patterns in East Antarctica during the last two interglacials. Across the East Antarctic plateau, regional differences, with respect to the common East Antarctic signal, appear to have similar patterns during the current and last interglacials. We identify two abrupt shifts in isotopic records during the glacial inception at TALDICE and EDML, likely caused by regional sea ice expansion. These regional differences are discussed in terms of moisture origin and in terms of past changes in local elevation histories, which are compared to ice sheet model results. Our results suggest that elevation changes may contribute significantly to inter-site differences. These elevation changes may be underestimated by current ice sheet models.
Publisher: Copernicus Publications
Keywords: Antarktis; Dronning Maud Land; Sørishavet; atmosfæren; glasiologi; iskjerner; klimatologi; meteorologi; stabile isotoper

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi

Resources for fish feed in future mariculture - Olsen, Yngvar (Aquaculture Environment Interactions, 2011)
There is a growing concern about the ability to produce enough nutritious food to feed the global human population in this century. Environmental conflicts and a limited freshwater supply constrain further developments in agriculture; global fisheries have levelled off, and aquaculture may have to play a more prominent role in supplying human food. Freshwater is important, but it is also a major challenge to cultivate the oceans in an environmentally, economically and energy-friendly way. To support this, a long-term vision must be to derive new sources of feed, primarily taken from outside the human food chain, and to move carnivore production to a lower trophic level. The main aim of this paper is to speculate on how feed supplies can be produced for an expanding aquaculture industry by and beyond 2050 and to establish a roadmap of the actions needed to achieve this. Resources from agriculture, fish meal and fish oil are the major components of pellet fish feeds. All cultured animals take advantage of a certain fraction of fish meal in the feed, and marine carnivores depend on a supply of marine lipids containing highly unsaturated fatty acids (HUFA, with ≥3 double bonds and ≥20 carbon chain length) in the feed. The availability of HUFA is likely the main constraint for developing carnivore aquaculture in the next decades. The availability of fish meal and oil will decrease, and the competition for plant products will increase. New harvested resources are herbivore zooplankton, such as Antarctic krill and red feed, and new produced resources are macroalgae, transgenic higher HUFA-producing plants and bacterial biomass. These products are to a limited extent components of the human food chain, and all these resources will help to move cultured carnivores to lower trophic levels and can thereby increase the production capacity and the sustainability of the production. Mariculture can only become as successful as agriculture in the coming century if carnivores can be produced at around Trophic Level 2, based mainly on plant resources. There is little potential for increasing the traditional fish meal food chain in aquaculture. KEYWORDS: Global aquaculture · Mariculture · Feed resources · Marine lipids · HUFA · Trophic level
Keywords: Sørishavet; alger; bakterier; biomasse; bioressurser; fiskeri; havbruksnæring; jordbruk; krill; marin biologi; marine planter; matproduksjon; oseanografi; zooplankton

Spring phytoplankton onset after the ice break-up and sea-ice signature (Adélie Land, East Antarctica) - Riaux-Gobin, Catherine; Poulin, Michel; Dieckmann, Gerhard; Labrune, Céline; Vétion, Gilles (Polar Research, 2011)
The phytoplankton onset following the spring ice break-up in Adélie Land, East Antarctica, was studied along a short transect, from 400 m off the continent to 5 km offshore, during the austral summer of 2002. Eight days after the ice break-up, some large colonial and solitary diatom cells, known to be associated with land-fast ice and present in downward fluxes, were unable to adapt in ice-free waters, while some other solitary and short-colony forming taxa (e.g., Fragilariopsis curta, F. cylindrus) did develop. Pelagic species were becoming more abundant offshore, replacing the typical sympagic (ice-associated) taxa. Archaeomonad cysts, usually associated with sea ice, were recorded in the surface waters nearshore. Rough weather restricted the data set, but we were able to confirm that some microalgae may be reliable sea-ice indicators and that seeding by sea ice only concerns a few taxa in this coastal area of East Antarctica. Keywords: Ice break-up; phytoplankton; sea-ice signature; East Antarctica
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; havis; oseanografi; sjøis

Deglacial history of the West Antarctic Ice Sheet in the western Amundsen Sea Embayment - Smith, James A.; Hillenbrand, Claus-Dieter; Kuhn, Gerhard; Larter, Robert D.; Graham, Alastair G.C.; Ehrmann, Werner; Moreton, Steven G.; Forwick, Matthias (Quaternary Science Reviews, 2011)
The Amundsen Sea Embayment (ASE) drains approximately 35% of the West Antarctic Ice Sheet (WAIS) and is one of the most rapidly changing parts of the cryosphere. In order to predict future ice sheet behaviour, modellers require long-term records of ice-sheet melting to constrain and build confidence in their simulations. Here, we present detailed marine geological and radiocarbon data along three palaeo-ice stream tributary troughs in the western ASE to establish vital information on the timing of deglaciation of the WAIS since the Last Glacial Maximum (LGM). We have undertaken multi-proxy analyses of the cores (core description, shear strength, x-radiographs, magnetic susceptibility, wet bulk density, total organic carbon/nitrogen, carbonate content and clay mineral analyses) in order to: (1) characterise the sedimentological facies and depositional environments; and (2) identify the horizon(s) in each core that would yield the most reliable age for deglaciation. In accordance with previous studies we identify three key facies, which offer the most reliable stratigraphies for dating deglaciation by recording the transition from a grounded ice sheet to open marine environments. These facies are: i) subglacial, ii) proximal grounding line, and iii) seasonal open marine. In addition, we incorporate ages from other facies (e.g., glaciomarine diamictons deposited at some distance from the grounding line, such as glaciogenic debris flows and iceberg-rafted diamictons and turbates) into our deglacial model. In total, we have dated 78 samples (mainly the acid insoluble organic (AIO) fraction, but also calcareous foraminifers), which include 63 downcore and 15 surface samples. Through careful sample selection prior to dating, we have established a robust deglacial chronology for this sector of the WAIS. Our data show that deglaciation of the western ASE was probably underway as early as 22,351 calibrated years before present (cal yr BP), reaching the mid-shelf by 13,837 cal yr BP and the inner shelf to within c.10–12 km of the present ice shelf front between 12,618 and 10,072 cal yr BP. The deglacial steps in the western ASE broadly coincide with the rapid rises in sea-level associated with global meltwater pulses 1a and 1b, although given the potential dating uncertainty, additional, more precise ages are required before these findings can be fully substantiated. Finally, we show that the rate of ice-sheet retreat increased across the deep (up to1600 m) basins of the inner shelf, highlighting the importance of reverse slope and pinning points in accelerated phases of deglaciation.
Keywords: Amundsenhavet; Sørishavet; deglasiasjon; glasiologi; innlandsis; isshelf; marin geologi

Using fluorescence to characterize dissolved organic matter in Antarctic sea ice brines - Stedmon, Colin A; Thomas, David N; Papadimitriou, Stathys; Granskog, Mats A; Dieckmann, Gerhard S (Journal of Geophysical Research: Biogeosciences, 2011)
Sea ice plays a dynamic role in the air-sea exchange of CO2. In addition to abiotic inorganic carbon fluxes, an active microbial community produces and remineralizes organic carbon, which can accumulate in sea ice brines as dissolved organic matter (DOM). In this study, the characteristics of DOM fluorescence in Antarctic sea ice brines from the western Weddell Sea were investigated. Two humic-like components were identified, which were identical to those previously found to accumulate in the deep ocean and represent refractory material. Three amino-acid-like signals were found, one of which was unique to the brines and another that was spectrally very similar to tryptophan and found both in seawater and in brine samples. The tryptophan-like fluorescence in the brines exhibited intensities higher than could be explained by conservative behavior during the freezing of seawater. Its fluorescence was correlated with the accumulation of nitrogen-rich DOM to concentrations up to 900 μmol L−1 as dissolved organic carbon (DOC) and, thus, potentially represented proteins released by ice organisms. A second, nitrogen-poor DOM fraction also accumulated in the brines to concentrations up to 200 μmol L−1 but was not correlated with any of the fluorescence signals identified. Because of the high C:N ratio and lack of fluorescence, this material is thought to represent extracellular polymeric substances, which consist primarily of polysaccharides. The clear grouping of the DOM pool into either proteinaceous or carbohydrate-dominated material indicates that the production and accumulation of these two subpools of DOM in sea ice brines is, to some extent, decoupled.
Keywords: Sørishavet; Weddellhavet; fluorescens; gassutveksling; havis; karbondioksid; marin økologi; mikrobielle organismer; mikrobiologi; sjøis

Overvåking av havklima i Antarktis - Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor (Klima : norsk magasin for klimaforskning, 2011)
Publisher: CICERO senter for klimaforskning Place: Oslo
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer

Near-surface eddy dynamics in the Southern Ocean - Trani, Marilisa; Falco, Pierpaolo; Zambianchi, Enrico (Polar Research, 2011)
The Antarctic Circumpolar Current (ACC) is a crucial component of the global ocean conveyor belt, acting as a zonal link among the major ocean basins but, to some extent, limiting meridional exchange and tending to isolate the ocean south of it from momentum and heat income. In this work we investigate one of the most important mechanisms contributing to the poleward transfer of properties in the Southern Ocean, that is the eddy component of the dynamics. For this particular purpose, observations obtained from near-surface drifters have been used: they represent a very useful data set to analyse the eddy field because of their ability to catch a large number of scales of motion while providing a quasi-synoptic coverage of the investigated area. Estimates of the eddy heat and momentum fluxes are carried out using data taken from the Global Drifter Program databank; they refer to Surface Velocity Program drifter trajectories collected in the area south of 358S between 1995 and 2006. Eddy kinetic energies, variance ellipses, momentum and heat fluxes have been calculated using the pseudo-Eulerian method, showing patterns in good agreement with those present in the literature based on observational and model data, although there are some quantitative differences. The eddy fluxes have been separated into their rotational and divergent portions, the latter being responsible for the meridional transports. The associated zonal and depth-exponentially integrated meridional heat transport exhibits values spanning over a range between -0.4 PW and -1.1 PW in the ACC region, consistent with previous estimates. Keywords: Antarctic Circumpolar Current; eddy fluxes; Global Drifter Program data; Lagrangian oceanography; Helmholtz decomposition.
Keywords: Sørishavet; havstrømmer; hydrografi; oseanografi; virvelstrømmer

An inter-comparison of six latent and sensible heat flux products over the Southern Ocean - Yu, Lejiang; Zhang, Zhanhai; Zhong, Shiyuan; Zhou, Mingyu; Gao, Zhiqiu; Wu, Huiding; Sun, Bo (Polar Research, 2011)
The latent heat fluxes (LHF) and sensible heat fluxes (SHF) over the Southern Ocean from six different data sets are inter-compared for the period 1988- 2000. The six data sets include three satellite-based products, namely, the second version of the Goddard Satellite-Based Surface Turbulent Fluxes data set (GSSTF-2), the third version of the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS-3) and the Japanese Ocean Fluxes Data Sets with Use of Remote Sensing Observations (J-OFURO); two global reanalysis products, namely, the National Centers for Environmental Prediction-Department of Energy Reanalysis 2 data set (NCEP-2) and the European Centre for Medium-Range Weather Forecasts 40 Year Re-analysis data set (ERA-40); and the Objectively Analyzed Air-Sea Fluxes for the Global Oceans data set (OAFlux). All these products reveal a similar pattern in the averaged flux fields. The zonal mean LHF fields all exhibit a continuous increase equatorward. With an exception of HOAPS-3, the zonal mean SHF fields display a minimum value near 50°S, increasing both pole- and equatorward. The differences in the standard deviation for LHF are larger among the six data products than the differences for SHF. Over the regions where the surface fluxes are significantly influenced by the Antarctic Oscillation and the Pacific-South American teleconnection, the values and distributions of both LHF and SHF are consistent among the six products. It was found that the spatial patterns of the standard deviations and trends of LHF and SHF can be explained primarily by sea-air specific humidity and temperature differences; wind speed plays a minor role. Keywords: Latent heat flux; sensible heat flux; Southern Ocean.
Keywords: Sørishavet; klimatologi; meteorologi; observasjoner

Natural iron enrichment around the Antarctic Peninsula in the Southern Ocean - Ardelan, M. V.; Holm-Hansen, O.; Hewes, C. D.; Reiss, C. S.; Silva, N. S.; Dulaiova, H.; Steinnes, E.; Sakshaug, E. (Biogeosciences, 2010)
As part of the US-AMLR program in January-February of 2006, 99 stations in the South Shetland Islands-Antarctic Peninsula region were sampled to understand the variability in hydrographic and biological properties related to the abundance and distribution of krill in this area. Concentrations of dissolved iron (DFe) and total acid-leachable iron (TaLFe) were measured in the upper 150 m at 16 of these stations (both coastal and pelagic waters) to better resolve the factors limiting primary production in this area and in downstream waters of the Scotia Sea. The concentrations of DFe and TaLFe in the upper mixed layer (UML) were relatively high in Weddell Sea Shelf Waters (~0.6 nM and 15 nM, respectively) and low in Drake Passage waters (~0.2 nM and 0.9 nM, respectively). In the Bransfield Strait, representing a mixture of waters from the Weddell Sea and the Antarctic Circumpolar Current (ACC), concentrations of DFe were ~0.4 nM and of TaLFe ~1.7 nM. The highest concentrations of DFe and TaLFe in the UML were found at shallow coastal stations close to Livingston Island (~1.6 nM and 100 nM, respectively). The ratio of TaLFe:DFe varied with the distance to land: ~45 at the shallow coastal stations, ~15 in the high-salinity waters of Bransfield Strait, and ~4 in ACC waters. Concentrations of DFe increased slightly with depth in the water column, while that of TaLFe did not show any consistent trend with depth. Our Fe data are discussed in regard to the hydrography and water circulation patterns in the study area, and with the hypothesis that the relatively high rates of primary production in the central regions of the Scotia Sea are partially sustained by natural iron enrichment resulting from a northeasterly flow of iron-rich coastal waters originating in the South Shetland Islands-Antarctic Peninsula region.
Keywords: Sør-Shetlandsøyene; Sørishavet; biogeokjemi; fytoplankton; hydrografi; marin biologi; marin kjemi; oseanografi

An isopycnic ocean carbon cycle model - Assmann, K. M.; Bentsen, M.; Segschneider, J.; Heinze, C. (Geoscientific Model Development, 2010)
The carbon cycle is a major forcing component in the global climate system. Modelling studies, aiming to explain recent and past climatic changes and to project future ones, increasingly include the interaction between the physical and biogeochemical systems. Their ocean components are generally z-coordinate models that are conceptually easy to use but that employ a vertical coordinate that is alien to the real ocean structure. Here, we present first results from a newly-developed isopycnic carbon cycle model and demonstrate the viability of using an isopycnic physical component for this purpose. As expected, the model represents well the interior ocean transport of biogeochemical tracers and produces realistic tracer distributions. Difficulties in employing a purely isopycnic coordinate lie mainly in the treatment of the surface boundary layer which is often represented by a bulk mixed layer. The most significant adjustments of the ocean biogeochemistry model HAMOCC, for use with an isopycnic coordinate, were in the representation of upper ocean biological production. We present a series of sensitivity studies exploring the effect of changes in biogeochemical and physical processes on export production and nutrient distribution. Apart from giving us pointers for further model development, they highlight the importance of preformed nutrient distributions in the Southern Ocean for global nutrient distributions. The sensitivity studies show that iron limitation for biological particle production, the treatment of light penetration for biological production, and the role of diapycnal mixing result in significant changes of nutrient distributions and liniting factors of biological production.
Keywords: Sørishavet; biogeokjemi; karbon syklus; klimamodeller

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Millennial scale evolution of the Southern Ocean chemical divide - Charles, Christopher D.; Pahnke, Katharina; Zahn, Rainer; Mortyn, P.G.; Ninnemann, Ulysses; Hodell, D.A. (Quaternary Science Reviews, 2010)
The chemical properties of the mid-depth and deep Southern Ocean are diagnostic of the mechanisms of abrupt changes in the global ocean throughout the late Pleistocene, because the regional water mass conversion and mixing help determine global ocean gradients. Here we define continuous time series of Southern Ocean vertical gradients by differencing the records from two high deposition rate deep sea sedimentary sequences that span the last several ice age cycles. The inferred changes in vertical carbon and oxygen isotopic gradients were dominated by variability on the millennial scale, and they followed closely the abrupt climate events of the high latitude Northern Hemisphere. In particular, the stadial events of at least the last 200kyr were characterized by enhanced mid-deep gradients in both δ13C (dissolved inorganic carbon) and δ18O (temperature). Interstadial events, conversely, featured reduced vertical gradients in both properties. The glacial terminations represented exceptions to this pattern of variability, as the vertical carbon isotopic gradient flattened dramatically at times of peak warmth in the Southern Ocean surface waters and with little or no corresponding change δ18O gradient. The available evidence suggests that properties of the upper layer of the Southern Ocean (Antarctic Intermediate Water) were influenced by an atmospherically mediated teleconnection to high latitude Northern Hemisphere.
Keywords: Sørishavet; geologi; oseanografi; paleoklimatologi

Observations of the Antarctic Slope Undercurrent in the southeastern Weddell Sea - Chavanne, Cédric P; Heywood, Karen J; Nicholls, Keith W; Fer, Ilker (Geophysical Research Letters, 2010)
The Antarctic Slope Front presents a dynamical barrier between the cold Antarctic shelf waters in contact with ice shelves and the warmer subsurface waters offshore. Two hydrographic sections with full-depth current measurements were undertaken in January and February 2009 across the slope and shelf in the southeastern Weddell Sea. Southwestward surface-intensified currents of ∼30 cm s−1, and northeastward undercurrents of 6–9 cm s−1, were in thermal-wind balance with the sloping isopycnals across the front, which migrated offshore by 30 km in the time interval between the two sections. A mid-depth undercurrent on February 23 was associated with a 130-m uplift of the main pycnocline, bringing Warm Deep Water closer to the shelf break. This vertical displacement, comparable to that caused by seasonal variations in wind speed, implies that undercurrents may affect the exchanges between coastal and deep waters near the Antarctic continental margins.
Keywords: Sørishavet; Weddellhavet; hydrografi; isbrem; isshelf; kontinentalmargin; kontinentalsokkel; oseanografi; understrømmer

Holocene Antarctic climate variability from ice and marine sediment cores: insights on ocean-atmosphere interaction - Divine, Dmitry; Koç, Nalân; Isaksson, Elisabeth; Nielsen, Simon H; Crosta, Xavier; Godtliebsen, Fred (Quaternary Science Reviews, 2010)
Holocene climate variability in the southeast Atlantic sector of the Southern Ocean and Antarctic is assessed and quantified through integration of available marine sediment core and Antarctic ice core data. We use summer sea surface temperature (SSST) and sea ice presence (SIP) reconstructions from two marine sediment cores recovered north (50 °S) and south (53.2 °S) of the present day Antarctic Polar Front (APF), as well as an atmospheric temperature and sea ice proxy from the EPICA ice core from Dronning Maud Land (EDML). We find reasonably good agreement in the timing of climate evolution in the analyzed series. Almost all records show a gradual glacial-to-Holocene climate transition, interrupted by the Antarctic cold reversal around 13 000 cal yr BP, and early Holocene climatic optimum (HCO) at about 11 000 cal yr BP. During the early HCO, the seasonal ice cover retreats to south of 53 °S; it then readvances in the course of the mid- to late Holocene. The maximum winter sea ice edge position during the recent 10 000 years varied mainly within 51–53 °S, with sporadic growth to north of 50 °S, a position similar to that during the last glacial. The onset of the Neoglacial period after ca 4000 yr BP is associated with a steepening of the SSST gradient between the marine core sites, strengthening of the westerlies and cooling in the inland ice sheet. The agreement in timing between elevated SSST during the early HCO and decreased deuterium excess in EDML and other ice cores from different locations in the East Antarctic suggests that the retreat of sea ice during the early HCO and weakening of the APF was a general feature of the East Antarctic climate during that time.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; holocene; iskjerner; klimaendringer; oseanografi; paleoklimatologi

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

Hva skjedde med vågehvalen i Antarktis? - Fujise, Yoshihiro; Hatanaka, Hiroshi; Ohsumi, Seiji (Ottar, 2010)
Jakten på de store bardehvalene i antarktiske farvann startet på begynnelsen av 1900-tallet og reduserte bestandene sterkt. Vågehvalen ble mindre utsatt for fangst og fikk kanskje en fordel da de større konkurrentene forsvant? Det japanske forskningsprogrammet JARPA har studert endringer i det marine økosystemet i Antarktis.
Keywords: Sørishavet; kval; marin biologi; økosystemer

Neogene biochronology of Antarctic diatoms: A comparison between two quantitative approaches, CONOP and UAgraph - Galster, Federico; Guex, Jean; Hammer, Oyvind (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
A quantitative biochronological study by Cody et al. (2008) integrates comprehensive diatom biostratigraphy, magnetostratigraphy, and tephrostratigraphy from 32 Neogene sections around the Southern Ocean and Antarctic continental margin. A recent method, known as Constrained Optimization (CONOP), which can be viewed as a multidimensional version of graphic correlation, is applied to that very interesting database. The goal of the present paper is to discuss some theoretical aspects of quantitative biochronology and to compare the constrained optimization with the deterministic method called Unitary Associations (UAM), a graph theoretical model. We illustrate the fact that the UAM is an extremely powerful and unique theory allowing an in-depth analysis of the internal conflicting inter-taxon stratigraphic relationships, inherent to any complex biostratigraphical database.
Keywords: Antarktis; Sørishavet; biokronologi; diatomeer; paleogeografi; paleoklimatologi; paleontologi; paleoøkologi

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Publisher: SAGE Publications Inc
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

Polarskipet Antarctics stolte historie. Del 2 - Goldberg, Fred (Polarboken, 2010)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; logistikk

Isopycnal diffusivities in the Antarctic Circumpolar Current inferred from Lagrangian floats in an eddying model - Griesel, Alexa; Gille, Sarah T; Sprintall, Janet; McClean, Julie L; Lacasce, Joseph H; Maltrud, Mathew E (Journal of Geophysical Research: Oceans, 2010)
Lagrangian subsurface isopycnal eddy diffusivities are calculated from numerical floats released in several regions of the Antarctic Circumpolar Current (ACC) of the 0.1° Parallel Ocean Program. Lagrangian diffusivities are horizontally highly variable with no consistent latitudinal dependence. Elevated values are found in some areas in the core of the ACC, near topographic features, and close to the Brazil-Malvinas Confluence Zone and Agulhas Retroflection. Cross-stream eddy diffusivities are depth invariant in the model ACC. An increase of Lagrangian eddy length scales with depth is masked by the strong decrease with depth of eddy velocities. The cross-stream diffusivities average 750 ± 250 m2 s−1 around the Polar Frontal Zone. The results imply that parameterizations that (only) use eddy kinetic energy to parameterize the diffusivities are incomplete. We suggest that dominant correlations of Lagrangian eddy diffusivities with eddy kinetic energy found in previous studies may have been due to the use of too short time lags in the integration of the velocity autocovariance used to infer the diffusivities. We find evidence that strong mean flow inhibits cross-stream mixing within the ACC, but there are also areas where cross-stream diffusivities are large in spite of strong mean flows, for example, in regions close to topographic obstacles such as the Kerguelen Plateau.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; oseanografi; vannmasser; vannvirvler

Data-based estimation of anthropogenic carbon and acidification in the Weddell Sea on a decadal timescale - Hauck, J.; Hoppema, M.; Bellerby, R. G. J.; Völker, C.; Wolf-Gladrow, D. (Journal of Geophysical Research: Oceans, 2010)
The amount of anthropogenic CO2 (Cant) that entered the Weddell Sea between 1992 and 2008 (Cant1992?2008) was assessed using the extended multiple linear regression (eMLR) method. In the Warm Deep Water (WDW) and the Weddell Sea Bottom Water (WSBW), Cant1992?2008 values were insignificant, whereas values as high as 8 ?mol kg?1 were observed over the shelf. Cant1992?2008 concentrations in the surface layer varied with latitude between 2 and 11 ?mol kg?1. Weak intrusion of anthropogenic CO2 into Weddell Sea Deep Water (WSDW) was demonstrated (Cant1992?2008 yields 1.5?2 ?mol kg?1). That more Cant1992?2008 was found in the WSDW than in the WSBW is surprising, but can be explained by intense ventilation of the WSDW originating from east of the Weddell Gyre. The invasion of Cant1992?2008 provokes a shift in the equilibria of the carbonate system, resulting in acidification and reduction of CO32? concentration. The mean decrease of pH in the upper 200 m layer was 0.016. The largest decrease of calcite and aragonite saturation states was observed at the surface. This implies that surface waters might become undersaturated with respect to aragonite in the future while the underlying WDW is still saturated. Results of this analysis suggest that complete undersaturation of surface waters in the Weddell Sea will be reached after the 21st century.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; havforsuring; karbondioksid; oseanografi

Swarm characteristics of Antarctic krill Euphausia superba relative to the proximity of land during summer in the Scotia Sea - Klevjer, Thor Aleksander; Tarling, Geraint A.; Fielding, S. (Marine Ecology Progress Series, 2010)
We studied the relationship between the proximity of land and the distribution and swarming characteristics of Antarctic krill across the Scotia Sea in January and February 2003. Krill swarms identified with a Simrad EK60 (38 kHz, 120 kHz) echosounder were grouped into 4 categories according to distance from shoreline: 0 to 50 km, 50 to 100 km, 100 to 200 km and >200 km. Cross-sectional areas of swarms were significantly larger inshore, with a mean value of 120 m^2 in the 0 to 50 km zone compared to <80 m^2 further offshore. The packing concentration of krill within inshore swarms was also significantly greater, with an average density of 95 ind. m^–3 compared to between 24 and 31 ind. m^–3 elsewhere. A large proportion of the biomass was concentrated into a small number of large, dense swarms throughout the survey area, and this trend increased with decreasing distance from shore. The highest median number of swarms per km and krill acoustic biomass per km was found in the 50 to 100 km zone. However, a significantly greater number of large, biomass-rich swarms occurred in the 0 to 50 km zone compared to all other zones. Swarms in the 0 to 50 km zone were also significantly further apart. The majority of swarms were located in the upper 50 m during the daytime although they were marginally deeper in the night in offshore regions. Krill are likely to move between inshore and offshore environments continuously over their lifetimes. The change in krill behaviour between environments could be a response to local predatory threats over short spatial and temporal scales.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; oseanografi; plankton

Distribution and demography of Antarctic krill in the Southeast Atlantic sector of the Southern Ocean during the austral summer 2008 - Krafft, Bjørn A.; Melle, W.; Knutsen, T.; Bagøien, E.; Broms, C.; Ellertsen, B.; Siegel, V. (Polar Biology, 2010)
This study documents horizontal distribution and demography of Antarctic krill (Euphausia superba) from the Southern Ocean during January–March 2008. The cruise predominantly occurred in CCAMLR Subarea 48.6, where knowledge about the ecosystem is limited. E. superba were not found north of 52°S. The biomass, estimated from trawl catches, was highest (63.09 g/m2) at a station 680 km southeast of Bouvetøya and at two stations 1,400 and 600 km southeast and southwest of Bouvetøya, 54.67 and 61.38 g/m2, respectively. Body length ranged from 19 to 61 mm (N = 8,538), with a mean of 42.0 ± 6.4 mm (SD). The overall sex ratio was 1:1, 46.2% males (13.2% adults and 33.0% subadults), 46.1% females (33.6% adults and 12.5% subadults), while 7.5% were juveniles. Trawl stations dominated by adults were found west and north of Bouvetøya. Stations with high proportions of subadults and juveniles were mainly found southeast of the island. Four cluster groups were differentiated: analyzing data on krill sex proportions, maturity stages, hydrography, nutrients and chlorophyll concentrations. Two groups represented stations located in the northern part of the study area, where E. superba were absent; water temperatures were higher and the nutrient concentrations lower compared to the groups where E. superba were present. This study shows that bathymetric features like the North Weddell Ridge including Bouvetøya are important for concentrating krill probably due to water mass characteristics and advective processes which influence regional krill demography. The southern regions of CCAMLR sector 48.6 are essential for understanding regional krill recruitment and production.
Keywords: Bouvetøya; Sørishavet; krill; marin biologi; marine økosystemer; zooplankton

Importance of the contribution of Limacina helicina faecal pellets to the carbon pump in Terra Nova Bay (Antarctica) - Manno, C.; Tirelli, V.; Accornero, A.; Fonda Umani, S. (Journal of Plankton Research, 2010)
The understanding of the role of the pteropods Limacina helicina in the ecosystem has become of greater interest as the debate on ocean acidification and its consequences for calcifying organisms has increased. Four incubation experiments were carried out in January and February 2006 in Terra Nova Bay Polynya (Ross Sea) to identify the faecal pellets (FPs) produced by L. helicina. Mean FP production rates were 6.1 ± 1.3 and 10.9 ± 2.1 pellets day−1 individual−1 in January and February, respectively. FPs produced by L. helicina had an oval shape with a more lengthened side. The identification of L. helicina faeces allowed us to quantify the amounts of L. helicina FPs in the material collected by sediment traps deployed in the same area from 1998 to 2001. We found that L. helicina FPs flux ranged from 71 × 103 FP m−2 year−1 to 362 × 103 FP m−2 year−1 and reach maximum values in March–April every year. The FPs flux of this organism contributed 19% of the particle organic carbon flux. The carbon pump may be modified if the L. helicina population declines as a consequence of the predicted acidification in polar and subpolar waters.
Keywords: Rosshavet; Sørishavet; havforsuring; krill; marin biologi; oseanografi; plankton

An observation of the banded structure of the Antarctic Coastal Current at the prime meridian - Núñez-Riboni, Ismael; Fahrbach, Eberhard (Polar Research, 2010)
Observations of three bands of westward flow and two countercurrents, spanning roughly 50 km from the ice-shelf edge in front of the Fimbul Ice Shelf (prime meridian) in Antarctica, are presented. A comparison with a numerical model and the proximity of two of these current cores to the ice shelf suggest that they split from the Antarctic Coastal Current because of the influence of sea ice on the surface drag. A comparison with previous studies suggests that the other core is the current associated with the Antarctic Slope Front. Because the Fimbul ice shelf overhangs the continental shelf, the Antarctic Coastal Current displaces offshore, getting close to the Antarctic Slope Front. The obtained structure is derived from conductivity–temperature–depth geostrophic velocities from February 2005, referenced with detided acoustic Doppler current profiler velocities.
Keywords: Sørishavet; geostrofisk; havis; havstrømmer; hydrografi; kyststrøm; meteorologi; sjøis

Land and sea-ice properties in Antarctica: bridging the gap between the ground and satellite measurements in the western Ross Sea region - Rack, Wolfgang; Langhorne, Pat; Haas, Christian; Clavano, Wendy; Gough, Alex; Kruetzmann, Nikolai; Pinchin, James; Riger-Kusk, Mette (Ice and climate news, 2010)
Keywords: Antarktis; Sørishavet; glasiologi; havis; isshelf

Wintertime mixed layer measurements at Maud Rise, Weddell Sea - Sirevaag, Anders; McPhee, Miles G; Morison, James H; Shaw, William J; Stanton, Timothy P (Journal of Geophysical Research: Oceans, 2010)
Sea ice plays a crucial role in the exchange of heat between the ocean and the atmosphere, and areas of intense air-sea-ice interaction are important sites for water mass modification. The Weddell Sea is one of these sites where a relatively thin first-year ice cover is constantly being changed by mixing of heat from below and stress exerted from the rapidly changing and intense winds. This study presents mixed layer turbulence measurements obtained during two wintertime drift stations in August 2005 in the eastern Weddell Sea, close to the Maud Rise seamount. Turbulence in the boundary layer is found to be controlled by the drifting ice. Directly measured heat fluxes compare well with previous studies and are well estimated from the mixed layer temperatures and mixing. Heat fluxes are also found to roughly balance the conductive heat flux in the ice; hence, little freezing/melting was observed. The under-ice topography is estimated to be hydraulically very smooth; comparison with a steady 1-D model shows that these estimates are made too close to the ice-ocean interface to be representative for the entire ice floe. The main source and sink of turbulent kinetic energy are shear production and dissipation. Observations indicate that the dynamics of the under-ice boundary layer are influenced by a horizontal variability in mixed layer density and an increasing amount of open leads in the area.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; havis; hydrografi; oseanografi; pyknoklin; sjøis

A consistent data set of Antarctic ice sheet topography, cavity geometry, and global bathymetry - Timmermann, Ralph; Le Brocq, Anne M; Deen, Tara J; Domack, Eugene W; Dutrieux, Pierre; Galton-Fenzi, Benjamin K; Hellmer, Hartmut H; Humbert, Angelika; Jansen, Daniela; Jenkins, Adrian; Lambrecht, Astrid; Makinson, Keith; et al. (Earth Syst. Sci. Data, 2010)
Sub-ice shelf circulation and freezing/melting rates in ocean general circulation models depend critically on an accurate and consistent representation of cavity geometry. Existing global or pan-Antarctic data sets have turned out to contain various inconsistencies and inaccuracies. The goal of this work is to compile in- dependent regional fields into a global data set. We use the S-2004 global 1-minute bathymetry as the backbone and add an improved version of the BEDMAP topography (ALBMAP bedrock topography) for an area that roughly coincides with the Antarctic continental shelf. The position of the merging line is individually chosen in different sectors in order to get the best out of each data set. High resolution gridded data for upper and lower ice surface topographies and cavity geometry of the Amery, Fimbul, Filchner-Ronne, Larsen C and George VI Ice Shelves, and for Pine Island Glacier are carefully merged into the ambient ice and ocean topographies. Multibeam survey data for bathymetry in the former Larsen B cavity and the southeastern Bellingshausen Sea have been obtained from the data centers of Alfred Wegener Institute (AWI), British Antarctic Survey (BAS) and Lamont-Doherty Earth Observatory (LDEO), gridded, and blended into the existing bathymetry map. The resulting global 1-minute topography data set (RTopo-1) contains maps for upper and lower ice surface heights, bedrock bathymetry, and consistent masks for open ocean, grounded ice, floating ice, and bare land surface.
Publisher: Copernicus Publications
Keywords: Antarktis; Sørishavet; batymetri; glasiologi; havbunnen; topografi

Venom on ice: First insights into Antarctic octopus venoms - Undheim, E.A.B.; Georgieva, D.N.; Thoen, H.H.; Norman, J.A.; Mork, J.; Betzel, C.; Fry, B.G. (Toxicon, 2010)
The venom of Antarctic octopus remains completely unstudied. Here, a preliminary investigation was conducted into the properties of posterior salivary gland (PSG) extracts from four Antarctica eledonine (Incirrata; Octopodidae) species (Adelieledone polymorpha, Megaleledone setebos, Pareledone aequipapillae, and Pareledone turqueti) collected from the coast off George V’s Land, Antarctica. Specimens were assayed for alkaline phosphatase (ALP), acetylcholinesterase (AChE), proteolytic, phospholipase A2 (PLA2), and haemolytic activities. For comparison, stomach tissue from Cirroctopus sp. (Cirrata; Cirroctopodidae) was also assayed for ALP, AChE, proteolytic and haemolytic activities. Dietary and morphological data were collected from the literature to explore the ecological importance of venom, taking an adaptive evolutionary approach. Of the incirrate species, three showed activities in all assays, while P. turqueti did not exhibit any haemolytic activity. There was evidence for cold-adaptation of ALP in all incirrates, while proteolytic activity in all except P. turqueti. Cirroctopus sp. stomach tissue extract showed ALP, AChE and some proteolytic activity. It was concluded that the AChE activity seen in the PSG extracts was possibly due to a release of household proteins, and not one of the secreted salivary toxins. Although venom undoubtedly plays an important part in prey capture and processing by Antarctica eledonines, no obvious adaptations to differences in diet or morphology were apparent from the enzymatic and haemolytic assays. However, several morphological features including enlarged PSG, small buccal mass, and small beak suggest such adaptations are present. Future studies should be conducted on several levels: Venomic, providing more detailed information on the venom compositions as well as the venom components themselves; ecological, for example application of serological or genetic methods in identifying stomach contents; and behavioural, including observations on capture of different types of prey.
Keywords: Sørishavet; biokjemi; bløtdyr; marin biologi; toksikologi

Genetic identification of Southern Ocean octopod samples using mtCOI - Undheim, Eivind Andreas Baste; Norman, Janette Ann; Thoen, Hanne Halkinrud; Fry, Bryan Grieg (Comptes Rendus. Biologies, 2010)
East Antarctic octopods were identified by sequencing mtCOI and using four analytical approaches: Neighbor-joining by Kimura-2-Parameter-based distances, character-based, BLAST, and Bayesian Inference of Phylogeny. Although the distance-based analytical approaches identified a high proportion of the sequences (99.5% to genus and 88.1% to species level), these results are undermined by the absence of a clear gap between intra-and interspecific variation. The character-based approach gave highly conflicting results compared to the distance-based methods and failed to identify apomorphic characters for many of the species. While a DNA independent approach is necessary for validation of the method comparisons, crude morphological observations give early support to the distance-based results and indicate extensive range expansions of several species compared to previous studies. Furthermore, the use of distance-based phylogenetic methods nevertheless group specimens into plausible species clades that are highly useful in non-taxonomical or non-systematic studies. (C) 2010 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Publisher: Elsevier
Keywords: Sørishavet; blekksprut; genetikk; marin biologi; taksonomi

The acoustic properties of Salpa thompsoni - Wiebe, Peter H.; Chu, Dezhang; Kaartvedt, Stein; Hundt, Anna; Melle, Webjorn; Ona, Egil; Batta-Lona, Paola (ICES Journal of Marine Science, 2010)
Wiebe, P. H., Chu, D., Kaartvedt, S., Hundt, A., Melle, W., Ona, E., and Batta-Lona, P. 2010. The acoustic properties of Salpa thompsoni. – ICES Journal of Marine Science, 67: 583–593.Aggregations of the salp Salpa thompsoni were encountered during the Antarctic krill and ecosystem-studies cruise on the RV “G.O. Sars” from 19 February to 27 March 2008. The salp's in situ target strength (TS), size, number of individuals in aggregate chains, and chain angle of orientation were determined. Shipboard measurements were made of Salpa thompsoni's material properties. Individual aggregates were mostly 45.5–60.6 mm in mean length; relatively rare solitaries were ∼100 mm. Chains ranged from 3 to at least 121 individuals, and in surface waters (<20 m), they showed no preferred angle of orientation. Sound-speed contrast (h) ranged from 1.0060 to 1.0201 and density contrast (g) estimates between 1.0000 and 1.0039. The in situ TS distributions peaked between −75 and −76 dB at 38 kHz, with a secondary peak at approximately −65 dB. TS ranged between −85 and −65 dB at 120 and 200 kHz and peaked around −74 dB. The measured in situ TS of salps reasonably matched the theoretical scattering-model predictions based on multi-individual chains. The backscattering from aggregate salps gives rise to TS values that can be similar to krill and other zooplankton with higher density and sound-speed contrasts.
Keywords: Bouvetøya; Sørishavet; copepoder; ekkolodd; krill; marin biologi; marine økosystemer; oseanografi; plankton

Cloning and heterologous expression of two cold-active lipases from the Antarctic bacterium Psychrobacter sp. G - Xuezheng, Lin; Shuoshuo, Cui; Guoying, Xu; Shuai, Wang; Ning, Du; Jihong, Shen (Polar Research, 2010)
Antarctic bacteria producing extracellular lipolytic enzymes with activity at low temperature were isolated, and the most promising strain, named G, was identified as a Psychrobacter species based on 16S rDNA sequence alignment. The genomic DNA of this bacterium was used to construct its plasmid genomic library into pUC118 plasmid vectors, and to screen the cold-active lipolytic enzyme genes. Two genes encoding for cold-active lipolytic enzymes, Lip-1452 (with an open reading frame of 1452 bp in length) and Lip-948 (with an open reading frame of 948 bp in length), were screened. The primary structure of the two lipases deduced from the nucleotide sequence showed a consensus pentapeptide containing the active serine (Lip-1452, GDSAG, and Lip-948, GNSMG) and a conserved His-Gly dipeptide in the N-terminal part of the enzyme. Protein sequence alignment and conserved regions analysis indicated that the two lipases probably belonged to family IV and family V of the bacterial lipolytic enzymes, respectively. The upstream and downstream sequences of the two lipolytic lipases were also obtained. The two lipase genes were cloned into the expression vector pCold III and integrated into Escherichia coli BL21 (DE3). The functional expression of both lipase genes by E. coli BL21 (DE3) cells was observed as the formation of clear haloes around colonies on a 1% (vol/vol) tributyrin plate upon induction with isopropyl-b-Dthiogalactopyranoside at 5°C. A lipase activity assay showed that the specific activity of the pCold III+Lip-948 expression system was up to 3.7 U ml-1, whereas that of pCold III+Lip-1452 was very low.
Keywords: Sørishavet; bakterier; bioteknologi; genkloning; genuttrykk; marin biologi; mikroorganismer

The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Publisher: Cambridge University Press
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Mixing on the continental slope of the southern Weddell Sea - Daae, Kjersti L.; Fer, Ilker; Abrahamsen, E. Povl (Journal of Geophysical Research: Oceans, 2009)
Shipboard hydrography and current profiles collected in 2003 and time series from moored current meters deployed in late 1990s are analyzed to study the variability of mixing in the southeastern Weddell Sea. Profiles of eddy diffusivity Kρ are inferred from fine-scale shear (vertical derivative of horizontal velocity) and strain (vertical derivative of isopycnal displacement) variance using parameterizations which relate the internal wave energy to the dissipation rate at small scales. The highest mixing rates are seen near the bottom where the eddy diffusivities are elevated by 1 order of magnitude from those in the interior and exceed 10−4 m2 s−1. The observations show latitudinal variability in Kρ, particularly near the bottom, where Kρ significantly increases near 74° 28′S, the critical latitude for lunar semidiurnal (M2) tides. In this region, the critical latitude coincides with near-critical topography on the upper continental slope, a situation which favors generation of M2 internal waves. Consistent with the results from fine-scale shear and strain parameterizations, which indicate highest bottom diffusivities near the critical latitude, independent analysis of current time series from moored instruments shows a thickening of the frictional bottom boundary layer near the critical latitude. Semidiurnal tidal dynamics at the upper continental slope together with the critical latitude effects lead to mixing that might significantly affect the regional heat budget and the circulation in the study area.
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; hydrografi; kontinentalmargin; oseanografi; vannvirvler

Tropical Pacific - high latitude south Atlantic teleconnections as seen in δ18O variability in Antarctic coastal ice cores - Divine, Dmitry; Isaksson, Elisabeth; Kaczmarska, Marzena; Godtliebsen, Fred; Oerter, Hans; Schlosser, Elisabeth; Johnsen, Sigfus J; van den Broeke, M; van de Wal, R S W (Journal of Geophysical Research: Atmospheres, 2009)
We use a network of eight ice cores from coastal Dronning Maud Land (DML), Antarctica, to examine the role of the tropical ENSO (El Niño-Southern Oscillation) in the temporal variability of δ18O in annual accumulation. The longest record from the S100 ice core covering the period 1737–1999 is used to analyze the teleconnections between the tropical Pacific and coastal DML on decadal scales and longer. A shorter stacked coastal DML δ18O series spanning 1955–1999 is constructed to assess the variability of ENSO teleconnection on interannual scales. Results suggest that, on typical ENSO timescales of 2–6 years, the strength of the teleconnection varies in time, being stronger for years with generally negative phase of the Southern Annular Mode (SAM). On the timescales of approximately two decades (bidecadal), positive isotope anomalies are associated with oceanic warming and a westward sea surface temperature (SST) gradient in the equatorial Pacific. Bidecadal variability in SAM, forced by the tropical Pacific, is proposed as a critical element in the teleconnection. Our analysis suggests that a multidecadal positive trend in the annual mean δ18O values from the analyzed cores can be indicative of the atmospheric warming that begun in this part of the DML already in the 1910s. The trend in δ18O, quantified in terms of long-term surface air temperature (SAT) changes, is consistent with the instrumental data. Yet, we speculate that the accurate estimation of SAT trends requires an assessment of the potential role of secular SAM and sea ice extent changes in shaping the isotopic signal.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; klima

Shelf-derived iron inputs drive biological productivity in the southern Drake Passage - Dulaiova, H.; Ardelan, M. V.; Henderson, P. B.; Charette, M. A. (Global Biogeochemical Cycles, 2009)
In the Southern Ocean near the Antarctic Peninsula, Antarctic Circumpolar Current (ACC) fronts interact with shelf waters facilitating lateral transport of shelf-derived components such as iron into high-nutrient offshore regions. To trace these shelf-derived components and estimate lateral mixing rates of shelf water, we used naturally occurring radium isotopes. Short-lived radium isotopes were used to quantify the rates of shelf water entrainment while Fe/228Ra ratios were used to calculate the Fe flux. In the summer of 2006 we found rapid mixing and significant lateral iron export, namely, a dissolved iron flux of 1.1 × 105 mol d−1 and total acid leachable iron flux of 1.1 × 106 mol d−1 all of which is transported in the mixed layer from the shelf region offshore. This dissolved iron flux is significant, especially considering that the bloom observed in the offshore region (0.5–2 mg chl a m−3) had an iron demand of 1.1 to 4 × 105 mol Fe. Net vertical export fluxes of particulate Fe derived from 234Th/238U disequilibrium and Fe/234Th ratios accounted for only about 25% of the dissolved iron flux. On the other hand, vertical upward mixing of iron rich deeper waters provided only 7% of the lateral dissolved iron flux. We found that similarly to other studies in iron-fertilized regions of the Southern Ocean, lateral fluxes overwhelm vertical inputs and vertical export from the water column and support significant phytoplankton blooms in the offshore regions of the Drake Passage.
Keywords: Sørishavet; Sørishavsstrømmen; biogeokjemi; fytoplankton; marin kjemi; oseanografi; radiumisotoper

Evidence for northward expansion of Antarctic Bottom Water mass in the Southern Ocean during the last glacial inception - Govin, Aline; Michel, Elisabeth; Labeyrie, Laurent; Waelbroeck, Claire; Dewilde, Fabien; Jansen, Eystein (Paleoceanography, 2009)
We investigated deep water changes in the Southern Ocean during the last glacial inception, in relationship to surface hydrology and global climatology, to better understand the mechanisms of the establishment of a glacial ocean circulation. Changes in benthic foraminiferal δ13C from three high-resolution cores are compared and indicate decoupled intermediate and deep water changes in the Southern Ocean. From the comparison with records from the North Atlantic, South Atlantic, and the Southern Ocean, we show that the early southern deep water δ13C drop observed at the MIS 5.5–5.4 transition occurred before any significant reduction of North Atlantic Deep Water ventilation. We propose that this drop is linked to the northward expansion of poorly ventilated Antarctic Bottom Water (AABW) mass in the Southern Ocean. Associated with an early cooling in the high southern latitudes, the westerly winds and surface oceanic fronts would migrate equatorward, thus weakening the upwelling of Circumpolar Deep Waters. Reduced heat brought to Antarctic surface waters would enhance sea ice formation during winters and the deep convection of cold and poorly ventilated AABW.
Keywords: AABW; Sørishavet; bunnvann; havstrømmer; hydrologi; paleoklimatologi; paleoseanografi; vannmasser

The water column as an attenuating factor of the UVR effects on bacteria from a coastal Antarctic marine environment - Hernández, Edgardo A; Ferreyra, Gustavo A; Ruberto, Lucas A M; Mac Cormack, Walter P (Polar Research, 2009)
The effect of UVR on the viability of the culturable bacterial community fraction (CBC), and two of their isolated components (Arthrobacter-UVvi and Bizionia-UVps), was studied in the top few metres of the water column at Potter Cove, King George Island, Antarctica. Quartz flasks containing CBC from surface waters were exposed to solar radiation at depths of 0, 1 and 3 m. Similar experiments using UVps and UVvi isolates were performed. In some experiments interferential filters were used to discriminate photosynthetic active radiation (PAR), UV-A and UV-B. CBC from depths of 0, 10 and 30 m were also exposed to surface solar radiation. The deleterious effect of UVR was observed at the surface and at a depth of 1 m, but not at a depth of 3 m. Studies with interferential filters showed low bacterial viability values at depths of 0 and 1 m under both UVR treatments. However, under low radiation doses the effect attributed to UV-B was higher than that caused by UV-A. The surface CBC was more resistant to UVR compared with CBC from a depth of 30 m. The results showed that CBC inhabiting waters above the pycnocline (located at a depth of 5–10 m) are more efficiently adapted to UVR than are those from below the pycnocline. The impact of UVR on the marine bacterioplankton studied was only detected in the first metre of the stratified water column of Potter Cove, which has high levels of suspended particulate matter. These results support the evidence for a significant UVR-attenuating effect in the water column of this coastal Antarctic water.
Keywords: Sørishavet; UV-stråling; bakterier; marin biologi; plankton; statistisk analyse; ultrafiolett stråling; vannsøyle

Kvalfangst i Sørishavet - Knarvik, Olaf (Kjelda, 2009)
Keywords: Sørishavet; fotografi; hvalfangst

Ice-ocean processes over the continental shelf of the southern Weddell Sea, Antarctica: A review - Nicholls, Keith W.; Østerhus, Svein; Makinson, Keith; Gammelsrød, Tor; Fahrbach, Eberhard (Reviews of Geophysics, 2009)
Interactions between the Southern Ocean and the Weddell Sea ice shelves are important both to the Antarctic Ice Sheet and to the production of globally significant water masses. Here we review the interaction between the Filchner-Ronne Ice Shelf and the shelf sea in which it floats. The continental shelf processes leading to the production of Weddell Sea deep and bottom waters from the original off-shelf source waters are discussed, and a new view is offered of the initial production of High-Salinity Shelf Water. Data from ship-based measurements at the ice front, from glaciological methods, and from measurements made within the sub–ice shelf cavity itself are used to describe the pattern of flows beneath the ice shelf. We also consider the variability observed within the cavity from tidal to interannual time scales and finish with a discussion of future research priorities in the region.
Keywords: AABW; Antarktis; Sørishavet; Weddellhavet; glasiologi; innlandsis; isfront; isshelf; oseanografi; vannmasser

Evolution of first-year and second-year snow properties on sea ice in the Weddell Sea during spring-summer transition - Nicolaus, Marcel; Haas, Christian; Willmes, Sascha (Journal of Geophysical Research: Atmospheres, 2009)
Observations of snow properties, superimposed ice, and atmospheric heat fluxes have been performed on first-year and second-year sea ice in the western Weddell Sea, Antarctica. Snow in this region is particular as it does usually survive summer ablation. Measurements were performed during Ice Station Polarstern (ISPOL), a 5-week drift station of the German icebreaker RV Polarstern. Net heat flux to the snowpack was 8 W m−2, causing only 0.1 to 0.2 m of thinning of both snow cover types, thinner first-year and thicker second-year snow. Snow thinning was dominated by compaction and evaporation, whereas melt was of minor importance and occurred only internally at or close to the surface. Characteristic differences between snow on first-year and second-year ice were found in snow thickness, temperature, and stratigraphy. Snow on second-year ice was thicker, colder, denser, and more layered than on first-year ice. Metamorphism and ablation, and thus mass balance, were similar between both regimes, because they depend more on surface heat fluxes and less on underground properties. Ice freeboard was mostly negative, but flooding occurred mainly on first-year ice. Snow and ice interface temperature did not reach the melting point during the observation period. Nevertheless, formation of discontinuous superimposed ice was observed. Color tracer experiments suggest considerable meltwater percolation within the snow, despite below-melting temperatures of lower layers. Strong meridional gradients of snow and sea-ice properties were found in this region. They suggest similar gradients in atmospheric and oceanographic conditions and implicate their importance for melt processes and the location of the summer ice edge.
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; klimatologi; meteorologi; målinger; oseanografi; sjøis; snø; økosystemer

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Observations on the relationship between the Antarctic coastal diatoms Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen and sea ice concentrations during the late Quaternary - Pike, Jennifer; Crosta, Xavier; Maddison, Eleanor J.; Stickley, Catherine E.; Denis, Delphine; Barbara, Loïc; Renssen, Hans (Marine Micropaleontology, 2009)
The available ecological and palaeoecological information for two sea ice-related marine diatoms (Bacillariophyceae), Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen, suggests that these two species have similar sea surface temperature (SST), sea surface salinity (SSS) and sea ice proximity preferences. From phytoplankton observations, both are described as summer or autumn bloom species, commonly found in low SST waters associated with sea ice, although rarely within the ice. Both species form resting spores (RS) as irradiance decreases, SST falls and SSS increases in response to freezing ice in autumn. Recent work analysing late Quaternary seasonally laminated diatom ooze from coastal Antarctic sites has revealed that sub-laminae dominated either by T. antarctica RS, or by P. glacialis RS, are nearly always deposited as the last sediment increment of the year, interpreted as representing autumn flux. In this study, we focus on sites from the East Antarctic margin and show that there is a spatial and temporal separation in whether T. antarctica RS or P. glacialis RS form the autumnal sub-laminae. For instance, in deglacial sediments from the Mertz Ninnis Trough (George V Coast) P. glacialis RS form the sub-laminae whereas in similar age sediments from Iceberg Alley (Mac.Robertson Shelf) T. antarctica RS dominate the autumn sub-lamina. In the Dumont d'Urville Trough (Adélie Land), mid-Holocene (Hypsithermal warm period) autumnal sub-laminae are dominated by T. antarctica RS whereas late Holocene (Neoglacial cool period) sub-laminae are dominated by P. glacialis RS. These observations from late Quaternary seasonally laminated sediments would appear to indicate that P. glacialis prefers slightly cooler ocean–climate conditions than T. antarctica. We test this relationship against two down-core Holocene quantitative diatom abundance records from Dumont d'Urville Trough and Svenner Channel (Princess Elizabeth Land) and compare the results with SST and sea ice concentration results of an Antarctic and Southern Ocean Holocene climate simulation that used a coupled atmosphere–sea ice–vegation model forced with orbital parameters and greenhouse gas concentrations. We find that abundance of P. glacialis RS is favoured by higher winter and spring sea ice concentrations and that a climatically-sensitive threshold exists between the abundance of P. glacialis RS and T. antarctica RS in the sediments. An increase to >0.1 for the ratio of P. glacialis RS:T. antarctica RS indicates a change to increased winter sea ice concentration (to >80% concentration), cooler spring seasons with increased sea ice, slightly warmer autumn seasons with less sea ice and a change from ~7.5months annual sea ice cover at a site to much greater than 7.5months. In the East Antarctic sediment record, an increase in the ratio from <0.1 to above 0.1 occurs at the transition from the warmer Hypsithermal climate into the cooler Neoglacial climate (~4cal kyr) indicating that the ratio between these two diatoms has the potential to be used as a semi-quantitative climate proxy.
Keywords: Sørishavet; Weddellhavet; diatomeer; havis; marin biologi; mikropaleontologi; paleontologi; paleoøkologi; sjøis

Antarctic ascidians: an isolated and homogeneous fauna - Primo, Carmen; Vázquez, Elsa (Polar Research, 2009)
Several biogeographical studies have already been performed on the ascidians of the Antarctic region. However, new data obtained in the last few years have led us to a revision of the biogeography of this fauna. To examine the biogeographical structure of the Antarctic region, we divided it into 10 sectors, depending on the principal geographical features, and then applied cluster analysis and a multi-dimensional scaling ordination to a presence/absence matrix of species for each biogeographical area. Our study shows that Antarctic ascidians are a very homogeneous fauna, with a high level of endemism in the whole region (25–51% of Antarctic endemic species per sector), but with a low percentage of sector endemism (only up to 10%). This probably results from isolation arising from the Antarctic Convergence, and the vast geographical distances from adjacent regions, as well as from the relative constancy of the hydrographical conditions and the dispersal of organisms through circumpolar currents. In fact, cosmopolitan species represented only 0–7% of the total ascidian fauna in all sectors. Only the Bellingshausen Sea (low sample size), Bouvetøya (young and isolated, with an impoverished ascidian fauna) and the South Sandwich Islands (also young and isolated) are relatively separated. The insular sectors were more closely related to the South America and sub- Antarctic regions than the continental ones, showing a latitudinal gradient.
Keywords: Sørishavet; biogeografi; fauna; sekkdyr; zoogeografi

Variability and predictability of Antarctic krill swarm structure - Tarling, Geraint A.; Klevjer, Thor; Fielding, Sophie; Watkins, Jon; Atkinson, Angus; Murphy, Eugene; Korb, Rebecca; Whitehouse, Mick; Leaper, Russell (Deep Sea Research Part I: Oceanographic Research Papers, 2009)
Swarming is a fundamental part of the life of Euphausia superba, yet we still know very little about what drives the considerable variability in swarm shape, size and biomass. We examined swarms across the Scotia Sea in January and February 2003 using a Simrad EK60 (38 and 120kHz) echosounder, concurrent with net sampling. The acoustic data were analysed through applying a swarm-identification algorithm and then filtering out all non-krill targets. The area, length, height, depth, packing-concentration and inter-swarm distance of 4525 swarms was derived by this method. Hierarchical clustering revealed 2 principal swarm types, which differed in both their dimensions and packing-concentrations. Type 1 swarms were generally small (<50m long) and were not very tightly packed (<10ind.m−3), whereas type 2 swarms were an order of magnitude larger and had packing concentrations up to 10 times greater. Further sub-divisions of these types identified small and standard swarms within the type 1 group and large and superswarms within the type 2 group. A minor group (swarm type 3) was also found, containing swarms that were isolated (>100km away from the next swarm). The distribution of swarm types over the survey grid was examined with respect to a number of potential explanatory variables describing both the environment and the internal-state of krill (namely maturity, body length, body condition). Most variables were spatially averaged over scales of ∼100km and so mainly had a mesoscale perspective. The exception was the level of light (photosynthetically active radiation (PAR)) for which measurements were specific to each swarm. A binary logistic model was constructed from four variables found to have significant explanatory power (P<0.05): surface fluorescence, PAR, krill maturity and krill body length. Larger (type 2) swarms were more commonly found during nighttime or when it was overcast during the day, when surface fluorescence was low, and when the krill were small and immature. A strong pattern of diel vertical migration was not observed although the larger and denser swarms tended to occur more often at night than during the day. The vast majority of krill were contained within a minor fraction of the total number of swarms. These krill-rich swarms were more common in areas dominated by small and immature krill. We propose that, at the mesoscale level, the structure of swarms switches from being predominantly large and tightly packed to smaller and more diffuse as krill grow and mature. This pattern is further modulated according to feeding conditions and then level of light.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; marine økosystemer; plankton

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Pleomorphism in the Antarctic flagellate Pyramimonas gelidicola (Prasinophyceae, Chlorophyta) - van den Hoff, John; Ferris, John M (Polar Research, 2009)
Species of the genus Pyramimonas (Prasinophyceae) are a common, widespread, but minor component of the Antarctic marine phytoplankton. They are often associated with the seasonal sea-ice environment. Pyramimonas gelidicola (McFadden, Moestrup & Wetherbee, 1982) was isolated from the water column of a saline Antarctic lake, and observations on the organism’s life history as it grew in unialgal cultures were made. The alga proved to be pleomorphic: capable of producing several morphologically distinct life stages. We recorded motile single-celled quadriflagellates that formed two statistically distinct size classes, a rare uniflagellate cell-type, and aggregations of quadriflagellate cells, multilobed forms and an encystment stage. Multilobed forms and cell aggregations, never before observed in an Antarctic Pyramimonas species, are presumed to be growth medium-induced morphotypes. Multilobed forms contained an equal number of nuclei and lobes, suggesting that they are the product of asexual reproduction. Some of the morphotypes we report here may never be observed under natural field conditions, but the potential for this alga to alternate between morphotypes is clearly demonstrated.
Keywords: Sørishavet; alger; fytoplankton; marin biologi

Satellite microwave observations of the interannual variability of snowmelt on sea ice in the Southern Ocean - Willmes, Sascha; Haas, Christian; Nicolaus, Marcel; Bareiss, Jörg (Journal of Geophysical Research: Oceans, 2009)
Snowmelt processes on Antarctic sea ice are examined. We present a simple snowmelt indicator based on diurnal brightness temperature variations from microwave satellite data. The method is validated through extensive field data from the western Weddell Sea and lends itself to the investigation of interannual and spatial variations of the typical snowmelt on Antarctic sea ice. We use in-situ measurements of physical snow properties to show that despite the absence of strong melting, the summer period is distinct from all other seasons with enhanced diurnal variations of snow wetness. A microwave emission model reveals that repeated thawing and refreezing cause the typical microwave emissivity signatures that are found on perennial Antarctic sea ice during summer. The proposed melt indicator accounts for the characteristic phenomenological stages of snowmelt in the Southern Ocean and detects the onset of diurnal snow wetting. An algorithm is presented to map large-scale snowmelt onset based on satellite data from the period between 1988 and 2006. The results indicate strong meridional gradients of snowmelt onset with the Weddell, Amundsen, and Ross Seas showing earliest (beginning of October) and most frequent snowmelt. Moreover, a distinct interannual variability of melt onset dates and large areas of first-year ice where no diurnal freeze thawing occurs at the surface are determined.
Article Number: C03006
Keywords: Amundsenhavet; Rosshavet; Sørishavet; Weddellhavet; fjernmåling; havis; miljøsatellitter; oseanografi; sjøis; snøsmelting

Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra, Lidia; Hernández-León, Santiago; Almeida, Carlos; Bécognée, Pierrick (Polar Research, 2009)
The vertical distribution (0–550 m) of zooplankton biomass, and indices of respiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA synthetases activity [AARS]), were studied in waters off the Antarctic Peninsula during the austral summer of 2000. The dominant species were the copepod Metridia gerlachei and the euphausiid Euphausia superba. We observed a vertical krill/copepod substitution in the water column. The zooplankton biomass in the layer at a depth of 200–500 m was of the same magnitude as the biomass in the layer at a depth of 0–200 m, indicating that biomass in the mesopelagic zone is an important fraction of the total zooplankton in Antarctic waters. The metabolic rates of the zooplankton community were sustained by less than 0.5% of the primary production in the area, suggesting that microplankton or small copepods are the main food source. Neither food availability nor predation seemed to control mesozooplankton biomass. The wide time lag between the abundance peak of the dominant copepod (M. gerlachei) and the phytoplankton bloom is suggested to be the main explanation for the low summer zooplankton biomass observed in these waters.
Keywords: Sørishavet; biomasse; fytoplankton; hydrologi; krill; metabolisme; oseanografi; zooplankton

Persistent organohalogen contaminant burdens in Antarctic krill (Euphausia superba) from the eastern Antarctic sector: A baseline study - Bengtson Nash, Susan M; Poulsen, Anita H.; Kawaguchi, So; Vetter, Walter; Schlabach, Martin (Science of the Total Environment, 2008)
A baseline for persistent organohalogen compound (POC) accumulation in the Antarctic keystone species, Antarctic krill (Euphausia superba) has been established for a 50° longitudinal range of the eastern Antarctic sector. Samples of adult krill, caught from 12 sites distributed between 30° and 80°E (60–70°S), were analysed for >100 organohalogen compounds including chlorinated pesticides, polychlorinated biphenyls (PCBs), polybrominated organic compounds and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs). Organochlorine pesticides dominated measured krill contaminant burdens with hexachlorobenzene (HCB) as the single most abundant compound quantified. Krill HCB concentrations were comparable to those detected at this trophic level in both the Arctic and temperate northwest Atlantic, lending support for the hypothesis that HCB will approach global equilibrium at a faster rate than other POCs. Para, para′-dichlorodiphenylethene (p,p′-DDE) was detected at notable concentrations. Measurements of DDT and its degradation products provide an important baseline for monitoring the temporal and geographical influence of renewed, DDT usage for malaria-control in affected southern hemisphere countries. In contrast to the Arctic, PCBs did not feature prominently in contaminant burdens of Antarctic krill. The major commercial polybrominated diphenyl ether (PBDE) congeners -99 and -47 were quantified at low background levels with clear concentration spikes observed at around 70°E , in the vicinity of modern, active research stations. The likelihood that local anthropogenic activities are supplementing low PBDE levels, delivered otherwise primarily via long range environmental transport, is discussed. The suspected naturally occurring brominated organic compound, 2,4,6-tribromoanisole (TBA), was a ubiquitous contaminant in all samples whereas the only PCDD/Fs quantifiable were trace levels of octachlorodibenzo-p-dioxin (OCDD) and 1,2,3,4,7,8/1,2,3,4,7,9-hexachlorodibenzofuran (HxCDF). With the aims of; i) Generating a robust and broadly applicable POC auditing platform for the scarcely studied eastern Antarctic sector; ii) Determining the compounds accumulating in Antarctic krill for further toxicity evaluation studies and iii) Establishing a baseline for Antarctic predator exposure to POCs, this study represents one of the most comprehensive reports of POC contamination of the Antarctic food web to date.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; menneskelig påvirkning; miljøgifter; plankton; toksikologi

"En livbåt halvfull av vann er funnet". Forlis og ulykker i hvalfangsten på 1920-tallet - Børresen, Dag Ingemar (Norsk sjøfartsmuseum. Årbok, 2008)
Publisher: Norsk sjøfartsmuseum
Keywords: Sørishavet; hvalbåter; hvalfangere; hvalfangstindustri; hvalkokerier; isfangsten; pelagisk; sjøfolk

Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Regeneration of Fe(II) during EIFeX and SOFeX - Croot, Peter L.; Bluhm, Kathrin; Schlosser, Christian; Streu, Peter; Breitbarth, Eike; Frew, Russell D.; Ardelan, Murat van (Geophysical Research Letters, 2008)
Investigations into Fe(II) cycling during two Southern Ocean mesoscale iron enrichment experiments, SOFeX and EIFeX, clearly show the importance of Fe(II) to iron speciation during these experiments. In both cases the added Fe(II) persisted significantly longer than its expected oxidation time indicating a significant Fe reduction process at work. During EIFeX diel studies showed a strong photochemically induced cycle in Fe(II) production in sunlit surface waters. Our results suggest that the photochemical cycling of iron may also be important in unfertilized waters of the Southern Ocean.
Keywords: Sørishavet; biogeokjemi; fytoplankton; marin biologi; polarområdene

Predicting the fate of ice shelves - Galton-Fenzi, Benjamin K (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Fast-ice distribution in East Antarctica during 1997 and 1999 determined using RADARSAT data - Giles, A Barry; Massom, Robert A; Lytle, Victoria I (Journal of Geophysical Research: Oceans, 2008)
We present the first detailed maps of fast ice around East Antarctica (75°E–170°E), using an image correlation technique applied to RADARSAT ScanSAR images from November in 1997 and 1999. This method is based upon searching for, and distinguishing, correlated regions of the ice-covered ocean which remain stationary, in contrast to adjacent moving pack ice. Within the overlapping longitudinal range of ∼86°E–150.6°E, the total fast-ice area is 141,450 km2 in 1997 and 152,216 km2 in 1999. Calibrated radar backscatter data are also used to determine the distribution of two fast-ice classes based on their surface roughness characteristics. These are “smooth” fast ice (−25.4 dB to −13.5 dB) and “rough” fast ice (−13.5 dB to −2.5 dB). The former comprises ∼67% of the total area, with rough fast ice making up the remaining ∼33%. An estimate is made of fast-ice volume, on the basis of fast-ice type as a proxy measure of ice thickness and area. Results suggest that although fast ice forms 2–16% of the total November sea ice area for this sector of East Antarctica in 1997 and 1999 (average 8.3% across maps), it may comprise 6–57% of the total ice volume (average ∼28% across maps). Grounded icebergs play a key role in fast-ice distribution in all regions apart from 150°E–170°E. These are “snapshot” estimates only, and more work is required to determine longer-term spatiotemporal variability.
Keywords: Sørishavet; batymetri; biologi; havis; kartlegging; landfast is; satellite bilder; sjøis; økologi

Antarctic ices shelves in a changing climate - Jenkins, Adrian (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Decline in energy storage in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Tamura, Tsutomu; Zenitani, Ryoko; Bando, Takeharu; Kato, Hidehiro; Walløe, Lars (Polar Biology, 2008)
The annual trend in energy storage in the Antarctic minke whale was examined using catch data from all 18 survey years in the Japanese Whale Research Program (JARPA). Regression analyses clearly showed that blubber thickness, girth and fat weight have been decreasing for nearly 2 decades. The decrease per year is estimated at approximately 0.02 cm for mid-lateral blubber thickness and 17 kg for fat weight, corresponding to 9% for both measurements over the 18-year period. Furthermore, "date", "extent of diatom adhesion", "sex", "body length", "fetus length", "latitude", "age" and "longitude" were all identified as partially independent predictors of blubber thickness. The direct interpretation of this substantial decline in energy storage in terms of food availability is difficult, since no long-term krill abundance series is available. However, an increase in the abundance of krill feeders other than minke whales and a resulting decrease in the krill population must be considered as a likely explanation.
Keywords: Sørishavet; hvaler; krill; marin biologi; plankton; vågehvaler

Crustal structure and tectonic provinces of the Riiser-Larsen Sea area (East Antarctica): results of geophysical studies - Leitchenkov, German; Guseva, J; Gandyukhin, V; Grikurov, G; Kristoffersen, Yngve; Sand, M; Golynsky, A; Aleshkova, N (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; seismologi; stratigrafi

Halo of ice deformation observed over the Maud Rise seamount - Lindsay, Ronald; Kwok, Ronald; de Steur, Laura; Meier, Walt (Geophysical Research Letters, 2008)
A distinctive halo of sea ice deformation was observed above the Maud Rise seamount in the eastern Weddell Sea in the winter of 2005. The deformation halo is coincident with a halo of low mean ice concentration that is often observed in the region. Monthly mean ice vorticity estimates for the months July through November reveal the deformation zone most clearly in an arc about 100 km northwest of the seamount where there is a strong gradient in the bathymetry at depths of 3000–5000 m. The deformation was computed from satellite-based ice motion vectors derived from Envisat Synthetic Aperture Radar backscatter images. The deformation halo is evidence of a Taylor cap circulation over the seamount, which has been described and analyzed with modeling studies and concurrent oceanographic observations obtained during an extensive field campaign.
Keywords: Sørishavet; Weddellhavet; havis; havstrømmer; hydrografi; oseanografi; sjøis; vannvirvler

Wintertime ocean conditions over the southern Weddell Sea continental shelf, Antarctica - Nicholls, Keith W; Boehme, Lars; Biuw, Martin; Fedak, Michael A (Geophysical Research Letters, 2008)
During the austral winter of 2007 a Weddell Seal tagged with a miniaturized conductivity-temperature-depth (CTD) instrument travelled over the central southern Weddell Sea continental shelf. The instrument yielded 750 CTD profiles, 250 of them to the sea floor. The data show a full depth flow of water onto the shelf via a sill at the shelf break (74°S 44°W). The warmth from the core of the flow was able to maintain the surface mixed layer above the freezing point, resulting in a band of reduced ice-production. An estimate of the on-shelf flux suggests that this flow accounts for most of the estimated 3 Sv of water draining from the southern Weddell Sea continental shelf.
Keywords: Sørishavet; Weddellhavet; kontinentalsokkel; marin zoologi; oseanografi; saltinnhold; seler; temperatur

Hilsen fra Sørishavet - Pedersen, Ronald (Berlevågingen, 2008)
Keywords: Sørishavet; forskning; krill; marinbiologi; teknologi

Comparison of contemporary and fossil diatom assemblages from the western Antarctic Peninsula shelf - Pike, Jennifer; Allen, Claire S.; Leventer, Amy; Stickley, Catherine E.; Pudsey, Carol J. (Marine Micropaleontology, 2008)
During the past ten years, the Antarctic Peninsula has been identified as the most rapidly warming region of the Southern Hemisphere and it is important to place this warming in the context of the natural climate and oceanographic variability of the recent geological past. Many biological proxies, such as marine diatom assemblages, have been used to determine Southern Ocean palaeoceanographic conditions during the Late Quaternary, however, few investigations have attempted to link observations of modern floras with the fossil record. In this study we examine a suite of modern austral spring (December 2003) and summer (February 2002) surface water samples from along the western Antarctic Peninsula (WAP) continental shelf and compare these to core-top, surface sediment samples. Using detrended correspondence analysis (DCA) and principal component analysis (PCA) of diatom abundance data we investigate the relationship of contemporary diatom floras with the fossil record. This multivariate analysis reveals that our modern assemblages can be divided into three groups: summer southern WAP sites, summer northern WAP sites, and spring WAP sites. Sea surface temperature (SST) is an important environmental variable for explaining seasonal differences in diatom assemblages between spring and summer, but sea surface salinity (SSS) is more important for understanding temporally-equivalent regional variations in assemblage. Our summer diatom samples are more reminiscent of early season assemblages, reflecting the unusually late sea ice retreat from the region that year. When the modern assemblages are compared to the fossil record, it is clear that most of the important diatoms from the summer assemblage are not preserved into the sediments, and that the fossil record more closely reflects spring assemblages. This observation is important for any future attempts to quantitatively reconstruct palaeoceanographic conditions along the WAP during the Late Quaternary and highlights the need for many more such studies in order to address longer timescales, such as interannual variability, in the context of the fossil record.
Keywords: Sørishavet; Vestantarktis; diatomeer; marin biologi; marin geologi; mikropaleontologi; paleoseanografi

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Rødt gull i Sørishavet - Stephansen, Susanne Moen (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2008)
En rekelignende skapning i Sørishavet er Kjell Inge Røkkes nye yndling. Den kan nemlig brukes i alt fra slankemidler til fiskefôr. Men vet vi nok om krill til å slippe trålerne løs? Forskningsskipet G.O. Sars har vært på tokt for å finne u mer.
Keywords: Sørishavet; krill; marin biologi

Land-fast ice variation during the past five decades: Lützow-Holm Bay, Antarctica - Ushio, Shuki (Ice and climate news, 2008)
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Blocking primers to enhance PCR amplification of rare sequences in mixed samples – a case study on prey DNA in Antarctic krill stomachs - Vestheim, Hege; Jarman, Simon N. (Frontiers in Zoology, 2008)
Identification of DNA sequence diversity is a powerful means for assessing the species present in environmental samples. The most common molecular strategies for estimating taxonomic composition depend upon PCR with universal primers that amplify an orthologous DNA region from a range of species. The diversity of sequences within a sample that can be detected by universal primers is often compromised by high concentrations of some DNA templates. If the DNA within the sample contains a small number of sequences in relatively high concentrations, then less concentrated sequences are often not amplified because the PCR favours the dominant DNA types. This is a particular problem in molecular diet studies, where predator DNA is often present in great excess of food-derived DNA.
Keywords: Scotiahavet; Sørishavet; genetikk; genetisk analyse; krill; marin biologi; plankton; taksonomi

Seasonal forecast of Antarctic sea ice and beyond - Yuan, Xiaojun (Ice and climate news, 2008)
Keywords: Sørishavet; glasiologi; havis

Liksomoppdagerne i Antarktis - Aasheim, Stein P (Snø & ski: årbok, 2007)
Keywords: Sørishavet; ekspedisjoner

Growth rate and its variability in erect Antarctic bryozoans - Barnes, David K. A.; Webb, Karen E.; Linse, Katrin (Polar Biology, 2007)
Climate is altering rapidly in parts of the Arctic and Antarctic but we know little about how marine organisms are responding to, or might respond to such changes. Knowledge of within-taxon variability is the vital context (currently missing) to interpretation of environmental signals. We investigated growth in six species and three genera of erect Antarctic bryozoans, an ideal model taxon to investigate such response. Cellarinella margueritae, C. nodulata, C. rogickae, C. watersi, Melicerita obliqua and Stomhypselosaria watersi, extended 3.4, 5.2, 4.6, 4.1, 4.9 and 4.5 mm year(-1) and synthesised 24, 55, 45, 176, 34 and 46 mg CaCO3 year(-1), respectively. The maximum ages of these species ranged from 11 to 15 years except M. obliqua, which reached 32 years. This is the first investigation of growth rates of closely related Antarctic invertebrate species and reports the slowest growth rates of bryozoans known from anywhere to date. Our data coupled with that from literature shows that Antarctic bryozoan growth varies << 10(1) between species, 10(1) between genera, 10(2) between morphologies and is similar to 10(1) slower than in tropical or temperate regions. However, within encrusting types the slowest growing species grow at similar rates from poles to tropics. Age was a strong confounding factor across our Antarctic study species but age-standardised data showed a possible decline in annual growth from 1992 to 2003. We identify several factors increasing this environmental signal strength, including (1) the importance of generic (though not necessarily species) identification and (2) use of dry-mass or ash-free dry-mass as the measures of growth.
Keywords: Sørishavet; bryozoa; klimaendringer; marin biologi; mosdyr

Variations in behavior and condition of a Southern Ocean top predator in relation to in situ oceanographic conditions - Biuw, Martin; Boehme, L.; Guinet, C.; Hindell, M.; Costa, D.; Charrassin, J.-B.; Roquet, F.; Bailleul, F.; Meredith, M.; Thorpe, S.; Tremblay, Y.; McDonald, B.; et al. (Proceedings of the National Academy of Sciences, 2007)
Responses by marine top predators to environmental variability have previously been almost impossible to observe directly. By using animal-mounted instruments simultaneously recording movements, diving behavior, and in situ oceanographic properties, we studied the behavioral and physiological responses of southern elephant seals to spatial environmental variability throughout their circumpolar range. Improved body condition of seals in the Atlantic sector was associated with Circumpolar Deep Water upwelling regions within the Antarctic Circumpolar Current, whereas High-Salinity Shelf Waters or temperature/salinity gradients under winter pack ice were important in the Indian and Pacific sectors. Energetic consequences of these variations could help explain recently observed population trends, showing the usefulness of this approach in examining the sensitivity of top predators to global and regional-scale climate variability.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; marin biologi; oseanografi; sjøelefanter

Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

Diversity and species distribution of polychaetes, isopods and bivalves in the Atlantic sector of the deep Southern Ocean - Ellingsen, Kari E.; Brandt, Angelika; Ebbe, Brigitte; Linse, Katrin (Polar Biology, 2007)
We examined deep-sea benthic data on polychaetes, isopods and bivalves from the Atlantic sector of the Southern Ocean. Samples were taken during the expeditions EASIZ II (1998), ANDEEP I and II (2002) (depth: 742-6,348 m). The range between sites varies from 3 to 1,900 km. Polychaetes (175 species in total) and isopods (383 species) had a high proportion of species restricted to one or two sites (72 and 70%, respectively). Bivalves (46 species) had a higher proportion of species represented at more sites. Beta diversity (Whittaker and Jaccard) was higher for polychaetes and isopods than for bivalves. The impact of depth on species richness was not consistent among groups; polychaetes showed a negative relationship to depth, isopods displayed highest richness in the middle depth range (2,000-4,000 m), whereas bivalves showed no clear relationship to depth. Species richness was not related to latitude (58-74 degrees S) or longitude (22-60 degrees W) for any group.
Keywords: Sørishavet; biodiversitet; flerbørstemarker; isopoder; marin biologi; muslinger; skjell; tanglus

Modulation of the bipolar seesaw in the Southeast Pacific during Termination 1 - Lamy, Frank; Kaiser, Jérôme; Arz, Helge W; Hebbeln, Dierk; Ninnemann, Ulysses; Timm, Oliver; Timmermann, Axel; Toggweiler, J R (Earth and Planetary Science Letters, 2007)
The termination of the last ice age (Termination 1; T1) is crucial for our understanding of global climate change and for the validation of climate models. There are still a number of open questions regarding for example the exact timing and the mechanisms involved in the initiation of deglaciation and the subsequent interhemispheric pattern of the warming. Our study is based on a well-dated and high-resolution alkenone-based sea surface temperature (SST) record from the SE-Pacific off southern Chile (Ocean Drilling Project Site 1233) showing that deglacial warming at the northern margin of the Antarctic Circumpolar Current system (ACC) began shortly after 19,000 years BP (19 kyr BP). The timing is largely consistent with Antarctic ice-core records but the initial warming in the SE-Pacific is more abrupt suggesting a direct and immediate response to the slowdown of the Atlantic thermohaline circulation through the bipolar seesaw mechanism. This response requires a rapid transfer of the Atlantic signal to the SE-Pacific without involving the thermal inertia of the Southern Ocean that may contribute to the substantially more gradual deglacial temperature rise seen in Antarctic ice-cores. A very plausible mechanism for this rapid transfer is a seesaw-induced change of the coupled ocean–atmosphere system of the ACC and the southern westerly wind belt. In addition, modelling results suggest that insolation changes and the deglacial CO2 rise induced a substantial SST increase at our site location but with a gradual warming structure. The similarity of the two-step rise in our proxy SSTs and CO2 over T1 strongly demands for a forcing mechanism influencing both, temperature and CO2. As SSTs at our coring site are particularly sensitive to latitudinal shifts of the ACC/southern westerly wind belt system, we conclude that such latitudinal shifts may substantially affect the upwelling of deepwater masses in the Southern Ocean and thus the release of CO2 to the atmosphere as suggested by the conceptual model of [Toggweiler, J.R., Rusell, J.L., Carson, S.R., 2006. Midlatitude westerlies, atmospheric CO2, and climate change during ice ages. Paleoceanography 21. doi:10.1029/2005PA001154].
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; oseanografi; paleoklimatologi

The Southern Ice Ocean Model Intercomparison Project (SIOMIP) - O'Farrell, Siobhan (Ice and climate news, 2007)
Keywords: Sørishavet; forskning; glasiologi; havis

A seismo-stratigraphic analysis of glaciomarine deposits in the eastern Riiser-Larsen Sea (Antarctica) - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geophysical Researches, 2007)
Keywords: Sørishavet; innlandsis; kontinentalsokkel; seismologi; stratigrafi

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Quantitative analysis of soft-bottom molluscs in the Bellingshausen Sea and around Peter I Island - Troncoso, Jesús S; Aldea, Cristian; Arnaud, Patrick; Ramos, Ana; García, Francisco (Polar Research, 2007)
Macrobenthic soft-bottom molluscs were sampled in 30 stations located in the Bellingshausen Sea at depths ranging from 90 to 3304 m. The samples were collected using a quantitative grab box-corer during the cruises BENTART 03, from 24 January to 3 March 2003, and BENTART 06, from 2 January to 16 February 2006. Molluscs represent 1074 specimens belonging to 62 species of Polyplacophora, Gastropoda, Bivalvia and Scaphopoda. The bivalve Cyamiocardium denticulatum was the most abundant species (448 specimens). The abundance per station varied between 1 and 446 specimens. The Shannon–Wiener diversity index ranged between one specimen and 2.36, the Pielou evenness index ranged between 0.00 and 1 and species richness ranged from 1 to 14 species. Diversity showed great variations at different stations. After multivariate analysis (cluster analysis and nonmetrical multidimensional scaling) based on Bray–Curtis similarities, we were able to separate two principal clusters. The first cluster groups together species from shallower bottoms near Peter I Island and the Antarctic Peninsula, and the second cluster groups together species from deeper bottoms in the Bellingshausen Sea. The combination of environmental variables with the highest correlations with faunistic data was that of depth and coarse sand at the surface.
Keywords: Peter I. Øy; Sørishavet; bløtdyr; marin biologi; marine økosystemer; mollusker; oseanografi

International Workshop on Antarctic Sea-Ice Thickness, Hobart, Tasmania, 5-7 July 2006 - Worby, Tony; Ackley, Steve (Ice and climate news, 2007)
Keywords: Sørishavet; glasiologi; havis; konferanser

Antarctic sea ice processes and climate program, The International Polar Year - Ackley, Steve; Worby, Tony (Ice and climate news, 2006)
Keywords: Sørishavet; forskning; glasiologi; havis; klima

The biodiversity of the deep Southern Ocean benthos - Brandt, A; De Broyer, C; De Mesel, I; Ellingsen, K.E; Gooday, A.J; Hilbig, B; Linse, K; Thomson, M.R.A; Tyler, P.A (Philosophical Transactions of the Royal Society B: Biological Sciences, 2006)
Our knowledge of the biodiversity of the Southern Ocean (SO) deep benthos is scarce. In this review, we describe the general biodiversity patterns of meio-, macro- and megafaunal taxa, based on historical and recent expeditions, and against the background of the geological events and phylogenetic relationships that have influenced the biodiversity and evolution of the investigated taxa. The relationship of the fauna to environmental parameters, such as water depth, sediment type, food availability and carbonate solubility, as well as species interrelationships, probably have shaped present-day biodiversity patterns as much as evolution. However, different taxa exhibit different large-scale biodiversity and biogeographic patterns. Moreover, there is rarely any clear relationship of biodiversity pattern with depth, latitude or environmental parameters, such as sediment composition or grain size. Similarities and differences between the SO biodiversity and biodiversity of global oceans are outlined. The high percentage (often more than 90%) of new species in almost all taxa, as well as the high degree of endemism of many groups, may reflect undersampling of the area, and it is likely to decrease as more information is gathered about SO deep-sea biodiversity by future expeditions. Indeed, among certain taxa such as the Foraminifera, close links at the species level are already apparent between deep Weddell Sea faunas and those from similar depths in the North Atlantic and Arctic. With regard to the vertical zonation from the shelf edge into deep water, biodiversity patterns among some taxa in the SO might differ from those in other deep-sea areas, due to the deep Antarctic shelf and the evolution of eurybathy in many species, as well as to deep-water production that can fuel the SO deep sea with freshly produced organic matter derived not only from phytoplankton, but also from ice algae.
Publisher: Royal Society
Keywords: Sørishavet; bentos; biodiversitet; biogeografi; marin biologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G.J.; Bester, Marthán N.; Kirkman, Steve P.; Lydersen, Christian; Kovacs, Kit M. (Marine Pollution Bulletin, 2006)
Entanglements of Antarctic fur seals Arctocephalus gazella were recorded during four summers from 1996 to 2002 at the subantarctic island, Bouvetøya. Rates of entanglement varied between 0.024% and 0.059%. These rates are low for a pinniped population and might be because of the geographic isolation of the haulout site. An apparent decrease in the levels of entanglement over the course of the study was likely due, at least in part, to the removal of entanglements by observers. At least two-thirds of entangling materials were generated by fishery sources. Since there is no known local source of anthropogenic marine pollution, seals become entangled either in waters distant from the island, or when materials drift into local waters. Significantly more subadults were found entangled than expected from the postulated population age class distribution.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin forurensning; pelsseler; pinnipedier

the Antarctic buoy program faces new challenges - Haas, Christian (Ice and climate news, 2006)
Keywords: Sørishavet; glasiologi; havis; klima

Fra Stangsgate til Sørishavet - Henningsen, Rune (Broen: aasgaardstrandiana, 2006)
Keywords: Sørishavet; historie; hvalfangst

Norwegian-Japanese whaling relations in the early 20th century : a case of successful technology transfer - Mageli, Eldrid (Scandinavian Journal of History, 2006)
Publisher: Routledge
Keywords: Japan; Norge; Sørishavet; hvalindustri; pelagisk hvalfangst

Comparison of the microalgal community within fast ice at two sites along the Ross Sea coast, Antarctica - Ryan, K.G.; Hegseth, E.N.; Martin, A.; Davy, S.K.; O'Toole, R.; Ralph, P.J.; McMinn, A.; Thorn, C.J. (Antarctic Science, 2006)
Diverse microbial communities survive within the sea ice matrix and are integral to the energy base of the Southern Ocean. Here we describe initial findings of a four season survey (between 1999–2004) of community structure and biomass of microalgae within the sea ice and in the underlying water column at Cape Evans and Cape Hallett, in the Ross Sea, Antarctica as part of the Latitudinal Gradient Project. At Cape Evans, bottom-ice chlorophyll a levels ranged from 4.4 to 173 mg Chl a m−2. Dominant species were Nitzschia stellata, N. lecointei, and Entomoneis kjellmanii, while the proportion of Berkeleya adeliensis increased steadily during spring. Despite being obtained later in the season, the Cape Hallett data show considerably lower standing stocks of chlorophyll ranging from 0.11 to 36.8 mg Chl a m−2. This difference was attributed to a strong current, which may have ablated much of the bottom ice biomass and provided biomass to the water below. This loss of algae from the bottom of the ice may explain why the ice community contributed only 2% of the standing stock in the total water column. Dominant species at Cape Hallett were Nitzschia stellata, Fragilariopsis curta and Cylindrotheca closterium. The low biomass at Cape Hallett and the prevalence of smaller-celled diatoms in the bottom ice community indicate that the ice here is more typical of pack ice than fast ice. Further data will allow us to quantify and model the extent to which ice-driven dynamics control the structure and function of the sea ice ecosystem and to assess its resilience to changing sea ice conditions.
Edition: 2006/11/14 Publisher: Cambridge University Press
Keywords: Rosshavet; Sørishavet; alger; biomasse; fytoplankton; marin biologi

"Brategg" og ekspedisjonen til Antarktis i 1947/48: om skuta, ekspedisjonen og deltakrane - Sefland, Magnus (Isflaket, 2006)
Keywords: Peter I. Øy; Sørishavet; båter; ekspedisjoner; historie

Modeling ocean processes below Fimbulisen, Antarctica - Smedsrud, Lars H.; Jenkins, Adrian; Holland, David M.; Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2006)
Model simulations of circulation and melting beneath Fimbulisen, Antarctica, obtained using an isopycnic coordinate ocean model, are presented. Model results compare well with available observations of currents and hydrography in the open ocean to the north of Fimbulisen and suggest that Warm Deep Water exists above the level of a sub-ice-shelf bedrock sill, the principal pathway for warm waters to enter the sub-ice-shelf cavity. The model shows a southward inflow of Warm Deep Water over this sill and into the cavity, producing a mean cavity temperature close to −1.0°C. This leads to high levels of basal melting (>10 m/a) at the grounding line of Jutulstraumen and an average melting over the ice shelf base close to 1.9 m/a. The southward inflow is a compensating flow caused by the northward outflow of fresh, cold water produced by the basal melting. Results on inflow and melting are difficult to validate since no in situ measurements yet exist in the cavity. If such high melt rates are realistic, the mass balance of Fimbulisen must be significantly negative, and the ice shelves along Dronning Maud Land must contribute about 4.4 mSv of melt water to the Weddell Sea, about 15% of the total Antarctic meltwater input to the Southern Ocean.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; geofysikk; hydrografi; isshelf; oseanografi

A review of bipolarity concepts: history and examples from Radiolaria and Medusozoa (Cnidaria) - Stepanjants, Sofia D; Cortese, Giuseppe; Kruglikova, Svetlana Borisovna; Bjørklund, Kjell R (Marine Biology Research, 2006)
Bipolarity, its history and general interpretation are investigated and discussed herein. Apart from the classical view, namely that a bipolar distribution is a peculiar biogeographical phenomenon, we propose that it is ecologically controlled too. This approach was used for bipolarity assessment within the following groups: Phaeodaria, Nassellaria, Spumellaria (Radiolaria) and Medusozoa (Cnidaria). We recognize 46 bipolar radiolarian species and three radiolarian genera. However, although species concepts in radiolarians are relatively stable and well known, the high-rank taxonomy of radiolarians is still not well defined. Caution should therefore be taken in the interpretation of distribution data at a taxonomic level higher than the species. In the Medusozoa, bipolarity is observed for 23 species and 32 genera. The different ways in which bipolarity can develop are discussed under the different groups, but preference has been given to the recent and most probable routes of migration. In our investigation of the bipolarity phenomenon, we reviewed more than 400 articles dealing with taxonomy, ecology and biogeography of the modern fauna in both groups.
Keywords: Sørishavet; marinbiologi; migrasjon; nesledyr; plankton; økologi

Kvalfangst - Urdal, Sverre (Segn og soge: sogeblad for Ølen og Bjoa, 2006)
Keywords: Sørishavet; hvalfangst

Amundsen Sea ice production and transport - Assmann, Karen M.; Hellmer, Hartmut H.; Jacobs, Stanley S. (Journal of Geophysical Research: Oceans, 2005)
Drift and variability of sea ice in the Amundsen Sea are investigated with ice buoys deployed in March 2000 and a coupled ice-ocean model. The Bremerhaven Regional Ice Ocean Simulations (BRIOS) model results are compared with in situ ocean, atmosphere, and sea ice measurements; satellite observations; and 8?19 months of buoy drift data. We identify a zone of coastal westward drift and a band of faster eastward drift, separated by a broad transition region characterized by variable ice motions. The model represents drift events at scales approaching its resolution but is limited at smaller scales and by deficiencies in the National Centers for Environmental Prediction forcing. Two thirds of the modeled ice production in the southern Amundsen moves westward near the coast, its transport modulated by meridional wind strength, damping sea ice formation in the eastern Ross Sea. Half of the ice exported from the Ross moves eastward into the northern Amundsen Sea, a net sea ice sink that also receives more than one third of the ice generated to its south. A low rate of exchange occurs with the Bellingshausen Sea, which must have a more independent ice regime. Snow ice formation resulting from high precipitation accounts for one quarter of the ice volume in the Amundsen Sea, aiding the formation of thick ice in a region with generally divergent ice drift. Freshwater extraction by sea ice formation is roughly balanced by precipitation and ice shelf melting, but a positive trend in the surface flux is consistent with an Amundsen source for reported freshening in the Ross Sea.
Publisher: John Wiley & Sons, Ltd
Keywords: Amundsenhavet; Rosshavet; Sørishavet; geofysikk; havis; oseanografi

Iron and mixing affect biological carbon uptake in SOIREE and EisenEx, two Southern Ocean iron fertilisation experiments - Bakker, Dorothee C.E.; Bozec, Yann; Nightingale, Philip D.; Goldson, Laura; Messias, Marie-José; de Baar, Hein J.W.; Liddicoat, Malcolm; Skjelvan, Ingunn; Strass, Volker; Watson, Andrew J. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
This study explores the changes in the surface water fugacity of carbon dioxide (fCO2) and biological carbon uptake in two Southern Ocean iron fertilisation experiments with different hydrographic regimes. The Southern Ocean Iron Release Experiment (SOIREE) experiment was carried out south of the Antarctic Polar Front (APF) at 61°S, 141°E in February 1999 in a stable hydrographic setting. The EisenEx experiment was conducted in a cyclonic eddy north of the APF at 48°S, 21°E in November 2000 and was characterised by a rapid succession of low to storm-force wind speeds and dynamic hydrographic conditions. The iron additions promoted algal blooms in both studies. They alleviated algal iron limitation during the 13-day SOIREE experiment and probably during the first 12 days of EisenEx. The fCO2 in surface water decreased at a constant rate of 3.8μatmday−1 from 4 to 5 days onwards in SOIREE. The fCO2 reduction was 35μatm after 13 days. The evolution of surface water fCO2 in the iron-enriched waters (or ‘patch’) displayed a saw tooth pattern in EisenEx, in response to algal carbon uptake in calm conditions and deep mixing and horizontal dispersion during storms. The maximum fCO2 reduction was 18–20μatm after 12 and 21 days with lower values in between. The iron-enriched waters in EisenEx absorbed four times more atmospheric CO2 than in SOIREE between 5 and 12 days, as a result of stronger winds. The total biological uptake of inorganic carbon across the patch was 1389ton C (±10%) in SOIREE and 1433ton C (±27%) in EisenEx after 12 days (1ton=106g). This similarity probably reflects the comparable size of the iron additions, as well as algal growth at a similar near-maximum growth rate in these regions. The findings imply that the different mixing regimes had less effect on the overall biological carbon uptake across the iron-enriched waters than suggested by the evolution of fCO2 in surface water.
Keywords: Sørishavet; alger; biogeokjemi; hydrografi; karbondioksid; marin kjemi; oseanografi

Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene

Pioneer whalers in the Ross Sea, 1923–33 - Barr, William; Watt, James P C (Polar Record, 2005)
On Christmas Eve 1923, the whaling factory ship Sir James Clark Ross, commanded by Captain Carl Anton Larsen and accompanied by five catchers, reached the front of the Ross Ice Shelf; these were the first whaling vessels to operate in the Ross Sea. They had been dispatched by the Norwegian whaling company Hvalfangeraktienselskapet Rosshavet, which had obtained a licence from the British government. For most of the 1923–24 season, Sir James Clark Ross occupied an uneasy anchorage in the deep waters of Discovery Inlet, a narrow embayment in the front of the Ross Ice Shelf, while her catchers pursued whales widely in the Ross Sea. During that first season they killed and processed 221 whales (211 blue whales and 10 fin whales), which yielded 17,300 barrels of oil. During the next decade, with the exception of the 1931–32 season, Sir James Clark Ross and two other factory ships operated by Rosshavet, C.A. Larsen and Sir James Clark Ross II, operated in the Ross Sea. From the 1926–27 season onwards these ships were joined by up to three other factory ships and their catchers, operated by other companies. During the decade 1923–33 the Rosshavet ships killed and processed 9122 whales in the Ross Sea sector, mainly in the open waters of the Ross Sea south of the pack-ice belt. Total harvest for all factory ships from the Ross Sea sector for the period was 18,238 whales (mainly blue whales) producing 1,490,948 barrels of oil. From 1924 onwards the Rosshavet catchers wintered in Paterson Inlet on Stewart Island, New Zealand, and from 1925 onwards a well-equipped shipyard, Kaipipi Shipyard, operated on Price Peninsula in Paterson Inlet to service the Rosshavet ships.
Publisher: Cambridge University Press
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; hvalfangere; hvalfangstselskaper; pelagisk

Cryosphere-hydrosphere interactions: Numerical modeling using the regional ocean Modeling System (ROMS) at different scales - Bergamasco, Andrea; Budgell, W. P.; Carniel, Sandro; Sclavo, Mauro (Il Nuovo cimento della Società Italiana di Fisica. C. Geophysics and space physics, 2005)
Conveyor belt circulation controls global climate through heat and water fluxes with atmosphere and from tropical to polar regions and vice versa. This circulation, commonly referred to as thermohaline circulation (THC), seems to have millennium time scale and nowadays-a non-glacial period-appears to be as rather stable. However, concern is raised by the buildup Of CO2 and other greenhouse gases in the atmosphere (IPCC, Third assessment report: Climate Change 2001, A contribution of working group I, II and III to the Third Assessment Report of the Intergovernmental Panel on Climate Change (Cambridge Univ. Press, UK) 2001, http://www.ipcc.ch) as these may affect the THC conveyor paths. Since it is widely recognized that dense-water formation sites act as primary sources in strengthening quasi-stable THC paths (Stommel H., Tellus, 13 (1961) 224), in order to simulate properly the consequences of such scenarios a better understanding of these oceanic processes is needed. To successfully model these processes, air-sea-ice-integrated modelling approaches are often required. Here we focus on two polar regions using the Regional Ocean Modeling System (ROMS). In the first region investigated, the North Atlantic-Arctic, where open-ocean deep convection and open-sea ice formation and dispersion under the intense air-sea interactions are the major engines, we use a new version of the coupled hydrodynamic-ice ROMS model. The second area belongs to the Antarctica region inside the Southern Ocean, where brine rejections during ice formation inside shelf seas origin dense water that, flowing along the continental slope, overflow becoming eventually abyssal waters. Results show how nowadays integrated-modelling tasks have become more and more feasible and effective; numerical simulations dealing with large computational domains or challenging different climate scenarios can be run on multi-processors platforms and on systems like LINUX clusters, made of the same hardware as PCs, and codes have been accordingly modified. This relevant numerical help coming from the computer science can now allow scientists to devote larger attention in the efforts of understanding the deep mechanisms of such complex processes.
Paper presented at: 8th Workshop on Calculation of High Performances in Italy, Milan, Italy. November 24-25, 2004.
Keywords: Sørishavet; geofysikk; klimaendringer; klimamodeller; oseanografi; polarområdene

On the taxonomic status of the Antarctic amphipod crustacean genera Eclysis (Astyridae) and Bathypanoploea (Stilipedidae), with partial redescription of their type species and description of Bathypanoploea polarsterni n. sp. - Berge, Jørgen; Vader, Wim (Organisms Diversity & Evolution, 2005)
The monotypic genus Eclysis K.H. Barnard, 1932 and its type species, E. similis Barnard, are redescribed based upon a newly discovered second specimen. The genus Bathypanoploea Schellenberg, 1939 is reviewed; B. schellenbergi Holman and Watling, 1983 is fixed as the type species. B. polarsterni n. sp. is described; Alexandrella pulchra Ren in Ren and Huang, 1991 is a new junior synonym of B. schellenbergi. The morphology of Eclysis and Bathypanoploea is examined, as well as their relationships to the Astyridae and Stilipedidae. See also Electronic Supplement at: http://www.senckenberg.de/odes/05-03.htm
Keywords: Sørishavet; amfipoder; taksonomi; zoologi

Southern Ocean deep-sea isopod species richness (Crustacea, Malacostraca): influences of depth, latitude and longitude - Brandt, Angelika; Ellingsen, Kari E.; Brix, Saskia; Brökeland, Wiebke; Malyutina, Marina (Polar Biology, 2005)
We examined deep-sea epibenthic sledge isopod data from the Atlantic sector of the Southern Ocean (SO) (depth range=742–5,191 m). Samples were taken during the expeditions EASIZ II (ANT XV-3) in 1998 and ANDEEP I and II (ANT XIX3/4) in 2002. A total of 471 isopod species were recorded from 28 sites. The species richness of the epibenthic sledge samples was highly variable (6–82 species). Species richness was highest at site 131-3 in 3,053 m depth in the north-eastern Weddell Sea. The highest numbers of species were sampled in the middle depth range and lower species richness was found in the shallower and deeper parts of the study area. Depth is suggested to explain isopod species richness better than both latitude and longitude. Between 58°S and 65°S, the number of species ranged from 9 to 82 (mean=35.9). Further south in the Weddell Sea, between 73°S and 74°S, species richness was lower and the number of species ranged from 6 to 35 (mean=19.2). With regard to longitude, the highest species richness (up to 82 species) was found between 50°W and 60°W in the area of the South Shetland Islands and around the Antarctic Peninsula, while numbers did not exceed 50 species in the eastern Weddell Sea. The haul length, ranging from 807 to 6,464 m, was positively correlated with depth; however, there was no linear relationship between haul length and species richness. We therefore suggest that depth was the most important factor explaining isopod species richness. However, only 28 sites were visited and the statistical power is thus limited. Sampling in the deep sea is expensive and time consuming and as yet this is the best isopod data set available from the Atlantic sector of the SO. Future expeditions are therefore important to better explain the current patterns of benthic diversity in Antarctica.
Keywords: Sør-Shetlandsøyene; Sørishavet; Weddellhavet; biodiversitet; isopoder; marin biologi

Polar bivalves are characterized by high antioxidant defences - Camus, Lionel; Gulliksen, Bjørn; Depledge, Michael H; Jones, Malcolm B (Polar Research, 2005)
Inevitably, aerobic life leads to the formation of deleterious reactive oxygen species (ROS) which participate in biomolecule oxidation, hence augmenting biomolecule turnover. Organisms have adapted to counteract the noxious effects of ROS by developing a battery of antioxidant defences (AOX) which comprise enzymes and low-molecular weight scavengers. Past studies have reported elevated AOX levels in polar pectinid bivalves compared with temperate congeners. This fi nding is controversial as mitochondrial ROS generation is low in polar versus temperate species, and, to date, there is no generally accepted explanation of the causes of increased basal AOX levels in polar waters. We suggest that the low food availability in those ecosystems may result in polar marine ectotherms diverting some energy into the maintenance of high AOX. We tested this hypothesis by comparing the total oxyradical scavenging capacity (peroxyl, hydroxyl and peroxynitrite) of three clam species: Laternula elliptica (Antarctic), Mya truncata (Arctic) and Mya arenaria (temperate). The data confi rmed that polar bivalves are characterized by higher AOX. Herein, we propose that high AOX is required in environments characterized by low food availability as AOX effi ciently protects biomolecules, notably the RNA expressed at high levels by cold-water ectotherms. Also, high AOX may explain the relatively long lifespan of most polar ectotherms.
Keywords: Sørishavet; marin biologi; muslinger; polarområdene

Telonema antarcticum sp. nov., a common marine phagotrophic flagellate - Klaveness, Dag; Shalchian-Tabrizi, Kamran; Thomsen, Helge Abildhauge; Eikrem, Wenche; Jakobsen, Kjetill S. (International Journal of Systematic and Evolutionary Microbiology, 2005)
Telonema is a widely distributed group of phagotrophic flagellates with two known members. In this study, the structural identity and molecular phylogeny of Telonema antarcticum was investigated and a valid description is proposed. Molecular phylogeny was studied using small-subunit rRNA (SSU rRNA) gene sequences. The pear-shaped cell had two subequal flagella that emerged laterally on the truncated antapical tail. One flagellum had tripartite hairs. The cell was naked, but had subsurface vesicles containing angular paracrystalline bodies of an unknown nature. A unique complex cytoskeletal structure, the subcortical lamina, was found to be an important functional and taxonomic feature of the genus. Telonema has an antero-ventral depression where food particles are ingested and then transferred to a conspicuous anterior food vacuole. The molecular phylogeny inferred from the SSU rRNA gene sequence suggested that Telonema represents an isolated and deep branch among the tubulocristate protists.
Publisher: Microbiology Society Type: Journal Article
Keywords: Sørishavet; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi

Interplay of turbidite and contourite deposition along the Cosmonaut Sea/Enderby Land margin, East Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V.; Løvås, O.; Sand, Morten; Brekke, Harald (Marine Geology, 2005)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes on the continental rise. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents redepositing the sediments into a large-scale plastered drift deposit prior to the main glacigenic input along the margin. High-relief elongated and sometimes semicircular depositional structures are found on the upper continental rise, stratigraphically above the regional sediment lens, and were mainly deposited by the action of closely spaced turbidity currents. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of down-slope turbidity transport and westward flowing bottom currents. The elongated sediment mounds on the upper and lower continental rise were deposited after initiation of glacigenic input to the slope and rise.
Keywords: Antarktis; Sørishavet; marin geofysikk; marin geologi

Holocene climate evolution in the high-latitude Southern Hemisphere simulated by a coupled atmosphere-sea ice-ocean-vegetation model - Renssen, Hans; Goosse, Hugues; Fichefet, Thierry; Masson-Delmotte, Valérie; Koç, Nalân (Holocene, 2005)
The Holocene climate is simulated in a 9000-yr-long transient experiment performed with the ECBilt-CLIO-VECODE coupled atmosphere-sea ice-ocean-vegetation model. This experiment is forced with annually varying orbital parameters and atmospheric concentrations of CO2 and CH4. The objective is to study the impact of these long-term forcings on the surface temperature evolution during different seasons in the high-latitude Southern Hemisphere. We find in summer a thermal optimum in the midHolocene (6-3 ka BP), with temperatures locally 3°C above the preindustrial mean. In autumn the temperatures experienced a long-term increase, particularly during the first few thousand years. The opposite trend was simulated for winter and spring, with a relatively warm Southern Ocean at 9 ka BP in winter (up to 3.5°C above the preindustrial mean) and a warm continent in spring (+3°C), followed by a gradual cooling towards the present. These long-term temperature trends can be explained by a combination of (1) a delayed response to orbital forcing, with temperatures lagging insolation by 1 to 2 months owing to the thermal inertia of the system, and (2) the long memory of the Southern Ocean. This long memory is related to the storage of the warm late winter-spring anomaly below the shallower summer mixed layer until next winter. Sea ice plays an important role as an amplifying factor through the ice-albedo and ice-insulation feedbacks. Our experiments can help to improve our understanding of the Holocene signal in proxies. For instance, the results suggest that, in contrast to recent propositions, teleconnections to the Northern Hemisphere appear not necessarily to explain the history of Southern Hemisphere temperature changes during the Holocene.
Keywords: Sørishavet; holocene; klimaendringer; klimamodeller; paleoklimatologi

Warming of the deep water in the Weddell Sea along the Greenwich meridian: 1977–2001 - Smedsrud, Lars H. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
The Weddell Deep Water (WDW) warmed substantially along the Greenwich meridian following the Weddell Polynya of the 1970s. Areas affected by the polynya contained ∼14GJ/m2 more heat in 2001 than in 1977. This warming would require a flux of ∼390W/m2 if it were to take place over a year. Large variations in heat content of the WDW are found between the Antarctic coast and Maud Rise (64°S). The small variation found north of Maud Rise is opposite in phase to that to the south, and the warming was close to monotonic south of 68°S. The mean warming of WDW along the section is ∼0.032°C per decade, comparable to the warming of the Antarctic Circumpolar Current. The mean warming compares with a surface heat flux of 4W/m2 over the 25 year period, an order of magnitude higher than the warming of the global ocean. As variation in mean salinity of the WDW follows the warming/cooling events, variation in inflow probably explains a cooling event between 1984 and 1989, and a warming event between 1989 and 1992. Cooling during the late 1990s is probably related to the reappearance of a polynya like feature in some winter months as an area 100km in diameter close to Maud Rise with 10–20% lower sea ice concentrations than the surrounding ocean.
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi; polynja

Dagbok fra en Sydhavstur 1906 - Sørlle, Petter; Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2005)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Sørishavet; dagbøker; hvalfangere; hvalfangstindustri; hvalindustri; hvalkokeri; polareksspedisjoner

Whaler's cross on Deception Island - Barr, Susan; Downie, Rod; Sánchez, Rodolfo (Polar Record, 2004)
The cemetery at Whalers Bay, Deception Island, was the largest in the Antarctic prior to being partially buried and partially washed away during a volcanic eruption in 1969. In 2002 a wooden cross at Argentina's Decepción Station was identified as being that of the Norwegian whaler Peder Knapstad. It was removed, secured in a base, and re-erected at Whalers Bay.
Edition: 2004/01/19 Publisher: Cambridge University Press
Keywords: Antarktis; Deceptionøya; Sørishavet; kulturminneforvaltning; kulturminner

Interannual controls on Weddell Sea surface water fCO2 during the autumn–winter transition phase - Bellerby, Richard G.J.; Hoppema, Mario; Fahrbach, Eberhard; de Baar, Hein J.W.; Stoll, Michel H.C. (Deep Sea Research Part I: Oceanographic Research Papers, 2004)
The fugacity of carbon dioxide (fCO2) of the surface waters of the Weddell Sea along the prime meridian has been described for the austral autumn in 1996 and 1998. For individual years, fCO2 has a strong linear relationship with sea surface temperature, although the relationships cannot be reconciled to provide an interannually consistent algorithm for remotely sensed assessment of fCO2. However, from the assumption that Weddell Sea surface water has a single end member (upwelled Warm Deep Water) we have determined the relative contributions of heating, ice-melt, and biological activity on fCO2. A breakdown of the controls shows that the measured annual fCO2 distributions can be recreated for both transects by adjusting solely for thermodynamic forcing, and model adjustments for salinity are small except in regions of significant upwelling during 1998. The incorporation of nitrate utilisation into the model results in a general and significant underestimation of fCO2. This runs contrary to the earlier findings of Sabine and Key (Mar. Chem. 60 (1998) 95) in the Southern Ocean although it is consistent with models in the area (Louanchi et al., Deep-Sea Res. I 48 (2001) 1581). A major caveat to these findings is the significant departure of the thermodynamic model and a tightening of the nitrate-adjusted model in 1998 in areas with deeper mixing in the southern Weddell Sea. We propose that there are two reasons for the discrepancies in our model: the source waters are not as homogenous as the model assumes; and there are geographical and seasonal variations of CO2 exchange with the atmosphere and the input of inorganic carbon and nitrate from below the mixed layer resulting in imbalances in the mixed layer concentration ratios.
Keywords: Sørishavet; Weddellhavet; karbon syklus; karbondioksid; marin biologi; marin kjemi; oseanografi

Two new Antarctic stegocephalid (Amphipoda: Stegocephalidae: Stegocephalinae) species, with implications for the phylogeny and classification of the two genera Pseudo and Schellenbergia - Berge, Jørgen; Vader, Wim (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
Descriptions and figures of two new species of the genus Pseudo Berge & Vader, 2001 (Stegocephalidae: Stegocephalinae) are presented, but the two species are not given formal scientific names due to lack of material (both are only known by a single specimen each). However, the two new species have a significant impact on the classification and proposed phylogeny of the subfamily, as the two genera Pseudo Berge & Vader, 2001 and Schellenbergia Berge & Vader, 2001 now have to be considered synonymous. Pseudo is selected as the senior synonym. A discussion of the relationships among the genera of the subfamily Stegocephalinae is provided.
Keywords: Sørishavet; amfipoder; fylogenetikk; taksonomi; zoologi

A survey of amphipod associates of sea urchins, with description of new species in the genera Lepidepecreella (Lysianassoidea: lepidepecreellid group) and Notopoma (Photoidea: Ischyroceridae) from Antarctic cidarids - Berge, Jørgen; Vader, Wim; Lockhart, Susanne (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
The known associations between amphipods and echinoids are listed, separated into five different categories depending upon the nature of the associations. The new species Lepidepecreella andeep, found attached around the mouth of the cidarid sea urchin Aporocidaris antarctica, is described, as well as the new species Notopoma cidaridis. The tubes of the latter were found attached to the spines of the cidarid sea urchin Rhynchocidaris triplopora. These cases represent the first associations reported between amphipods and echinoids in the Antarctic. A key to both genera is provided.
Keywords: Sørishavet; Weddellhavet; amfipoder; krepsdyr; pigghuder; sjøpiggsvin; taksonomi; zoologi

The distribution and speciation of iron along 6°E in the Southern Ocean - Croot, Peter L.; Andersson, Karen; Öztürk, Murat; Turner, David R. (The SWEDARP 1997/98 Expedition, 2004)
The distribution and speciation of iron was determined along a transect in the eastern Atlantic sector (6°E) of the Southern Ocean during a collaborative Scandinavian/South African Antarctic cruise conducted in late austral summer (December 1997/January 1998). Elevated concentrations of dissolved iron (>0.4nM) were found at 60°S in the vicinity of the Spring Ice Edge (SIE) in tandem with a phytoplankton bloom, chiefly dominated by Phaeocystis sp. This bloom had developed rapidly after the loss of the seasonal sea ice cover. The iron that fuelled this bloom was mostly likely derived from sea ice melt. In the Winter Ice Edge (WIE), around 55°S, dissolved iron concentrations were low (<0.2nM) and corresponded to lower biological productivity, biomass. In the Antarctic Polar Front, at approximately 50°S, a vertical profile of dissolved iron showed low concentrations (<0.2nM); however, a surface survey showed higher concentrations (1–3nM), and considerable patchiness in this dynamic frontal region. The chemical speciation of iron was dominated by organic complexation throughout the study region. Organic iron-complexing ligands ([L]) ranged from 0.9 to 3.0nM Fe equivalents, with complex stability logKFeL′=21.4–23.5. Estimated concentrations of inorganic iron (Fe′) ranged from 0.03 to 0.79pM, with the highest values found in the Phaeocystis bloom in the SIE. A vertical profile of iron-complexing ligands in the WIE showed a maximum consistent with a biological source for ligand production and near surface minimum possibly consistent with loss via photodecomposition. This work further confirms the role iron that has in the Southern Ocean in limiting primary productivity.
Keywords: Bouvetøya; Sørishavet; biogeokjemi; marin kjemi; oseanografi

Diesel oil and PCB-degrading psychrotrophic bacteria isolated from Antarctic seawaters (Terra Nova Bay, Ross Sea) - De Domenico, Maria; Lo Giudice, Angelina; Michaud, Luigi; Saitta, Marcello; Bruni, Vivia (Polar Research, 2004)
Fifty-seven Antarctic marine bacteria were examined for their ability to degrade commercial diesel oil as the sole organic substrate at both 4 °C and 20 °C. Based on the preliminary screening, two isolates (B11 and B15) with high capacity to degrade diesel oil were selected and their biodegradation effi ciency was quantifi ed by gas chromatographic analysis. As expected for psychrotrophs, diesel oil biodegradation was slower at 4 °C than at 20 °C. The two strains also mineralized the C28 n-paraffi n octacosane at 20 °C and polychlorinated biphenyls (PCBs) at 4 °C and 20 °C.
Keywords: Rosshavet; Sørishavet; bakterier; biologisk nedbrytning; kjemi; marin biologi; marin økologi

Evaluating global ocean carbon models: The importance of realistic physics - Doney, Scott C; Lindsay, Keith; Caldeira, Ken; Campin, J.-M.; Drange, Helge; Dutay, Jean-Claude; Follows, Michael; Gao, Yongqi; Gnanadesikan, Anand; Gruber, N; Ishida, Akio; Joos, Fortunat; et al. (Global Biogeochemical Cycles, 2004)
A suite of standard ocean hydrographic and circulation metrics are applied to the equilibrium physical solutions from 13 global carbon models participating in phase 2 of the Ocean Carbon-cycle Model Intercomparison Project (OCMIP-2). Model-data comparisons are presented for sea surface temperature and salinity, seasonal mixed layer depth, meridional heat and freshwater transport, 3-D hydrographic fields, and meridional overturning. Considerable variation exists among the OCMIP-2 simulations, with some of the solutions falling noticeably outside available observational constraints. For some cases, model-model and model-data differences can be related to variations in surface forcing, subgrid-scale parameterizations, and model architecture. These errors in the physical metrics point to significant problems in the underlying model representations of ocean transport and dynamics, problems that directly affect the OCMIP predicted ocean tracer and carbon cycle variables (e.g., air-sea CO2 flux, chlorofluorocarbon and anthropogenic CO2 uptake, and export production). A substantial fraction of the large model-model ranges in OCMIP-2 biogeochemical fields (±25–40%) represents the propagation of known errors in model physics. Therefore the model-model spread likely overstates the uncertainty in our current understanding of the ocean carbon system, particularly for transport-dominated fields such as the historical uptake of anthropogenic CO2. A full error assessment, however, would need to account for additional sources of uncertainty such as more complex biological-chemical-physical interactions, biases arising from poorly resolved or neglected physical processes, and climate change.
Keywords: Sørishavet; biogeokjemi; hydrografi; karbon syklus; karbondioksid; klimaendringer; oseanografi

Ice shelf water overflow and bottom water formation in the southern Weddell Sea - Foldvik, Arne; Gammelsrød, Tor; Østerhus, Svein; Fahrbach, Eberhard; Rohardt, Gerd; Schröder, Michael; Nicholls, Keith William; Padman, Laurie; Woodgate, Rebecca A. (Journal of Geophysical Research: Oceans, 2004)
Cold shelf waters flowing out of the Filchner Depression in the southern Weddell Sea make a significant contribution to the production of Weddell Sea Bottom Water (WSBW), a precursor to Antarctic Bottom Water (AABW). We use all available current meter records from the region to calculate the flux of cold water (<−1.9°C) over the sill at the northern end of the Filchner Depression (1.6 ± 0.5 Sv), and to determine its fate. The estimated fluxes and mixing rates imply a rate of WSBW formation (referenced to −0.8°C) of 4.3 ± 1.4 Sv. We identify three pathways for the cold shelf waters to enter the deep Weddell Sea circulation. One path involves flow constrained to follow the shelf break. The other two paths are down the continental slope, resulting from the cold dense water being steered northward by prominent ridges that cross the continental slope near 36°W and 37°W. Mooring data indicate that the deep plumes can retain their core characteristics to depths greater than 2000 m. Probably aided by thermobaricity, the plume water at this depth can flow at a speed approaching 1 m s−1, implying that the flow is occasionally supercritical. We postulate that such supercriticality acts to limit mixing between the plume and its environment. The transition from supercritical to slower, more uniform flow is associated with very efficient mixing, probably as a result of hydraulic jumps.
Keywords: Sørishavet; Weddellhavet; havstrømmer; isshelf; oseanografi

The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Effect of solar radiation and the subsequent dark periods on two newly isolated and characterized Antarctic marine bacteria - Hernández, Edgardo A; Ferreyra, Gustavo A; Mac Cormack, Walter P (Polar Research, 2004)
Two strains of psychrotolerant Antarctic marine bacteria were isolated and characterized using biochemical and molecular techniques. Sequencing of 16S rRNA gene showed that UVvi strain belongs to the genus Arthrobacter whereas UVps strain is related to the Flexibacter-Cytophaga-Bacteroides (FCB) group. Response of the strains to solar radiation was studied during the summer of 1999 in Potter Cove, near Jubany station (South Shetland Island, Antarctica). The effect of photosynthetically available radiation (PAR, 400-700 nm), ultraviolet-A (UV-A, 320-400 nm) and ultraviolet-B radiation (UV-B, 280-320 nm) on cell viability was studied using mixed cultures in quartz bottles covered with interferential filters and exposed to solar radiation. In all experiments, four treatments were used: dark (with light screened out), PAR (with UV radiation screened out), PAR+UV-A (UV-B screened out) and PAR+UV-A+UV-B. Under the assayed conditions, PAR+UV-A and PAR+UV-A+UV-B radiation showed similar negative effects on the viability of the studied strains. However, at the end of the exposure time, mortality values in PAR+UV-A+UV-B treatments were higher than those observed under PAR+UV-A treatments. In both PAR+UV-A and PAR+UV-A+UV-B treatments we observed high levels of hydrogen peroxide compared with the dark control. The Arthrobacter UVvi strain showed significant recovery in dark conditions after exposure to the PAR+UV-A but not after the PAR+UV-A+UV-B treatment. This strain proved to be more resistant to UV radiation than the FCB group-related UVps strain. The results showed that UV radiation has a deleterious effect on these Antarctic marine bacteria and also revealed that the analysed components of the Antarctic bacterioplankton may have different responses when they are exposed to the same irradiance conditions.
Keywords: Sørishavet; UV-stråling; bakterier; biokjemi; marin biologi; ozonlaget; plankton; ultrafiolett stråling

Input of Glaciomarine Sediments along the East Antarctic Continental Margin; Depositional Processes on the Cosmonaut Sea Continental Slope and Rise and a Regional Acoustic Stratigraphic Correlation from 40° W to 80° E - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, , V; Kudryavtsev, Genadii (Marine Geophysical Researches, 2004)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes in the continental slope and rise area. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents, which redeposited the sediments into a large scale drift deposit prior to the main glaciogenic input along the margin. High-relief semicircular or elongated depositional structures are also found on the upper continental rise stratigraphically above the regional sediment lens, and were deposited by the combined influence of downslope and alongslope sediment transport. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of downslope turbidity transport and westward flowing bottom currents after initiation of glacigenic input to the slope and rise. We compare the seismostratigraphic signatures along the continental margin segments of the adjacent Riiser Larsen Sea, the Weddell Sea and the Prydz Bay/Cooperation Sea, focussing on indications that may be interpreted as a preglacial-glaciomarine transition in the depositional environment. We suggest that earliest glaciogenic input to the continental slope and rise occurred in the Prydz Bay and possibly in the Weddell Sea. At a later stage, an intensification of the oceanic circulation pattern occurred, resulting in the deposition of the regional plastered drift deposit along the Cosmonaut Sea margin, as well as the initiation of large drift deposits in the Cooperation Sea. At an even later stage, possibly in the middle Miocene, glacial advances across the continental shelf were initiated along the Cosmonaut Sea and the Riiser Larsen Sea continental margins.
Keywords: Sørishavet; Weddellhavet; marin geofysikk; marin geologi; oseanografi

Seismic expression of glaciomarine deposits in the eastern Riiser Larsen Sea, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J.; Gandjukhin, V. (Marine Geology, 2004)
By studying multichannel seismic data across the continental slope and rise of the eastern Riiser Larsen Sea and through a comparison with other East Antarctic continental margins, the base of the glaciomarine deposits has been traced in this area. The seismic data reveal the presence of large channel-levee complexes as well as multiple types of contourite accumulations. Downslope and alonglope processes thus interacted in forming the glaciomarine deposits. The deposits are attributed to the advances of ice sheet, delivering huge amounts of sediment to the shelf edge and upper slope during glacial maxima. Oversteepening and instability generated down-slope turbidity currents forming channel–levee complexes whereas the contourite accumulations were probably mostly formed during interglacials. The spatial distribution of the current controlled deposits indicates that bottom currents flow along the western slope of the Gunnerus Ridge.
Keywords: Dronning Maud Land; Sørishavet; marin geologi; oseanografi; seismologi

Holocene climate in the Atlantic sector of the Southern Ocean: Controlled by insolation or oceanic circulation? - Nielsen, Simon Harder Holm; Koç, Nalân; Crosta, Xavier (Geology, 2004)
The Holocene climate of the Southern Ocean is not well understood, mainly because of the lack of high-resolution reconstructions of ocean surface properties. Here we present a 12,500-yr-long, decadal-scale record of Holocene sea-surface temperatures and sea- ice presence from the Polar Front of the East Atlantic Southern Ocean. The record shows gradual climate change, with no abrupt Neoglacial cooling, and an unprecedented late Holocene warming. The dominant forcing factor appears to be precessional insolation; Northern Hemisphere summer insolation correlates to at least the early to middle Holocene climate trend. Spectral analysis reveals centennial-scale cyclic climate changes with periods of 1220, 1070, 400, and 150 yr. The record shows good correlation to East Antarctic ice cores and to climate records from South Georgia and Bunger Oasis. However, the record shows out-of-phase behavior with regard to climate records from the western Antarctic Peninsula and the Peru-Chile Current; such behavior hints at a climatic divide through Patagonia, the Drake Passage, and between West and East Antarctica.
Keywords: Antarktis; Sørishavet; geologi; havis; klimaendringer; paleoklimatologi

Measurements of ice thickness and seabed topography under the Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2004)
This paper presents results from seismic measurements of the ice and water column thickness of the Fimbul Ice Shelf in the northeastern Weddell Sea. Seismic reflection measurements were conducted at 183 stations covering most of the ice shelf. Seismic velocities in the ice were derived from refraction measurements at 12 stations, distributed evenly across the area, as well as from temperature and density data from the Fimbul Ice Shelf. Velocities in the water were derived from temperature and salinity data from beneath the Fimbul Ice Shelf. Ice thicknesses were found to vary between 160 m and 550 m with uncertainties up to ±10 m. Water column thicknesses up to 900 m were found within the central ice shelf cavity, and values exceed 2000 m where the ice shelf overhangs the continental slope. Uncertainties in water column thickness are estimated to be ±60 m, and are dominated by the uncertainties in the shape of the seabed. Ice draft and seabed elevation was derived from ice and water column thickness assuming hydrostatic pressure. The resulting map of seabed elevation and water column thickness suggests that the strong westward flowing coastal current will be steered under the ice shelf and thus drive a sub-ice-shelf flow. Warm Deep Water does not have direct access to the ice shelf cavity, while relatively cold coastal waters shallower than 500 m will interact closely with the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; isshelf; oseanografi

Iron enrichment and photoreduction of iron under UV and PAR in the presence of hydroxycarboxylic acid: implications for phytoplankton growth in the Southern Ocean - Öztürk, Murat; Croot, Peter L.; Bertilsson, Stefan; Abrahamsson, Katarina; Karlson, Bengt; David, Roland; Fransson, Agneta; Sakshaug, Egil (The SWEDARP 1997/98 Expedition, 2004)
Iron(III) photoreduction and the responses of phytoplankton under ultraviolet (UV) and photosynthetically available radiation (PAR) were investigated with the presence of hydroxycarboxylic acid (glucaric acid (GA), a model compound for organic acids excreted by phytoplankton). The incubation experiments were carried out on board using seawater samples collected in the location of the winter ice edge (WIE) and the spring ice edge (SIE) of the Southern Ocean. In this paper, we focus on the results of experiment in WIE. Throughout the experiments, dissolved Fe(II), major nutrients and in vivo fluorescence were monitored regularly. In addition, Chl-a, POC/PON, cell densities of phytoplankton and bacteria, bacterial production, organic peroxide, hydrogen peroxide and total CO2 were measured. The results from the WIE show that iron enrichment had a substantial effect on phytoplankton growth rate. Fe(III) addition in the presence of GA (FeGA) gave higher Fe(II) concentration and higher growth rate of phytoplankton than those in controls. Our results suggest that hydroxycarboxylic acid had a significant chemical and biological impact. The presence of GA influenced iron photochemistry and iron availability to phytoplankton. Phytoplankton growth responses to iron enrichments in incubations under UV and PAR were completely dissimilar. It seems that FeGA addition prominently changes the harmful effect of UV on the phytoplankton population. This study provides preliminary information on how the photoreduction of iron(III) and the phytoplankton growth are affected by iron enrichment in the presence of hydroxycarboxylic acid.
Keywords: Sørishavet; biokjemi; fotosyntese; marin biologi; oseanografi; phytoplankton

The diatom Fragilariopsis cylindrus and its potential as an indicator species for cold water rather than for sea ice - Quillfeldt von, Cecilie Hellum (Vie et Milieu / Life & Environment, 2004)
The importance of the diatom Fragilariopsis cylindrus (Grunow) Krieger in Helmcke & Krieger in the Arctic and Antarctic is well known. It is used as an indicator of sea ice when the paleoenvironment is being described. It is often among the dominant taxa in different sea ice communities, sometimes making an important contribution to a subsequent phytoplankton growth when released by ice melt. However, it may also dominate phytoplankton blooms in areas never experiencing sea ice. The use of F. cylindrus as an indicator for reconstruction of palaeoceanographic conditions is assessed from literature records. Its potential as an indicator species for sea ice appears to vary from region to region, but it is a good indicator of cold water.
Keywords: Sørishavet; diatomeer; marin biologi; paleoseanografi; phytoplankton; polarområdene

Light rather than iron controls photosynthate production and allocation in Southern Ocean phytoplankton populations during austral autumn - van Oijen, Tim; van Leeuwe, Maria A.; Granum, E.; Weissing, Franz J.; Bellerby, Richard G. J.; Gieskes, W. W. C.; de Baar, Hein J. W. (Journal of Plankton Research, 2004)
The role of iron and light in controlling photosynthate production and allocation in phytoplankton populations of the Atlantic sector of the Southern Ocean was investigated in April–May 1999. The 14C incorporation into five biochemical pools (glucan, amino acids, proteins, lipids and polysaccharides) was measured during iron/light perturbation experiments. The diurnal Chl a-specific rates of carbon incorporation into these pools did not change in response to iron addition, yet were decreased at 20 μmol photons m−2 s−1, an irradiance comparable with the one at 20–45 m in situ depth. This suggests that the low phytoplankton biomass encountered (0.1–0.6 μg Chl a L−1) was mainly caused by light limitation in the deep wind mixed layer (>40 m). Regional differences in Chl a-specific carbon incorporation rates were not found in spite of differences in phytoplankton species composition: at the Antarctic Polar Front, biomass was dominated by a diatom population of Fragilariopsis kerguelensis, whereas smaller cells, including chrysophytes, were relatively more abundant in the Antarctic Circumpolar Current beyond the influence of frontal systems. Because mixing was often in excess of 100 m in the latter region, diatom cells may have been unable to fulfil their characteristically high Fe demand at low average light conditions, and thus became co-limited by both resources. Using a model that describes the 14C incorporation, the consistency was shown between the dynamics in the glucan pool in the field experiments and in laboratory experiments with an Antarctic diatom, Chaetoceros brevis. The glucan respiration rate was almost twice as high during the dark phase as during the light phase, which is consistent with the role of glucan as a reserve supplying energy and carbon skeletons for continued protein synthesis during the night.
Keywords: Sørishavet; biokjemi; fotosyntese; fytoplankton; marin biologi; oseanografi; planteplankton

Adaptations and lifestyle in polar marine environments: a biological challenge for the study of fish evolution - Verde, Cinzia; Cocca, Ennio; de Pascale, Donatella; Parisi, Elio; di Frisco, Guido (Polar Research, 2004)
The climatic features of Antarctic waters are more extreme and constant than in the Arctic. The Antarctic has been isolated and cold longer than the Arctic. The polar ichthyofaunas differ in age, endemism, taxonomy, zoogeographic distinctiveness and physiological tolerance to environmental parameters. The Arctic is the connection between the Antarctic and the temperate-tropical systems. Paradigmatic comparisons of the pathways of adaptive evolution of fish from both poles address the oxygen-transport system and the antifreezes of northern and southern species, (i) Haemoglobin evolution has included adaptations at the biochemical, physiological and molecular levels. Within the study of the molecular bases offish cold adaptation, and taking advantage of the information on haemoglobin amino acid sequence, we analysed the evolutionary history of the ? and ? globins of Antarctic, Arctic and temperate haemoglobins as a basis for reconstructing phylogenetic relationships. In the trees, the constant physico-chemical conditions of the Antarctic waters are matched by clear grouping of globin sequences, whereas the variability typical of the Arctic ecosystem corresponds to high sequence variation, reflected by scattered intermediate positions between the Antarctic and non-Antarctic clades. (ii) Antifreeze (glyco)proteins and peptides allow polar fish to survive at sub-zero temperatures. In Antarctic Notothenioidei the antifreeze gene evolved from a trypsinogen-like serine protease gene. In the Arctic polar cod the genome contains genes which encode nearly identical proteins, but have evolved from a different genomic locus–a case of convergent evolution.
Keywords: Sørishavet; biokjemi; biologi; evolusjon; fauna; fisker; fysiologi; klima; miljø; zoogeografi; økosystemer

Evidence for orbitally controlled size variations of the East Antarctic Ice Sheet during the late Miocene - Grützner, J.; Rebesco, M.A.; Cooper, A.K.; Forsberg, C.F.; Kryc, K.A.; Wefer, G. (Geology, 2003)
Ocean Drilling Program Site 1165 penetrated drift sediments on the East Antarctic continental rise and recovered sediments from a low-energy depositional environment. The sediments are characterized by prominent alternations between a green to greenish-gray diatom-bearing hemipelagic facies and gray to dark gray hemiturbiditic facies. Our investigation of an upper Miocene section, using high-resolution color spectra, multisensor core logs, and X-ray fluorescence scans, reveals that sedimentation changes occur at Milankovitch orbital frequencies of obliquity and precession. We use this finding to derive an astronomical calibrated time scale and to calculate iron mass-accumulation rates, as a proxy for sediment-accumulation rates. Terrigenous iron fluxes change by as much as 100% during each obliquity cycle. This change and an episodic pattern of enhanced ice-rafted debris deposition during times of deglaciation provide evidence for a dynamic and likely wet-based late Miocene East Antarctic Ice Sheet (EAIS) that underwent large size variations at orbital time scales. The dynamic behavior of the EAIS implies that a significant proportion of the variability seen in oxygen isotope records of the late Miocene reflects Antarctic ice-volume changes.
Keywords: Antarktis; Sørishavet; geologi; glasiologi; maringeologi; paleoklimatologi

Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

Metandania tordi, a new stegocephalid (Crustacea: Peracarida: Amphipoda) species from the Southern Ocean - Berge, Jørgen; Vader, Wim (Proceedings of the Biological Society of Washington, 2003)
A new stegocephalid (Amphipoda) species, Metandania tordi n.sp, is described, belonging to the subfamily Andaniexinae Berge & Vader 2001. The new species is the first record of the genus in the southern hemisphere. In addition, a morphological trait, previously not figured nor described within this family, is presented: a process proximally on the inner anterior surface of the fourth coxa. This locking-process is interpreted, and named accordingly, to enhance a relative stabilization of the third and fourth coxae. A brief comparison of the morphology of the fourth coxa between all five stegocephalid subfamilies is presented.
Keywords: Sørishavet; amfipoder; marin biologi; taksonomi

Sea ice extent and the global climate system - Dick, Chad (Polar Research, 2003)
Sea ice is a remarkable component of the global climate system. It can form over up to about 10 % of the global ocean area, and creates an insulating barrier between the relatively warm seawater and the cold atmosphere, allowing a temperature difference that may be tens of degrees over only a couple of meters. It reduces evaporation from the ocean, leading to a drier atmosphere than would otherwise exist. Sea ice modifies the radiation balance at the Earth’s surface because it supports snow (the most reflective of the Earth’s natural surfaces, with an albedo of up to approximately 0.8), where otherwise there would be seawater (the least reflective, with an albedo of about 0.07). As sea ice forms it excludes brine, deepening the ocean surface mixed layer and influencing the formation of deep and bottom water. As it melts, it releases relatively fresh water, stratifying the upper layers of the ocean. Through these processes sea ice exerts an enormous influence on the atmospheric and oceanic circulation in cold regions and indeed the climate of the rest of the globe.
Keywords: Sørishavet; globale klimasystemet; havis; klimaendringer; polarområdene; sjøis

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

Description and evaluation of the bergen climate model: ARPEGE coupled with MICOM - Furevik, Tore; Bentsen, Mats; Drange, Helge; Kindem, I. K. T.; Kvamstø, Nils Gunnar; Sorteberg, Asgeir (Climate Dynamics, 2003)
A new coupled atmosphere–ocean–sea ice model has been developed, named the Bergen Climate Model (BCM). It consists of the atmospheric model ARPEGE/IFS, together with a global version of the ocean model MICOM including a dynamic–thermodynamic sea ice model. The coupling between the two models uses the OASIS software package. The new model concept is described, and results from a 300-year control integration is evaluated against observational data. In BCM, both the atmosphere and the ocean components use grids which can be irregular and have non-matching coastlines. Much effort has been put into the development of optimal interpolation schemes between the models, in particular the non-trivial problem of flux conservation in the coastal areas. A flux adjustment technique has been applied to the heat and fresh-water fluxes. There is, however, a weak drift in global mean sea-surface temperature (SST) and sea-surface salinity (SSS) of respectively 0.1 °C and 0.02 psu per century. The model gives a realistic simulation of the radiation balance at the top-of-the-atmosphere, and the net surface fluxes of longwave, shortwave, and turbulent heat fluxes are within observed values. Both global and total zonal means of cloud cover and precipitation are fairly close to observations, and errors are mainly related to the strength and positioning of the Hadley cell. The mean sea-level pressure (SLP) is well simulated, and both the mean state and the interannual standard deviation show realistic features. The SST field is several degrees too cold in the equatorial upwelling area in the Pacific, and about 1 °C too warm along the eastern margins of the oceans, and in the polar regions. The deviation from Levitus salinity is typically 0.1 psu – 0.4 psu, with a tendency for positive anomalies in the Northern Hemisphere, and negative in the Southern Hemisphere. The sea-ice distribution is realistic, but with too thin ice in the Arctic Ocean and too small ice coverage in the Southern Ocean. These model deficiencies have a strong influence on the surface air temperatures in these regions. Horizontal oceanic mass transports are in the lower range of those observed. The strength of the meridional overturning in the Atlantic is 18 Sv. An analysis of the large-scale variability in the model climate reveals realistic El Niño – Southern Oscillation (ENSO) and North Atlantic–Arctic Oscillation (NAO/AO) characteristics in the SLP and surface temperatures, including spatial patterns, frequencies, and strength. While the NAO/AO spectrum is white in SLP and red in temperature, the ENSO spectrum shows an energy maximum near 3 years.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; polarområdene

Calcareous dinoflagellate associations and Maastrichtian–Tertiary climatic change in a high-latitude core (ODP Hole 689B, Maud Rise, Weddell Sea) - Hildebrand-Habel, Tania; Streng, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
The distribution of calcareous dinoflagellates has been analysed for the Maastrichtian–Miocene interval of Ocean Drilling Project Hole 689B (Maud Rise, Weddell Sea). The investigation thus represents a primary evaluation of the long-term evolution in high-latitude calcareous dinoflagellate assemblages during the transition from a relatively warm Late Cretaceous to a cold Neogene climate. Major assemblage changes during this interval occurred in characteristic steps: (1) an increase in relative abundance of tangentially structured species – particularly Operculodinella operculata – at the Cretaceous/Tertiary boundary; (2) a diversity decrease and several first and last appearances across the Middle–Late Eocene boundary, possibly attributed to increased climate cooling; (3) a diversity decrease associated with the dominance of Calciodinellum levantinum in the late Early Oligocene; (4) the reappearance and dominance of Pirumella edgarii in the Early Miocene, probably reflecting a warming trend; (5) monogeneric assemblages dominated by Caracomia spp. denoting strong Middle Miocene cooling. The results not only extend the biogeographic ranges of many taxa into the Antarctic region, but also indicate that the evolution of high-latitude calcareous dinoflagellate assemblages parallels the changing environmental conditions in the course of the Cenozoic climate transition. Therefore, calcareous dinoflagellates contribute to our understanding of the biotic effects associated with palaeoenvironmental changes and might possess the potential for reconstructing past conditions. The flora in the core includes one new taxon: Caracomia arctica forma spinosa Hildebrand-Habel and Streng, forma nov. Additionally, two new combinations are proposed: Fuettererella deflandrei (Kamptner, 1956) Hildebrand-Habel and Streng, comb. nov. and Fuettererella flora (Fütterer, 1990) Hildebrand-Habel and Streng, comb. nov.
Keywords: Sørishavet; Weddellhavet; geologi; klimaendringer; paleogeografi; paleoklimatologi; polarområdene

Postglacial marine environmental changes in Maxwell Bay, King George Island, West Antarctica - Khim, Boo-Keun; Yoon, Ho Il (Polar Research, 2003)
Sediment textural properties and total organic carbon (TOC) contents of three sediment cores from Maxwell Bay, King George Island, West Antarctica, record changes in Holocene glaciomarine sedimentary environments. The lower sedimentary unit is mostly composed of TOC-poor diamictons, indicating advanced coastal glacier margins and rapid iceberg discharge in proximal glaciomarine settings with limited productivity and meltwater supply. Fine-grained, TOC-rich sediments in the upper lithologic unit suggest more open water and warm conditions, leading to enhanced biological productivity due to increased nutrient-rich meltwater supply into the bay. The relationship between TOC and total sulfur (TS) indicates that the additional sulfur within the sediment has not originated from in situ pyrite formation under the reducing condition, but rather may be attributed to the detrital supply of sand-sized pyrite from the hydrothermal-origin, quartz-pyrite rocks widely distributed in King George Island. The evolution of bottom-water hydrography after deglaciation was recorded in the benthic foraminiferal stable-isotopic composition, corroborated by the TOC and lithologic changes. The Ø18O values indicate that bottom-water in Maxwell Bay was probably mixed gradually with intruding 18O-rich seawater from Bransfield Strait. In addition, the Ø13C values reflect a spatial variability in the carbon isotope distribution in Maxwell Bay, depending on marine productivity as well as terrestrial carbon fluxes by meltwater discharge. The distinct lithologic transition, dated to approximately 8000 yr BP (uncorrected) and characterized by textural and geochemical contrasts, highlights the postglacial environmental change by a major coastal glacier retreat in Maxwell Bay.
Keywords: Sørishavet; geofysikk; geokjemi; marin geologi; miljøendringer; sedimenter

Water mass modification over the continental shelf north of Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Padman, Laurie; Schröder, Michael; Woodgate, Rebecca A.; Jenkins, Adrian; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2003)
We use new data from the southern Weddell Sea continental shelf to describe water mass conversion processes in a formation region for cold and dense precursors of Antarctic Bottom Water. The cruises took place in early 1995, 1998, and 1999, and the time series obtained from moored instruments were up to 30 months in length, starting in 1995. We obtained new bathymetric data that greatly improve our definition of the Ronne Depression, which is now shown to be limited to the southwestern continental shelf and so cannot act as a conduit to northward flow from Ronne Ice Front. Large-scale intrusions of Modified Warm Deep Water (MWDW) onto the continental shelf occur along much of the shelf break, although there is only one location where the MWDW extends as far south as Ronne Ice Front. High-Salinity Shelf Water (HSSW) produced during the winter months dominates the continental shelf in the west. During summer, Ice Shelf Water (ISW) exits the subice cavity on the eastern side of the Ronne Depression, flows northwest along the ice front, and reenters the cavity at the ice front's western limit. During winter the ISW is not observed in the Ronne Depression north of the ice front. The flow of HSSW into the subice cavity via the Ronne Depression is estimated to be 0.9 ± 0.3 Sv. When combined with inflows along the remainder of Ronne Ice Front (reported elsewhere), sufficient heat is transported beneath the ice shelf to power an average basal melt rate of 0.34 ± 0.1 m yr−1.
Art. no. 3260
Keywords: AABW; Sørishavet; Weddellhavet; geofysikk; havstrømmer; isshelf; kontinentalsokkel; oseanografi

How fast do demersal longlines sink? - Robertson, Graham; Moe, Egil; Haugen, Roy; Wienecke, Barbara (Fisheries Research, 2003)
Longlines that sink fast reduce the time available to seabirds to attack baited hooks and are important in efforts to minimise seabird by-catch in longline fisheries. We measured sink rates in still seawater of longlines commonly used in the world’s demersal fisheries. Lines with integrated weight (lead cores) sank two to three times faster (45–52cm/s) than conventional (unweighted) lines. Conventional 9mm diameter lines made from polyester sank at 23cm/s compared to 18cm/s for 9mm Silver lines (blend of polyester, polyethylene and polypropylene). Samples of lines set by hand in still water sank significantly faster than longlines set from a fishing vessel, presumably because of the effect of the sea swell and upwellings from the propeller on the line set from the vessel.
Keywords: Sørishavet; fiskefartøy; fiskerier

Validation of AMSR sea-ice products in the Bellinghausen Sea, Antarctica - Steffen, Konrad (Ice and climate news, 2003)
Keywords: Sørishavet; glasiologi; havis; teknologi

The mid-Pliocene (4.3–2.6 Ma) benthic stable isotope record of the Southern Ocean: ODP Sites 1092 and 704, Meteor Rise - Andersson, Carin; Warnke, Detlef A.; Channell, James E.T.; Stoner, Joseph S.; Jansen, Eystein (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
We present mid-Pliocene (4.3–2.6 Ma) benthic stable oxygen and carbon isotope data from Ocean Drilling Program Site 1092 (ODP Leg 177) drilled in the sub-Antarctic sector of the Southern Ocean. The results are compared with the stable isotope results from nearby Site 704 (ODP Leg 114). Oxygen isotope data show that minimum values are about 0.5‰ less than those of the Holocene, which is consistent with the results from Site 704, indicating only minor deglaciation of Antarctica during the studied interval. Oxygen isotope data from both Site 1092 and Site 704 are slightly higher relative to Pacific values during several intervals which could be related to the contribution of warm, saline North Atlantic Deep Water (NADW). Comparisons of benthic carbon isotope gradients between sites located in the North Atlantic, sub-Antarctic sector of the Southern Ocean, and Pacific indicate that at times, the gradient between the Southern Ocean and the Pacific evolved differently than the Atlantic–Pacific gradient. This suggests that variations in NADW strength alone might not be responsible for the observed carbon isotope values in the Southern Ocean.
Keywords: Sørishavet; geologi; oseanografi; paleomagnetisme; paleontologi; stabile isotoper

Contracted spleen in seals, estimates of dilated organs, and diving capacity - Cabanac, A. J. (Polar Biology, 2002)
The spleens of several seals from both the Arctic and the Antarctic were isolated and weighed when contracted. Spleens of the crabeater, leopard, and Weddell seals formed 0.23%, 0.39%, and 0.86% of the seals' body weights; those of the hooded and harp seals formed 0.56% and 0.35% of the seals' body weights. In these 5 phocids, a contracted spleen relates to the seal's body weight according to the equation (in which weights are in kilograms; n=26; r2=0.65): contracted spleen=0.006 (body weight)-0.11. Further, using the criterion reported in the literature that contracted spleens of hooded seal and harp seals weigh 80% less than when dilated, the sizes of dilated spleens were estimated for the 5 phocids of the study, plus that of the southern elephant seal. Dilated spleens ranged from 1 to 4% of the seal's body weight, which is in agreement with determinations of dilated spleens reported in the literature (harbor, 0.8–3.0%; harp, 1.5%; hooded, 2.2–4.0%). The general correlation among dilated spleens and the 6 phocids' body weights is: dilated spleen=0.026 (body weight)-0.39(where weights are in kilograms; n=31; r2=0.70). The size of the spleen (either contracted or dilated) from the different species of seals in this study appeared to be correlated with the diving capacity of the phocids, as given in the literature. The phocids with greater diving capacities are the ones with the larger spleens.
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; marin biologi; pinnipedier; seler

Low phytoplankton biomass and ice algal blooms in the Weddell Sea during the ice-filled summer of 1997 - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum (Antarctic Science, 2002)
The summer of 1997 was characterized by unusually large amounts of pack ice in the southeastern Weddell Sea, and less than 10% of the area that is commonly ice-free in summer was open. A modest phytoplankton bloom developed in the upper mixed layer in the northernmost area (72°S). The bloom peaked in mid-February with max chlorophyll concentrations of 1.5 μg l−1, and integrated stocks of 55–60 mg m−2. Autotrophic flagellates dominated the biomass (80–90% of the chlorophyll) at first, while diatoms increased relative to flagellates during the bloom. Nutrient deficits, however, indicated that a much larger biomass was produced than was observed. Freezing starting after mid-February probably terminated the bloom, resulting in a pelagic growth season limited in time (less than two months) and space. The sea ice had a distinct brown layer of algae, usually at 1–2 m depth, with average chlorophyll biomass of 10.3 mg m−2. The ice cover exhibited a substantial amount of ridges, with ice algae growing in cavities and other structures, but with lower biomass than in the bands. Ice algae were also found growing on the lower 2 m of the ice shelf (visible at low tide). The overall growth season in the ice lasted several months, and ice algal production may have exceeded pelagic production in the Weddell Sea during the growth season of 1997. Pennate diatoms, like Fragilariopsis curta and F. cylindrus, dominated both in ice and in open water above the pycnocline, while Phaeocystis antarctica dominated in deeper layers and in crack pools. Euphausiids, particularly young stages, were frequently observed grazing on ice algae in ridges and on all sides of the floes, (confirmed by the gut content). Ice algae would thus have served as an ample food supply for the krill in the summer of 1997.
Edition: 2004/04/22 Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; fytoplankton; havis alger; hydrografi; krill; oseanografi

Renewal time and transport of unventilated Central Intermediate Water of the Weddell Sea derived from biogeochemical properties - Hoppema, Mario; de Baar, Hein J. W.; Fahrbach, Eberhard; Bellerby, Richard G. J. (Journal of Marine Research, 2002)
We have investigated the intermediate water mass of the central Weddell Gyre using TCO2 and oxygen data of FS Polarstern cruises in 1992, 1996 and 1998. This water mass, designated as Central Intermediate Water (CIW), is enriched in CO2 and depleted in O-2 relative to its source water due to biological degradation. CO2 enrichment and O-2 depletion were quantified by calculating the difference between the concentrations in the CIW and those in the, more southern source water, the Circumpolar Deep Water, which derives from the Antarctic Circumpolar Current. Inventories of enrichment and depletion were determined over the whole depth range of CIW, i.e. about 200800 m. The O-2 depletion inventory was greater than that of TCO2 enrichment which is in line with a biological origin of the signal. Spatial and interannual variation appeared to be small. Because subsurface remineralization in the central Weddell Gyre is largely restricted to the CIW, the export production estimate from previous work has been applied to compute the renewal time of CIW from these inventories. A renewal time of only three years was found. TCO2- and O-2-based computations were consistent, the former showing larger variation, though. From renewal time and volume of the CIW, a transport velocity (renewal rate) of 6-7 Sv was obtained. Of this, about I Sv is upwelled into the surface layer. The remaining 5-6 Sv CIW must be exported to the north, which is opposite to previous views. Results of water mass age and transport rate have thus been obtained using a method based on biogeochemical parameters. As the CIW cannot be identified by temperature and salinity, nor with transient tracers because it is hardly ventilated, this is the only way to obtain such results. As part of the CIW export, a large amount of remineralized CO2 enters the abyssal oceans where it is sequestered for long periods of time. The CIW is a principal and highly efficient player in the biological pump mechanism of the Southern Ocean.
Keywords: AABW; Sørishavet; Weddellhavet; biogeokjemi; geofysikk; havstrømmer; oseanografi; vannmasser

Annual export production in the interior Weddell Gyre estimated from a chemical mass balance of nutrients - Hoppema, Mario; de Baar, Hein J.W.; Bellerby, Richard G.J.; Fahrbach, Eberhard; Bakker, Karel (The Southern Ocean I: Climatic Changes in the Cycle of Carbon in the Southern Ocean, 2002)
Nitrate, phosphate and silicate data are presented from 1992 austral winter and 1998 austral autumn cruises with “FS Polarstern” in the Weddell Gyre. Because in the Weddell Gyre, away from the boundary current, the surface layer is eventually formed from upwelled deep water, the difference in nutrient concentrations between these layers can be used to compute net nutrient consumptions (identical with the export production). This method renders a value for the export production that is based on observed annual changes. The results are consistent for two years and two regions within the central gyre. The calculated net nitrate and phosphate consumptions were scaled to net carbon consumptions using canonical Redfield ratios, yielding 16–17μmolCkg−1yr−1. This equals 21±4gCm−2yr−1 as a robust estimate for the marginal ice zone. The net annual silicate consumption in the surface layer, which equals the export of biogenic silica, amounts to 15–18μmolkg−1yr−1. There is a tendency for higher values in the eastern Weddell Gyre. The estimated silicate consumption of about 1.8molSim−2yr−1 is relatively high compared to earlier estimations of biogenic silica export. The silicate to carbon consumption ratio of about 1 is very high, and documents the dominance of diatoms in the export of organic material. Résumé Sont présentées les distributions verticales de nitrate, de phosphate et de silicate en Mer de Weddell, pour les périodes de l’hiver austral 1992 et de l’automne austral 1998. Les eaux de surface du tourbillon à grande échelle de la Mer de Weddell (temps de résidence égal à 2.9 ans) sont formées par l’upwelling des eaux profondes. La différence de concentrations des sels nutritifs entre les couches profondes et de surface permettent de calculer la consommation annuelle, équivalente à la production exportée de l’élément nutritif considéré vers les couches profondes. Les résultats sont comparables pour les deux scénarios annuels étudiés. La production exportée de carbone pour les eaux de surface de la zone marginale de la glace, calculée à partir des consommations annuelles en nitrates et phosphates après transformation grâce aux rapports de Redfield, est estimée à 16–17μmolCkg−1yr−1 soit en moyenne 21±4gCm−2yr−1. La consommation annuelle de silicate est estimée à 1.8mol Si m−2yr−1, relativement élevée en comparaison des estimations antérieures. Le rapport molaire Si/C, voisin de 1 dans le matériel exporté, traduit la dominance des diatomées dans l’export de matières organiques.
Keywords: Sørishavet; Weddellhavet; fytoplankton; geofysikk; karbondioksid; marin biologi; oseanografi

Species richness of marine soft sediments - John, S Gray (Marine Ecology Progress Series, 2002)
Marine soft sediments comprise one of the largest and oldest habitats in the world, yet remarkably little is known about patterns of species richness. Here I present a short review of patterns of species richness and possible factors that influence such patterns. Species richness in general is remarkably high in both shallow coastal areas and the deep sea. However, there are clear differences the deep-sea has higher number of species for a given number of individuals than the coast. This can be explained by the larger amounts of primary production that reach coastal compared with deep-sea sediments, leading to higher numbers of individuals per unit area. Species density (the number of species per unit area) is also higher in the deep-sea than in coastal areas, but it is not obvious why this is so. Most studies of the broad patterns of species richness have used samples taken at small scales only. The problem with such analyses is that unless a large number of samples are taken, the true underlying pattern (or lack of it) may be wrongly interpreted. Recent studies have analysed species richness at larger scales. In general there seems to be a cline of increasing species richness from the Arctic to the tropics, but this is not the case in the southern hemisphere, where Antarctic species richness is high. However, it is not known whether high species richness in the Antarctic occurs at all spatial scales. To what extent these patterns are determined by evolutionary factors remains to be determined by the application of molecular methods. The available evidence suggests that environmental factors such as productivity, temperature, and sediment grain-size diversity play dominant roles in determining patterns of regional-scale species richness and patterns in species turnover, and it is probably the regional scale that primarily determines local species richness. KEYWORDS: Diversity · Deep sea · Coasts · Patterns · Scales
Keywords: Sørishavet; biodiversitet; marin biologi; polarområdene

Contribution of algal sinking and zooplankton grazing to downward flux in the Lazarev Sea (Southern Ocean) during the onset of phytoplankton bloom: a lagrangian study - Pakhomov, Evgeny A.; Froneman, Pierre W.; Wassmann, Paul; Ratkova, Tatjana; Arashkevich, Elena (Marine Ecology Progress Series, 2002)
ABSTRACT: Hydrography, chlorophyll a, phytoplankton and zooplankton dynamics and the vertical flux of particulate organic carbon (POC) and pigments in the upper 200 m were investigated for 12 consecutive days during a drogue study conducted in the open waters of the ice-edge zone of the Lazarev Sea during the austral summer (December/January) 1994/95. Results of the study indicate that during the experiment, primary production, although variable, increased from ~300 to ~800 mgC m^-2d^-1. This increase could likely be related to development of a shallow pycnocline. Analysis of sediment trap data showed that the vertical carbon flux resulting from sedimentation and grazing activity was greatest in the upper water column (<80 m). The importance of grazers to total POC flux was highest at the beginning and the end of the investigation and accounted for up to 15% of total carbon flux. The contribution of grazers to vertical flux was negligible (<2%) during the intermediate part of the Southern Ocean Drogue study. Lower contribution of grazers to sedimentation of POC at depth can likely be related to community composition of zooplankton. Sedimentation of phytoplankton cells from the upper water column increased during the study. Here, downward POC flux resulting from sedimentation of microphytoplankton was equivalent to 15-75% of the total. Increase in sedimentation of phytoplankton during the study can be related to an increase in the average size of phytoplankton cells. Transport of POC from surface waters to deeper depths resulting from sedimentation or grazing activity was equivalent to <48% of total daily primary production, measured at 50 m, while the same value for phytoplankton flux did not exceed 27% of the total. Zooplankton density was insufficient to exert either a positive (via faecal pellets) or negative (via reducing suspended phytoplankton concentration) effect on particulate carbon sedimentation. This resulted in algal sink being the most important mechanism in downward POC flux during the onset of the phytoplankton bloom period in the Marginal Ice Zone, even in the presence of pelagic tunicates.
Keywords: Sørishavet; alger; biokjemi; marin biologi; oseanografi; phytoplankton; zooplankton

Seaweeds in Cold Seas: Evolution and Carbon Acquisition - Raven, John A.; Johnston, Andrew M.; Kübler, Janet E.; Korb, Rebecca; Mcinroy, Shona G.; Handley, Linda L.; Scrimgeour, Charlie M.; Walker, Diana I.; Beardall, John; Clayton, Margaret M.; Vanderklift, Mathew; Fredriksen, Stein; et al. (Annals of Botany, 2002)
Much evidence suggests that life originated in hydrothermal habitats, and for much of the time since the origin of cyanobacteria (at least 2·5 Ga ago) and of eukaryotic algae (at least 2·1 Ga ago) the average sea surface and land surface temperatures were higher than they are today. However, there have been at least four significant glacial episodes prior to the Pleistocene glaciations. Two of these (approx. 2·1 and 0·7 Ga ago) may have involved a ‘Snowball Earth’ with a very great impact on the algae (sensu lato) of the time (cyanobacteria, Chlorophyta and Rhodophyta) and especially those that were adapted to warm habitats. By contrast, it is possible that heterokont, dinophyte and haptophyte phototrophs only evolved after the Carboniferous–Permian ice age (approx. 250 Ma ago) and so did not encounter low (≤5 °C) sea surface temperatures until the Antarctic cooled some 15 Ma ago. Despite this, many of the dominant macroalgae in cooler seas today are (heterokont) brown algae, and many laminarians cannot reproduce at temperatures above 18–25 °C. By contrast to plants in the aerial environment, photosynthetic structures in water are at essentially the same temperature as the fluid medium. The impact of low temperatures on photosynthesis by marine macrophytes is predicted to favour diffusive CO2 entry rather than a CO2‐concentrating mechanism. Some evidence favours this suggestion, but more data are needed.
Keywords: Sørishavet; alger; biogeografi; botanikk; makroalger; marin biologi

Revision of Stegosoladidus Barnard and Karaman, 1987 (Crustacea: Amphipoda: Stegocephalidae), redescription of two species and description of three new species - Berge, Jørgen (Journal of Natural History, 2001)
Stegosoladidus simplex (K. H. Barnard, 1930) and S. ingens (Chevreux, 1906) are both figured and redescribed. Three new species (Stegosoladidus antarcticus, S. complex and S. debroyeri) are described. The terminology used for classification of both setae and different setae arrangements is discussed, and the main types of setae are figured.
Publisher: Taylor & Francis
Keywords: Sørishavet; amfipoder; taksonomi; zoologi

Antarctic marine benthic biodiversity in a world-wide latitudinal context - Gray, John S. (Polar Biology, 2001)
In the 1950s and 1960s, the first data sets were assembled to examine whether or not there was a latitudinal gradient of species richness in the sea. These data comprised very few species and were from very small areas. However, recent data from large species lists covering broad geographical ranges suggest strongly that there is a gradient of increasing species richness from the Arctic to the tropics. However, the Southern Ocean has high species richness and in the southern hemisphere there is no clear evidence of a cline of increasing richness from pole to tropic. The great richness of the Southern Ocean compared with the Arctic is probably due to its great age, the fact that it covers a much larger area and that it has higher structural heterogeneity formed by living organisms. The importance of area as a determinant of species richness needs to be studied in more detail since most studies have been confined to small areas. A number of hypotheses have been proposed to explain the species:area relationship and these are discussed. An alternative explanation for the latitudinal cline in the northern hemisphere is the energy-input hypothesis, but again this has not been adequately tested. Two studies on the relationship between local and regional species richness show a significant positive correlation. These findings suggest that local assemblages are not tightly organised and saturated with species but are open to recruitment from the regional species pool. Whether or not such a relationship holds in Antarctica is unknown. It is concluded that further studies of the Southern Ocean are likely to provide new findings fundamental to the "new" discipline of macroecology, which examines patterns and processes at the geographic scale.
Keywords: Sørishavet; bentiske organismer; bentos; biodiversitet; marin biologi; økologi

Direct measurements reveal insignificant storage of anthropogenic CO2 in the Abyssal Weddell Sea - Hoppema, Mario; Roether, Wolfgang; Bellerby, Richard G. J.; de Baar, Hein J. W. (Geophysical Research Letters, 2001)
In the northern Weddell Gyre at the prime meridian, Total TCO2 changes in the Weddell Sea Bottom Water (WSBW) have been investigated. Following a suggestion by [Poisson and Chen, 1987], the TCO2 difference at potential temperatures of 0.2°C and −0.8°C was determined using data from 1996 and 1998. No significant difference was found to similar differences for the years 1973 and 1981 reported by Poisson and Chen. Thus, over a period of 25 years an at most minor amount of anthropogenic CO2 has penetrated into the WSBW at this location. This suggests that this abyssal subpolar region is relatively unimportant for the storage of anthropogenic CO2. The same core of WSBW exhibited a marked increase of chlorofluorocarbon (CFC). For the Southern Ocean, therefore, CFCs are apparently of limited value as analogues of anthropogenic CO2, in contrast to some other ocean provinces.
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; drivhusgasser; geofysikk; klimagasser

Historien om skuta Vesleper - Olsen, Else Mehren (Follominne: årbok, 2001)
Keywords: Antarktis; Bouvetøya; Peter I. Øy; Sørishavet; ekspedisjoner; historie; hvalfangst

Phytoplankton dynamics at the ice-edge zone of the Lazarev Sea (Southern Ocean) during the austral summer 1994/1995 drogue study - Pakhomov, Evgeny; Ratkova, Tatjana; Froneman, Pierre W.; Wassmann, Paul (Polar Biology, 2001)
Phytoplankton dynamics in the open waters of the ice-edge zone of the Lazarev Sea were investigated over 12 consecutive days during a drogue study conducted in austral summer (December/January) 1994/1995. Throughout the study, the upper water column (<30 m) was stratified with a well-defined pycnocline evident. Although a subsurface intrusion of colder, more saline water into the region was recorded on days 5–9 of the experiment, its effect on the water column structure was negligible. Total surface chlorophyll a biomass doubled between days 1 and 5 (from 0.82 to 1.62 mg m–3), and then showed a tendency to stabilise, while the depth-integrated chlorophyll a standing stock displayed an increasing trend during the entire experiment. All changes in biomass were associated with an increase in microphytoplankton. Flagellates and picoplankton dominated cell counts, while diatoms composed most of the phytoplankton biovolume. Results of the study indicate that, during the period of investigation, average cell abundance decreased. Coupled with this decrease was an increase in the biovolume and average size of the phytoplankton. Phytoplankton succession was observed in the ice edge during the drogue study. Typical ice-associated species of genera Haslea, Fragilariopsis and Chaetoceros, which dominated at the beginning of study, were replaced by open-water species of genera Corethron, Dactyliosolen and Rhizosolenia. The shift in phytoplankton species composition and size can likely be related to high light intensities and grazing by microzooplankton. The intrusion of colder, more saline water on day 5 appeared to modify the diatom succession, indicating extreme variability in phytoplankton dynamics in the near ice-edge zone of the Lazarev Sea.
Keywords: Sørishavet; fytoplankton; marin biologi; oseanografi

Protecting whales by distorting uncertainty: non-precautionary mismanagement? - Schweder, Tore (Fisheries Research, 2001)
Precautionary management is based on science, and is incompatible with large fluctuations in the management regime. Whaling is managed by the International Whaling Commission, and has seen large fluctuations. It is argued that both the period of intense Antarctic whaling and the current period of protectionism have been unduly prolonged by scientists expanding out of proportion the uncertainty surrounding management issues. In the 1950s, uncertainty concerning fin whale stock status and trend was consistently distorted from one quarter, and in the 1990s a minority in the Scientific Committee blocked consensus over the revised management procedure that had been successfully developed by the Committee. In both cases, the political consequence of expanded uncertainty in the science was lack of action resulting in a continuation of business as usual. Extending a period of heavy exploitation longer than the resource can sustain is mismanagement. Extending a period of extreme protectionism when the resource is known to scientists to sustain valuable exploitation is also mismanagement even from a conservationist point of view. This might, in fact, erode the role of science in management and thus prepare the ground for subsequent overexploitation. Distorting uncertainty by injecting controversy or otherwise expanding uncertainty has contributed to excessive fluctuations in management regimes and consequently in stock abundance. Detrimental fluctuations might continue, since science is side tracked and management now is based on sentiments that might fade.
Keywords: Den internasjonale hvalfangstkommisjonen; Sørishavet; fiskeri; hvalfangst; marine økosystemer

Kvalfangsteventyret i Antarktis - Tokheim, Henrik (Vindetreet: sogeskrift for Vindafjord, 2001)
Keywords: Sørishavet; historie; hvalfangst

IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Oceanographic observations south of Berkner Island: preliminary results - Nicholls, Keith W; Østerhus, Svein; Makinson, Keith; Johnson, Mark (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Sørishavet; oseanografi

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Publisher: Taylor & Francis
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Publisher: John Wiley & Sons, Ltd
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler

Functional biodiversity of lipids in Antarctic zooplankton: Calanoides acutus, Calanus propinquus, Thysanoessa macrura and Euphausia crystallorophias - Falk-Petersen, Stig; Sargent, John R; Lønne, Ole Jørgen; Timofeev, Sergej (Polar Biology, 1999)
Zooplankton samples were collected in January 1993 off Dronning Maud Land along a transect from open waters to the marginal ice zone close to the Antarctic ice shelf. Thysanoessa macrura was caught in open waters while Calanoides acutus and Calanus propinquus were mainly sampled between ice floes in the marginal ice zone. The “ice-krill”Euphausia crystallorophias was found over the shelf directly associated with ice floes. T. macrura had a lipid content up to 36% of its dry weight with the dominant lipid class, wax ester, accounting for 45–50% of the total lipid. The predominance of 18:1 fatty alcohols is the striking characteristic of the wax esters. Small specimens of E. crystallorophias had lipid levels up to 26% of their dry weight with, unexpectedly, triacylglycerols being the dominant lipid (up to 41% of total lipid). The small levels of wax esters in these animals (3–6% of total lipid) had phytol as a major constituent. Large specimens of E. crystallorophias had up to 34% of their dry weight as lipid, with wax esters (47% of total lipid) dominated by 16:0 and 14:0 fatty alcohols as the major lipid. Calanus propinquus had lipid levels of up to 34% of their dry weight, with triacylglycerols (up to 63% of total lipid) being the dominant lipid. High levels of 22:1 (n-9) fatty acid were present in the triacylglycerols. Calanoides acutus had lipid levels up to 35% of the dry weight with wax esters accounting for up to 83% of total lipid. High levels of (n-3) polyunsaturated fatty acids were recorded with 20:5(n-3), 22:6(n-3) and 18:4(n-3) being the dominant moieties. On the basis of their lipid compositions we deduce that: (1) Calanoides acutus is the strictest herbivore among the four species studied, heavily utilizing the typical spring bloom; (2) T. macrura is essentially omnivorous, probably utilizing the less defined bloom situations found in oceanic waters; (3) E. crystallorophias is an omnivore well adapted to utilize both a bloom situation and to feed on ice algae and micro-zooplankton associated with the ice; (4) Calanus propinquus seems to be the most opportunistic feeder of the four species studied, probably grazing heavily on phytoplankton during a bloom and, during the rest of the year, feeding on whatever material is available, including particulates, flagellates and other ice-associated algae. We conclude that the different biochemical pathways generating large oil reserves of different compositions, enabling species to utilize different ecological niches, are major determinants of biodiversity in polar zooplankton.
Keywords: NARE 1992/93; Sørishavet; biodiversitet; biokjemi; dyreplankton; krill; lipider; marin biologi; zooplankton

In search of an elusive Antarctic circumpolar wave in sea ice extents: 1978–1996 - Gloersen, Per; Huang, Norden E. (Polar Research, 1999)
For ease in discerning an Antarctic circumpolar wave in the perimeter of the ice pack, we construct a time series of the sea ice extents (essentially the area within the ice perimeter) in 1-degree longitudinal sectors for the period 1978-1996, as observed with the multichannel microwave imagers on board the NASA Nimbus 7 and the DOD (Dept. of Defense) DMSP (Defense Meteorological Satellite Program) F8, F11, and F13 satellites. After converting the time series into complex numbers by means of a Hilbert transform, we decompose the time series of the 360 sectors into its complex principal components (CPCs), effectively separating the spatial and temporal values. Then we decompose the real and imaginary parts of the temporal portions of the first three CPCs (complex principal compenents) by Empirical Mode Decomposition into their intrinsic modes, each representing a narrow frequency band, resulting in a collection of three CPCs for each intrinsic mode. Finally, we reconstruct the data in two different ways. First, we low-pass filter the data by combining all of the intrinsic modes of each CPC with periods longer than two years, which we designate as lowpass filtered. Next, we select the intrinsic mode of each CPC with periods of approximately four years, which we designate the quasiquadrennial (QQ) modes. The low-pass filtered time series shows eastward propagating azimuthal motion in the Ross and Weddell Seas, but no clearly circumpolar motion. The QQ time series, on the other hand, clearly shows eastward propagating circumpolar waves, but with occasional retrograde motion to the west.
Keywords: Rosshavet; Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; oseanografi

Residue determinants and sequence analysis of cold-adapted trypsins - Schrøder Leiros, Hanna-Kirsti; Willassen, Nils Peder; Smalås, Arne O. (Extremophiles, 1999)
The digestive enzyme trypsin is among the most extensively studied proteins, and its structure has been reported from a large number of organisms. This article focuses on the trypsins from vertebrates adapted to life at low temperatures. Cold-adapted organisms seem to have compensated for the reduced reaction rates at low temperatures by evolving more active and less temperature-stable enzymes. We have analyzed 27 trypsin sequences from a variety of organisms to find unique attributes for the cold-adapted trypsins, comparing trypsins from salmon, Antarctic fish, cod, and pufferfish to other vertebrate trypsins. Both the "cold" and the "warm" active trypsins have about 50 amino acids that are unique and conserved within each class. The main unique features of the cold-adapted trypsins attributable to low-temperature adaptation seem to be (1) reduced hydrophobicity and packing density of the core, mainly because of a lower (Ile + Leu)/(Ile + Leu + Val) ratio, (2) reduced stability of the C-terminal, (3) lack of one warm trypsin conserved proline residue and one proline tyrosine stacking, (4) difference in charge and flexibility of loops extending the binding pocket, and (5) different conformation of the "autolysis" loop that is likely to be involved in substrate binding.
Keywords: Sørishavet; biokjemi; fisker; marin biologi; mikrobiologi; polarområdene

Polare jubileer i 1997 og 1998 - Barr, Susan (Polarboken, 1998)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

Research cruise of the Scandinavian South African Antarctic expedition, December 1997 to February 1998 - Froneman, P.W.; Pakhomov, Evgeny; Turner, D.; Abrahamson, K.; Karlsson, B.; Godhe, Anna; Bertilsson, Stefan; Graneli, Wilhelm; Carlsson, Per; Wängberg, Sten-Åke; Wulff, Angela; Croot, Peter; et al. (South African Journal of Science, 1998)
Focuses on the Scandinavian/South African Antarctic expedition conducted between December 4, 1997 to February 6, 1998 which determined the role of Southern Ocean in the global carbon cycle in physical and biological oceanographic studies. Aims of the expedition; Underway sampling conducted; Biological results of the expedition; Conclusions.
Keywords: NARE ekspedisjoner; Sørishavet; fytoplankton; krill; marin biologi; oseanografi

Nitrogen uptake in the infiltration community, an ice algal community in Antarctic pack-ice - Kristiansen, Svein; Farbrot, Tove; Kuosa, Harri; Myklestad, Sverre M; Quillfeldt von, Cecilie Hellum (Polar Biology, 1998)
An infiltration community was the dominating ice algal community in pack-ice off Queen Maud Land, Southern Ocean, in January 1993. The community was dominated by autotrophic processes, and the most common species were the prymnesiophyte Phaeocystis antarctica and the diatoms Chaetoceros neglectus and Fragilariopsis cylindrus. The concentration of chlorophyll a was 1.3–47.9 μg l−1, and the inner part of the community was nitrate depleted. Uptake rates of nitrate, nitrite, ammonium, urea and amino acids were measured using 15N. Nitrate was the major nitrogen source for ice algal growth (67 ± 6% nitrate uptake). It is suggested that % nitrate uptake in the infiltration community decreases during the growth season, from 92% during spring (literature data) to 67% during summer. Scalar irradiance in the infiltration community was high and variable. It reached ca. 2000 μmol m−2 s−1 at some locations, and nitrate uptake rate was potentially photoinhibited at irradiances >500 μmol m−2 s−1. Nitrate uptake rate in an average infiltration community (0.6 m of snow cover) was lowered by 13% over a 2-week period due to photoinhibition.
Keywords: Sørishavet; Weddellhavet; alger; marin biologi

Establishing chronologies from acid-insoluble organic 14C dates on Antarctic (Ross Sea) and Arctic (North Atlantic) marine sediments - Licht, Kathy J; Cunningham, Wendy L; Andrews, John T; Domack, Eugene W; Jennings, Anne E (Polar Research, 1998)
Keywords: Rosshavet; Sørishavet; paleoseanografi; polarområdene; sedimentologi

Gut length, food transit time and diving habit in phocid seals - Mårtensson, Per-Erik; Nordøy, Erling; Messelt, Edward; Blix, Arnoldus Schytte (Polar Biology, 1998)
Keywords: Sørishavet; seler; zoologi

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Experimental formation of sea ice: importance of water circulation and wave action for incorporation of phytoplankton and bacteria - Weissenberger, Jürgen; Grossmann, Sönnke (Polar Biology, 1998)
The efficiency of physical concentration mechanisms for enrichment of algae and bacteria in newly formed sea-ice was investigated under defined conditions in the laboratory. Sea-ice formation was simulated in a 3,000 l tank under different patterns of water movement. When ice formed in an artificially generated current pattern, algal cells were substantially enriched within the ice matrix. Enrichment factors for chlorophyll a calculated from the ratio between the concentrations in ice and underlying water reached values of up to 53. Repeated mixing of ice crystals into the water column, as well as flow of water through the new ice layer, contributed to the enrichment of algae in the ice. Wave action during ice formation revealed lower phytoplankton enrichment factors of up to 9. Mixing of floating ice crystals with underlying water and pumping of water into the ice matrix by periodical expansion and compression of the slush ice layer were responsible for the wave-induced enrichment of algal cells. Physical enrichment of bacteria within the ice was negligible. Bacterial biomass within new ice was enhanced only when the concentration of algae was high. At low algal biomass, bacteria experienced substantial losses in the ice, most likely due to brine drainage, which were not observed for the microalgae. Bacterial cells are therefore not scavenged by ice crystals and the observed enrichment and sustainment of bacterial biomass within newly formed ice depend on their attachment to cells or aggregates of algae. Division rates of bacteria changed only slightly during ice formation.
Keywords: Sørishavet; Weddellhavet; alger; bakterier; fytoplankton; havis; marin biologi; polarområdene

Døde menn vender tilbake: Shackletons høyst private Whitbread-seilas - Winge, Jon (Norsk sjøfartsmuseum. Årbok, 1998)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Endurance (skip); Ernest Henry Shackleton; Sørishavet; ekspedisjoner; oppdagelsesreiser; skipsfart

Moorings from the Filchner Trough and the Ronne Ice Shelf front: preliminary results - Woodgate, Rebecca A; Schröder, Michael; Østerhus, Svein (Filchner-Ronne Ice Shelf Programme. Report, 1998)
Keywords: Sørishavet; oseanografi

Productivity in the 20th century Antarctic pelagic shore station whaling: growth and stagnation in two technological regimes. - Basberg, Bjørn L (The Great Circle, 1997)
Publisher: Australian Association for Maritime History
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangststasjoner; hvalindustri; pelagisk

Indentation testing on ice from the Filchner Ronne Ice Shelf area, Antarctica: preliminary results - Gerland, Sebastian (Filchner-Ronne Ice Shelf Programme. Report, 1997)
Keywords: Antarktis; Sørishavet; glasiologi; havis

Lack of population subdivision among the minke whales (Balaenoptera acutorostrata) from Icelandic and Norwegian waters based on mitochondrial DNA sequences - Bakke, Ingrid; Johansen, Steinar; Bakke, [Øyvind]; El-Gewely, Mohamed Raafat (Marine Biology, 1996)
The minke whale (Balaenoptera acutorostrata) is subject to commercial whaling, but stock identification and assessment are still uncertain. Mitochondrial DNA (mtDNA) sequences were determined to examine the population structure of minke whales from the central and northeastern parts of the North Atlantic, as well as the Antarctic regions IV and V. The analyses include 345 nucleotide positions of the control region of 110 individuals, and 250 nucleotide positions of the NADH dehydrogenase subunit 2 gene for a representative selection of North Atlantic minke whales. Maximum parsimony analyses and sequence divergence calculations did not reveal any genetic differentiation between individuals from the central and northeastern parts of the North Atlantic. These results do not support the International Whaling Commission's separation of minke whales in this area into different management units, and they are in conflict with previously reported results from allozyme analyses. Comparison of minke whale control region sequences showed that the sequence diversity of North Atlantic minke whales is substantially lower (0.0065) than that of Antarctic minke whales (0.0166), and clearly demonstrated that individuals from these two areas represent genetically distinct populations.
Keywords: Sørishavet; bioteknologi; genetikk; hvaler; marin biologi; polarområdene

Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways - Kattner, Gerhard; Hagen, Wilhelm; Falk-Petersen, Stig; Sargent, John R.; Henderson R. James (Marine Ecology Progress Series, 1996)
The unique predominance of oleyl alcohols (18:1) is the striking characteristic of the lipids of the Antarctic euphausiid Thysanoessa macrura. The 2 isomers 18:1(n-9) and 18:1(n-7) occurred in similar proportions in the wax esters of T. macrura and comprised up to 80% of the total fatty alcohols. The remainder consisted mostly of the 20:1(n-9) alcohol along with small amounts of the 22:1(n-11) alcohol. No marine zooplankton species has previously been reported which produces wax esters with significant amounts of 18 carbon fatty alcohols. T. macrura specimens were collected in the high Antarctic Weddell Sea during autumn 1992 and summer 1993. Their lipid levels were high, about 40 to 50% of the dry mass with up to 70% of the total lipid as wax esters. The wax ester fatty acids were dominated by the saturates 14:0 and 16:0, which, along with the monounsaturate 18:1(n-9), accounted for more than 80% of the total fatty acids. Phospholipids contained high levels of (n-3) polyunsaturated fatty acids (20:5 and 22:6) typical of membrane lipids from marine zooplankton. The precise significance of the unique wax ester composition in T. macrura is not clear but this discovery underscores the biochemical adaptability of Antarctic zooplankton species to a constantly cold and highly seasonal polar environment.
Keywords: Sørishavet; Weddellhavet; biokjemi; dyreplankton; hoppekreps; krill; marin biologi; zooplankton; økologi

Modelling the ocean response to secular surface temperature transitions - Mork, K. A.; Skagseth, Øystein (Climate Dynamics, 1996)
The ocean response to surface temperature transients is simulated with the use of the Hamburg large-scale geostrophic (LSG) ocean general circulation model (OGCM). The transition, from the present to a climate corresponding to a doubling of the atmospheric CO2 content, is compared with the reversed transition. For the Atlantic, the time scale for the deep ocean to adjust to the temperature changes was similar for both transitions. In the Pacific, the time scale is shorter for the present to warm transition than for the reverse case, a result of increased production of Antarctic bottom water (AABW) during the warm climate. While the transition from cold to warm climate shows no secular variability, the reversed transition generates considerable variability on time scales of 300–400 years. For the warm climate, oscillations with periods of 45 years are found in the Southern Ocean. Results of principal oscillation pattern (POP) analysis indicate that these oscillations are due to interaction between convection in the Southern Ocean and advected salinity anomalies in the Antarctic Circumpolar Current (ACC) and the Southern Pacific Ocean.
Fulltext: https://www.researchgate.net/publication/225411625_Modelling_the_ocean_response_to_secular_surface_temperature_transitions
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; vannmasser

Effects of UV radiation on post-bloom phytoplankton populations in Kvalsund, North Norway - Walter Helbling, E.; Eilertsen, Hans Chr.; Villafañe, Virginia E.; Holm-Hansen, Osmund (Journal of Photochemistry and Photobiology B: Biology, 1996)
Our studies in the coastal waters in North Norway show that rates of photosynthesis of natural phytoplankton assemblages are strongly inhibited by solar UV radiation. When exposed to high irradiances of direct solar radiation, photosynthetic rates were increased by approximately 150% when all UV radiation was excluded from samples, with UVB radiation being responsible for approximately 50% of the total inhibition. There was no discernible threshold value for inhibition of photosynthesis by UV radiation, even at UV (280–400 nm) irradiances as low as 0.1 W m−2. When natural assemblages were incubated in situ, inhibition of photosynthetic rates were detectable down to 10 m, where solar irradiance was about 3% of the radiation incident on the sea surface. Based on the inhibition of photosynthetic rates at very low fluences of UV radiation, post-bloom assemblages of phytoplankton in North Norway and possibly also in the Arctic ocean appear to be more sensitive to solar UV radiation than phytoplankton from the Southern Ocean.
Keywords: Sørishavet; fotosyntese; fytoplankton; marin biologi; polarområdene; ultrafiolett stråling

Hvalen – ressurs og politikk – Historisk overblikk - Fløistad, Brit (Vestfoldminne, 1995)
Publisher: Museumsforlaget
Keywords: Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Distribution and diving behaviour of crabeater seals (Lobodon carcinophagus) off Queen Maud Land - Nordøy, Erling S.; Folkow, Lars; Blix, Arnoldus Schytte (Polar Biology, 1995)
Eight crabeater seals (Lobodon carcinophagus) (three females, five males), ranging in body mass between 125 and 220 kg, were captured off Queen Maud Land (70-72 degrees S, 7-16 degrees W) during the last week of February, just after moulting, and tagged with Argos satellite-linked dive recorders to provide data on location and diving depth and duration. During the first few weeks of March the seals were moving in the pack ice along the continental shelf edge, close to the coast of Queen Maud Land. In April and May, when the pack ice extended northwards, most of the seals moved north, one reaching 63 degrees S in late May. In the first half of June the two remaining seals turned south and moved back deep into the pack ice. The seals made about 150 dives per day each throughout the study period. Ninety percent of these were made to depths of less than 52 m. Individual maximum diving depths varied between 288 and 528 m. In March the seals were most active at night, when the dive depth was shallower than during the day. In April and May the seals were more active during day-time, with an absence of any diurnal change in diving depth. These results support the notion that crabeater seals predominantly feed on krill in Antarctic pack ice, even when winter returns to the waters off Queen Maud Land.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; biodiversitet; marin biologi; seler; telemetri; zoologi; økologi

Åpning av Foyn-seminaret 23.januar 1995 - Olsen, Jan Henry T (Vestfoldminne, 1995)
Publisher: Vestfoldmuseene
Keywords: Den internasjonale hvalfangstkommisjonen; Norge; Svend Foyn; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstkvotene; pelagisk

Variability in nutrient concentrations around Elephant Island, Antarctica, during 1991-1993 - Silva S, Nelson; Helbling, E Walter; Villafañe, Virginia; Amos, Anthony F; Holm-Hansen, Osmund (Polar Research, 1995)
Keywords: Elefantøya; Sørishavet; næringsstoffer; vannmasser

Water mass distribution and tides along the Filchner-Ronne ice shelf: preleminary [sic] results from the Norwegian Antarctic Expedition 1992/93 - Gammelsrød, Tor (Filchner-Ronne Ice Shelf Programme. Report, 1994)
Keywords: Sørishavet; oseanografi

Synedropsis gen. nov., a genus of araphid diatoms associated with sea ice - Hasle, Grethe Rytter; Medlin, Linda K.; Syvertsen, Erik E. (Phycologia, 1994)
A new araphid diatom genus, Synedropsis Hasle, Medlin et Syvertsen, is described from sea ice. The generitype, Synedropsis hyperborea (Grunow) Hasle, Medlin et Syvertsen from the Arctic, was first described as a species of Synedra, as was the antarctic Synedropsis fragilis (Manguin) Hasle, Syvertsen et Medlin. A second antarctic species of Synedropsis is a new combination of Cymatosira laevis Heiden in Heiden & Kolbe. In addition four new taxa, S. hyperboreoides Hasle, Syvertsen et Medlin, S. recta Hasle, Medlin et Syvertsen, S. lata Hasle, Medlin et Syvertsen and S. lata var. angustata Hasle, Medlin et Syvertsen are described from the Antarctic. The valve wall is laminar with uniseriate, often poorly developed striae and a wide sternum. Each valve possesses apical fields composed of slits. A labiate process is positioned near one apical slit field. The valve outline for most species exhibits considerable stadial variation. The girdle has several bands, most with one row of poroids close to the pars interior. Thus Synedropsis is closely related to the marine Fragilaria striatula Lyngbye except in the structure of the apical fields and the number of bands. Species observed in uncleaned material appeared in stellate or, more seldom, ribbon-shaped colonies. Synedropsis hyperborea is a common epiphyte on the ice-associated Melosira arctica Dickie in the Arctic. The antarctic species were found mainly in the bottom ice community, S. fragilis as an epiphyte on other diatoms.
Publisher: Taylor & Francis
Keywords: Rosshavet; Sørishavet; Weddellhavet; botanikk; diatomeer; havis; kiselalger; marin biologi; plankton

Occurrence of Pseudoterranova decipiens (Nematoda) in fish from the Southeastern Weddell Sea (Antarctic) - Palm, Harry; Andersen, Karin; Klöser, Heinz; Plötz, Joachim (Polar Biology, 1994)
Eleven fish species from the Weddell Sea (Antarctic) were examined for infestation with anisakid nematodes. Two species of the genus Contracaecum and the sealworm Pseudoterranova decipiens were isolated from the liver and the body cavity of fish affected. Only two specimens of P. decipiens (1.4%) partly invaded the belly flaps. The following fish species were infested by P. decipiens at the given prevalences: Cygnodraco mawsoni (74.4%), Trematomus scotti (23.2%), Pagetopsis maculatus (10.0%), Cryodraco antarcticus (7.1%), Trematomus lepidorhinus (3.0%), and Dolloidraco longedorsalis (2.7%). All of these, except Trematomus scotti, are new host records. Chaenodraco wilsoni, Chionodraco myersi, Gerlachea australis, Racovitzia glacialis and T. eulepidotus were not infested. The reasons for low prevalence and intensity of infestation are seen in the difficulties of P. decipiens in completing its benthic life cycle in the Weddell Sea environment, in the absence of shallow coastal waters due to the floating shelf-ice. Cygnodraco mawsoni is a crucial intermediate host, without which completion of the parasite life cycle might not be possible. In order to clarify the taxonomical position of Antarctic Pseudoterranova, morphological comparisons with specimens of P. decipiens from the German and Norwegian coast were made using scanning electron microscopy. Results revealed no differences; hence, all specimens studied belong to the same species P. decipiens.
Keywords: Sørishavet; Weddellhavet; biodiversitet; fisker; marin biologi; økologi

Hvalfangstlæge for 40 år siden - Husby, Jakob; Kolltveit, Bård (Norsk sjøfartsmuseum. Årsberetning, 1993)
Publisher: Museet Place: Oslo
Keywords: Anglo Norse ekspedisjonene; Sørishavet; erindringer; historie; hvalfangst; hvalkokerier; pelagisk

Ice algae during EPOS, leg 1: assemblages, biomass, origin and nutrients - Syvertsen, Erik E; Kristiansen, Svein (Polar Biology, 1993)
Keywords: Sørishavet; Weddellhavet; alger; biomasse

The Antarctic Treaty system and the law of the sea. Review of Christopher C. Joyner: Antarctica and the law of the sea - Vidas, Davor (International Challenges, 1993)
Keywords: Sørishavet; jus; litteratur

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Nitrogen uptake in the Weddell Sea during late winter and spring - Kristiansen, Svein; Syvertsen, Erik E; Farbrot, Tove (Polar Biology, 1992)
Keywords: Sørishavet; Weddellhavet; alger; biologi

Glaciomarine turbidite and current controlled deposits in Prydz Bay, Antarctica - Kuvaas, Berit; Leitchenkov, German (Marine Geology, 1992)
A thick sequence (up to 2200 m) of presumed post late Eocene/early Oligocene glaciomarine sediments is inferred to be present on the Prydz Bay continental rise. In the absence of information from drillholes, we correlate to ODP Leg 119 drillsites on the shelf and compare with the seismic reflection pattern of glaciomarine sequences in the Weddell Sea. The inferred glaciomarine sediments in Prydz Bay appear to be deposited in a complex manner, suggesting interaction by both turbidity cur rents and strong bottom currents. Reflection seismic profiles from the lower continental slope and rise shows an abundance of current influenced deposits, such as sediment waves and large sediment ridges with similarities to contourite drifts. In addition, large channel-levee complexes are abundant, suggesting deposition by turbidity currents and other massflow processes. Large channels and sediment ridges trend oblique to the continental margin. The geometry and character of the seismic reflection pattern suggest that the ridges have been deposited under the combined influence of overflow from downslope channelized turbidity currents and strong bottom water flow. The observed sediment waves and the difference along eastern and western channel margins suggest that bottom currents are flowing towards the west. We suggest that the initiation of turbidite sedimentation occurred in the late Eocene-early Oligocene, when the Amery Ice Shelf reached the shelf edge for the first time. Onset of current controlled deposition may possibly be related to the opening of the Drake Passage at the Oligocene/Miocene boundary.
Keywords: Sørishavet; Weddellhavet; havbunnen; kontinentalmargin; marin geologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi

Gigantisk isfjell i Sør-Atlanteren - Orheim, Olav (Polarboken, 1992)
Keywords: Sørishavet; glasiologi; isfjell

Studies through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; oseanografi

The role of the microbial loop in Antarctic pelagic ecosystems - Azam, Farooq; Smith, David C; Hollibaugh, James T (Polar Research, 1991)
Keywords: Sørishavet; fytoplankton; oseanografi; økosystemer

Hvalbåter over og under vann - Basberg, Bjørn L; Nævestad, Dag (Norsk sjøfartsmuseum Årsberetning, 1991)
Keywords: Sørishavet; historie; hvalfangst; skip

Whaling or Shipping? Conflicts over the Use of the Norwegian Whaling Fleet during World War II - Basberg, Bjørn Lorens (International Journal of Maritime History, 1991)
When the United Kingdom entered World War n in September 1939 the Norwegian merchant marine was immediately affected, as its ships became the targets of German submarines. Between September 1939 and April 1940 (when Norway was occupied by the Nazis), more than fifty Norwegian ships were lost, mainly in the North Sea and the north Atlantic. In November 1939 an agreement was reached between the British government and the Norwegian Shipowners Association to place almost half the Norwegian merchant fleet at Britain's disposal under the so-called "charter parties scheme." The king and the Norwegian government fled to London and established a government-inexile during the German occupation, but before their departure it was decided to establish an agency in the British capital to operate and manage Norwegian shipping. It was named the Norwegian Shipping and Trade Mission (Nortraship) and became the world's largest shipowner, controlling more than one thousand ships at the outset of the war.'
Publisher: SAGE Publications Ltd
Keywords: Norge; Sørishavet; andre verdenskrig; hvalbåter; hvalfangstindustri; hvalindustri; pelagisk hvalfangst

Phytoplankton-bacteria relationship in the Antarctic marine ecosystem - Billen, Gilles; Becquevort, Sylvie (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; bakterier; biomasse; fytoplankton; marin biologi; oseanografi; økofysiologi; økosystemer

The physiology of polar marine zooplankton - Clarke, Andrew; Peck, Lloyd S (Polar Research, 1991)
Keywords: Sørishavet; marin biologi; polarområdene; zooplankton

Primary production in polar waters: relation to nutrient availability - Harrison, W G; Cota, G F (Polar Research, 1991)
Keywords: Sørishavet; fytoplankton; oseanografi

Krill Enzymes. A New Concept for Efficient Debridement of Necrotic Ulcers - Hellgren, L.; Karlstam, B.; Mohr, Viggo; Vincent, J. (International Journal of Dermatology, 1991)
The article discusses the new concept for surgery of necrotic ulcers using the krill enzymes. The krill peptide hydrolases represent a new and important alternative to mammalian or microbial enzymes for distinctive medical applications, such as debridemen.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting

Hvalfangernes mat til hverdag og fest - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1991)
Keywords: Sørishavet; ernæring; hvalfangst

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Publisher: Routledge
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Factors controlling the development of phytoplankton blooms in the Antarctic Ocean — a mathematical model - Sakshaug, Egil; Slagstad, Dag; Holm-Hansen, Osmund (Marine Chemistry, 1991)
A mathematical model describing the development of phytoplankton blooms as a function of the depth of the wind-mixed layer, spectral distribution of light, passage of atmospheric low-pressure systems, size of the initial phytoplankton stock and loss rates is presented. Model runs represent shade-adapted, large-celled, bloom-forming diatoms. Periodic deep mixing caused by strong winds may severely retard the development of blooms and frequently abort them before macronutrients are completely exhausted. Moderate depths of mixing (40-50 m) in combination with a moderately large total loss rate (about 0.01 3 h-1) can prevent blooms from developing during the brightest time of the year. Complete exhaustion of macronutrients in the upper waters is likely only if the wind-mixed layer is less than 10 m deep, i.e. in very sheltered waters, and also in the marginal ice zone when ice is melting. We do not exclude the possibility of control of phytoplankton biomass by iron in ice-free, deep-sea parts of the Antarctic Ocean, but the implied enhancement of export production through addition of iron might be restricted because of limitation by light, i.e. vertical mixing.
Keywords: Scotiahavet; Sørishavet; fytoplankton; marin biologi; oseanografi

Conference report: preservation or exploitation - Stokke, Olav Schram (Marine Policy, 1991)
Keywords: Sørishavet; forvaltning; jus; politikk

Symposium report: "The Antarctic Treaty System in World Politics" - Stokke, Olav Schram (International Challenges, 1991)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Antarctica's cultural heritage: can ICOMOS help? - Barr, Susan (Icomos information, 1990)
Keywords: Antarktis; Sørishavet; historie; kulturminneforvaltning

The practical implications of the eco-system approach in CCAMLR - Beddington, John R; Basson, M; Gulland, J A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

The tides of the southern Weddell Sea - Foldvik, Arne; Middleton, Jason H; Foster, Theodore D (Deep Sea Research Part A. Oceanographic Research Papers, 1990)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; tidevann

Has CCAMLR worked? management policies and ecological needs - Heap, John A (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; økologi

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Publisher: Inter-Research Science Center
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton

Glaciologic and oceanographic studies on Fimbulisen during NARE 1989/90 - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1990)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; glasiologi; isbrem; oseanografi

The implementation of CCAMLR: is the decision-making machinery conductive to good management? - Orrego Vicuña, Francisco (International Challenges, 1990)
Keywords: Sørishavet; forvaltning; miljøvern; politikk

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

The relationship between the ATS and the LOS convention of 1982 - Safronchuk, Vasiliy S (International Challenges, 1990)
Keywords: Antarktis; Sørishavet; havrett; jus; politikk

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser

Zwischen Kooperation und Konfrontation. Deutschland, Norwegen und die Walfangfrage in den 1930er Jahren - Scholl, Lars Ulrich (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1990)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Norge; Sørishavet; Tyskland; historie; hvalfangere; hvalfangstindustri; hvalolje; pelagisk; samarbeid

På hvalfangst med blyant og farvestifter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; kunst; pelagisk

Pierce's kastebørse - et "Reodor Felgen" -patent med lang levetid - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Publisher: Museene Place: Sandefjord
Keywords: Sørishavet; historie; hvalfangst; hvalolje; patenter; pelagisk; utstyr

Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Genetic homogeneity of krill (Euphausia superba Dana) in the Southern Ocean - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1989)
Development of a comprehensive picture of the genetic population structure of the Antarctic krill (Euphausia superba) has been hampered by a lack of genetic data from two major areas of the species' distribution, the Bellingshausen Sea and the Ross Sea. Evidence from earlier studies of a discrete “Bellingshausen Sea” population was based on anomalous allele frequencies in two sample sets that were collected near the west coast of the Antarctic Peninsula rather than in the Bellingshausen Sea proper. In this paper we describe the first biochemical genetic data obtained on krill from the central Bellingshausen Sea and from the Ross Sea. Analyses of eight polymorphic loci in samples from these two areas have failed to provide any evidence of population structuring within the Pacific sector of the Southern Ocean, and have indicated that Pacific sector krill cannot be genetically discriminated from Atlantic sector krill or Indian Ocean sector krill. These findings further support the hypothesis of a single circumpolar breeding population of Antarctic krill.
Keywords: Rosshavet; Sørishavet; biokjemi; genetikk; krill; marin biologi; plankton

Phytoplankton blooms in the vicinity of palmer station, Antarctica - Holm-Hansen, Osmund; Mitchell, Brian Gregory; Hewes, Christopher D; Karl, David Michael (Polar Biology, 1989)
Fifteen oceanographic stations were occupied in the vicinity of Anvers Island, Antarctica, in January of 1985 and 1987. All stations showed high phytoplankton biomass (4.0 to 30 μg chl-a/liter) which was either uniformly distributed in the upper mixed layer or showed a pronounced sub-surface maximum at 4–5 m depth. As phosphate was less than 0.02 μm and nitrate about 2.0 μm in surface waters, it appears that nutrient limitation of phytoplankton growth may be of importance during such blooms. This view is supported by chemical measurements of the particulate material which showed high chl-a/ATP ratios (about 7.7), as well as high POC/ATP ratios (about 700). Microscopical analysis revealed a dominance of large-celled diatoms and the near absence of heterotrophic protozoans. Size fractionation studies showed that the nanoplankton accounted for only 28% of the total phytoplankton biomass. When phytoplankton biomass reaches the levels found at these stations, it appears that the cells are light-limited and hence dark-adapted, which results in the high chl-a/ATP ratios and the low assimilation values (0.49–1.64) obtained in our studies. Under such conditions greater than 50% of the total phytoplankton biomass is found below the 1% light level.
Keywords: Sørishavet; biomasse; fytoplankton; oseanografi

The relationship between science and politics in international management of marine living resources: the case of CCAMLR - Indreeide, Thor Vidar (International Challenges, 1989)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Hjelpekrysser kaprer norske hvalfangere - Nilsen, Tore L.; Thowsen, Atle (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1989)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Sørishavet; andre verdenskrig; historie; hvalbåter; hvalfangstflåten; pelagisk

Life at the Ice Edge - Sakshaug, Egil; Skjoldal, Hein Rune (Ambio, 1989)
Publisher: [Springer, Royal Swedish Academy of Sciences]
Keywords: Sørishavet; alger; forurensning; fytoplankton; krill; miljø; planteplankton; zooplankton

Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Biochemical genetics and population structure of Euphausia superba - Fevolden, Svein Erik (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1988)
Keywords: Sørishavet; biokjemi; krill; plankton

Genetic population structure of Euphausia superba DANA in the Atlantic Sector of the Southern Ocean as demonstrated by different electrophoretic techniques - Fevolden, Svein Erik; Schneppenheim, Reinhard (Polar Biology, 1988)
Electrophoretic analyses of allele distributions at nine polymorphic gene loci were conducted in samples of Euphausia superba from the Bransfield Strait, off the South Orkney Islands, and from the south-eastern part of the Weddell Sea. The aim was to determine whether reported phenotypic differences between krill stocks from these areas could be linked to genotypic differences. Despite minor deviations of genotype distributions from Hardy-Weinberg expectations, the data gave no evidence of genetic heterogeneity over the sampled area, and the hypothesis of a single genetically homogeneous krill population could not be rejected. Genetic data for four selected loci were verified by using two different electrophoretic methods. Results from these two techniques yielded no discrepancies in interpretation of the data.
Keywords: Sør-Orknøyene; Sørishavet; Weddellhavet; genetikk; krill; marin biologi; plankton

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Minnesmerket på Østre Halsen over antarktispioneren C.A. Larsen - Larsen, Hans-Kjell (Polarboken, 1988)
Keywords: Sørishavet; biografi; historie; hvalfangst

Antarctic icebergs: production, distribution and disintegration (abstract) - Orheim, Olav (Annals of Glaciology, 1988)
A programme of systematic iceberg observations was initiated in 1981 by Norsk Polarinstitutt through the SCAR Working Group on Glaciology. Icebergs are recorded every 6 h and in five length groups: 10-50, 50-200, 200-500 and 500-1000 m, and those over 1000 m, which are described individually. Data on more than 100 000 icebergs are now on file at Norsk Polarinstitutt, and practically all ships travelling to and from Antarctica participate in the collection of data. This paper presents the first comprehensive analysis of the iceberg data. The quality of the data set is discussed, with consideration of potential errors in and limitations of the data, and various statistical evaluations. Representative distribution data are presented, and used to determine iceberg production, disintegration and mean residence times, and regional and total Antarctic calving rates. The incidence of large-scale calving in particular is evaluated, including the remarkably large break-offs in recent years. These exceed both the total annual accumulation on the Antarctic continent and the mean annual calving rate as determined from ship observations. The results show further: (1) that there are more than 200 000 icebergs south of the Antarctic Convergence, (2) that there are large regional differences in iceberg calving rates and iceberg sizes, and (3) that the calving rate from Antarctica is higher than that given in most previous estimates, which implies (4) that the mass balance of the Antarctic ice sheet is not positive as suggested by most recent estimates.
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi

Palaeoceanography of the subantarctic South Atlantic - Ciesielski, Paul; Kristoffersen, Yngve (Nature, 1987)
Keywords: Sørishavet; oseanografi

Biochemistry of the autolytic processes in Antarctic krill post mortem. Autoproteolysis - Ellingsen, Trond E.; Mohr, Viggo (Biochemical Journal, 1987)
1. Autoproteolysis post mortem was examined at 0 degree C by following the changes in the major classes of krill (Euphausia superba and Euphausia crystallorophias) proteins and by liberation of peptides and free amino acids, and was based on experiments conducted on board expedition vessels in the Antarctic. 2. Primarily salt-soluble proteins were broken down during the first week of incubation, whereas water-soluble and insoluble proteins were degraded to a much smaller extent. The enzymes responsible for the hydrolysis presumably originate primarily from the digestive apparatus of the krill. 3. In general, the individual amino acids were released at rates corresponding to their relative occurrence in the bulk protein of the krill. Alanine was liberated in larger amounts than would be expected from the composition of the krill protein, and was evidently formed also by reactions other than proteolysis. Glutamic acid, and certain amino acids which presumably occur with high frequency adjacent to glumatic acid residues in the krill protein, were liberated only to a limited extent, and accumulated in smaller peptides. 4. During proteolysis, arginine seemed to be converted to some degree into ornithine, and on prolonged incubation conversion of arginine and lysine into their corresponding decarboxylation products, agmatine and cadaverine, appeared to take place.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40primeS and long. 10°W, lat. 69°20primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Meeting abstract from: AAPG Annual Convention, Los Angeles, California, June 7-10, 1987
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Evolution of under water sides of ice shelves and icebergs - Orheim, Olav (Annals of Glaciology, 1987)
A systematic programme of side-scan sonar and plumb- line soundings was carried out in the Weddell Sea area in 1985 to measure the under-water sides of ice shelves and icebergs. From these observations the following model is suggested for the evolution of the ice front: (1) Initial stage: fracturing of the ice shelves takes place along smooth, curvi-linear segments with vertical faces. (2) Formative stage: the freshly formed vertical face is eroded both by wave and swell action around the water line, by small calvings from the undercut, overhanging subaerial face, and by submarine melting. The melting has a minimum at 50–100 m depth, and increases with depth to a rate of around 10 m a−1 at 200 m, This is about twice the rate of erosion at the water line. The variation in melting with depth results from a combination of summer melting by near-surface water, and year-round melting by water masses that are increasingly warmer than the pressure melting-point with depth. (3) Mature stage: this stage is reached after a few years of exposure. The backward erosion of the face leads to a shape with a prominent under-water “nose” with a maximum projection to more than 50 m at 50–100 m depth. The ramp above this slopes upwards to meet the vertical wall about 5 m below the water line. The ice below the nose is melted back beyond the above-water face. There is no net buoyancy and ice shelves at this mature stage are generally not up-warped at the front.
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi

Icebergs in the Southern Ocean (abstract) - Orheim, Olav (Annals of Glaciology, 1987)
Relatively little data on the distribution of Antarctic icebergs were available prior to 1980. The published literature included size data of about 5000 icebergs, and position data of 12 000 icebergs. There were indications that the size data were biased in favour of larger icebergs. A programme of systematic iceberg observations was therefore initiated by Norsk Polarinstitutt in 198! through the SCAR Working Group on Glaciology. This programme is based on standard “blue” forms distributed to all ships going to Antarctica. The icebergs are recorded every 6 h and in Five length groups: 10–50, 50–200, 200–500, and 500–1000 m, and those over 1000 m are described individually. The amount of data has increased greatly from the start in 1981–82. The position of 70 000 icebergs, including 50 000 that had been size classified, were on file at Norsk Polarinstitutt by December 1985, and the data set is growing rapidly. Most ships travelling to and from Antarctica now participate in collection of the data. ( shows the locations of the icebergs sighted.) Fig. 1. Location of iceberg observations under the programme initiated in 1981. Main ship tracks are clearly reflected. The average observation represents 14 icebergs. The size distribution of the classified icebergs observed under this programme up to December 1985 is given in : Table I The “standard size” (length, width, and thickness) is based on our observations from three Antarctic expeditions which carried out dedicated iceberg studies. Many icebergs are of course not right-angled parallelepipedal in shape, but this is a good approximation for most of the larger icebergs. The data are based both on visual sightings and on radar observations. Duplicate observations from a ship moving at slow or zero speed are as far as possible eliminated, both during observation, and by critical appraisal before the data are filed. The data editing also includes evaluation of data quality, especially in connection with radar observations, and comparison of positions and dimensions of the large icebergs in order to reduce to a minimum repeated observations from different vessels of icebergs >1000 m. These account for most of the iceberg mass (see ). Consideration of iceberg-distribution patterns and the observed area of the Southern Ocean, and of duplicate observations, indicates more than 300 000 icebergs south of the Antarctic Convergence, with a total ice mass of about 1016 kg. Consideration of mean residence times indicates an annual iceberg production from the continent of 23–1015 kg, which is considerably higher than most other recent estimates. This also suggests that the Antarctic ice sheet is in balance. The data indicate large regional differences in iceberg sizes, the most noticeable being between the two sides of the Antarctic Peninsula, and between the Amery Ice Shelf/ Prydz Bay area and the remainder of East Antarctica. These differences are probably mainly related to different calving sites. About one-third of the observed icebergs are over the continental shelf of Antarctica. The total under-water area of these icebergs is two orders of magnitude less than the under-water area of the Antarctic ice shelves. The annual total iceberg melting and its effect on the water masses over the continental shelf has been calculated from ocean-water temperature variations at 200 m depth and estimated melt rates. This turns out to be an order of magnitude less than the annual effect of melting sea ice. The iceberg data considered here are probably under-represented with respect to the smallest sizes, and they do not include icebergs that have become <10 m. Inclusion of these ice bodies would increase the total melt.
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi

Motortankskipenes inntog. En komparasjon av utviklingen i dansk, norsk og svensk skipsbyggingsindustri, ca. 1912 til 1933 - Basberg, Bjørn L (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1986)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Sørishavet; historie; hvalbåter; hvalfangstindustri; pelagisk; skipsbyggerier; skipsfart

Kaptein C.A. Larsen: mannen som grunnla den moderne hvalfangsten i Sydishavet - Fagerli, Torkel (Polarboken, 1986)
Keywords: Sørishavet; biografi; historie; hvalfangst

Genetic variation of Euphausia superba Dana in the Antarctic Peninsula waters - Fevolden, Svein Erik (Sarsia, 1986)
Nine samples of Antarctic krill collected at seven localities in the Palmer Archipelago and Bransfield Strait west of the Antarctic Peninsula were analysed for genetic variation at eight enzyme loci. Despite significant among sample heterogeneity in allele frequencies, no convincing evidence was found to support the hypothesis of distinct genetic stocks of Euphausia superba in the investigated area. Allele frequency distributions could not be correlated to regional differences in size patterns. Allelic proportions at the PGI locus did not indicate that the investigated krill was genetically different from E. superba from the Weddell Sea region (from earlier investigations). Deviations of genotypes, or allele frequencies from those expected under Hardy-Weinberg equilibrium, however, may indicate regional, or yearly variation due to occasional selection.
Publisher: Taylor & Francis
Keywords: Sørishavet; Weddellhavet; genetikk; krill; plankton

Oceanographic research during NARE-84/85 - Foldvik, Arne (Filchner-Ronne Ice Shelf Programme. Report, 1986)
Keywords: Sørishavet; oseanografi

Proteases of Antarctic krill—a new system for effective enzymatic debridement of necrotic ulcerations - Hellgren, L.; Mohr, Viggo; Vincent, J. (Experientia, 1986)
The Antarctic krill (Euphausia superba) possesses an ‘over-dimensioned’ digestive system, which is of vital importance for the survival of this euphaucean shrimp in the extreme marine environment. The isolated enzymes contain a well-balanced mixture of both endo- and exopeptidases, assuring fast and complete breakdown of proteinaceous material. These unique properties have now been shown to be extremely valuable for the effective removal of necrotic debris, fibrin or blood crusts in vitro. Therefore the krill enzymes should be considered as an important resource in the future management of necrotic wounds.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

Glaciological research on the Norwegian Antarctic Research Expedition (NARE) 1984/85 - Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1986)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Photoadaptation in Antarctic phytopfankton: variations in growth rate, chemical composition and P versus I curves - Sakshaug, Egil; Holm-Hansen, Osmund (Journal of Plankton Research, 1986)
The response of phytoplankton to variations in the light regime was studied during the VULCAN and ACDA cruises in the Antarctic. Unenriched batch cultures of 12–19 days' duration reached chl concentrations of 10–50 μg−1 and exhibited exponential growth rates, with the maximal rate being 0.41 doubl, day−1. Ice edge algae exhibited maximum growth rates at photon flux densities (PFD) of 30–100 μE m−2S−1 and the growth rate was reduced by about 30% at 500–1000 μE m−2S−1 The chl/C ratio ranged between 0.004 and 0.018, with the lowest ratios at PFDs above 500 μE m−2S−1 chl/C ratios were also below maximum at PFDs below 40–50 μE m−2S−1 The C:N:P ratios were close to the Redfield ratios; the Si/C ratio averaged 0.16 (atoms), and the ATP/C ratio averaged from 0.0024 to 0.0050 in different culture senes. When thawed after having been frozen for 10 days, shade-adapted cultures were in a much better condition than sun-adapted ones. P versus I data showed that the maximum assimilation number varied from 0.75 to 4.4 μg C (μg chl)−1h−1. It varied inversely with the chl/C ratio; therefore the maximum carbon turnover rate varied little between samples (0.024/0.035 h−1). Low biomass communities exhibited relatively high values for α (the initial slope of P versus I curves), low values for 1sat (160–330 μE m−2S−1), and they were susceptible to photoinhibition. In contrast, communities dominated by Odontella weissflogii exhibited low values for α, a high value for Isat (560 μE m−2S−1 and they tolerated high PFDs. The photo-adaptational status of the phytoplankton in natural water samples is discussed relative to the profile of water column stability and mixing processes.
Keywords: Sørishavet; alger; biokjemi; fytoplankton; marin biologi; oseanografi; planteplankton

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Publisher: Cambridge University Press
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Hydrographic observations from the Weddell Sea during the Norwegian Antarctic Research Expedition 1976/77 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; hydrografi; kontinentalsokkel; observasjoner

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

The distribution of lipid in the tissues of Antarctic krill, Euphausia superba - Saether, Olav; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. The distribution of lipid in the tissues of Euphausia superba has been examined by histological and chemical methods. 2. The total lipid content of krill from different catches may vary considerably, and the variations are probably due both to differences in nutritional status and maturity of the roe of female krill. 3. Female krill contained about twice as much lipid as male krill from the same haul. 4. The roe is the dominating lipid depot in female krill; in both male and female krill lipid-rich areas are found along the digestive tract, between muscle bundles and beneath the exoskeleton. 5. Both the phosphoglyceride- and triacylglycerol content of body fractions of E. superba varied in proportion to the total lipid content, thus supporting the contention that both phosphoglycerides and triacylglycerols serve as depot lipids in this species of krill.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Resting spore formation in the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo - Syvertsen, Erik E. (Polar Biology, 1985)
The resting spore morphology of the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo are described. Both species form endogenous resting spores. The spore valve of C. furcatus differ from those of the vegetative cells primarily by (i) a greater convexity and (ii) a coarser and more distinctly fasciculated areolation. This resting spore is identical to the diatom traditionally identified as C. stellaris var. symbolophorus (Grunow) Jørgensen in the Antarctic. The resting spore of T. australis differs from the vegetative cells by (i) a lack of clusters of strutted processes in a modified ring on valve face, (ii) a coarser areolation and tangential rows of areolae and (iii) a narrower and more simply structured girdle. The resting spore valve of T. australis has been described as belonging to a separate species, Actinocyclus excentricus Peragallo.
Keywords: Sørishavet; diatomeer; marinbiologi

Size Frequency Pattern of Euphausia Superba in the Antarctic Peninsula Waters in the Austral Summer of 1983 - Fevolden, Svein Erik; George, Robert Y. (Journal of Crustacean Biology, 1984)
In the austral summer of 1983, schools of krill from Bransfield Strait and Palmer Archipelago were analyzed for composition in terms of size frequencies and maturity stages. Juveniles dominated in all schools, and mature animals never exceeded 6.8% of the animals at any sampling site. Gravid females were encountered in only four out of 15 schools and were never more frequent than 1.8% of the animals in any school. Among subadults and juveniles the largest animals were found on the inside of Palmer Archipelago. Smaller nonreproductive animals were on the outside and in Bransfield Strait. A second group of juveniles, in a size range of 12-15 mm, was more pronounced north of Crocker Passage than south of the Passage. Their potential origin from a more slowly growing and later spawning Southern Weddell Sea population is discussed. Lack of reproductive animals in the Bransfield/South Shetlands vicinity may reflect yearly variation in this region. A hypothesis is put forward on the basis of this study that Palmer Archipelago is a nursery ground for krill spawned elsewhere. The sites of origin of this krill could be ascertained on the basis of studies of enzyme polymorphism in these populations.
Keywords: Sørishavet; Weddellhavet; krepsdyr; krill; marin biologi; plankton

Ti nye år: Vestfold Historielag 60 år - Thoresen, Per (Vestfoldminne, 1984)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; hvalfangst; kulturhistorie; pelagisk

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

The antarctic diatoms Thalassiosira dichotomica (Kozlova) comb. nov. and T. ambigua kozlova - Fryxell, Greta A.; Hasle, Grethe Rytter (Polar Biology, 1983)
Two small antarctic diatoms, usually missed by traditional collection methods, have been studied in light and electron microscopes. Porosira dichotomica has been transferred to Thalassiosira since its valve structure and process pattern agree better with that genus. T. dichotomica is unusual in that some lines of areola walls are extended, sail-like, out from the valve, supporting Kozlova's original drawings. T. ambigua, the smaller of the two, has many similarities in structure with T. dichotomica, but has granules on the margin, lacks the sail-like structures on the valve, and has minor differences in processes and areola size. Bands stay together in T. ambigua and show more fine structure than many species in the genus.
Keywords: Sørishavet; diatomeer; marin biologi; oseanografi

Modelling of antarctic tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
The prediction of the motions of a tabular iceberg in a seaway is a problem which cannot be solved with a simple approach. The main difficulty lies in the size and mass of the iceberg, which produce frequency-dependent hydrodynamical effects as it moves in the water. Specifically, any solution must take into account both the added inertia and the generation of surface waves caused by the motions of the berg. Early attempts at modelling, which did not include these terms, could not accurately predict the complicated response behaviour seen in field data. In this paper we discuss some modifications to a two-dimensional simulation of floating bodies in waves, which must be applied when the motions and the hydro-dynamical pressures beneath tabular icebergs are required.
Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; bølger; glasiologi; isbreer

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

Technological change in the Norwegian whaling industry: A case-study in the use of patent-statistics as a technology indicator - Basberg, Bjørn L (Research Policy, 1982)
This paper presents an example of the use of patent statistics as a technology indicator in one industry. The first part deals with the problem of interpretation. Through examination of several other partial technology indicators, it is concluded that at least in this industry, patent statistics provide a reliable indicator, not only for the timing of inventions, but for the timing of innovations and diffusion as well. The reason is that the intervals between the stages in the innovation process are very short. This contradicts evidence from many other industries, and it is therefore emphasized that generalizations are unwarranted. The second part of this paper deals with the possible causes of technological change in Norwegian whaling. The methodology is inspired by J. Schmookler's work. Thus, the patents are correlated with other indicators of economic development in the industry. But while Schmookler's view is that the patent activity is determined by social demand and economic growth, the conclusions for the Norwegian whaling industry point in the opposite direction: the technological transformation that took place during the 1920s and early 1930s was forced upon the firms in their efforts to cut costs, which was achieved by rationalizing production and catching methods in line with a downward price trend for whale oil.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hvalbåten gjennom 100 år - Devig, Thor N (Vestfoldminne, 1982)
Publisher: Vestfoldmuseene
Keywords: Norge; Sørishavet; Vestfold; båter; hvalfangere; hvalfangstindustri; hvalindustri; lokalhistorie

Vil noen satse formuen på isfjelltauing i Sørishavet? - Orheim, Olav (Polarboken, 1982)
Keywords: Sørishavet; isfjell; logistikk

Present-day glaciation in the South Shetland Islands - Orheim, Olav; Govorukha, Leonid Sergeevich (Annals of Glaciology, 1982)
This paper presents mass-balance results from Deception Island for 1968–69 to 1973–74, from King George Island for the balance years 1969–70 and 1970–71, and from Livingston Island from 1971–72 to 1973–74. The accumulation areas of all localities are in the soaked fades, with a firn/ice transition at King George Island at 12 to 20 m depth. Of the glaciers studied, only “Gl” on Deception Island terminates wholly on land and has a relatively large ablation area. The mass-balance curves are similar for King George Island and Livingston Island, with equilibrium lines at around 150 m elevation. “Gl“ on Deception Island has more negative summer balances, and the equilibrium line ranged from 275 to 370 m during the six balance years. Here, there were no years of positive net mass balance, and large negative net values during the 1970–71 to 1972–73 balance years. This resulted from a lowered albedo caused by ash from the August 1970 eruption. Ash layers from the Deception Island eruptions are also observed on Livingston Island and King George Island, where they form stratigraphic markers in the accumulation areas of the glaciers. Annual balance variations from 1957–58 to 1970–71, based on stratigraphic studies at Deception Island and King George Island, show good correlations, indicating that the variations reflect changes in regional climate.
Keywords: Sørishavet; glasiologi

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

Iceberg response to sea state (abstract only) - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Annals of Glaciology, 1982)
Keywords: Sørishavet; glasiologi

Krill: mat i mengder i Sørishavet - Sakshaug, Egil (Syn og segn, 1982)
Keywords: Sørishavet; krill; marinbiologi

Evidence for a late Wisconsin glaciation of the Weddell Sea - Elverhøi, Anders (Nature, 1981)
Keywords: Sørishavet; Weddellhavet; forskning; glasiologi; sedimentologi; stratigrafi

Glaciomarine sediments and suspended particulate matter, Weddell sea, Antarctica (abstract only) - Elverhøi, Anders; Roaldset, Elen (Annals of Glaciology, 1981)
Samples of glaciomarine sediments and suspended particulate matter filtered from sea-water were collected in the Weddell Sea during the Norwegian Antarctic Research Expedition (NARE) in 1978–79. Analyses have provided information on the textural and mineralogical composition of shelf sediments, on the nature of biogenic and inorganic suspended particulate matter, and on the total sediment transport to the shelf areas and further into the deeper waters (). The shelf waters contain 0.1 to 1.2 g m–3 of suspended particulate matter, which is close to the range of 0.5 to 1.5 g m–3 reported for suspension concentrations in the oceans, but considerably lower than that found for some other glaciomarine environments such as the Bering Sea {}up to 13-15 g m–3 ()) and off Kongsbreen, Spitsbergen {}up to 500 g m–3 ()). Suspended particles from the Weddell Sea have maximum sizes of 50 to 70 µm and mean diameters in the range of 10 to 20 µm. In contrast, the bottom sediments on the outer shelf are deficient in the corresponding fractions. This reflects that when floating Antarctic ice supplies material to the Weddell Sea, the coarser fragments (>20-70 µm) are deposited, while the medium silt and finer fractions go into suspension. Considering the suspended-load data and the bottom-current measurements on the shelf break, it is evident that in January 1979 an average of 8.6 × 104tonnes d–1 (or 32 × 106 tonnes a–l) of particulate matter was transported by the current from the central Weddell Sea to the South Atlantic deep water. Morphological (scanning electron microscopy) and chemical analyses show the suspended material to be dominated by silica organisms (diatoms), and also to contain clastic grains of phyllosilicates, feldspar, quartz, zircon, in a few cases Al- and Fe-hydroxides/oxides also; authigenic “Fe-sepiolite” and secondary gypsum. Mineralogical analyses (X-ray diffraction) of the bottom sediments show the fine sand silt fractions to contain mainly clastic materials like illite, smectite-vermiculite, and quartz. Biogenic silica (cristobalite) and carbonate (Mg-calcite) as well as authigenic Fe-silicates (“Fe-sepiolite”) are also present.
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi; sedimenter

Enzyme polymorphism in Antarctic krill (Euphausiacea); genetic variation between populations and species - Fevolden, Svein Erik; Ayala, Fransisco J. (Sarsia, 1981)
By means of enzyme electrophoretical assays three samples of Euphausia superba, all from the Atlantic sector of the Antarctic Ocean, were examined to see whether or not they represent genetically separated populations. The same samples were also compared with E. superba from off the Western coast of the Antarctic Peninsula, representing the Pacific sector. The latter animals have previously been studied by other authors. One sample of a second species of Antarctic krill, E. crystallorophias, was likewise examined. Thirty-five loci were studied in E. superba, and it is concluded that the three samples from the Atlantic sector most probably do not represent reproductively isolated populations. Their average heterozygosity, about 10%, is however greater than the value previously found for the ‘Pacific’ E. superba, 5.8 %. Calculations of the genetic identity and genetic distance between the Atlantic and ‘Pacific’ samples of E. superba suggest they represent separate populations. The average heterozygosity of E. crystallorophias was estimated to be between 9.1 and 9.4 %, from studies of 33 loci. The genetic distance between this species and E. superba was estimated at 0.989. The results are finally discussed in terms of postulated theories on genetic variability versus environmental heterogeneity.
Publisher: Taylor & Francis
Keywords: NARE 1976/77; NARE 1978/79; Sørishavet; genetikk; krill; marin biologi; plankton

Bacteriologigal characteristics of Antarctic krill (Crustacea, Euphausiacea) - Fevolden, Svein Erik; Eidså, Gudmunn (Sarsia, 1981)
The bacterial flora of two species of Antarctic krill, Euphausia superba Dana and E. crystallorophias Holt & Tattersall, was studied with the aim of investigating the role played by bacteria during the claimed rapid deterioration of these animals. The number of bacteria on fresh krill was characterized as low, but started to increase exponentially after a few days of storage at low temperatures. Dominant species were of the genera Moraxella, Pseudomonas, and Alteromonas. Comparing the low initial number of bacteria with the high autolytic activity it is suggested that the rapid degradation of krill during the first days of storage is induced by autolysis and not by bacterial activity.
Publisher: Taylor & Francis
Keywords: Sørishavet; biokjemi; krill; lyskreps; marin biologi; plankton

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

Field experiments on Antarctic tabular icebergs - Kristensen, Monica; Orheim, Olav; Wadhams, Peter (Polar Record, 1981)
Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi; is; isfjell; isshelf; kalv; kalving

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Blåhvalen, kan de reddes? - Smelror, Morten (Naturen, 1981)
Keywords: Sørishavet; hvaler; hvalfangst

Hvalfangerne forteller. Innsammlig av hvalfangstens tradisjonsmateriale i Vestfold - Wexelsen, Einar; Devig, Thor N (Vestfoldminne, 1981)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; erindringer; historie; hvalfangere; hvalfangst; hvalfangstnæring; pelagisk

A note on Norwegian observations of whales in the Antarctic - Fevolden, Svein Erik (Report of the International Whaling Commission, 1980)
Keywords: Sørishavet; hvaler; zoologi

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Measurements of oscillations and flexure of icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; havis; is; isbreer

Measurements of the radiation temperature of Antarctic icebergs and the surrounding surface water - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; ekspedisjoner; glasiologi; havis; is; isbreer

Physical characteristics and life expectancy of tabular Antarctic icebergs - Orheim, Olav (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; isfjell; isfront; isshelf; kalving; stratigrafi

Some satellite tracked iceberg drifts in the Antarctic - Vinje, Torgny E (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; oseanografi; sjøis; vannmasser

A new process for the utilization of Antarctic krill - Ellingsen, Trond E.; Mohr, Viggo (Process Biochemistry, 1979)
Keywords: NARE 1976/77; Sørishavet; biokjemi; krill; lyskreps; marinbiologi; plankton

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Publisher: Taylor & Francis
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

The genus Thalassiosira: species with internal extensions of the strutted processes - Fryxell, Greta A; Hasle, Grethe Rytter (Phycologia, 1979)
Publisher: Taylor & Francis
Keywords: Sørishavet; diatomeer; marinbiologi; oseanografi

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and icebergs - Gade, Herman G. (Journal of Physical Oceanography, 1979)
Steady-state conditions are assumed to exist everywhere in the case of melting of the underside of an infinite slab of ice floating in sea water. Basic transfer equations for heat and salt are established and solutions derived for the interior corresponding to given far field values of the temperature and salinity of the water. The solutions are discussed in the T-S diagram where the behavior is particularly simple. Determining parameters are the characteristic velocities ks/d and Ks/h, where ks and Ks are the molecular and turbulent diffusivities, respectively, of salt, d and h the thicknesses of the corresponding laminar and turbulent layers. Also the nonmelting/nonfreezing case is discussed and the determining parameter established. Application of the theory to the Ross Ice Shelf (Little America V) gives acceptable results with d = 2 × 10−3 m and Ks = 20 −30 × 10−4 m2 s−1. Analysis of the static stability of the melt water mixtures reveals that with ambient temperatures approaching 17°C, the stratification becomes unstable. Icebergs brought to tropical waters will cause melt water mixtures to intrude at subsurface levels. Finally, convection obtained in laboratory experiments with melting ice in sea water is reported to be in concordance with the theoretically derived stability criterion.
Keywords: Sørishavet; geofysikk; glasiologi; hydrologi; oseanografi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Publisher: Cambridge University Press
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

Fluoride in Antarctic Krill (Euphausia superba) and Atlantic Krill (Meganyctiphanes norvegica) - Soevik, Torleif; Braekkan, Olaf R. (Journal of the Fisheries Research Board of Canada, 1979)
Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F−/kg fat free dry matter, compared with 570 and 750 mg F−/kg in raw and boiled muscle. Biological availability was measured in a chick assay, and showed fluoride in krill to be equally utilized as sodium fluoride added to the diet. Key words: krill, red feed, deep sea prawn, fluoride.
Keywords: Sørishavet; biokjemi; forurensning; krill; marin biologi; miljøgifter; plankton

De norske Antarktis-ekspedisjonene 1976-77 og 1978-79: biologiske undersøkelser på Bouvetøya og i havet - Sømme, Lauritz; Fevolden, Svein Erik (Det norske videnskaps-akademi. Årbok, 1979)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biologi; geografi

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Seismikk i Weddellhavet - Haugland, Kristen (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

Om Antarktis, isfjell og havnivå - Maisey, George H (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; geologi; havbunnen; topografi

Biota of the antarctic pack ice: R/V Hero cruise 77-5 - Siniff, D.; Laws, R.; Oritsland, T.; Stirling, I.; Bengtson, J.; Demaster, D.; Reichle, R. (Antarctic Journal of the United States, 1978)
Between 22 October and 20 November 1977, we used National Science Foundation's R/v Hero to conduct studies of Antarctic seals in pack-ice areas of the Antarctic Peninsula. Our principal focus was on crabeater seals, but we also were interested in other pack-ice species, particularly leopard seals. Our work centered on (a) collecting female crabeater and leopard seals for reproductive material depicting various stages of the reproductive cycle, (b) documenting further the social structure and reproductive behavior of crabeater seals, (c) observing daily activity patterns and local movements of crabeater seals at fast-ice concentrations, and (d) investigating crabeater seal behavior at weaning and their interaction with leopard seals.
Keywords: Antarktis; Sørishavet; marin biologi; seler

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

Meteorologiske observasjoner på antarktisekspedisjonen 1978/79 - Vinje, Torgny E. (Været: populærvitenskapelig tidsskrift, 1978)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; meteorologi

The biogeography of some marine planktonic diatoms - Hasle, Grethe Rytter (Deep Sea Research and Oceanographic Abstracts, 1976)
Keywords: Sørishavet; biogeografi; ekspedisjoner; forskning; fytoplankton; marinbiologi; plankton; planteplankton

Smia på Fevang - Thoresen, Per (Vestfoldminne, 1976)
Publisher: Vestfoldmuseene
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangere; hvalfangst; pelagisk

Conditional instability of sea water at the freezing point - Foldvik, Arne; Kvinge, Thor (Deep Sea Research and Oceanographic Abstracts, 1974)
Keywords: AABW; Sørishavet; bunnvannet; havis; oseanografi; sjøis; sjøvann

Teori om internasjonale forhandlinger: Forhandlingene 1958-59 om kvoteregulering av hvalfangsten i Antarktis - Midgaard, Knut (Internasjonal politikk, 1974)
Keywords: Norge; Sørishavet; hvalfangstkvoter; internasjonal politikk; pelagisk hvalfangst

Retrieval of current meters and study of thermohaline convection in the Weddell Sea - Bø, Redair; Foldvik, Arne; Kvinge, Thor (Antarctic Journal of the United States, 1973)
Keywords: Sørishavet; Weddellhavet; geofysikk; oseanografi

Bergens deltakelse i den moderne hvalfangst - Tønnessen, Johan Nicolay (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1973)
Publisher: Stiftelsen Bergens sjøfartsmuseum Place: Bergen
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; skipsfart

Hvalfangstens historie - Tønnessen, Johan Nicolay; Solhaug, Trygve (Historisk tidsskrift, 1973)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

Deception: Sydpollandets aktive vulkan - Orheim, Olav (Polarboken, 1972)
Keywords: Sørishavet; geofysikk

Joh. N. Tønnessen: Den moderne hvalfangst historie. Opprinelse og utvikling. Bind 2-4. Utgitt av Norges hvalfangstforbund, Sandefjord 1967, 1969, 1970. - Solhaug, Trygve (Historisk tidsskrift, 1972)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; bokanmeldelser; historie; hvalfangst; pelagisk

En reise til Sydpolskontinentet "Antarktis" (Polarposten, 1971)
Keywords: Antarktis; Sørishavet; turisme

Diatoms: Cleaning and Mounting for Light and Electron Microscopy - Hasle, Grethe R; Fryxell, Greta A (Transactions of the American Microscopical Society, 1970)
Publisher: [American Microscopical Society, Wiley]
Keywords: Sørishavet; Weddellhavet; diatomeer; marinbiologi; oseanografi

Norwegian pelagic sealing reconnaissance in the Scotia Sea, 1964 - Øritsland, Torger (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Norwegian Antarctic whaling, 1905–68: an historical appraisal - Tønnessen, Johan Nicolay (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Norge; Sørishavet; historikk; hvalfangst; hvalfangstkvoten

"Cutty Shark" i hvalfangsten tjeneste - Berg, Knut (Årbok. Sandefjord bymuseum, 1969)
Publisher: Sandefjord bymuseum Place: Sandefjord
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

"Forlandet" ex "Femern" ex "Foca" - Knap, Johan (Årbok. Sandefjord bymuseum, 1969)
Publisher: Sandefjord bymuseum Place: Sandefjord
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

The distribution of zooplankton in the southern ocean and its dependence on the circulation of water - Voronina, N. M. (Sarsia, 1968)
The distribution of zooplankton in the Southern Ocean depends on seasonal changes in quantity and on redistribution of the plankton by currents. In the upper 100 m the meridianal component of the current shifts the maxima of some species northwards from the divergence zone at a mean velocity of about 20 cm/sec. In the Antarctic convergence zone the water sinks at a mean velocity of 10.5 m/day. This brings about an increase of the total plankton amounting to about 3% per day. As the southward flow of deep water is very slow the transfer of plankton in this layer is negligible.
Publisher: Taylor & Francis
Keywords: Sørishavet; marin biologi; oseanografi; plankton

Ny øy ved Deception (Polarboken, 1968)
Keywords: Sørishavet; geofysikk

Erobringen av Antarktis. Spredte glimt fra hvalfangstens historie - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1968)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk

Morphology and distribution of the marine centric diatom Thalassiosira antarctica Comber - Hasle, Grethe R; Heimdal, Berit R (Journal of the Royal Microscopical Society, 1968)
Keywords: Sørishavet; diatomeer; fytoplankton; marinbiologi; plankton

Estimates of local seal populations in the Antarctic, 1930/37 - Mackintosh, N A (Norsk hvalfangst-tidende, 1967)
Keywords: Sørishavet; seler; zoologi

International co-operation in Antarctic whale marking 1960 to 1965 - Brown, S G (Norsk hvalfangst-tidende, 1966)
Keywords: Sørishavet; hvaler; hvalfangst

The swarming of krill and problems of estimating the standing stock - Mackintosh, N A (Norsk hvalfangst-tidende, 1966)
Keywords: Sørishavet; krepsdyr; krill; marinbiologi

Discovery II in the Antarctic - Tønnessen, Johan Nicolay (Norsk hvalfangst-tidende, 1965)
Keywords: Sørishavet; historie; hvalfangst

"Pelagos" ex "Athenic" - Berg, Knut (Vestfold-minne, 1964)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; historie; hvalbåter; hvalfangerflåte; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Folketro på hvalfangst - Eriksen, Erling (Vestfold-minne, 1964)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; erindringer; fortellinger; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Antarctic fin whales with exceptionally long baleen plates - Jonsgård, Åge (Norsk hvalfangst-tidende, 1964)
Keywords: Sørishavet; hvaler; marin biologi

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Publisher: Vestfold historielag
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Internasjonalt samarbeide i antarktisk hvalmerking fra 1957 til 1960, og en oversikt over spredningen av merkede hval i Antarktis - Brown, S G (Norsk hvalfangst-tidende, 1962)
Keywords: Sørishavet; hvaler; hvalfangst

Lys over "tåkeheimen" i sør: den videnskapelige serie fra Lars Christensens ekspedisjoner avlsuttet - Isachsen, Fridtjov (Norsk hvalfangst-tidende, 1962)
Keywords: Antarktis; Sørishavet; forskning; litteratur; naturvitenskap; vitenskap

Tre funn av sverd fra sverdfisk (Xiphias gladius) i antarktisk finnhval (Balenoptera physalus (L)) - Jonsgård, Åge (Norsk hvalfangst-tidende, 1962)
Keywords: Sørishavet; hvaler; marinbiologi; zoologi

Sjøpattedyr observert av det sovjetiske vitenskapsakademis ekspedisjon rundt jorden i 1957/58 - Zenkovich, B A (Norsk hvalfangst-tidende, 1962)
Keywords: Sørishavet; hvaler; marinbiologi

Tønsbergs sjøfart gjennom 100 år - Eriksen, Erling (Vestfoldminne, 1961)
Publisher: Vestfoldmuseene
Keywords: Sørishavet; Vestfold; historie; hvalfangstindustri; hvalkokerier; pelagisk; skipsbyggerier

To slags minkehval i Antarktis = Two kinds of minke whale in the Antarctic - Williamson, Gordon R (Norsk hvalfangst-tidende, 1961)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi

Litt om hvalfangsten i Antarktis og dens framtid (bygget på Norsk hvalfangst-tidende) (Polarboken, 1960)
Keywords: Sørishavet; hvalfangst

Gjenfundne hvalmerker i den antarktiske fangstsesong 1959/60 = Whale marks recovered in the Antarctic whaling season 1959/60 - Brown, S G (Norsk hvalfangst-tidende, 1960)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Norsk hvalfangst: hovedtrekk i utviklingen - Eckstrøm, Kåre (Sosialøkonomen, 1960)
Keywords: Sørishavet; historie; hvalfangst

Hvalfangsten og Vestfold - Hasvoll, Bertold (Sosialøkonomen, 1960)
Keywords: Sørishavet; hvalfangst

Kvotefordeling og inspeksjonsordning norske krav i hvalfangstrpolitikken: nøytrale vitenskapsmenn undersøker fangstgrunnlaget - Jahn, Gunnar (Sosialøkonomen, 1960)
Keywords: Sørishavet; hvalfangst; politikk

Ynglende pelssel på Syd-Orknøyene = Fur seals breeding in the South Orkney Islands - Øritsland, Torger (Norsk hvalfangst-tidende, 1960)
Keywords: Sørishavet; pattedyr; seler; zoologi

Skipbrudd i Sydhavet - Borge, Johannes (Kystvakt, 1959)
Keywords: Sørishavet; ekspedisjoner; historie

Gjenfundne hvalmerker i sesongene 1955/56 og 1958/59 i Antarktis og i Syd-Afrika i 1958 og 1959 = Whale marks recovered in the Antarctic seasons 1955/56, 1958/59, and in South Africa 1958 and 1959 - Brown, S G (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Spermhvalens forekomst i Sydishavet og månens eventuelle innflytelse på forekomstene = Occurrence of the sperm whale in the Antarctic and the possible influence of the moon - Holm, John L; Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nytt funn av sverd fra sverdfisk (Xiphias gladius) i blåhval (Balaenoptera musculus) i Sydishavet = New find of sword from swordfish (Xiphias gladius) in blue whale (Balaenoptera musculus in Antarctic - Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; fisker; hvaler; marin zoologi; zoologi

Et hvalfangerbrev - Larsen, Tryggen (Magasinet for alle, 1959)
Keywords: Sørishavet; hvalfangst

Hvalmerking utført av norske hvalbåter i Antarktis i sesongene 1956/57 og 1957/58 : whale marking carried out by Norwegian catchers in the Antarctic, seasons 1956/57 and 1957/58 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvalfangst; marin zoologi

Gjenfunne hvalmerker i den antarktiske sesong 1957/58 = Whale marks recovered during the Antarctic whaling season 1957/58 - Brown, S G (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

En lege på hvalfangst - Martens, Odd (Polarboken, 1958)
Keywords: Sørishavet; hvalfangst; medisin

Some corrections to: Hans Bogen. Main events in the history of Antarctic exploration - Richter, Søren (Norsk hvalfangst-tidende, 1958)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; litteratur

Undersøkelser av knølhvalen (Megaptera nodosa) i Bellingshausenhavet = Studies on the humpback whale (Megaptera nodosa) in the Bellingshausen Sea - Symons, H W; Weston, R D (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi

Hvalfangsten i Antarktis 1956-57; en orientering (Polarboken, 1957)
Keywords: Sørishavet; hvalfangst

Gjenfunne hvalmerker i Antarktis i sesongen 1956/57 = Whale marks recovered during the Antarctic whaling season 1956/57 - Brown, S G (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Er det ønskelig og forsvarlig å utvide sesongen for fangst av knøl i Sydishavet? = Is it desirable and justified to extend the open season for humpback whaling in the Antarctic? - Jonsgård, Åge; Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; marinbiologi

Norsk kartleggingsarbeid i Antarktis: kaptein H.E. Hansen fyller 70 år = Norwegian mapping in the Antarctic: captain H.E. Hansen reaches his 70th birthday - Ruud, Johan T (Norsk hvalfangst-tidende, 1957)
Keywords: Antarktis; Sørishavet; biografi; historie; kartlegging

Rapport om hvalmerking utført av norske hvalbåter i Antarktis i sesongen 1955/56 = Report on whale marking carried out by Norwegian catchers in the Antarctic season 1955/56 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

En underbeskattet knølhvalbestand? = An underfished humpback population? - Symons, H W; Weston, R D (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marinbiologi

Hvalfangsten i Antarktis sesongen 1955-56 (Polarboken, 1956)
Keywords: Sørishavet; hvalfangst

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ash, C E (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nylig gjenfunne hvalmerker = Whale marks recently discovered - Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvaler; marin zoologi

Phytoplankton and Hydrography of the Pacific Part of the Antarctic Ocean - Hasle, Grethe Rytter (Nature, 1956)
Keywords: Sørishavet; fytoplankton; hydrografi

Foreløpige beregninger av den sydlige bestand av store bardehval = Preliminary estimates of the southern populations of the larger baleen whales - Mackintosh, N A; Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Euphasia superba og de antarktiske overflatestrømmer: en foreløpig meddelelse om hvalfødens utbredelse - Marr, James William Slessor (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; krill; marin biologi

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ottestad, Per (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Internasjonal regulering av hvalfangsten: et tilbakeblikk og en vurdering - Ruud, Johan T (Samtiden, 1956)
Keywords: Sørishavet; forvaltning; historie; hvalfangst; politikk

Vet vi noe om bestanden av finnhval i Sydishavet? = Do we know anything about the stocks of fin whales in the Antarctic? - Ruud, Johan T (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Hvalkokeriet i arbeid: en populær orientering - Sundt, H (Polarboken, 1956)
Keywords: Sørishavet; hvalfangst

Om størrelsen på den antarktiske finnhvalbestand sett i relasjon til fangstens størrelse = On the size of the Antarctic fin whale stock relative to the size of the catch - Symons, H W; Mackintosh, N A; Brown, S G; Salvesen, H K (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Beregninger av den sydlige bestand av store bardehval = Estimates of the southern populations of the larger baleen whales - Vangstein, Einar (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; marin zoologi

Hvalfangst og lægearbeid - Albretsen, C S R (Tidsskrift for den Norske Laegeforening, 1955)
Keywords: Sørishavet; hvalfangere; hvalfangst; medisin

Den internasjonale regulering av hvalfangsten - Eckstrøm, Kåre (Polarboken, 1955)
Keywords: Sørishavet; hvalfangst; jus

Nylig gjenfunne hvalmerker = Whale marks recently recovered - Mackintosh, N A (Norsk hvalfangst-tidende, 1955)
Keywords: Sørishavet; hvaler; marin zoologi

Hvalfangsten i Antarktis i sesongen 1954-55 - Østbye, Harald (Polarboken, 1955)
Keywords: Sørishavet; hvalfangst

Sør i Norge, sør i isen: sagaen om en hvalfangerslekt - Torkildsen, Torbjørn (Polarboken, 1955)
Keywords: Sørishavet; biografi; hvalfangst

Finn- og blåhvalenes trekk i Antarktis = The movements of fin and blue whales in Antarctic waters - Brown, S G (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; hvaler; marin zoologi

Internasjonalt samarbeid i hvalmerking : "Enern"s tokt til Sydishavet i 1953 : the voyage of the "Enern" to the Antarctic 1953 = International co-operation in whale marking - Clarke, Robert; Ruud, Johan T (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; ekspedisjoner; hvalbestanden; hvalfangst

Internasjonalt samarbeid i hvalmerking : Annen del av "Enern"s tokt til Sydishavet 1953 og forsøk med hvalmerker utført på flytende kokerier sesongen 1954 : The second period of the voyage of the "Enern" to the Antarctic 1953 and trials with whale marks conducted on board floating factories in the season 1954 = International co-operation in whale marking - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; ekspedisjoner; hvalbestanden; hvalfangst

Tidal currents off the antarctic ice barrier, Queen Maud Land - Sverdrup, Harald Ulrik (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1954)
Observations of tidal currents in lat. 71° 01′ S, long. 10° 55′ W indicate that a semi-diurnal tidal wave progresses towards the WSW, that is, parallel to the main direction of the barrier. ForM2 the cotidal hour appears to be about 7h, in good agreement with the value 6.7h, that is derived from observations of the atmospheric pressure. Furthermore, the current measurements indicate that the ratio(K1+O1)/(M2+S2) is large, perhaps as large as 2.5.
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; havstrømmer; klimaendringer; meteorologi; oseanografi; tidevann

Verdien av de meteorologiske observasjoner fra hvalkokeriene = The value of meteorological observations from whaling factory ships - Vowinckel, E (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; klima; meteorologi; observasjoner

Finnhval (Balaenoptera physalus) med 6 fostre = Fin whale (Balaenoptera physalus) with six foetuses - Jonsgård, Åge (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; marin zoologi

Fra Den internasjonale hvalfangstkommisjons 5. årsmøte i London iår - Lie, Just (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst; politikk

From The International Whaling Commission's fifth annual meeting in London this year - Lie, Just (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst

Hvalfangstsesongen i Antarktik i 1952-53 - Østbye, Harald (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst

The Antarctic whaling season 1952-53 - Østbye, Harald (Polar-årboken, 1953)
Keywords: Sørishavet; hvalfangst

Finnes det et fredningsfelt for bardehval i Antarktis? = Does there exist a sanctuary for baleen whales in the Antarctic? - Schubert, Kurt (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

On Conditions for the Vernal Blooming of Phytoplankton - Sverdrup, Harald Ulrik (ICES Journal of Marine Science, 1953)
Keywords: Sørishavet; forskning; oseanografi; planteplankton

Nylig gjenfundne hvalmerker = Whale marks recently recovered (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; hvaler; marin zoologi

Whale catching in the Antarctic season 1951/52 - Østbye, Harald (Norsk polar-tidende, 1952)
Keywords: Sørishavet; hvalfangst

Modern whaling and its prospects - Ruud, Johan T (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; forvaltning; hvaler; hvalfangst

Meteorologiske observasjoner på norske hvalkokerier = Meteorological observations on Norwegian factory ships - Sverdrup, Harald Ulrik (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; meteorologi

Nye hvalfangstekspedisjoner = New whaling expeditions (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst

The International Whaling Commission møtes i Cape Town (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst

Omkring konsesjonsordningen for den pelagiske hvalfangst = Concession arrangement for pelagic whaling - Knudtzon, Hans Thomas (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst; jus

Whale catching in the Antarctic season 1950/51 - Østbye, Harald (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst

Norsk-britisk-svensk vitenskapelig ekspedisjon til Antarktis 1949/52. 4 = Norwegian-British-Swedish scientific expedition to the Antarctic 1949/52. 4 - Sverdrup, Harald Ulrik (Norsk hvalfangst-tidende, 1951)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; fly; kartlegging

Det italienske hvalselskap og Howaldtswerke - Westphal, Adolf (Norsk polar-tidende, 1951)
Keywords: Sørishavet; hvalfangst; politikk

Norsk hvalfangstpolitikk i etterkrigsårene - Knudtzon, Hans Thomas (Polar-årboken, 1950)
Keywords: Sørishavet; hvalfangst; politikk

Summary of preceding article about the Norwegian whaling policy after the war - Knudtzon, Hans Thomas (Polar-årboken, 1950)
Keywords: Sørishavet; hvalfangst; politikk

Blod, svette og tårer - Orud, Hilmar (Magasinet for alle, 1950)
Keywords: Sørishavet; hvalfangst

The Antarctic whaling season 1949/50 - Østbye, Harald (Polar-årboken, 1950)
Keywords: Sørishavet; hvalfangst

Undersøkelser over blåhvalens alder i de antarktiske pelagiske fangster 1945/46 - 1948/49 = Investigations of the age of the blue whales in the Antarctic pelagic catches 1945/46 - 1948/49 - Ruud, Johan T (Norsk hvalfangst-tidende, 1950)
Keywords: Sørishavet; hvaler; marin zoologi

Norsk-britisk-svensk vitenskapelig ekspedisjon til Antarktis 1949/52. 2 = Norwegian-British-Swedish scientific expedition to the Antarctic 1949/52. 2 - Sverdrup, Harald Ulrik (Norsk hvalfangst-tidende, 1950)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; logistikk

Kort oversikt over den norske pelagiske hvalfangst 1939-1949 - Bogen, Hans (Liv og virke ved polene : polarboken 1949, 1949)
Publisher: Norsk polarklubb Place: Oslo
Keywords: Sørishavet; historie; hvalfangst

Elektrisk hvaldreping - Brøther, Dagfinn (Teknisk ukeblad : Norges fremste på teknologi, 1948)
Keywords: Sørishavet; historie; hvalfangst; hvalfangstnæring; pelagisk; teknologi

"Brategg"-ekspedisjonen = The "Brategg" expedition - Holgersen, Holger (Norsk hvalfangst-tidende, 1948)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ornitologi; oseanografi

Die "Brategg"-Expedition - Schubert, Kurt (Polarforschung, 1948)
Keywords: Peter I. Øy; Sørishavet; ekspedisjoner; geofysikk

"Brategg"-ekspedisjonen 1947-48 = The "Brategg" expedition 1947-48 (Norsk hvalfangst-tidende, 1947)
Keywords: Sørishavet; ekspedisjoner; forskning

Hvalbåt forlist i Antarktik = Catching boat wrecked in the Antarctic (Norsk hvalfangst-tidende, 1947)
Keywords: Sørishavet; forlis; hvalfangst

Vestfold og hvalfangsten - Bogen, Hans (Årbok for Den norske turistforening, 1947)
Keywords: Sørishavet; historie; hvalfangst; økonomi

The Falkland Islands Dependencies Survey, 1943-46 - Wordie, James Mann (Norsk hvalfangst-tidende, 1947)
Keywords: Antarktis; Sørishavet; ekspedisjoner; forskning; kartlegging; logistikk

Historien om Antarktis (Norsk hvalfangst-tidende, 1945)
Keywords: Antarktis; Sørishavet; historie; hvalfangst; litteratur; selfangst

Hvalfangerne drar sørpå igjen: 2.000-2.500 norske hvalfangere engasjert (Polar-årboken, 1945)
Keywords: Sørishavet; hvalfangst

Da hvalfangerne lurte tyskerne i Sydishavet: en god skrøne - Andersen, Ottar (Polar-årboken, 1945)
Keywords: Sørishavet; hvalfangst

Tyskernes sjørøveri i Sydishavet: hvalskytter Finn Bryde forteller - Arnesen, Odd (Polar-årboken, 1945)
Keywords: Sørishavet; hvalfangst

Vår ishavsflåte og selfangsten : ishavsskutenes innsats i arktisk og antarktisk forskning - Hansen, Rolf (Vår Flåte, 1944)
Keywords: Sørishavet; ekspedisjoner; forskning; polarområdene; selfangst

De første norske oppdagelser i Sørishavet - Aagaard, Bjarne (Nordmannsforbundet, 1943)
Keywords: Carl Anton Larsen; Sørishavet; ekspedisjoner; oppdagelsesreiser

Hvalrådets skrifter no.20: scientific results of marine biological reseqarch - Bergersen, Birger; Lie, J; Ruud, Johan T (Norsk hvalfangst-tidende, 1940)
Keywords: Sørishavet; forskning; hvaler; hvalfangst; marin zoologi

Hvalfangsten og fettindustrien: norsk hvalolje for 1320 millioner kroner i årene 1920-1939 - Bruun, Svend Foyn (Polar-årboken, 1940)
Keywords: Sørishavet; hvalfangst

Några drag av den antarktiska kontinentens biologiska historia - Skottsberg, Carl (Det Kongelige norske videnskabers selskab. Forhandlinger, 1940)
Keywords: Antarktis; Sørishavet; biologi; botanikk; evolusjon; paleogeografi

De norske opdagelser i Sydishavet: fra C. A. Larsens tid til Christensens ekspedisjon 1937 - Aagaard, Bjarne (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; hvalfangst; oppdagelsesreiser

Farve og form på hvalfeltet - Finne, Henrik (Polar-årboken, 1939)
Keywords: Sørishavet; hvalfangst; kunst

Japan vil overta hegemoniet i hvalfangsten! - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Sørishavet; hvalfangst; politikk; økonomi

Sydhavssesongen 1938-39 - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Sørishavet; hvalfangst

Til Sydishavet på jakt efter storhvalen - Slaattelid, Aasm. (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; sjøfolk

Ny banke i Antarktis (Polar-årboken, 1938)
Keywords: Sørishavet; kartlegging

Små notater om de "menige" hvalfangere fra 1905-1930 - Bogen, Hans (Polar-årboken, 1938)
Keywords: Sørishavet; hvalfangst

Om hvalfangstens naturgrunnlag - Ruud, Johan T (Naturen, 1938)
Keywords: Sørishavet; hvaler; marinbiologi; zoologi

Hvalfangsten: et tilbakeblikk og en oversikt på grunnlag av norske patenter - Swensen, T (Teknisk ukeblad : Norges fremste på teknologi, 1938)
Keywords: Sørishavet; hvalfangst; patenter; pelagisk; teknologi

Hvalfangst-kunsten og nordmennene (Polar-årboken, 1937)
Keywords: Sørishavet; hvalfangst; politikk

Moderniseringen av vår hvalfangstflåte: et viktig ledd i en rasjonell utnyttelse av hvalen - Christensen, Chr. Fred. (Polar-årboken, 1937)
Keywords: Sørishavet; hvalfangst; logistikk

The Story of Whaling - Hjort, Johan (The Scientific Monthly, 1937)
Publisher: American Association for the Advancement of Science
Keywords: Sørishavet; historie; hvalfangst

Ekspansjonen i hvalfangsten. Hvaloljeprisen. - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Lars Christensen; Sørishavet; hvalfangere; hvalfangstindustri; hvalindustri; hvalolje; pelagisk

Hjemkomsten. Hvlafangsten historie fra dens første begynnelse - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Blåhvalungen legger på sig 100 kg. i døgnet - Ruud, Johan T (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; blåhval; hvalfangst; paleontologi; pelagisk; zoologi

En arbeidsnatt ombord i et hvalkokeri - Slaattelid, Aasm. (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangere; hvalfangst; pelagisk; sjøfolk

Elektrisk hvalskytning - Weber, Albert (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Publisher: Hvalfangstliv Place: Tønsberg
Keywords: Sørishavet; hvalfangst; pelagisk; teknologi

Er vi nordmenn uundværlige i hvalfangsten? (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Publisher: Aschehoug
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Omkring navngivningen i hvalfangstflåten - Bogen, Hans (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst; logistikk

Over 400 000 hval og 1500 millioner kroner i løpet av 30 år, men hvor lenge vil det vare nu? - Bogen, Hans (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst

Norske ekspedisjoners virksomhet i Antarktis - Paulsen, Harald B (Polar-årboken, 1936)
Keywords: Antarktis; Sørishavet; kartlegging

Hvor tusener nordmenn henter sitt utkomme: daglig liv på fangstfeltet i Sydishavet - Romnæs, Nils (Polar-årboken, 1936)
Keywords: Sørishavet; hvalfangst

Blåhval - Ruud, Johan T (Kvalitet, 1936)
Keywords: Sørishavet; hval; hvalfangst

Fangstsesongen i Sydhavet 1933-34 (Norsk hvalfangst-tidende, 1935)
Keywords: Sørishavet; hvalfangst

Hvalfangstens aristokrati - Bogen, Hans (Polar-årboken, 1935)
Keywords: Sørishavet; hvalfangst

Human Activities and the Study of Life in the Sea: An Essay on Methods of Research and Experiment - Hjort, Johan (Geographical Review, 1935)
Publisher: [American Geographical Society, Wiley]
Keywords: Sørishavet; historie; hvalfangst

Fra »Norvegia« - Ekspedisjonene. Noen meteorologiske og oceanografiske resultater - Mosby, Hakon (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Publisher: Routledge
Keywords: Norvegia ekspedisjoner; Sørishavet; meteorologi; oseanografi; strømmer; vannmasser

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Wie entsteht die Antarktische Konvergenz? - Sverdrup, Harald Ulrik (Annalen der Hydrographie und Maritimische Meteorologie, 1934)
Keywords: Sørishavet; forskning; havstrømmer; meteorologi; oseanografi

Iskart for 1930-31 over isgrenser i Sydishavet (Norsk hvalfangst-tidende, 1933)
Keywords: Sørishavet; glasiologi; havis

Til Sydishavet - Christensen, Lars (Polar-årboken, 1933)
Keywords: Sørishavet; ekspedisjoner; hvalfangst

On vertical circulation in the ocean due to the action of the wind with application to conditions within the Antarctic circumpolar current - Sverdrup, Harald Ulrik (Discovery Reports, 1933)
Keywords: Sørishavet; ekspedisjoner; forskning; havstrømmer; oseanografi

Antarctic Whaling Season, 1931–32 (Polar Record, 1932)
Publisher: Cambridge University Press
Keywords: Norvegia ekspedisjoner; Sørishavet; hvalfangst

Blaahvalfangsten i Antarctic 1929/30 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst

Finnhvalfangsten i Antarctic 1929/30 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst

Hvalraadets skrifter (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst; litteratur

Polaraaret 1932-1933 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; forskning; klima; meteorologi; oseanografi

Sydhavet: norske selskapers fangst av de forskjellige hvalarter sæsongen 1930/31 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; hvaler; hvalfangst

A Brief History of Whaling - Hjort, Johan (Polar Record, 1932)
Publisher: Cambridge University Press
Keywords: Sørishavet; historie; hvalfangst

Antarktis - Walnum, Ragnv. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1932)
Publisher: Routledge
Keywords: Sørishavet; hvalfangere; isforholdene; isgrenser; iskartet; kart; pakkis

Fangst og forskning i Sydishavet (Norsk hvalfangst-tidende, 1931)
Keywords: Sørishavet; historie; hvalfangst; litteratur

On the conditions for the production of plankton in the sea - Gran, Haaken Hasberg (Conseil Perm. Internat. pour I'Explor. de la Mer. Rapp. et Proces-Verb., 1931)
Keywords: Sørishavet; Weddellhavet; krill; marin biologi; oseanografi; plankton; zooplankton

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

The "Norvegia" Antarctic expedition of 1929-1930 - Long, A T (The Hydrographic Review, 1931)
Keywords: Antarktis; Dronning Maud Land; Sørishavet; ekspedisjoner; geografi; kartlegging; logistikk; oseanografi

"Norvegia"-ekspedisjonen (Norsk hvalfangst-tidende, 1930)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner

Antarctisk hval-aate - Broch, Hjalmar (Norsk hvalfangst-tidende, 1930)
Keywords: Sørishavet; krepsdyr; krill; litteratur; marin biologi

Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; kartlegging; oppdagelsesreiser

Fangstoversigt for Rosshavsfeltet sæsongen 1929-30 - Dingsør, Bernt (Norsk hvalfangst-tidende, 1930)
Keywords: Sørishavet; hvalfangst

Nitrates and Phosphates in the Southern Seas - Ruud, Johan T (ICES Journal of Marine Science, 1930)
Keywords: S.S.Vikingen 1929-30; Sørishavet; Weddellhavet; ekspedisjoner; hval; hvalfangst; krill; marin biologi; oseanografi; plankton; zooplankton

Hvalfangsten langs iskanten i Vest-Antarktis og ved Syd Shetland sæsongen 1928-29 (Norsk hvalfangst-tidende, 1929)
Keywords: Sørishavet; hvalfangst

Rosshavet (Norsk hvalfangst-tidende, 1929)
Keywords: Sørishavet; hvaler; hvalfangst

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Odd I.; Peter I. Øy; Sørishavet; ekspedisjonen; ekspedisjoner; historie; hval; hvalfangst

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Publisher: Routledge
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Litt om "Norveiga"-ekspedisjonen 1927-28 og dens arbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1929)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; forskning; geografi; marinbiologi; oseanografi

Modern Norwegian Whaling in the Antarctic - Isachsen, Gunnar (Geographical Review, 1929)
Publisher: [American Geographical Society, Wiley]
Keywords: Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Hvalmaalinger i Rosshavet (Norsk hvalfangst-tidende, 1928)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

"Southern Queen"s forlis (Norsk hvalfangst-tidende, 1928)
Keywords: Sørishavet; forlis; hvalfangst

James Cook - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Det er i år 150 år siden James Cook døde. Der er så mange jubileer og minnefester i våre dager at man undertiden synes det kan bli litt for meget av det gode. Men de efterfølgende minneord er helliget en mann som ingen der er geografisk interessert, nogensinde bør glemme.
Publisher: Routledge
Keywords: James Cook; Sørishavet; geografi; oppdagelsesreiser; polarekspedisjoner; polarfarere

Til hvalfangerne: videnskabelige samlerarbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1928)
Keywords: Antarktis; Sørishavet; museer; vitenskap

Die Eistrift im Weddelmeer - Sverdrup, Harald Ulrik (Annalen der Hydrographie und maritimen Meteorologie, 1928)
Keywords: Sørishavet; glasiologi; havis; oseanografi

Syd-Ørkney: sæsongen 1926/1927 (Norsk hvalfangst-tidende, 1927)
Keywords: Sørishavet; hvalfangst

Syd Shetland (Norsk hvalfangst-tidende, 1927)
Keywords: Sørishavet; hvaler; hvalfangst

H.J. Bull. Sydhavsekspeditionen 1893/1895 (Norsk hvalfangst-tidende, 1926)
Keywords: Sørishavet; ekspedisjoner; historie; hvaler; hvalfangst

Syd Shetland: sæsongen 1925/26 (Norsk hvalfangst-tidende, 1926)
Keywords: Sørishavet; hvalfangst

Rosshavet - Tofte, Eyvind (Norsk hvalfangst-tidende, 1926)
Keywords: Antarktis; Sørishavet; ekspedisjoner; hvalfangst

A/S "Rosshavet" (Norsk hvalfangst-tidende, 1925)
Keywords: Sørishavet; hvalfangst

Syd-Shetland: sæsongen 1924/1925 (Norsk hvalfangst-tidende, 1925)
Keywords: Sørishavet; hvalfangst

A new Antarctic expedition - Darnley, Rowland (Norsk hvalfangst-tidende, 1923)
Keywords: Sørishavet; ekspedisjoner; hvaler; marin zoologi

Hvalfangst i Rosshavet - Risting, Sigurd (Norsk hvalfangst-tidende, 1923)
Keywords: Sørishavet; ekspedisjoner; historie; hvaler; hvalfangst

Sydfelterne: av deres opdagelseshistorie (Norsk hvalfangst-tidende, 1919)
Keywords: Sørishavet; ekspedisjoner; geografi; historie

Fangst i Sydhavet (Norsk hvalfangst-tidende, 1917)
Keywords: Antarktis; Sørishavet; ekspedisjoner; fangst; historie; hvalfangst; selfangst

"Christmas House": the adventures of a shipwrecked crew - Bull, Henrik Johan; Ree, Harboe (Pall Mall magazine, 1907)
Keywords: Sørishavet; ekspedisjoner; historie

Antarctics sidste Færd. Foredrag den 18de februar 1904 - Larsen, Carl Anton (Det Norske geografiske selskabs aarbok, 1904)
Publisher: Aschehoug Place: Kristiania
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Den svenske antarktisekspedisjonen 1901–03; Otto Nordenskjöld; Sørishavet; vitenskapelige ekspedisjoner

Captain Larsen's Antarctic Journal - Cocks, Alfred Heneage (The Geographical Journal, 1894)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Carl Anton Larsen; D/S Jason; Sørishavet; dagbok; ekspedisjoner; hvalfangere; oppdagelsesreiser

Nogle optegnelser af sæl- og hvalfanger Jason's reise i Sydishavet 1893 og 94 - Larsen, Carl Anton (Det Norske geografiske selskabs aarbok, 1894)
Publisher: Haffner & Hille Place: Kristiania
Keywords: Carl Anton Larsen; D/S Jason; Sørishavet; ekspedisjoner; hvalfangere; oppdagelsesreiser

The Voyage of the "Jason" to the Antarctic Regions : abstract of journal kept by Capt. C. A. Larsen - Larsen, Carl Anton (The Geographical Journal, 1894)
Keywords: Carl Anton Larsen; D/S Jason; Sørishavet; dagbok; ekspedisjoner; hvalfangere; oppdagelsesreiser

Den moderne hvalfangstens kausalproblemer - Johnsen, Arne Odd (Historisk tidsskrift)
Publisher: Den norske historiske forening Place: Oslo
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; næring; pelagisk; økonomi